High-precision ice-flow velocities from ground observations on Dalk Glacier, Antarctica - Ai, Songtao; Wang, Shansi; Li, Yuansheng; Moholdt, Geir; Zhou, Chunxia; Liu, Leibao; Yang, Yuande (Polar Science, 2019)
Dalk Glacier, which has been monitored by CHINARE since 2007, is a calving outlet glacier near the Chinese Zhongshan Station in East Antarctica. Using in situ observational azimuthal data from 2007 to 2012, 67 high-precision spatial intersection points were calculated. Consequently, the ice-flow features of the tongue of Dalk Glacier were explored via ground measurements. The maximum observed ice-flow velocity (IV) was 192.72 m/a, at stake P9. The velocities then decreased with the distance from the central flow line on both sides of the glacier in a cross section. Further analysis showed the following: the velocities of each stake increased annually; the closer to the terminus, the faster the ice flowed; and the ascent ratio of the IVs was approximately 10.67 m/a2 in the main flow area. We also observed seasonal variations in the ice-flow velocities, including a speed-up in January 2009 preceding an ice-calving event. The elevation change measurements at the stakes showed fluctuations along the central flow line, which indicates ice-shelf grounding over a seamount that had not been previously identified.
Keywords: Antarktis; glasiologi

What and who is an Antarctic ambassador? - Alexander, Karen A.; Liggett, Daniela; Leane, Elizabeth; Nielsen, Hanne E. F.; Bailey, Jennifer L.; Brasier, Madeline J.; Haward, Marcus (Polar Record, 2019)
The term “Antarctic ambassadorship” is increasingly used to represent an individual’s connection to Antarctica and their subsequent advocacy. However, there is little clarity regarding the concept. To address this, we combined a literature review with an expert elicitation workshop. We argue that (i) the concept of Antarctic ambassador has been understood in myriad ways; (ii) Antarctic ambassadors have a connection to, knowledge of and passion for Antarctica; (iii) they also have a commitment to defending and advancing Antarctic values and (iv) Antarctic ambassadorship is about more than advocacy. We propose the first comprehensive definition of Antarctic ambassadorship. We hope this will provide a cornerstone upon which future research, and a more informed governance of Antarctic tourism, can be built.
Edition: 2020/05/20 Publisher: Cambridge University Press
Keywords: Antarktis; samfunnsfag

Warm Circumpolar Deep Water at the Western Getz Ice Shelf Front, Antarctica - Assmann, Karen; Darelius, Elin Maria K; Wåhlin, Anna K; Kim, Tae Wan; Lee, Sang Hoon (Geophysical Research Letters, 2019)
The Getz Ice Shelf is one of the largest sources of fresh water from ice shelf basal melt in Antarctica. We present new observations from three moorings west of Siple Island 2016–2018. All moorings show a persistent flow of modified Circumpolar Deep Water toward the western Getz Ice Shelf. Unmodified Circumpolar Deep Water with temperatures up to 1.5 °C reaches the ice shelf front in frequent episodes. These represent the warmest water observed at any ice shelf front in the Amundsen Sea. Mean currents within the warm bottom layer of 18–20 cm/s imply an advection time scale of 7 days from shelf break to ice shelf front. Zonal wind stress at the shelf break affects heat content at the ice shelf front on weekly to monthly time scales. Our 2-year mooring records also evince that upwelling over the shelf break controls thermocline depth on subannual to annual time scales.
Keywords: Antarktis; geofysikk; glasiologi; isbrem; isshelf; observasjoner

Chr. Christensen and C. A. Larsen: A comparative analysis of two whaling entrepreneurs - Basberg, Bjørn L (International Journal of Maritime History, 2019)
Keywords: Antarktis; historie; hvalfangere; hvalfangst

The Four Ladies of Prydz Bay: notes on the naming of a submarine formation in Australian Antarctic Territory - Bathie, Carol; Pett, Janet (The Victorian Naturalist, 2019)
Publisher: Field Naturalists Club of Victoria
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Nitrogen isotope fractionation explains the 15N enrichment of Antarctic cryptogams by volatilized ammonia from penguin and seal colonies - Bokhorst, Stef; van Logtestijn, Richard; Convey, Peter; Aerts, Rien (Polar Research, 2019)
Vegetation near bird and seal rookeries typically has high δ15N signatures and these high values are linked to the enriched δ15N values of rookery soils. However, Antarctic cryptogams are mostly dependent on atmospheric ammonia (NH3) and volatized NH3 from rookeries is severely depleted in δ15N-NH3. So there is an apparent discrepancy between the isotopically depleted source (NH3) and δ15N-enriched vegetation. In this article, we aim to resolve this discrepancy to better understand the mechanisms and processes involved in isotopic changes during nitrogen transfer between Antarctic marine and terrestrial ecosystems. Under laboratory conditions, we quantified whether volatized NH3 affects the isotopic signature of cryptogams. NH3 volatilizing from penguin guano and elephant seal dung was depleted (44–49‰) in δ15N when captured on acidified filters, compared to the source itself. Cryptogams exposed to the volatized NH3 were enriched (18.8–23.9‰) in δ15N. The moss Andreaea regularis gained more nitrogen (0.9%) than the lichen Usnea antarctica (0.4%) from volatilized NH3, indicating a potential difference in atmospheric NH3 acquisition that is consistent with existing field differences in nitrogen concentrations and δ15N between mosses and lichens in general. This study clarifies the δ15N enrichment of cryptogams resulting from one of the most important nitrogen pathways for Antarctic vegetation.
Keywords: Antarktis; fugler; kjemiske analyser; kryptogamer; lav; moser; planter; seler; økologi

Diversity and community structure of bacterioplankton in surface waters off the northern tip of the Antarctic Peninsula - Cao, Shunan; He, Jianfeng; Zhang, Fang; Lin, Ling; Gao, Yuan; Zhou, Qiming (Polar Research, 2019)
Global climate change is significantly affecting marine life off the northern tip of the Antarctic Peninsula, but little is known about microbial ecology in this area. The main goal of this study was to investigate the bacterioplankton community structure in surface waters using pyrosequencing and to determine factors influencing this community. Pelagibacterales and Rhodobacterales (Alphaproteobacteria), Oceanospirillales and Alteromonadales (Gammaproteobacteria), and Flavobacteriales (Bacteroidetes) were the core taxa in our samples, and the five most relatively abundant genera were Pelagibacter, Polaribacter, Octadecabacter, group HTCC2207 and Sulfitobacter. Although nutrients and chlorophyll a (chl a) contributed more to bacterioplankton community structure than water masses or depth, only 30.39% of the variance could be explained by the investigated environmental factors, as revealed by RDA and pRDA. No significant difference with respect to nutrients and chl a was observed among water masses or depth, as indicated by ANOVA. Furthermore, significant correlations among the dominant bacterial genera were more common than correlations between dominant genera and environmental factors, as revealed by Spearman analysis. We conclude that nutrients and chl a become homogeneous and that interpopulation interactions may have a central role in influencing the bacterial community structure in surface waters off the northern tip of the Antarctic Peninsula during the summer.
Keywords: Sørishavet; bakterier; bakterioplankton; fytoplankton; klimaendringer; marin biologi; plankton; pyrosekvensering; zooplankton

Ecological niche modelling of cold-water corals in the Southern Ocean (N Antarctic), present distribution and future projections due to temperature changes - Chaabani, Safa; López-González, Pablo J; Casado-Amezua, Pilar; Pehlke, Hendrik; Weber, Lukas; Martínez-Baraldés, Irene; Jerosch, Kerstin (Marine Ecology Progress Series, 2019)
An urgent necessity to understand the effect of climatic change on scleractinian cold-water coral (CWC) ecosystems has arisen due to increasing ocean warming and acidification over the last decades. Here, presence-absence records of 12 scleractinian CWC species from research expeditions and the literature were compiled and merged with model-generated pseudo-absence data and 14 environmental variables. The best-fitting results of 9 species distribution models (SDMs) were combined to an ensemble habitat suitability model for CWCs in the northern Southern Ocean (Weddell Sea and Antarctic Peninsula) by means of the open-source R package "biomod2". Furthermore, 2 future scenarios of increasing bottom sea temperature were used to investigate the spatial response of scleractinians to temperature change. The resulting (current scenario) potential ecological niches were evaluated with good to excellent statistical measures. The results predict that present areas of highest probability of CWC occurrence are around the Antarctic Peninsula, South Orkney Islands and Queen Maud Land, with preference to geomorphic features such as seamounts. The distribution of CWC habitats is mainly driven by distance to coast and ice shelves, bathymetry, benthic calcium carbonate, and temperature. Under warming conditions, CWCs are predicted to expand their distribution range by 6 and 10% in 2037 and 2150, respectively, compared to the present distribution. The future models using increased bottom temperature revealed a stable CWC distribution for most parts of the study area. However, habitat shifts are expected to the Filchner Trough region, the adjacent continental shelves, as well as to the eastern side of the Antarctic Peninsula. KEYWORDS: Scleractinian coral · Ensemble models · Environmental change · Habitat suitability model · Spatial distribution · Weddell Sea. Antarctica
Keywords: Sørishavet; Weddellhavet; batymetri; biodiversitet; global oppvarming; klimaendringer; marin biologi; miljøendringer; oseanografi; økosystemer

Prey differences drive local genetic adaptation in Antarctic fur seals - Cleary, Alison C; Bester, Marthán; Forcada, Jaume; Goebel, Michael; Goldsworthy, Simon D; Guinet, Christophe; Hoffman, Joseph I; Kovacs, Kit M; Lydersen, Christian; Lowther, Andrew D (Marine Ecology Progress Series, 2019)
Antarctic fur seal (Arctocephalus gazella) colonies are found on sub-Antarctic islands around the continent. These islands experience a range of conditions in terms of physical and biological habitat, creating a natural laboratory to investigate local genetic adaptation. One striking habitat difference is in the availability of Euphausia superba krill as prey, which has led to A. gazella exhibiting a range of diets. A. gazella in some colonies consume exclusively krill, while their conspecifics in other colonies feed mainly on fish and consume few to no krill. To investigate potential adaptations to these different prey fields, reduced representation genome sequencing was conducted on A. gazella from the 8 major colonies. Twenty-seven genomic regions exhibiting signatures of natural selection were identified. Two of these genomic regions were clearly associated with seals living in krill-dominated areas or those in fish-dominated areas. Twenty-two additional genomic regions under selection showed a pattern consistent with prey differences as the driver of selection after historical migrations from krill-dominated habitats where lineages evolved to present krill-poor habitat areas were taken into account. Only 1 of the genomic regions identified appeared to be explained by any other environmental variable analysed (depth). Genomic regions under prey-driven selection included genes associated with regulation of gene expression, skeletal development, and lipid metabolism. Adaptation to local prey has implications for spatial management of this species and for the potential impacts of climate- or harvest-driven reductions in krill abundance on these seals. KEY WORDS: Arctocephalus gazella · Double digest restriction-site associated DNA sequencing · ddRAD · Diet · Euphausia superba · Natural selection
Keywords: Bouvetøya; Sørishavet; genetikk; krill; marin biologi; pelsseler; plankton; zoologi; økosystemer

Patchy Lakes and Topographic Origin for Fast Flow in the Recovery Glacier System, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Jordan, Tom A; Kohler, Jack; Ferraccioli, Fausto; Corr, Hugh F; Olesen, Arne V; Forsberg, René; Casal, Tania G (Journal of Geophysical Research: Earth Surface, 2019)
The Recovery subglacial basin, with its largest glacier Recovery Glacier, has been identified as potentially the biggest contributor to future sea level rise from East Antarctica. Subglacial lakes along the main trunk have been detected from satellite data, with four giant lakes (Recovery Lakes A, B, C, and D) located at the onset of the fast ice flow (≥15 m/yr) and multiple smaller lakes along the glacier. The presence of subglacial water potentially plays a key role in the control of fast ice flow of Recovery Glacier. We present new insights on the Recovery Lakes from airborne radar data collected in 2013 and 2015. Using an adjusted classification scheme, we show that a single large area consisting of smaller lakes connected by likely saturated sediment, referred to as Lake AB, exists in the originally proposed area of the Recovery Lakes A and B. We estimate that the current size of Lake AB is ∼4,320 km2. Water likely leaks from the western shore of Lake AB lubricating the bed initiating fast ice flow at this location. The difference in the outlines of Lake AB and the Lakes A and B previously derived from surface features suggested that a larger paleolake existed here in the past. From our data, we find Recovery Lake C to be dry; we attribute fast ice flow originating from this area to be due to a topographic step and thus an increase in ice thickness rather than enhanced lubrication at the bed.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; radar observasjoner; satellite bilder; subglasial innsjø; topografi

Variability of Sediment Accumulation Rates in an Antarctic Fjord - Eidam, Emily F.; Nittrouer, Charles; Lundesgaard, Øyvind; Homolka, Khadijah; Smith, Craig (Geophysical Research Letters, 2019)
Fjords on the West Antarctic Peninsula (WAP) serve as sediment traps, preserving histories of glacial sediment supply. Regional warming trends are expected to change sediment supplies, altering water quality, depositional history, and ecosystem drivers. Our ability to assess magnitudes of these changes is limited by sparse data on modern sediment accumulation. Twelve new cores and four existing cores from Andvord Bay were used to characterize variability in sediment accumulation rates. These range from 1.5 to 7.9 mm/year (0.12 to 0.56 g·cm−2·year−1). Spatial differences and a weak down-fjord gradient in rates suggest diverse sediment sources, including from outside the fjord. This data set provides a comprehensive assessment of sedimentation during the past century, indicating little change in rates due to recent WAP warming, and sets a benchmark for assessing climate-related changes in sediment delivery and ecosystem drivers (e.g., burial disturbance) in the fjord over coming decades.
Keywords: Antarktis; akkumulasjon; bentiske organismer; biodiversitet; fjord; glasiologi; sedimenter; sedimentologi; tidevannsbreen

Geological mapping of Norway's least explored mountains - Elvevold, Synnøve; Myhre, Per Inge; Engvik, Ane K; Jacobs, Joachim (Fram forum, 2019)
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging; nunataker

Vannet som forandret fjellene - Engvik, Ane K (Bergtatt - Ane K. Engviks blogg, 2019)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

Assessment of Atmospheric Reanalyses With Independent Observations in the Weddell Sea, the Antarctic - Jonassen, Marius O; Välisuo, Ilona; Vihma, Timo; Uotila, Petteri; Makshtas, Alexander P; Launiainen, Jouko (Journal of Geophysical Research: Atmospheres, 2019)
Surface layer and upper-air in situ observations from two research vessel cruises and an ice station in the Weddell Sea from 1992 and 1996 are used to validate four current atmospheric reanalysis products: ERA-Interim, CFSR, JRA-55, and MERRA-2. Three of the observation data sets were not available for assimilation, providing a rare opportunity to validate the reanalyses in the otherwise datasparse region of the Antarctic against independent data. All four reanalyses produce 2 m temperatures warmer than the observations, and the biases vary from +2.0 K in CFSR to +2.8 K in MERRA-2. All four reanalyses are generally too warm also higher up in the atmospheric boundary layer (ABL), with biases up to +1.4 K (ERA-Interim). Cloud fractions are relatively poorly reproduced by the reanalyses, MERRA-2 and JRA-55 having the strongest positive and negative biases of about +30 % and −17 %, respectively. Skill scores of the error statistics reveal that ERA-Interim compares generally the most favorably against both the surface layer and the upper-air observations. CFSR compares the second best and JRA-55 and MERRA-2 have the least favorable scores. The ABL warm bias is consistent with previous evaluation studies in high latitudes, where more recent observations have been applied. As the amount of observations has varied depending on the decade, season, and region, the consistency of the warm bias suggests a need to improve the modeling systems, including data assimilation as well as ABL and surface parameterizations.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; meteorologi; observasjoner

Two species of Lumbricillus (Enchytraeidae, Annelida) new to Antarctica - Lee, Jeounghee; Klinth, Mårten J; Jung, Jongwoo (Polar Research, 2019)
The intertidal fauna of the Antarctic Peninsula has a relatively high species diversity, due to its warmer environment compared to other parts of Antarctica. Marine oligochaetes are, in general, one of the most diverse and ecologically important benthic organism groups, at least in the littoral zone. Antarctica has been one of the least studied areas with regard to oligochaete diversity. Here we report two Lumbricillus species (Lumbricillus antarcticus Stephenson, 1932 and Lumbricillus sejongensis sp. nov.) new to Antarctica, found in a tidal pool on the Barton Peninsula, King George Island. The diversity of this genus remains poorly known for Antarctica and the Subantarctic islands, and what we know is based on a few patchy studies.
Keywords: Sørishavet; belteormer; bentiske organismer; biodiversitet; fauna; marin biologi; tidevann

Field Observations and Physical-Biogeochemical Modeling Suggest Low Silicon Affinity for Antarctic Fast Ice Diatoms - Lim, Stephanie; Moreau, Sébastien; Vancoppenolle, Martin; Deman, Florian; Roukaerts, Arnout; Meiners, K M; Janssens, Julie; Lannuzel, Delphine (Journal of Geophysical Research: Oceans, 2019)
We use field observations from late spring and a one-dimensional sea-ice model to explore a high nutrient, high chlorophyll system in Antarctic land-fast ice. Lack of variability in chlorophyll a concentration and organic carbon content over the 17-day sampling period suggests a balance between macronutrient sources and biological uptake. Nitrate, nitrite, phosphate, and ammonium were measured at concentrations well above salinity-predicted levels, indicating nutrient accumulation fueled by remineralization processes. However, silicic acid (DSi) was depleted relative to seawater and was potentially limiting. One-dimensional physical-biogeochemical sea-ice model simulations at the observation site achieve extremely high algal growth and DSi uptake with a DSi half-saturation constant used for pelagic diatoms (KSi = 3.9 μM) and are not sufficiently improved by tuning the DSi:carbon ratio or DSi remineralization rate. In contrast, diatom biomass in the bottom ice, which makes up 70% of the observed chlorophyll, is simulated using KSi an order of magnitude higher (50 μM), a value similar to that measured in a few Antarctic diatom cultures. Some sea-ice diatoms may therefore experience limitation at relatively high ambient DSi concentrations compared to pelagic diatoms. Our study highlights the urgent need for observational data on sea-ice algal affinity for DSi to further support this hypothesis. A lower algal growth rate increases model predictions of DSi in the upper sea ice to more accurate concentrations. The model currently does not account for the non-diatom communities that dominate those layers, and thus, modeling diatom communities overpredicts DSi uptake in the upper ice.

A continent of and for whiteness?: “White” colonialism and the 1959 Antarctic Treaty - Mancilla, Alejandra (Polar Record, 2019)
There are at least four ways in which Antarctic colonialism was white: it was paradigmatically performed by white men; it consisted in the taking of vast, white expanses of land; it was carried out with a carte blanche (literally, “blank card”) attitude; and it was presented to the world as a white, innocent adventure. While the first, racial whiteness has been amply problematised, I suggest that the last three illuminate yet other moral wrongs of the Antarctic colonial project. Moreover, they might be constitutive of a larger class of “white” colonialisms beyond the White Continent.
Keywords: Antarktis; historie; politikk; samfunnsfag

Quantarctica 3 released - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; Melvær, Yngve; Tronstad, Stein (Fram forum, 2019)
Keywords: Antarktis; geofysikk; geografi; glasiologi; innlandsis; kartografi; satellite bilder

The life cycle of small- to medium-sized icebergs in the Amundsen Sea Embayment - Mazur, Aleksandra K.; Wåhlin, Anna K.; Kalén, Ola (Polar Research, 2019)
An object-based method for automatic iceberg detection has been applied to Advanced Synthetic Aperture Radar images in the Amundsen Sea Embayment (ASE), Antarctica. The images were acquired between 1 January 2006 and 8 April 2012 under varying meteorological, oceanographic and sea-ice conditions. During this time period, the icebergs were counted (average 1370 ± 50) and their surface area was estimated (average 1537.5 km2). The average surface area was about 2.5 times larger than the annual calved area (620 km2), indicating that the average iceberg age in the ASE is about 2.5 years, which was confirmed by observed residence times based on drift tracks. Most of the ASE icebergs were less than 1500 m long, and almost 90% of them were smaller than 2 km2. The proportion of small- and medium-sized icebergs (84.4%) was significantly higher than in the open ocean, where large icebergs (>10 km2) account for nearly the whole iceberg surface area. The opposite was true for the freshly calved icebergs in the ASE. The data indicate that the creation of icebergs in the ASE is dominated by steady small- to medium-scale calving from ice shelves fringing the embayment. In addition, rare calving events of giant icebergs occur on a decadal timescale. There is also some import of icebergs from the Bellingshausen Sea further east along the coast, in particular after large calving events there.
Keywords: Amundsenhavet; Sørishavet; batymetri; fjernmåling; havis; hydrologi; isberg; isbrem; isfjell; kalving; oseanografi; sjøis

A note on digital elevation model smoothing and driving stresses - McCormack, Felicity S; Roberts, Jason L; Jong, Lenneke M; Young, Duncan A; Beem, Lucas H (Polar Research, 2019)
Ice-flow fields, including the driving stress, provide important information on the current state and evolution of Antarctic and Greenland ice-sheet dynamics. However, computation of flow fields from continent-scale DEMs requires the use of smoothing functions and scales, the choice of which can be ad hoc. This study evaluates smoothing functions and scales for robust calculations of driving stress from Antarctic DEMs. Our approach compares a variety of filters and scales for their capacity to minimize the residual between predicted and observed flow direction fields. We find that a spatially varying triangular filter with a width of 8–10 ice thicknesses provides the closest match between the observed and predicted flow direction fields. We use the predicted flow direction fields to highlight artefacts in observed Antarctic velocities, demonstrating that comparison of multiple observational data sets has utility for quality control of continent-scale data sets.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis; isbreer; istykkelse

Review of The life of José María Sobral: scientist, diarist, and pioneer in Antarctica, by Mary R. Tahan (2018). Cham, Switzerland: Springer International Publishing. 336 pp. ISBN 978-3-319-67267-0 - Millar, Pat (Polar Research, 2019)
Keywords: Antarktis; Otto Nordenskjöld; bokanmeldelser; dagbøker; ekspedisjoner; geodesi; magnetisme; meteorologi; oppdagelsesreiser

Sea Ice Meltwater and Circumpolar Deep Water Drive Contrasting Productivity in Three Antarctic Polynyas - Moreau, Sebastien; Lannuzel, Delphine; Janssens, J.; Arroyo, Mar; Corkill, M; Cougnon, Eva; Genovese, C.; Legresy, Benoit; Lenton, Andrew; Puigcorbe, V.; Ratnarajah, L.; Rintoul, Steve; et al. (Journal of Geophysical Research: Oceans, 2019)
In the Southern Ocean, polynyas exhibit enhanced rates of primary productivity and represent large seasonal sinks for atmospheric CO2. Three contrasting east Antarctic polynyas were visited in late December to early January 2017: the Dalton, Mertz, and Ninnis polynyas. In the Mertz and Ninnis polynyas, phytoplankton biomass (average of 322 and 354 mg chlorophyll a (Chl a)/m2, respectively) and net community production (5.3 and 4.6 mol C/m2, respectively) were approximately 3 times those measured in the Dalton polynya (average of 122 mg Chl a/m2 and 1.8 mol C/m2). Phytoplankton communities also differed between the polynyas. Diatoms were thriving in the Mertz and Ninnis polynyas but not in the Dalton polynya, where Phaeocystis antarctica dominated. These strong regional differences were explored using physiological, biological, and physical parameters. The most likely drivers of the observed higher productivity in the Mertz and Ninnis were the relatively shallow inflow of iron-rich modified Circumpolar Deep Water onto the shelf as well as a very large sea ice meltwater contribution. The productivity contrast between the three polynyas could not be explained by (1) the input of glacial meltwater, (2) the presence of Ice Shelf Water, or (3) stratification of the mixed layer. Our results show that physical drivers regulate the productivity of polynyas, suggesting that the response of biological productivity and carbon export to future change will vary among polynyas.
Keywords: Sørishavet; biomasse; brehylle; fytoplankton; havis; isbrem; isshelf; marin biologi; oseanografi; polynja; sjøis

First evidence of a tetrapod footprint from the Triassic of northern Victoria Land, Antarctica - Mörs, Thomas; Niedźwiedzki, Grzegorz; Crispini, Laura; Läufer, Andreas; Bomfleur, Benjamin (Polar Research, 2019)
Here, we report on a tetrapod footprint from the Transantarctic Basin in the far north of Victoria Land, which marks the first record of terrestrial vertebrates for this region. The single specimen derives from a previously unknown lithological unit of Middle or Late Triassic age of the Beacon Supergroup in the Helliwell Hills in the central Rennick Glacier area. It differs in both size and morphology clearly from Middle Triassic trackway types from the upper Fremouw Formation of the Queen Alexandra Range in southern Victoria Land, and likely represents a primitive amniote, procolophonid or therapsid. The footprint is the third evidence of fossil vertebrate trackways in Antarctica.
Keywords: Antarktis; fossiler; paleobiologi; paleontologi; terrestriske virveldyr

Two-Timescale Carbon Cycle Response to an AMOC Collapse - Nielsen, Søren B; Jochum, Markus; Pedro, Joel B; Eden, Carsten; Nuterman, Roman (Paleoceanography and Paleoclimatology, 2019)
Atmospheric CO2 concentrations (pCO2) varied on millennial timescales in phase with Antarctic temperature during the last glacial period. A prevailing view has been that carbon release and uptake by the Southern Ocean dominated this millennial-scale variability in pCO2. Here, using Earth System Model experiments with an improved parameterization of ocean vertical mixing, we find a major role for terrestrial and oceanic carbon releases in driving the pCO2 trend. In our simulations, a change in Northern Hemisphere insolation weakens the Atlantic Meridional Overturning Circulation (AMOC) leading to increasing pCO2 and Antarctic temperatures. The simulated rise in pCO2 is caused in equal parts by increased CO2 outgassing from the global ocean due to a reduced biological activity and changed ventilation rates, and terrestrial carbon release as a response to southward migration of the Intertropical Convergence Zone. The simulated terrestrial release of carbon could explain stadial declines in organic carbon reservoirs observed in recent ice core δ13C measurements. Our results show that parallel variations in Antarctic temperature and pCO2 do not necessitate that the Southern Ocean dominates carbon exchange; instead, changes in carbon flux from the global ocean and land carbon reservoirs can explain the observed pCO2 (and δ13C) changes.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; paleoklimatologi; paleoseanografi; temperatur

Very Strong Atmospheric Methane Growth in the 4 Years 2014–2017: Implications for the Paris Agreement - Nisbet, Euan G; Manning, Martin; Dlugokencky, Ed; Fisher, Rebecca; Lowry, Dave; Michel, Sylvia; Myhre, Cathrine Lund; Platt, Stephen Matthew; Allen, Grant; Bousquet, Philippe; Brownlow, Rebecca; Cain, Michelle; et al. (Global Biogeochemical Cycles, 2019)
Atmospheric methane grew very rapidly in 2014 (12.7 ± 0.5 ppb/year), 2015 (10.1 ± 0.7 ppb/year), 2016 (7.0 ± 0.7 ppb/year), and 2017 (7.7 ± 0.7 ppb/year), at rates not observed since the 1980s. The increase in the methane burden began in 2007, with the mean global mole fraction in remote surface background air rising from about 1,775 ppb in 2006 to 1,850 ppb in 2017. Simultaneously the 13C/12C isotopic ratio (expressed as δ13CCH4) has shifted, now trending negative for more than a decade. The causes of methane's recent mole fraction increase are therefore either a change in the relative proportions (and totals) of emissions from biogenic and thermogenic and pyrogenic sources, especially in the tropics and subtropics, or a decline in the atmospheric sink of methane, or both. Unfortunately, with limited measurement data sets, it is not currently possible to be more definitive. The climate warming impact of the observed methane increase over the past decade, if continued at >5 ppb/year in the coming decades, is sufficient to challenge the Paris Agreement, which requires sharp cuts in the atmospheric methane burden. However, anthropogenic methane emissions are relatively very large and thus offer attractive targets for rapid reduction, which are essential if the Paris Agreement aims are to be attained.
Keywords: Antarktis; atmosfæren; atmosfærisk metan; fossilt brensel; global klimamodell; global oppvarming; klimaendringer; klimagasser; metanisotoper; metanutslipp; meteorologi; polarområdene

Groundwater discharge to the western Antarctic coastal ocean - Null, Kimberly A; Corbett, D Reide; Crenshaw, Jared; Peterson, Richard N; Peterson, Leigha E; Lyons, W Berry (Polar Research, 2019)
Submarine groundwater discharge (SGD) measurements have been limited along the Antarctic coast, although groundwater discharge is becoming recognized as an important process in the Antarctic. Quantifying this meltwater pathway is important for hydrologic budgets, ice mass balances and solute delivery to the coastal ocean. Here, we estimate the combined discharge of subglacial and submarine groundwater to the Antarctic coastal ocean. SGD, including subglacial and submarine groundwater, is quantified along the WAP at the Marr Glacier terminus using the activities of naturally occurring radium isotopes (223Ra, 224Ra). Estimated SGD fluxes from a 224Ra mass balance ranged from (0.41 ± 0.14)×104 and (8.2 ± 2.3)×104m3 d−1. Using a salinity mass balance, we estimate SGD contributes up to 32% of the total freshwater to the coastal environment near Palmer Station. This study suggests that a large portion of the melting glacier may be infiltrating into the bedrock and being discharged to coastal waters along the WAP. Meltwater infiltrating as groundwater at glacier termini is an important solute delivery mechanism to the nearshore environment that can influence biological productivity. More importantly, quantifying this meltwater pathway may be worthy of attention when predicting future impacts of climate change on retreat of tidewater glaciers.
Keywords: Sørishavet; biologi; geologi; grunnvann; hydrologi; isbreer; klimaendringer; tidevann

Influence of Summer Sublimation on δD, δ18O, and δ17O in Precipitation, East Antarctica, and Implications for Climate Reconstruction From Ice Cores - Pang, Hongxi; Hou, Shugui; Landais, Amaelle; Masson-Delmotte, Valérie; Jouzel, Jean; Steen-Larsen, Hans Christian; Risi, Camille; Zhang, Wangbin; Wu, Shuangye; Li, Yuansheng; An, Chunlei; Wang, Yetang; et al. (Journal of Geophysical Research: Atmospheres, 2019)
In central Antarctica, where accumulation rates are very low, summer sublimation of surface snow is a key element of the surface mass balance, but its fingerprint in isotopic composition of water (δD, δ18O, and δ17O) remains unclear. In this study, we examined the influence of summer sublimation on δD, δ18O, and δ17O in precipitation using data sets of isotopic composition of precipitation at various sites on the inland East Antarctica. We found unexpectedly low δ18O values in the summer precipitation, decoupled from surface air temperatures. This feature can be explained by the combined effects of weak or nonexistent temperature inversion and moisture recycling associated with sublimation-condensation processes in summer. Isotopic fractionation during the moisture-recycling process also explains the observed high values of d-excess and 17O-excess in summer precipitation. Our results suggest that the local cycle of sublimation-condensation in summer is an important process for the isotopic composition of surface snow, water vapor, and consequently precipitation on inland East Antarctica.
Keywords: Antarktis; geofysikk; iskjerner; paleoklimatologi; stabile isotoper

Subglacial Geology and Geomorphology of the Pensacola-Pole Basin, East Antarctica - Paxman, Guy J G; Jamieson, Stewart S R; Ferraccioli, Fausto; Jordan, Tom A; Bentley, Michael J; Ross, Neil; Forsberg, René; Matsuoka, Kenichi; Steinhage, Daniel; Eagles, Graeme; Casal, Tania G (Geochemistry, Geophysics, Geosystems, 2019)
The East Antarctic Ice Sheet (EAIS) is underlain by a series of low-lying subglacial sedimentary basins. The extent, geology, and basal topography of these sedimentary basins are important boundary conditions governing the dynamics of the overlying ice sheet. This is particularly pertinent for basins close to the grounding line wherein the EAIS is grounded below sea level and therefore potentially vulnerable to rapid retreat. Here we analyze newly acquired airborne geophysical data over the Pensacola-Pole Basin (PPB), a previously unexplored sector of the EAIS. Using a combination of gravity and magnetic and ice-penetrating radar data, we present the first detailed subglacial sedimentary basin model for the PPB. Radar data reveal that the PPB is defined by a topographic depression situated ~500 m below sea level. Gravity and magnetic depth-to-source modeling indicate that the southern part of the basin is underlain by a sedimentary succession 2–3 km thick. This is interpreted as an equivalent of the Beacon Supergroup and associated Ferrar dolerites that are exposed along the margin of East Antarctica. However, we find that similar rocks appear to be largely absent from the northern part of the basin, close to the present-day grounding line. In addition, the eastern margin of the basin is characterized by a major geological boundary and a system of overdeepened subglacial troughs. We suggest that these characteristics of the basin may reflect the behavior of past ice sheets and/or exert an influence on the present-day dynamics of the overlying EAIS.
Keywords: Antarktis; Sydpolen; Sørpolen; geofysikk; geomorfologi; glasiologi; innlandsis; subglasial geologi; subglasial topografi

Comparison of elastic moduli from seismic diving-wave and ice-core microstructure analysis in Antarctic polar firn - Schlegel, Rebecca; Diez, Anja; Löwe, Henning; Mayer, Christoph; Lambrecht, Astrid; Freitag, Johannes; Miller, Heinrich; Hofstede, Coen; Eisen, Olaf (Annals of Glaciology, 2019)
We compared elastic moduli in polar firn derived from diving wave refraction seismic velocity analysis, firn-core density measurements and microstructure modelling based on firn-core data. The seismic data were obtained with a small electrodynamic vibrator source near Kohnen Station, East Antarctica. The analysis of diving waves resulted in velocity–depth profiles for different wave types (P-, SH- and SV-waves). Dynamic elastic moduli of firn were derived by combining P- and S-wave velocities and densities obtained from firn-core measurements. The structural finite-element method (FEM) was used to calculate the components of the elastic tensor from firn microstructure derived from X-ray tomography of firn-core samples at depths of 10, 42, 71 and 99 m, providing static elastic moduli. Shear and bulk moduli range from 0.39 to 2.42 GPa and 0.68 to 2.42 GPa, respectively. The elastic moduli from seismic observations and the structural FEM agree within 8.5% for the deepest achieved values at a depth of 71 m, and are within the uncertainty range. Our observations demonstrate that the elastic moduli of the firn can be consistently obtained from two independent methods which are based on dynamic (seismic) and static (tomography and FEM) observations, respectively, for deeper layers in the firn below ~10 m depth.
Publisher: Cambridge University Press
Keywords: Antarktis; glasiologi; seismologi

GlobSed: Updated Total Sediment Thickness in the World's Oceans - Straume, Eivind O; Gaina, Carmen; Medvedev, Sergei; Hochmuth, Katharina; Gohl, Karsten; Whittaker, Joanne; Abdul Fattah, R; Doornenbal, J C; Hopper, John R (Geochemistry, Geophysics, Geosystems, 2019)
We present GlobSed, a new global 5-arc-minute total sediment thickness grid for the world's oceans and marginal seas. GlobSed covers a larger area than previously published global grids and incorporates updates for the NE Atlantic, Arctic, Southern Ocean, and Mediterranean regions, which results in a 29.7% increase in estimated total oceanic sediment volume. We use this new global grid and a revised global oceanic lithospheric age grid to assess the relationship between the total sediment thickness and age of the underlying oceanic lithosphere and its latitude. An analytical approximation model is used to mathematically describe sedimentation trends in major oceanic basins and to allow paleobathymetric reconstructions at any given geological time. This study provides a much-needed update of the sediment thickness distribution of the world oceans and delivers a model for sedimentation rates on oceanic crust through time that agrees well with selected drill data used for comparison.
Keywords: Sørishavet; batymetri; litosfæren; marin geofysikk; marin geologi; sedimenter; sedimentologi

Topographic Shelf Waves Control Seasonal Melting Near Antarctic Ice Shelf Grounding Lines - Sun, Sainan; Hattermann, Tore; Pattyn, Frank; Nicholls, Keith W; Drews, Reinhard; Berger, Sophie (Geophysical Research Letters, 2019)
The buttressing potential of ice shelves is modulated by changes in subshelf melting, in response to changing ocean conditions. We analyze the temporal variability in subshelf melting using an autonomous phase-sensitive radio-echo sounder near the grounding line of the Roi Baudouin Ice Shelf in East Antarctica. When combined with additional oceanographic evidence of seasonal variations in the stratification and the amplification of diurnal tides around the shelf break topography (Gunnerus Bank), the results suggest an intricate mechanism in which topographic waves control the seasonal melt rate variability near the grounding line. This mechanism has not been considered before and has the potential to enhance local melt rates without advecting different water masses. As topographic waves seem to strengthen in a stratified ocean, the freshening of Antarctic surface water, predicted by observations and models, is likely to increase future basal melting in this area.
Keywords: Sørishavet; glasiologi; isshelf; klimatologi; oseanografi; smelting; vannmasser

The Weddell Gyre, Southern Ocean: Present Knowledge and Future Challenges - Vernet, M; Geibert, Walter; Hoppema, Mario; Brown, Peter J; Haas, Christian; Hellmer, Hartmut H; Jokat, Wilfried; Jullion, L; Mazloff, M; Bakker, D C E; Brearley, J A; Croot, Peter L; et al. (Reviews of Geophysics, 2019)
The Weddell Gyre (WG) is one of the main oceanographic features of the Southern Ocean south of the Antarctic Circumpolar Current which plays an influential role in global ocean circulation as well as gas exchange with the atmosphere. We review the state-of-the art knowledge concerning the WG from an interdisciplinary perspective, uncovering critical aspects needed to understand this system's role in shaping the future evolution of oceanic heat and carbon uptake over the next decades. The main limitations in our knowledge are related to the conditions in this extreme and remote environment, where the polar night, very low air temperatures, and presence of sea ice year-round hamper field and remotely sensed measurements. We highlight the importance of winter and under-ice conditions in the southern WG, the role that new technology will play to overcome present-day sampling limitations, the importance of the WG connectivity to the low-latitude oceans and atmosphere, and the expected intensification of the WG circulation as the westerly winds intensify. Greater international cooperation is needed to define key sampling locations that can be visited by any research vessel in the region. Existing transects sampled since the 1980s along the Prime Meridian and along an East-West section at ~62°S should be maintained with regularity to provide answers to the relevant questions. This approach will provide long-term data to determine trends and will improve representation of processes for regional, Antarctic-wide, and global modeling efforts—thereby enhancing predictions of the WG in global ocean circulation and climate.
Keywords: Sørishavet; Weddellhavet; biologi; brehylle; geologi; havis; havstrømmer; isbrem; isshelf; kjemi; oseanografi; sjøis; vannmasser; vannvirvler

Project and Community Management in Polar Sciences – Challenges and Opportunities - Werner, Kirstin; Zaika, Yulia; Pavlov, Alexey K; Lidström, Sven; Pope, Allen; Badhe, Renuka; Brückner, Marlen; Cristini, Luisa (Adv. Geosci., 2019)
Because geoscientific research often occurs via community-instigated bursts of activity with multi-investigator collaborations variously labelled as e.g., years (The International Polar Year IPY), experiments (World Ocean Circulation Experiment WOCE), programs (International Ocean Discovery Program), missions (CRYOSAT spacecraft), or decades (The International Decade of Ocean Exploration IDOE), successful attainment of research goals generally requires skilful scientific project management. In addition to the usual challenges of matching scientific ambitions to limited resources, on-going coordination and specifically project management, planning and implementation of polar science projects often involve many uncertainties caused by, for example, unpredictable weather or ocean and sea ice conditions, large-scale logistical juggling; and often these collaborations are spatially distributed and take place virtually. Large amounts of funding are needed to procure the considerable infrastructure and technical equipment required for polar expeditions; permissions to enter certain regions must be requested; and potential risks for expedition members as well as technical issues in extreme environments need to be considered. All these aspects are challenging for polar science projects, which therefore need a well thought-through program including a realistic alternative “plan B” and possibly also a “plan C” and “plan D”. The four most challenging overarching themes in polar science project management have been identified: international cooperation, interdisciplinarity, infrastructure, and community management. In this paper, we address ongoing challenges and opportunities in polar science project management based on a survey among 199 project and community managers and an additional of 85 project team members active in the field of polar sciences. Case studies and survey results are discussed with the conclusive goal to provide recommendations on how to fully reach the potential of polar sciences project and community management.
Publisher: Copernicus Publications
Keywords: Antarktis; geovitenskap; internasjonal samarbeid; klimaendringer; miljøendringer; polarområdene

Surface heat budget in the Southern Ocean from 42°S to the Antarctic marginal ice zone: four atmospheric reanalyses versus icebreaker Aurora Australis measurements - Yu, Lisan; Jin, Xiangze; Schulz, Eric W (Polar Research, 2019)
Surface heat fluxes from four atmospheric reanalyses in the Southern Ocean are evaluated using air–sea measurements obtained from the Aurora Australis during off-winter seasons in 2010–12. The icebreaker tracked between Hobart, Tasmania (ca. 42°S), and the Antarctic continent, providing in situ benchmarks for the surface energy budget change in the Subantarctic Southern Ocean (58–42°S) and the eastern Antarctic marginal ice zone (MIZ, 68–58°S). We find that the reanalyses show a high-level agreement among themselves, but this agreement reflects a universal bias, not a “truth.” Downward shortwave radiation (SW↓) is overestimated (warm biased) and downward longwave radiation (LW↓) is underestimated (cold biased), an indication that the cloud amount in all models is too low. The ocean surface in both regimes shows a heat gain from the atmosphere when averaged over the seven months (October–April). However, the ocean heat gain in reanalyses is overestimated by 10–36 W m−2 (80–220%) in the MIZ but underestimated by 6–20 W m−2 (7–25%) in the Subantarctic. The biases in SW↓ and LW↓ cancel out each other in the MIZ, causing the surface heat budget to be dictated by the underestimation bias in sensible heat loss. These reanalyses biases affect the surface energy budget in the Southern Ocean by meaningfully affecting the timing of the seasonal transition from net heat gain to net heat loss at the surface and the relative strength of SW↓ at different regimes in summer, when the length-of-day effect can lead to increased SW↓ at high latitudes.
Keywords: Sørishavet; havis; klima; meteorologi; oseanografi

A nematode in the mist: Scottnema lindsayae is the only soil metazoan in remote Antarctic deserts, at greater densities with altitude - Zawierucha, Krzysztof; Marshall, Craig J; Wharton, David; Janko, Karel (Polar Research, 2019)
A decrease in biodiversity and density of terrestrial organisms with increasing altitude and latitude is a well-known ecogeographical pattern. However, studies of these trends are often taxonomically-biased toward well-known organisms and especially those with relatively large bodies, and environmental variability at the local scale may perturb these general effects. Here, we focus on understudied organisms—soil invertebrates—in Antarctic deserts, which are among the driest and coldest places on Earth. We sampled two remote Antarctic sites in the Darwin Glacier area and established an altitudinal gradient running from 210 to 836 m a.s.l. We measured soil geochemistry and organic matter content and linked these parameters with the presence of soil invertebrates. We found three general outcomes, two of which are consistent with general assumptions: (a) the hostile climatic condition of the Darwin Glacier region supports an extremely low diversity of soil metazoans represented by a single nematode species—Scottnema lindsayae; (b) soil geochemistry is the main factor influencing distribution of nematodes at the local scale. Contrary to our expectations, a positive correlation was found between nematode density and altitude. This last observation could be explained by an additional effect of soil moisture as we found this increased with altitude and may be caused by orographic clouds, which are present in this region. To the best of our knowledge such effects have been described in tropical and temperate regions. Potential effect of orographic clouds on soil properties in polar deserts may be a fruitful area of ecological research on soil fauna.
Keywords: Antarktis; biodiversitet; geokjemi; jord; metazoan; rundormer; økogeografi; økosystemer

Verification and Improvement of the Ability of CFSv2 to Predict the Antarctic Oscillation in Boreal Spring - Zhang, Dapeng; Huang, Yanyan; Sun, Bo; Li, Fei; Wang, Huijun (Advances in Atmospheric Sciences, 2019)
The boreal spring Antarctic Oscillation (AAO) has a significant impact on the spring and summer climate in China. This study evaluates the capability of the NCEP’s Climate Forecast System, version 2 (CFSv2), in predicting the boreal spring AAO for the period 1983–2015. The results indicate that CFSv2 has poor skill in predicting the spring AAO, failing to predict the zonally symmetric spatial pattern of the AAO, with an insignificant correlation of 0.02 between the predicted and observed AAO Index (AAOI). Considering the interannual increment approach can amplify the prediction signals, we firstly establish a dynamical–statistical model to improve the interannual increment of the AAOI (DY AAOI), with two predictors of CFSv2-forecasted concurrent spring sea surface temperatures and observed preceding autumn sea ice. This dynamical–statistical model demonstrates good capability in predicting DY AAOI, with a significant correlation coefficient of 0.58 between the observation and prediction during 1983–2015 in the two-year-out cross-validation. Then, we obtain an improved AAOI by adding the improved DY AAOI to the preceding observed AAOI. The improved AAOI shows a significant correlation coefficient of 0.45 with the observed AAOI during 1983–2015. Moreover, the unrealistic atmospheric response to March–April–May sea ice in CFSv2 may be the possible cause for the failure of CFSv2 to predict the AAO. This study gives new clues regarding AAO prediction and short-term climate prediction.
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi

Polarårboken Glacier (Polarboken, 2018)
Keywords: Antarktis; geografi; glasiologi

Signals from the south; humpback whales carry messages of Antarctic sea-ice ecosystem variability - Bengtson Nash, Susan M; Castrillon, Juliana; Eisenmann, Pascale; Fry, Brian; Shuker, Jon D; Cropp, Roger A; Dawson, Amanda; Bignert, Anders; Bohlin-Nizzetto, Pernilla; Waugh, Courtney A; Polkinghorne, Bradley J; Dalle Luche, Greta; et al. (Global Change Biology, 2018)
Abstract Southern hemisphere humpback whales (Megaptera novaeangliae) rely on summer prey abundance of Antarctic krill (Euphausia superba) to fuel one of the longest-known mammalian migrations on the planet. It is hypothesized that this species, already adapted to endure metabolic extremes, will be one of the first Antarctic consumers to show measurable physiological change in response to fluctuating prey availability in a changing climate; and as such, a powerful sentinel candidate for the Antarctic sea-ice ecosystem. Here, we targeted the sentinel parameters of humpback whale adiposity and diet, using novel, as well as established, chemical and biochemical markers, and assembled a time trend spanning 8 years. We show the synchronous, inter-annual oscillation of two measures of humpback whale adiposity with Southern Ocean environmental variables and climate indices. Furthermore, bulk stable isotope signatures provide clear indication of dietary compensation strategies, or a lower trophic level isotopic change, following years indicated as leaner years for the whales. The observed synchronicity of humpback whale adiposity and dietary markers, with climate patterns in the Southern Ocean, lends strength to the role of humpback whales as powerful Antarctic sea-ice ecosystem sentinels. The work carries significant potential to reform current ecosystem surveillance in the Antarctic region.
Keywords: Sørishavet; havis; hvaler; marin biologi; marine økosystemer; plankton; sjøis; stabile isotoper

SuperDARN Radar-Derived HF Radio Attenuation During the September 2017 Solar Proton Events - Bland, Emma C; Heino, Erkka; Kosch, Michael J; Partamies, Noora (Space Weather, 2018)
Two solar proton events in September 2017 had a significant impact on the operation of the Super Dual Auroral Radar Network (SuperDARN), a global network of high-frequency (HF) radars designed for observing F region ionospheric plasma convection. Strong polar cap absorption caused near-total loss of radar backscatter, which prevented the primary SuperDARN data products from being determined for a period of several days. During this interval, the high-latitude and polar cap radars measured unusually low levels of background atmospheric radio noise. We demonstrate that these background noise measurements can be used to observe the spatial and temporal evolution of the polar cap absorption region, using an approach similar to riometry. We find that the temporal evolution of the SuperDARN radar-derived HF attenuation closely follows that of the cosmic noise absorption measured by a riometer. Attenuation of the atmospheric noise up to 10 dB at 12 MHz is measured within the northern polar cap, and up to 14 dB in the southern polar cap, which is consistent with the observed backscatter loss. Additionally, periods of enhanced attenuation lasting 2–4 hr are detected by the midlatitude radars in response to M- and X-class solar flares. Our results demonstrate that SuperDARN's routine measurements of atmospheric radio noise can be used to monitor 8- to 20-MHz radio attenuation from middle to polar latitudes, which may be used to supplement riometer data and also to investigate the causes of SuperDARN backscatter loss during space weather events.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; ionosfæren; polarområdene; radiostøy

Variable Melt Production Rate of the Kerguelen HotSpot Due To Long-Term Plume-Ridge Interaction - Bredow, Eva; Steinberger, Bernhard (Geophysical Research Letters, 2018)
For at least 120 Myr, the Kerguelen plume has distributed enormous amounts of magmatic rocks over various igneous provinces between India, Australia, and Antarctica. Previous attempts to reconstruct the complex history of this plume have revealed several characteristics that are inconsistent with properties typically associated with plumes. To explore the geodynamic behavior of the Kerguelen hotspot, and in particular address these inconsistencies, we set up a regional viscous flow model with the mantle convection code ASPECT. Our model features complex time-dependent boundary conditions in order to explicitly simulate the surrounding conditions of the Kerguelen plume. We show that a constant plume influx can result in a variable magma production rate if the plume interacts with nearby spreading ridges and that a dismembered plume, multiple plumes, or solitary waves in the plume conduit are not required to explain the fluctuating magma output and other unusual characteristics attributed to the Kerguelen hotspot.
Keywords: Den antarktiske kontinentalplaten; Sørishavet; geodynamiske modeller; geovitenskap; plategrenser; platetektonikk; tektoniske plater; vulkaner

Contextualizing the 1997 warm event observed at Patriot Hills in the interior of West Antarctica - Carrasco, Jorge F (Polar Research, 2018)
Between 5 and 8 December 1997, the surface air temperature increased up to 3°C in the interior of West Antarctica, at Patriot Hills (PH), located at about 80°08’S, 81°16ʹ W, at an elevation of 855 m a.s.l. This was about 15°C warmer than the mean air temperature (−12°C) for this location at this time of the year. The ice surface field along the hills used as a runway for large aircraft melted, forming small ponds at the foot of the slope. This warm event was associated with a passing mid-tropospheric ridge that reached the interior of West Antarctica, whose anticyclonic circulation advected warm air towards the PH area. The foehn effect of the descending airflow on the northern slope of PH did not significantly contribute to the warming. The El Niño–Southern Oscillation (ENSO) was reaching its mature phase during the last quarter of 1997 and the warming/melting episode may be related to large-scale circulation associated with ENSO occurrence. However, warm events in the interior of West Antarctica may occur during any phase of ENSO. In contrast, the negative phase of the Antarctic Oscillation seems to support the development of the mid-tropospheric ridges that can advect warm maritime air towards the interior of West Antarctica. The 3°C registered at PH may be one of the highest near-surface air temperatures measured below 2500 m a.s.l. in the far interior coastal area of West Antarctica. This suggests a new subregion for determining air temperature records in Antarctica may need to be considered.
Keywords: Antarktis; føhn; føn; lufttemperatur; meteorologi; oppvarming; smelting; snø; sørlig oscillasjon

Response of Antarctic sea-ice algae to an experimental decrease in pH: a preliminary analysis from chlorophyll fluorescence imaging of melting ice - Castrisios, Katerina; Martin, Andrew; Müller, Marius N; Kennedy, Fraser; McMinn, Andrew; Ryan, Ken G (Polar Research, 2018)
Microorganisms confined to annual sea ice in the Southern Ocean are exposed to highly variable oxygen and carbonate chemistry dynamics because of the seasonal increase in biomass and limited exchange with the underlying water column. For sea-ice algae, physiological stress is likely to be exacerbated when the ice melts; however, variation in carbonate speciation has rarely been monitored during this important state-transition. Using pulse amplitude modulated fluorometry (Imaging-PAM, Walz), we documented in situ changes in the maximum quantum yield of photosystem II ( F v / F m ) of sea-ice algae melting out into seawater with initial pH values ranging from 7.66 to 6.39. Although the process of ice-melt elevated seawater pH by 0.2–0.55 units, we observed a decrease in F v / F m between 0.02 and 0.06 for each unit drop in pH during real-time fluorescence imaging. These results are considered preliminary but provide context for including carbonate chemistry monitoring in the design of future sea ice state-transition experiments. Imaging-PAM is a reliable technology for determining F v / F m , but is of limited use for obtaining additional photosynthetic parameters when imaging melting ice.
Keywords: Sørishavet; alger; fotosyntese; fysiologi; havis; karbonatkjemi; marin biologi; sjøis; økofysiologi

Feeding by Antarctic krill Euphausia superba in the West Antarctic Peninsula: differences between fjords and open waters - Cleary, Alison C; Durbin, Edward G; Casas, Maria C (Marine Ecology Progress Series, 2018)
Antarctic krill Euphausia superba are key components of Antarctic ecosystems, serving as the major prey item for most of the megafauna in the region. Coastal fjords along the West Antarctic Peninsula have been identified as biological hotspots, areas in which high biomasses of both E. superba and their megafauna predators are consistently observed. We investigated feeding by E. superba in fjords and adjacent open waters of the West Antarctic Peninsula. Next generation sequencing of stomach contents from 174 krill indicated a diverse diet, with broad patterns consistent with previous understanding of E. superba feeding. Diatom sequence reads were frequent and abundant, indicating a largely diatom-based diet, while the occasional presence of high abundances of copepod sequence reads suggests carnivory supplemented the diet. Striking differences were observed between the stomach contents of krill collected in fjords and those of krill collected in adjacent open waters. Chaetoceros spp. diatoms made up 71% of the stomach contents sequences of krill collected in fjords, but less than 10% of the stomach contents sequences of krill collected in open waters. These differences could not be explained by differences in the surface water phytoplankton communities, as in both open waters and fjords Chaetoceros spp. made up less than 10% of the surface water sequence read assemblages. These feeding differences highlight the importance of taking into account regional differences in krill feeding when considering E. superba’s roles in Southern Ocean ecosystems, and suggest krill in fjords may make use of vertical structure in phytoplankton assemblages.
Keywords: Sørishavet; biomasse; fytoplankton; krill; marin biologi; oseanografi; zoologi; økosystemer

Wind Stress Mediated Variability of the Filchner Trough Overflow, Weddell Sea - Daae, Kjersti Birkeland; Darelius, Elin Maria K; Fer, Ilker; Østerhus, Svein; Ryan, Svenja (Journal of Geophysical Research: Oceans, 2018)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Seasonal Outflow of Ice Shelf Water Across the Front of the Filchner Ice Shelf, Weddell Sea, Antarctica - Darelius, Elin Maria K; Sallée, Jean-Baptiste (Geophysical Research Letters, 2018)
Keywords: Sørishavet; Weddellhavet; bunnvann; isfront; isshelf; oseanografi

On the long-ignored scientific achievements of the Belgica expedition 1897–1899 - De Deckker, Patrick (Polar Research, 2018)
The Belgica expedition, which left Belgium in August 1897, was the first to spend 13 months continuously in Antarctic waters, before returning in late 1899. This was not only an exploratory venture, as new lands and oceans were charted, but more importantly it was an exceptional and successful scientific voyage. After the return of the expedition, a vast array of scientific data was processed and eventually 92 publications in some nine volumes funded by the Belgica Commission appeared over 40 years as a series called Résultats du voyage de la Belgica en 1897–99 sous le commandement de A. de Gerlache de Gomery – rapports scientifiques. Disappointingly, those significant results have been mostly ignored in the scientific literature and the paper here aims to inform scientists of the achievements of the Belgica expedition and where to obtain the information. Many of the climatological and oceanographic data obtained by the expeditioners ought to be examined in line with the changes that are occurring today in the Antarctic Peninsula region as a result of global warming. Some of the Belgica data form an important database to critically assess environmental changes over 120 years in the region of the Antarctic Peninsula.
Keywords: Antarktis; Belgica ekspedisjon; glasiologi; global oppvarming; klimaendringer; klimatologi; meteorologi; miljøendringer; oppdagelsesreiser; oseanografi; vitenskap

Basal Settings Control Fast Ice Flow in the Recovery/Slessor/Bailey Region, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F; Kohler, Jack; Olesen, Arne V; Forsberg, René (Geophysical Research Letters, 2018)
The region of Recovery Glacier, Slessor Glacier, and Bailey Ice Stream, East Antarctica, has remained poorly explored, despite representing the largest potential contributor to future global sea level rise on a centennial to millennial time scale. Here we use new airborne radar data to improve knowledge about the bed topography and investigate controls of fast ice flow. Recovery Glacier is underlain by an 800 km long trough. Its fast flow is controlled by subglacial water in its upstream and topography in its downstream region. Fast flow of Slessor Glacier is controlled by the presence of subglacial water on a rough crystalline bed. Past ice flow of adjacent Recovery and Slessor Glaciers was likely connected via the newly discovered Recovery-Slessor Gate. Changes in direction and speed of past fast flow likely occurred for upstream parts of Recovery Glacier and between Slessor Glacier and Bailey Ice Stream. Similar changes could also reoccur here in the future.
Keywords: Antarktis; geofysikk; geologi; glasiologi; havnivåstigning; isbre; isstrøm

A hut too far: history of the Argentine Ventimiglia shelter on Peter I Øy - Fontana, Pablo Gabriel (Polar Research, 2018)
This paper addresses the barely known history of an Argentine Antarctic hut: the Teniente Luis Ventimiglia hut, installed by the Argentine Antarctic Institute on Peter I Øy (Peter I Island) in March 1971. In examining the history of the only Argentine Antarctic facility outside of the Argentine Antarctic Sector, this article describes the reasons behind the establishment of the hut and the scientific work that took place there as well as previous Argentine expeditions to Peter I.
Keywords: Argentina; Peter I. Øy; ekspedisjoner; forskningsstasjoner; meteorologi; oseanografi

I Roald Amundsens fotspor til Sydpolen med besøk på Bettytoppen - Furholt, Astrid (Polarboken, 2018)
Keywords: Antarktis; ekspedisjoner; historie

A preliminary survey of the terrestrial arthropods of the Rosenthal Islands, Antarctica - Gantz, J D; Spacht, Drew E; Lee, Richard E (Polar Research, 2018)
The Rosenthal Islands lie along the western edge of the Antarctic Peninsula. They are largely inaccessible and the few research projects in the area have focused on seabird colonies, so nothing has been known about the arthropod fauna on these islands. We conducted a preliminary survey of the arthropods associated with large penguin colonies. We identified two species of Collembola (Cryptopygus antarcticus and Friesea grisea), four species of mites (Alaskozetes antarcticus, Hydrogamasellus racovitzai, Tectopenthalodes villosus and Rhagidia sp.) and one insect (Belgica antarctica). The mite A. antarcticus and the collembolan C. antarcticus were common in large aggregations at our collecting sites and were occasionally observed on the surface of penguin guano without vegetative cover. The insect, a chironomid midge, was less common and found only in vegetated areas.
Keywords: Antarktis; biologi; fauna; leddyr; midder; pingviner; zoologi

Facing the climate change conundrum at the South Pole: actors’ perspectives on the implications of global warming for Chilean Antarctic governance - Gladkova, Ekaterina; Blanco-Wells, Gustavo; Nahuelhual, Laura (Polar Research, 2018)
Antarctica is recognized as being geopolitically and scientifically important, and as one of the regions with the greatest potential to affect and be affected by global climate change. Still, little is known in practice about how climate change will be handled within the main governance framework of the continent: the Antarctic Treaty System (ATS). Using qualitative interviews, participant observations and policy document analysis, this paper explores the perspectives of Chilean scientific, political and non-governmental actors regarding the implications of climate change for the current Antarctic governance framework. Results corroborate a misalignment of the climate change agenda and the ATS, stemming from the divergent views displayed by a wide network of actors. From the interviews, two predominant visions emerge: (i) climate change as an opportunity, where actors recognize the role of Antarctica in regulating global climate and stress greater opportunities to conduct Antarctic-based climate change research, the need for strategic international collaboration, and the reinforcement of Chile’s position in Antarctica through science; (ii) climate change as a burden where actors acknowledge climate change as a global problem, largely external to Antarctica, express disbelief regarding the effectiveness of local actions to tackle climate change and do not associate with climate change governance. The study concludes that climate change may become a dividing, rather than a unifying, field of action in Chilean Antarctic governance, reinforcing previously existing geopolitical tendencies.
Keywords: Antarktis; Antarktistraktaten; geopolitikk; klimaendringer; vitenskap

Ice-rise stratigraphy reveals changes in surface mass balance over the last millennia in Dronning Maud Land - Goel, Vikram; Martín, Carlos; Matsuoka, Kenichi (Journal of Glaciology, 2018)
We use ice flow modelling to simulate the englacial stratigraphy of Blåskimen Island, an ice rise in Dronning Maud Land and elucidate the evolution of this data-sparse region. We apply a thermo-mechanically coupled Elmer/Ice model to a profile along flowlines and through the ice-rise summit, where surface mass balance (SMB), flow velocity and ice stratigraphy were recently measured. We conclude that: (i) the ice rise is presently thickening at a rate of 0.5~0.6 m ice equivalent per year (mieq a−1), which is twice an earlier estimate using the field data and the input–output method; (ii) present thickening started 20–40 years in the past, before which the ice rise was in a steady state; (iii) SMB contrast between the upwind and downwind slopes was stronger than the present value by ~23% (or 0.15 mieq a−1) prior to ~1100 years ago. Since then, this contrast has been decreasing overall. We surmise that these SMB changes are likely a result of synoptic-scale atmospheric changes, rather than local atmospheric changes controlled by local ice topography. Our technique effectively assimilates geophysical data, avoiding the complexity of ice flow beneath the ice divide. Thus, it could be applied to other ice rises to elucidate the recent glacial retreat.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Di(2-ethylhexyl) adipate (DEHA) detection in Antarctic krill (Euphasia superba Dana) - Han, Xiangning; Liu, Daicheng (Polar Research, 2018)
In this reported study, a novel high-performance thin-layer chromatography (HPTLC) method was developed for the detection and quantification of the toxic substance di(2-ethylhexyl) adipate (DEHA) in Antarctic krill. This procedure was based on the extraction of DEHA by ultrasonic solvent extraction with anhydrous ethanol, silica-gel column chromatographic separation, HPTLC detection and quantification using petroleum ether/ethyl acetate/ acetone/glacial acetic acid (29:1:0.5:2d*, v/v/v/v) as the developing solvent and bromine thymol blue solution as the chromogenic agent. The content of DEHA in freeze-dried Antarctic krill was found to be ca. 0.63 ± 0.05 mg/g. The structure of DEHA in the Antarctic krill was subsequently determined by gas chromatography–mass spectrometry (GC-MS) and infrared chromatography, which verified the presence of this compound in the krill. The HPTLC method exhibited excellent accuracy, with a recovery of 97.1–101.6% and good precision with a relative standard deviation of 2.47–4.90%. The DEHA in Antarctic krill oil was extracted by n-hexane and detected using the same method described above, which verified that DEHA was also present in krill oil at a concentration of ca. 2.16 ± 0.08 mg/g. The presence of DEHA in kill oil is very concerning because of its demonstrated harmful ecotoxicity, and since Antarctic krill is the key link in the food chain in the Antarctic coastal marine ecosystem. The adverse effects of DEHA on Antarctic krill and the source of DEHA will be explored in future research.
Keywords: Sørishavet; krill; marin forurensning; plankton; plastpartikler; økotoksikologi; økotoksiner

A Model-Based Evaluation of the Inverse Gaussian Transit-Time Distribution Method for Inferring Anthropogenic Carbon Storage in the Ocean - He, Yan-Chun; Tjiputra, Jerry; Langehaug, Helene R.; Jeansson, Emil; Gao, Yongqi; Schwinger, Jörg; Olsen, Are (Journal of Geophysical Research: Oceans, 2018)
The Inverse Gaussian approximation of transit time distribution method (IG-TTD) is widely used to infer the anthropogenic carbon (Cant) concentration in the ocean from measurements of transient tracers such as chlorofluorocarbons (CFCs) and sulfur hexafluoride (SF6). Its accuracy relies on the validity of several assumptions, notably (i) a steady state ocean circulation, (ii) a prescribed age tracer saturation history, e.g., a constant 100% saturation, (iii) a prescribed constant degree of mixing in the ocean, (iv) a constant surface ocean air-sea CO2 disequilibrium with time, and (v) that preformed alkalinity can be sufficiently estimated by salinity or salinity and temperature. Here, these assumptions are evaluated using simulated “model-truth” of Cant. The results give the IG-TTD method a range of uncertainty from 7.8% to 13.6% (11.4 Pg C to 19.8 Pg C) due to above assumptions, which is about half of the uncertainty derived in previous model studies. Assumptions (ii), (iv) and (iii) are the three largest sources of uncertainties, accounting for 5.5%, 3.8% and 3.0%, respectively, while assumptions (i) and (v) only contribute about 0.6% and 0.7%. Regionally, the Southern Ocean contributes the largest uncertainty, of 7.8%, while the North Atlantic contributes about 1.3%. Our findings demonstrate that spatial-dependency of , and temporal changes in tracer saturation and air-sea CO2 disequilibrium have strong compensating effect on the estimated Cant. The values of these parameters should be quantified to reduce the uncertainty of IG-TTD; this is increasingly important under a changing ocean climate.
Keywords: Sørishavet; antropogenisk CO2; fossilt brensel; karbondioksid; karbonlagring; klimaendringer; klimatologi

Provenance, transport and diagenesis of sediment in polar areas: a case study in Profound Lake, King George Island, Antarctica - Hernández, Ana C; Bastias, Joaquin; Matus, Daniela; Mahaney, William C (Polar Research, 2018)
Detailed scanning electron microscopy (SEM) micro-texture and mineralogical analysis of lacustrine sediment recovered from Profound Lake (also known as Uruguay Lake), Antarctica, was conducted in the foreland area of the Collins Glacier, King George Island. Very coarse and coarse sand grade size fractions (2 mm – 600 μm) were examined with SEM/ energy dispersive spectrometry, while the total sand fraction and fines (silt + clay) were examined using x-ray diffraction to determine relationships to source rock, weathering and transport history and long-term clay mineral weathering, all of which are poorly understood in polar areas. The mineralogy of these sediments was compared with petrographical information of the country rock to identify potential detrital sources. The association of recovered detrital minerals, sometimes strongly pre-weathered, supports release from source rock of basaltic and andesitic compositions. The micro-texture analysis of quartz, magnetite and various plagioclase grains show micro-features that reveal a complex weathering–diagenesis history tentatively extending into the Paleogene. The bedrock was eroded mostly by glacial processes and mechanical action presumed to result from glacial crushing. Alteration minerals, likely the product of pre-weathering, are probably sourced from weathered bedrock during contact with the sub-aerial atmosphere prior to entrainment. However, amorphous silica precipitation indicates weathering subsequent to glacial erosion from the source bedrock. Cracks of variable dimensions are mostly characteristic of either frost weathering or glacial transport, and involve mechanical and chemical processes.
Keywords: Antarktis; geologi; mineralogi; petrografi; polarområdene; sedimentologi

Antarctic environmental protection: strengthening the links between science and governance - Hughes, Kevin A; Constable, Andrew; Frenot, Yves; López-Martinez, Jerónimo; McIvor, Ewan; Njåstad, Birgit; Terauds, Aleks; Liggett, Daniela; Roldan, Gabriela; Wilmotte, Annick; Xavier, José C (Environmental Science & Policy, 2018)
The Antarctic has significant environmental, scientific, historic, and intrinsic values, all of which are worth protecting into the future. Nevertheless, the area is subject to an increasing level and diversity of human activities that may impact these values within marine, terrestrial and cryosphere environments. Threats to the Antarctic environment, and to the aforementioned values, include climate change, pollution, habitat destruction, wildlife disturbance and non-native species introductions. Over time, a suite of legally binding international agreements, which form part of the Antarctic Treaty System (ATS), has been established to help safeguard the Antarctic environment and provide a framework for addressing the challenges arising from these threats. Foremost among these agreements are the Protocol on Environmental Protection to the Antarctic Treaty and the Convention on the Conservation of Antarctic Marine Living Resources. Many scientists working in Antarctica undertake research that is relevant to Antarctic environmental policy development. More effective two-way interaction between scientists and those responsible for policy development would further strengthen the governance framework, including by (a) better communication of policy makers’ priorities and identification of related science requirements and (b) better provision by scientists of ‘policy-ready’ information on existing priorities, emerging issues and scientific/technological advances relevant to environmental protection. The Scientific Committee on Antarctic Research (SCAR) has a long and successful record of summarizing policy-relevant scientific knowledge to policy makers, such as through its Group of Specialists on Environmental Affairs and Conservation (GOSEAC) up to 2002, currently the SCAR Standing Committee on the Antarctic Treaty System (SCATS) and recently through its involvement in the Antarctic Environments Portal. Improvements to science-policy communication mechanisms, combined with purposeful consideration of funding opportunities for policy-relevant science, would greatly enhance international policy development and protection of the Antarctic environment.
Keywords: Antarktis; miljøvern

Current logistical capacity is sufficient to deliver the implementation and management of a representative Antarctic protected area system - Hughes, Kevin A; Grant, Susie M (Polar Research, 2018)
Antarctica’s terrestrial ecosystems are vulnerable to impacts resulting from climate change and local human activities. The Antarctic Treaty System (ATS) provides for the designation of protected areas through the Protocol on Environmental Protection to the Antarctic Treaty. Unsystematic use of agreed management tools, including Antarctic Specially Protected Areas (ASPAs), has resulted in a protected area system lacking representation across the full range of Antarctic terrestrial ecosystems and Antarctic Conservation Biogeographic Regions (ACBRs). Systematic Conservation Planning (SCP) methods provide established mechanisms to fulfil ATS protected area designation goals. However, how would a continent-wide ASPA system be delivered should appropriate sites be identified using SCP or other methods? Although the rate of area protection has slowed recently, we show that newer Consultative Parties to the Antarctic Treaty are increasingly active as ASPA proponents and may have scope for further engagement with protected area management activities. Furthermore, all 16 ACBRs were found to be within the operational footprint of at least two Parties, indicating that this current logistical footprint could support the implementation and management of a continent-wide ASPA system. Effective management of a representative Antarctic protected areas system could be delivered through greater participation by those Parties with currently more limited protected area management responsibilities and greater use of remote-sensing technologies for protected area monitoring, where appropriate. Crucially, political will to implement an ASPA system identified through SCP approaches may be greater once a pragmatic means of delivery and effective management has been identified.
Keywords: Antarktis; Antarktistraktaten; biodiversitet; forvaltning; klimaendringer; menneskelig påvirkning; miljøvern; områdevern; økosystemer

Basal Melt and Freezing Rates From First Noble Gas Samples Beneath an Ice Shelf - Huhn, Oliver; Hattermann, Tore; Davis, Peter E D; Dunker, Erich; Hellmer, Hartmut H; Nicholls, Keith W; Østerhus, Svein; Rhein, Monika; Schröder, Michael; Sültenfuß, Jürgen (Geophysical Research Letters, 2018)
A climatically induced acceleration in ocean-driven melting of Antarctic ice shelves would have consequences for both the discharge of continental ice into the ocean and thus global sea level, and for the formation of Antarctic Bottom Water and the oceanic meridional overturning circulation. Using a novel gas-tight in situ water sampler, noble gas samples have been collected from six locations beneath the Filchner Ice Shelf, the first such samples from beneath an Antarctic ice shelf. Helium and neon are uniquely suited as tracers of glacial meltwater in the ocean. Basal meltwater fractions range from 3.6% near the ice shelf base to 0.5% near the sea floor, with distinct regional differences. We estimate an average basal melt rate for the Filchner-Ronne Ice Shelf of 177 ± 95 Gt/year, independently confirming previous results. We calculate that up to 2.7% of the meltwater has been refrozen, and we identify a local source of crustal helium.
Keywords: Sørishavet; Weddellhavet; bunnvann; glasiologi; havnivå; innlandsis; isbrem; klimatologi; oseanografi; smelting; vannmasser

Deriving micro- to macro-scale seismic velocities from ice-core c axis orientations - Kerch, Johanna; Diez, Anja; Weikusat, Ilka; Eisen, Olaf (The Cryosphere, 2018)
One of the great challenges in glaciology is the ability to estimate the bulk ice anisotropy in ice sheets and glaciers, which is needed to improve our understanding of ice-sheet dynamics. We investigate the effect of crystal anisotropy on seismic velocities in glacier ice and revisit the framework which is based on fabric eigenvalues to derive approximate seismic velocities by exploiting the assumed symmetry. In contrast to previous studies, we calculate the seismic velocities using the exact c axis angles describing the orientations of the crystal ensemble in an ice-core sample. We apply this approach to fabric data sets from an alpine and a polar ice core. Our results provide a quantitative evaluation of the earlier approximative eigenvalue framework. For near-vertical incidence our results differ by up to 135 m s−1 for P-wave and 200 m s−1 for S-wave velocity compared to the earlier framework (estimated 1 % difference in average P-wave velocity at the bedrock for the short alpine ice core). We quantify the influence of shear-wave splitting at the bedrock as 45 m s−1 for the alpine ice core and 59 m s−1 for the polar ice core. At non-vertical incidence we obtain differences of up to 185 m s−1 for P-wave and 280 m s−1 for S-wave velocities. Additionally, our findings highlight the variation in seismic velocity at non-vertical incidence as a function of the horizontal azimuth of the seismic plane, which can be significant for non-symmetric orientation distributions and results in a strong azimuth-dependent shear-wave splitting of max. 281 m s−1 at some depths. For a given incidence angle and depth we estimated changes in phase velocity of almost 200 m s−1 for P wave and more than 200 m s−1 for S wave and shear-wave splitting under a rotating seismic plane. We assess for the first time the change in seismic anisotropy that can be expected on a short spatial (vertical) scale in a glacier due to strong variability in crystal-orientation fabric (±50 m s−1 per 10 cm). Our investigation of seismic anisotropy based on ice-core data contributes to advancing the interpretation of seismic data, with respect to extracting bulk information about crystal anisotropy, without having to drill an ice core and with special regard to future applications employing ultrasonic sounding.
Publisher: Copernicus Publications
Keywords: Antarktis; glasiologi

Mapping glacier-related research in polar regions: a bibliometric analysis of research output from 1987 to 2016 - Liang, Qi; Peng, Sha; Niu, Beibei; Zhou, Chunxia; Wang, Zhen (Polar Research, 2018)
We carried out a bibliometric analysis of literature related to glaciers in polar regions from the period 1987–2016 indexed in the Science Citation Index Expanded database. A comprehensive review was performed by analysing the research output trends, publication categories, main journals, leading countries and their collaborations, leading scientists, author keywords and Keywords Plus. The results indicated that the number of publications related to glaciers in polar regions has increased rapidly. The USA and several European countries, including the UK, France, Germany and Switzerland, are the leaders in the field of glacial studies, as reflected both in the productivity measures and in the distribution of core scientists. Quaternary Science Reviews, the Journal of Glaciology, and Geophysical Research Letters were the most productive journals for glacial studies. The synthesized analysis of the keywords demonstrated the current research emphases and hinted at future research trends. Reconstructing past climate changes through studies of ice-core records is one of the most important research subjects. Numerical modelling has become a commonly used tool in polar region glacial research. A better understanding of the responses of glaciers to widespread climatic warming is needed now and in the future.
Keywords: Antarktis; bibliometri; glasiologi; isbreer; klimaendringer; litteratur; miljøendringer; polarområdene

The relationship between coastal weather and foraging behaviour of chinstrap penguins, Pygoscelis antarctica - Lowther, Andrew D; Trathan, Phil; Tarroux, Arnaud; Lydersen, Christian; Kovacs, Kit M (ICES Journal of Marine Science, 2018)
There is increasing interest in using higher-trophic level predators as ecosystem indicators because their performance is presumed to be linked to the overall function of the ecosystem that supports them. In the southwest Atlantic sector of the Southern Ocean, Antarctic krill (Euphausia superba) supports huge predator populations as well as a growing commercial fishery. To utilize information from the ecosystem in an adaptive framework for sustainably managing krill catch levels, performance indices of krill predators have been proposed as a proxy for krill abundance. However, there are several potentially confounding sources of variability that might impact predator performance such as the effects of environmental variability and fishing pressure on krill availability at scales relevant to predators. In this context, our study capitalises on the occurrence of an unexpected El Niño event to characterise how environmental variability can drive changes in predator foraging behaviour. We demonstrate a clear link between coastal downwelling and changes in the at-sea habitat usage of chinstrap penguins (Pygoscelis antarctica) foraging in a local krill fishing area. Penguins tracked from their breeding colonies on Powell Island, Antarctic Peninsula, undertook fewer, longer foraging trips during the downwelling-affected season compared with the season where no such downwelling was detected, suggesting that changes in climate-driven oceanography may have reduced krill availability along the northern shelf of the island. Our study demonstrates that penguin foraging behaviour is modified by scale-dependent processes, which if not accounted for may result in erroneous conclusions being drawn when using penguins as bioindicators of krill abundance.
Keywords: Sørishavet; marinbiologi; meteorologi; ornitologi; pingviner; økologi

The moral limits of territorial claims in Antarctica - Mancilla, Alejandra (Ethics & International Affairs, 2018)
By virtue of the Antarctic Treaty, signed in 1959, the territorial claims to Antarctica of seven of the original signatories were held in abeyance or “frozen.” Considered by many as an exemplar of international law, the Antarctic Treaty System has come to be increasingly questioned, however, in a very much changed global scenario that presents new challenges to the governance of the White Continent. In this context, it is necessary to gain a clearer understanding of the moral weight of those initial claims, which stand (despite being frozen) as a cornerstone of the treaty. The aim of this article is to offer an appraisal of such claims, which may be divided into two main kinds: those grounded on some relevant link to the territory, and those grounded on official documents and geographical doctrines. After pointing to the limitations and challenges that they face, I conclude with some remarks about how this assessment ought to serve as a starting point to rethink the territorial status of Antarctica.
Keywords: Antarktis; historie; jus; politikk; ressurser

Observations of Ice Nucleating Particles Over Southern Ocean Waters - McCluskey, Christina S; Hill, Thomas C J; Humphries, Ruhi S; Rauker, Anne M; Moreau, Sebastien; Strutton, P G; Chambers, Scott Dudley; Williams, Alastair G; McRobert, I; Ward, J; Keywood, Melita D; Harnwell, J; et al. (Geophysical Research Letters, 2018)
A likely important feature of the poorly understood aerosol-cloud interactions over the Southern Ocean (SO) is the dominant role of sea spray aerosol, versus terrestrial aerosol. Ice nucleating particles (INPs), or particles required for heterogeneous ice nucleation, present over the SO have not been studied in several decades. In this study, boundary layer aerosol properties and immersion freezing INP number concentrations (nINPs) were measured during a ship campaign that occurred south of Australia (down to 53°S) in March–April 2016. Ocean surface chlorophyll a concentrations ranged from 0.11 to 1.77 mg/m3, and nINPs were a factor of 100 lower than historical surveys, ranging from 0.38 to 4.6 m−3 at −20 °C. The INP population included organic heat-stable material, with contributions from heat-labile material. Lower INP source potentials of SO seawater samples compared to Arctic seawater were consistent with lower ice nucleating site densities in this study compared to north Atlantic air masses.
Keywords: Sørishavet; atmosfæren; iskjerner; iskrystaller; klimatologi; marin organisk aerosol; meteorologi; skyer

Chinstrap penguin population genetic structure: one or more populations along the Southern Ocean? - Mura-Jornet, Isidora; Pimentel, Carolina; Dantas, Gisele P M; Petry, Maria Virginia; González-Acuña, Daniel; Barbosa, Andrés; Lowther, Andrew D; Kovacs, Kit M; Poulin, Elie; Vianna, Juliana A (BMC Evolutionary Biology, 2018)
Keywords: Bouvetøya; Sørishavet; fugler; genetikk; marin biologi; ornitologi; pingviner

Net Community Production in the Southern Ocean: Insights From Comparing Atmospheric Potential Oxygen to Satellite Ocean Color Algorithms and Ocean Models - Nevison, Cynthia; Munro, David; Lovenduski, Nicole; Cassar, Nicolas; Keeling, Ralph; Krummel, Paul; Tjiputra, Jerry (Geophysical Research Letters, 2018)
The contribution of oceanic net community production (NCP) to the observed seasonal cycle in atmospheric potential oxygen (APO) is estimated at Cape Grim, Tasmania. The resulting APONCP signal is compared to satellite and ocean model-based estimates of POC export and NCP across the Southern Ocean. The satellite products underestimate the amplitude of the observed APONCP seasonal cycle by more than a factor of 2. Ocean models suggest two reasons for this underestimate: (1) Current satellite products substantially underestimate the magnitude of NCP in early spring. (2) Seasonal O2 outgassing is supported in large part by storage of carbon in DOC and living biomass. More DOC observations are needed to help evaluate this latter model prediction. Satellite products could be improved by developing seasonally dependent relationships between remote sensing chlorophyll data and in situ NCP, recognizing that the former is a measure of mass, the latter of flux.
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; karboneksport; marin biologi; oseanografi

Mesospheric Nitric Acid Enhancements During Energetic Electron Precipitation Events Simulated by WACCM-D - Orsolini, Yvan J.; Smith-Johnsen, Christine; Marsh, Daniel R.; Stordal, Frode; Rodger, Craig J.; Verronen, Pekka T.; Clilverd, Mark A. (Journal of Geophysical Research: Atmospheres, 2018)
While observed mesospheric polar nitric acid enhancements have been attributed to energetic particle precipitation through ion cluster chemistry in the past, this phenomenon is not reproduced in current whole-atmosphere chemistry-climate models. We investigate such nitric acid enhancements resulting from energetic electron precipitation events using a recently developed variant of the Whole Atmosphere Community Climate Model (WACCM) that includes a sophisticated ion chemistry tailored for the D-layer of the ionosphere (50–90 km), namely, WACCM-D. Using the specified dynamics mode, that is, nudging dynamics in the troposphere and stratosphere to meteorological reanalyses, we perform a 1-year-long simulation (July 2009–June 2010) and contrast WACCM-D with the standard WACCM. Both WACCM and WACCM-D simulations are performed with and without forcing from medium-to-high energy electron precipitation, allowing a better representation of the energetic electrons penetrating into the mesosphere. We demonstrate the effects of the strong particle precipitation events which occurred during April and May 2010 on nitric acid and on key ion cluster species, as well as other relevant species of the nitrogen family. The 1-year-long simulation allows the event-related changes in neutral and ionic species to be placed in the context of their annual cycle. We especially highlight the role played by medium-to-high energy electrons in triggering ion cluster chemistry and ion-ion recombinations in the mesosphere and lower thermosphere during the precipitation event, leading to enhanced production of nitric acid and raising its abundance by 2 orders of magnitude from 10−4 to a few 10−2 ppb.
Keywords: Antarktis; elektroner; energiske partikler; geomagnetiske stormer; geovitenskap; ionosfæren; klimamodeller; meteorologi; polarområdene; salpetersyre; stratosfæren

Psoroma antarcticum, a new lichen species from Antarctica and neighbouring areas - Park, Chae Haeng; Hong, Soon Gyu; Elvebakk, Arve (Polar Biology, 2018)
Keywords: Antarktis; biodiversitet; botanikk; lav; moser; planter

Multi-temporal variation of the Ross Sea Polynya in response to climate forcings - Park, Jinku; Kim, Hyun-Cheol; Kidwell, Autumn; Hwang, Jihyun (Polar Research, 2018)
The multi-temporal scales of two physical characteristics (areas and occurrence time) of the Ross Sea Polynya (RSP) in Antarctica were analysed using a sea-ice concentration data set (1979–2014) derived from the Scanning Multichannel Microwave Radiometer, the Special Sensor Microwave Imager and Sensor Microwave Imager Sounder. Then, the Ensemble Empirical Mode Decomposition (EEMD) was applied to the data sets to decompose signals into finite numbers of intrinsic mode functions and a residual mode: long time trend. This approach allowed us to understand the long-term variability of the RSP area and occurrence in response to atmospheric forcing through teleconnections between low and high latitudes by comparing the Nino3.4 and Southern Annular Mode (SAM) indices. The nonlinear trend of the RSP areas derived from the EEMD residual had an upward trending shift in the early 1990s and was fairly consistent with the nonlinear trend of Nino3.4. However, the trend of RSP occurrence time progressively increased and had a significant effect on the long time scale. The trend of the RSP area is significantly correlated (+0.98) with the ratio of the trend of the meridional to zonal wind components related with the nonlinearity of Nino3.4, suggesting that meridional wind stress dominated the changes of the polynya area in the Ross Sea. In addition, the nonlinear trends between the SAM and RSP occurrence time show a strong positive correlation, contributing to the earlier onset of polynya expansion and delayed connection with the open ocean owing to enhanced southerly winds.
Keywords: Sørishavet; havis; klimaendringer; klimatologi; oseanografi; polynja; sjøis; sørlig oscillasjon

Influence of meteorological parameters on atmospheric CO2 at Bharati, the Indian Antarctic research station - Pathakoti, Mahesh; Gaddamidi, Sreenivas; Gharai, Biswadip; Sudhakaran Syamala, Prijith; Venkata Narasimha Rao, Pamaraju; Choudhury, Saroj Bandh; Venkata Raghavendra, Kaila; Dadhwal, Vinay Kumar (Polar Research, 2018)
During the 35th Indian Scientific Expedition to Antarctica, measurements of atmospheric carbon dioxide (CO 2 ) were carried out using a Li-Cor CO 2 /H 2 O analyser at Bharati, the Indian Antarctic research station. This study examines the short-term variability of atmospheric CO 2 during the austral summer (January–February) of 2016. An average of 396.25 ± 4.20 ppm was observed during the study period. Meteorological parameters such as relative humidity, precipitation, wind speed, air temperature and atmospheric boundary layer height in conjunction with photosynthetically active radiation, the biological activity indicator which modulates atmospheric CO 2 concentration have been investigated. High wind speed (>20 m s −1 ) combined with precipitation scavenges CO 2 in the atmosphere, resulting in low concentrations at the study site. The lowest CO 2 concentration of 385 ppm coincided with heavy precipitation of 15 mm during study period. Statistical analysis of the data shows that precipitation and relative humidity independently correlated 55% (r = −0.55) and 32% (r = −0.32), respectively, with the variability of CO 2 mixing in the atmosphere at the study site. Atmospheric CO 2 was significantly correlated with precipitation alone with a p value of 0.003. Further, multiple regression analysis was performed to test the significant relation between variability of atmospheric CO 2 and meteorological parameters. Long-range air-mass transport analysis depicted that the majority of the air masses are reaching the study site through the oceanic region.
Keywords: Antarktis; atmosfæren; drivhuseffekt; drivhusgasser; forskning; karbondioksid; klimagasser; luftmassetransport; meteorologi; nedbør; polarområdene

Planktonic food web structure at SSTF and PF in the Indian sector of the Southern Ocean during austral summer 2011 - Pillai, H U K; Anilkumar, N; Achuthankutty, C T; Mendes, C R; Sabu, P; Jayalakshmi, K V; Devi, C R Asha; Dessai, Deepti; George, Jenson; Pavithran, Sini; Hari Devi, C K; Tripathy, S C; et al. (Polar Research, 2018)
This study aims to describe the planktonic food web structure with respect to phytoplankton biomass (chlorophyll a ) and prevailing environmental conditions at the South Subtropical Front (SSTF) and the Polar Front (PF) in the Indian sector of the Southern Ocean. Sampling was carried out at each front for 72 hrs, at 6-hr intervals, during the austral summer 2011. Considerable variations were observed in the hydrography between these two fronts. A strong temperature minimum layer was observed at the PF. Although the surface primary production and chlorophyll a values showed similar trends at both the fronts, the water column values of these parameters showed major disparities. The phytoplankton composition also revealed marked difference between the fronts. A deep chlorophyll maximum concordant with the upper limit of the temperature minimum layer was prominent at the PF. The microzooplankton abundance at the SSTF was twice as high as at the PF. The mesozooplankton biovolume and population density also showed considerable variations between these fronts. Noticeable diel variations were observed in the surface mesozooplankton biovolumes at both the fronts and the copepod Pleuromamma gracilis showed active diel vertical migration at SSTF. Both the grazing and senescence indices showed significant variations between these fronts, suggesting a disparity in the ecological efficiency of the two regions. The variability observed in the plankton community structure with respect to the hydrography and the biological components measured suggests that a multivorous food web at the SSTF and a conventional food web at the PF prevailed during the period of study.
Keywords: Sørishavet; biomasse; fytoplankton; hydrografi; marin biologi; zooplankton; økosystemer

Interhemispheric Survey of Polar Cap Aurora - Reidy, Jade; Fear, Robert; Whiter, Daniel; Lanchester, Betty; Kavanagh, Andrew John; Milan, Steve; Carter, Jennifer; Paxton, Larry; Zhang, Yongliang (Journal of Geophysical Research: Space Physics, 2018)
This study investigates the interhemispheric nature of polar cap auroras via ultraviolet imaging, combined with particle data, to determine whether they occur on open or closed field lines. Data from the SSUSI (Special Sensor Ultraviolet Spectrographic Imager) instrument on board the DMSP (Defence Meteorological Satellite Program) spacecraft are examined. The DMSP spacecraft are in 90-min orbits; hence, images of each hemisphere are separated by 45 min providing a good opportunity for interhemispheric study. 21 polar cap arc (PCA) events are recorded in December 2015 which have particle data from the SSJ/4 particle spectrometer associated with an arc in at least one hemisphere. Nine events are found to contain 'arcs' consistent with a closed field line mechanism, that is, arcs associated with an ion signature present in both hemispheres. Six events contained arcs that were consistent with an 'open field line' mechanism, that is, they were associated with electron-only precipitation. Events containing arcs that were not consistent with either of these expectations are also explored, including an example of a 'non-conjugate' theta aurora and an interesting example of auroral morphology similar to a PCA which is associated with a geomagnetic storm. Seasonal effects are also investigated through a statistical analysis of PCAs over 4 months in 2015. It is found that PCAs are visible in the SSUSI data at least 20% of the time and that it is likely some are missed due to the spacecraft field of view and poor sensitivity in the summer hemisphere due to increased solar illumination.
Keywords: Antarktis; astronomi; energiske partikler; geomagnetiske stormer; meteorologi; polarlys; polarområdene; solvind

Increasing temperature may shift availability of euphausiid prey in the Southern Ocean - Richerson, Kate; Driscoll, Ryan; Mangel, Marc (Marine Ecology Progress Series, 2018)
Climate change is predicted to affect Southern Ocean biota in complex ways. Euphausiids play a crucial role in the trophodynamics of the ecosystem, and their status under future environmental scenarios is the subject of much concern. Thysanoessa macrura is the most widely distributed, numerically abundant, and ubiquitous euphausiid south of the Polar Front and may be an underappreciated prey species. T. macrura is eurythermic and may be better able to tolerate warming ocean temperatures in comparison to the more stenothermic Antarctic krill Euphausia superba. We use temperature-dependent growth models and biomass per recruit to investigate how the availability of this euphausiid to predators may change under a range of temperature scenarios. We contrast this with the availability of E. superba and find that, under some ranges of temperature change, increasing T. macrura growth may be able to partially compensate for decreasing E. superba growth in terms of biomass available for predators. However, in spite of its considerable biomass, other aspects of this species, such as its size and habitat, may limit its potential to replace E. superba in the diet of many predators. KEYWORDS: Thysanoessa macrura · Euphausia superba · Growth · Temperature · Climate change · Krill predators · Southern Ocean · Euphausiids · Modeling
Keywords: Sørishavet; biomasse; havoppvarming; klimaendringer; krill; marin biologi; marine økosystemer; miljøendringer; plankton

A New Bathymetry for the Southeastern Filchner-Ronne Ice Shelf: Implications for Modern Oceanographic Processes and Glacial History - Rosier, Sebastian H R; Hofstede, Coen; Brisbourne, Alex Mark; Hattermann, Tore; Nicholls, Keith William; Davis, Peter E D; Anker, Paul; Hillenbrand, Claus-Dieter; Smith, Andrew M; Corr, Hugh F (Journal of Geophysical Research: Oceans, 2018)
The Filchner-Ronne Ice Shelf, the ocean cavity beneath it, and the Weddell Sea that bounds it, form an important part of the global climate system by modulating ice discharge from the Antarctic Ice Sheet and producing cold dense water masses that feed the global thermohaline circulation. A prerequisite for modeling the ice sheet and oceanographic processes within the cavity is an accurate knowledge of the sub-ice sheet bedrock elevation, but beneath the ice shelf where airborne radar cannot penetrate, bathymetric data are sparse. This paper presents new seismic point measurements of cavity geometry from a particularly poorly sampled region south of Berkner Island that connects the Filchner and Ronne ice shelves. An updated bathymetric grid formed by combining the new data with existing data sets reveals several new features. In particular, a sill running between Berkner Island and the mainland could alter ocean circulation within the cavity and change our understanding of paleo-ice stream flow in the region. Also revealed are deep troughs near the grounding lines of Foundation and Support Force ice streams, which provide access for seawater with melting potential. Running an ocean tidal model with the new bathymetry reveals large differences in tidal current velocities, both within the new gridded region and further afield, potentially affecting sub-ice shelf melt rates.
Keywords: Sørishavet; batymetri; brehylle; innlandsis; isbrem; isshelf; klima; oseanografi; tidevann

Psychological Hibernation in Antarctica - Sandal, Gro Mjeldheim; van deVijver, Fons J. R.; Smith, Nathan (Frontiers in Psychology, 2018)
Human activity in Antarctica has increased sharply in recent years. In particular during the winter months, people are exposed to long periods of isolation and confinement and an extreme physical environment that poses risks to health, well-being and performance. The present study aimed to gain a better understanding of processes contributing to psychological resilience in this context. Specifically, the study examined how the use of coping strategies changed over time, and the extent to which changes coincided with alterations in mood and sleep. Two crews (N = 27) spending approximately 10 months at the Concordia station completed the Utrecht Coping List, the Positive and Negative Affect Schedule (PANAS), and a structured sleep diary at regular intervals (x 9). The results showed that several variables reached a minimum value during the midwinter period, which corresponded to the third quarter of the expedition. The effect was particularly noticeable for coping strategies (i.e., active problem solving, palliative reactions, avoidance, and comforting cognitions). The pattern of results could indicate that participants during Antarctic over-wintering enter a state of psychological hibernation as a stress coping mechanism.
Keywords: Antarktis; overvintring; polarekspedisjoner; polarforskere; polarområdene; psykologi

Description of plant communities on Half Moon Island, Antarctica - Schmitz, Daniela; Putzke, Jair; Pereira de Albuquerque, Margéli; Schünemann, Adriano Luis; Costa Beber Vieira, Frederico; de Carvalho Victoria, Filipe de Carvalho Victoria; Batista Pereira, Antônio (Polar Research, 2018)
During February–March of the austral summers of 2013/14 and 2014/2015, fieldwork was performed on Half Moon Island, South Shetland Archipelago, Antarctica, to evaluate the distribution and abundance of mosses and lichens, as well as to describe and map the plant communities there. The quadrat (20 × 20 cm) sampling method was employed in a phytosociological study that aimed to describe these communities. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The number of species totalled 38 bryophytes, 59 lichens, only one flowering plant (Deschampsia antarctica Desv.), and two macroscopic terrestrial algae. Five types of plant communities were identified on the island, as follows: (1) fruticose lichen and moss cushion, (2) moss carpet, (3) muscicolous lichen, (4) crustose lichen and (5) moss turf.
Keywords: Antarktis; botanikk; bryozoa; flora; fytososiologi; lav; moser; planter; økologi

Remarkable structural resistance of a nanoflagellate-dominated plankton community to iron fertilization during the Southern Ocean experiment LOHAFEX - Schulz, Isabelle; Montresor, Marina; Klaas, Christine; Assmy, Philipp; Wolzenburg, Sina; Gauns, Mangesh; Sarkar, Amit; Thiele, Stefan; Wolf-Gladrow, Dieter; Naqvi, Wajih; Smetacek, Victor (Marine Ecology Progress Series, 2018)
The genesis of phytoplankton blooms and the fate of their biomass in iron-limited, high-nutrient-low-chlorophyll regions can be studied under natural conditions with ocean iron fertilization (OIF) experiments. The Indo-German OIF experiment LOHAFEX was carried out over 40 d in late summer 2009 within the cold core of a mesoscale eddy in the productive south-west Atlantic sector of the Southern Ocean. Silicate concentrations were very low, and phytoplankton biomass was dominated by autotrophic nanoflagellates (ANF) in the size range 3-10 µm. As in all previous OIF experiments, the phytoplankton responded to iron fertilization by increasing the maximum quantum yield (Fv/Fm) and cellular chlorophyll levels. Within 3 wk, chlorophyll levels tripled and ANF biomass doubled. With the exception of some diatoms and dinoflagellates, the biomass levels of all other groups of the phyto- and protozooplankton (heterotrophic nanoflagellates, dinoflagellates and ciliates) remained remarkably stable throughout the experiment both inside and outside the fertilized patch. We attribute the unusually high biomass attained and maintained by ANF to the absence of their grazers, the salps, and to constraints on protozooplankton grazers by heavy predation exerted by the large copepod stock. The resistance to change of the ecosystem structure over 38 d after fertilization, indicated by homogeneity at regional and temporal scales, suggests that it was locked into a stable, mature state that had evolved in the course of the seasonal cycle. The LOHAFEX bloom provides a case study of a resistant/robust dynamic equilibrium between auto- and heterotrophic ecosystem components resulting in low vertical flux both inside and outside the patch despite high biomass levels. KEYWORDS: Antarctic · Protists · Fe-limitation · Si-limitation · Ecology-biogeochemistry relationship · Carbon:chlorophyll ratios · Ecosystem stability
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; marin biologi; økologi; økosystemer

A continent-wide search for Antarctic petrel breeding sites with satellite remote sensing - Schwaller, Mathew R; Lynch, Heather J; Tarroux, Arnaud; Prehn, Brandon (Remote Sensing of Environment, 2018)
The Antarctic petrel (Thalassoica antarctica) has been identified as a key species for monitoring the status and health of the Southern Ocean and Antarctic ecosystems. Breeding colonies of the Antarctic petrel are often found on isolated nunataks far from inhabited stations, some up to hundreds of kilometers from the shoreline. It is difficult therefore to monitor and census known colonies, and it is believed that undiscovered breeding locations remain to be found. We developed an algorithm that can detect Antarctic petrel colonies and used it to complete a continent-wide survey using Landsat-8 Operational Line Imager (OLI) imagery in Antarctica up to the southernmost extent of Landsat's orbital view at 82.68°S. Our survey successfully identified 8 known Antarctic petrel colonies containing 86% of the known population of Antarctic petrels. The survey also identified what appears to be a significant population of breeding birds in areas not known to host breeding Antarctic petrel colonies. Our survey suggests that the breeding population at Mt. Biscoe (66°13′S 51°21′E), currently reported to be in the 1000s, may actually be on the order of 400,000 breeding pairs, which would make it the largest known Antarctic petrel breeding colony in the world. The algorithm represents a first-ever attempt to apply satellite remote sensing to assess the distribution and abundance of the Antarctic petrel on a continent-wide basis. As such, we note several algorithm shortcomings and identify research topics for algorithm improvement. Even with these caveats, our algorithm for identifying Antarctic petrel colonies with Landsat imagery demonstrates the feasibility of monitoring their populations using satellite remote sensing and identifies breeding locations, including Mt. Biscoe, that should be considered high priorities for validation with directed field surveys.
Keywords: Antarktis; hekkekoloni; jordobservasjon; ornitologi; petreller; sjøfugler; zoologi

Nighttime mesospheric ozone enhancements during the 2002 southern hemispheric major stratospheric warming - Smith-Johnsen, Christine; Orsolini, Yvan; Stordal, Frode; Limpasuvan, Varavut; Pérot, Kristell (Journal of Atmospheric and Solar-Terrestrial Physics, 2018)
Sudden Stratospheric Warmings (SSW) affect the chemistry and dynamics of the middle atmosphere. Major warmings occur roughly every second winter in the Northern Hemisphere (NH), but has only been observed once in the Southern Hemisphere (SH), during the Antarctic winter of 2002. Observations by the Global Ozone Monitoring by Occultation of Stars (GOMOS, an instrument on board Envisat) during this rare event, show a 40% increase of ozone in the nighttime secondary ozone layer at subpolar latitudes compared to non-SSW years. This study investigates the cause of the mesospheric nighttime ozone increase, using the National Center for Atmospheric Research (NCAR) Whole Atmosphere Community Climate Model with specified dynamics (SD-WACCM). The 2002 SH winter was characterized by several reductions of the strength of the polar night jet in the upper stratosphere before the jet reversed completely, marking the onset of the major SSW. At the time of these wind reductions, corresponding episodic increases can be seen in the modelled nighttime secondary ozone layer. This ozone increase is attributed largely to enhanced upwelling and the associated cooling of the altitude region in conjunction with the wind reversal. This is in correspondence to similar studies of SSW induced ozone enhancements in NH. But unlike its NH counterpart, the SH secondary ozone layer appeared to be impacted less by episodic variations in atomic hydrogen. Seasonally decreasing atomic hydrogen plays however a larger role in SH compared to NH.
Keywords: Antarktis; atmosfæren; geovitenskap; ozonlaget

Revisiting perceptions and evolving culture: a community dialogue on women in polar research - Starkweather, Sandra; Seag, M; Lee, O; Pope, A (Polar Research, 2018)
Women have made outstanding contributions to polar research in recent decades, though full engagement may be hindered by persistent inequities, including notably the prevalence of workplace harassment. Remote field settings, such as those pervasive in polar research, have been identified as particularly susceptible to cultures of harassment. It was therefore timely at the Polar 2018 Open Science Conference in Davos, Switzerland, to convene a discussion focused on women’s perspectives and experiences. A panel discussion—“From Entering the Field to Taking the Helm: Perspectives of Women in Polar Research”—took place on 20 June 2018 and featured five women undertaking work from marine biotechnology to organizational leadership, across career levels. Over 300 conference attendees joined the lunchtime panel. The panellists’ perspectives on historical barriers, current challenges and future prospects revealed that while challenges persist, experiences vary greatly. Audience engagement underscored the need to sustain dialogue at polar meetings, to bring visibility to the statistics related to workplace harassment and to encourage polar science organizations to assume leadership on promoting equitable workplace culture.
Keywords: Antarktis; arbeidsmiljø; kjønn; kultur; likestilling; polarforskning; sosiologi; trakassering; vitenskap

Precipitation instruments at Rothera Station, Antarctic Peninsula: a comparative study - Tang, Malcolm S Y; Nettukandy Chenoli, Sheeba; Colwell, Steve; Grant, Rosey; Simms, Mairi; Law, John; Abu Samaha, Azizan (Polar Research, 2018)
Direct measurement of precipitation in the Antarctic using ground-based instruments is important to validate the results from climate models, reanalyses and satellite observations. Quantifying precipitation in Antarctica faces many unique challenges such as wind and other technical difficulties due to the harsh environment. This study compares a variety of precipitation measurements in Antarctica, including satellite data and reanalysis fields at Rothera Station, Antarctica Peninsula. The tipping bucket gauges (TBGs) were less sensitive than laserbased sensors (LBSs). The most sensitive LBS (Visibility and Present Weather Sensor, VPF-730) registered 276 precipitation days, while the most sensitive TBG (Universal Precipitation Gauge, UPG-1000) detected 152 precipitation days. Case studies of the precipitation and seasonal accumulation results show the VPF-730 to be the most reliable precipitation sensor of the evaluated instruments. The precipitation amounts given by the reanalyses were positively correlated with wind speed. The precipitation from the Japanese 55-year Reanalysis was most affected by wind speed. Case studies also show that during low wind periods, precipitation measurements from the instruments were very close to the precipitation measurement given by the Global Precipitation Climatology Project (GPCP) 1-degreedaily (1DD) data. During strong wind events, the GPCP 1DD did not fully capture the effect of wind, accounting for the relatively small precipitation amount. The Laser Precipitation Monitor (LPM) and Campbell Scientific-700 (CS700H) experienced instrumental errors during the study, which caused the precipitation readings to become exceedingly high and low, respectively. Installing multiple LBSs in different locations (in close proximity) can help identify inconsistency in the readings.
Keywords: Antarktis; analyser; klimatologi; meteorologi; nedbør; satellitt observasjoner

Temporal variation in trophic relationships among three congeneric penguin species breeding in sympatry - Tarroux, Arnaud; Lydersen, Christian; Trathan, Philip N; Kovacs, Kit M. (Ecology and Evolution, 2018)
Penguins are a monophyletic group in which many species are found breeding sympatrically, raising questions regarding how these species coexist successfully. Here, the isotopic niche of three sympatric pygoscelid penguin species was investigated at Powell Island, South Orkney Islands, during two breeding seasons (austral summers 2013–2014 and 2015–2016). Measurements of carbon (δ13C) and nitrogen (δ15N) stable isotope ratios were obtained from blood (adults) or feather (chicks) samples collected from Adélie Pygoscelis adeliae, chinstrap P. antarctica, and gentoo P. papua penguins. Isotopic niche regions (a proxy for the realized trophic niches) were computed to provide estimates of the trophic niche width of the studied species during the breeding season. The isotopic niche regions of adults of all three species were similar, but gentoo chicks had noticeably wider isotopic niches than the chicks of the other two species. Moderate to strong overlap in isotopic niche among species was found during each breeding season and for both age groups, suggesting that the potential for competition for shared food sources was similar during the two study years, although the actual level of competition could not be determined owing to the lack of data on resource abundance. Clear interannual shifts in isotopic niche were seen in all three species, though of lower amplitude for adult chinstrap penguins. These shifts were due to variation in carbon, but not nitrogen, isotopic ratios, which could indicate either a change in isotopic signature of their prey or a switch to an alternative food web. The main conclusions of this study are that (1) there is a partial overlap in the isotopic niches of these three congeneric species and that (2) they responded similarly to changes that likely occurred at the base of their food chain between the 2 years of the study.
Keywords: Antarktis; fôring; hekkekoloni; klimaendringer; krill; miljøendringer; pingviner; plankton; stabile isotoper; zoologi

Investigation of Babesia sp. in pygoscelid penguins at the South Shetland Islands - Thijl Vanstreels, Ralph Eric; Ferreira Junior, Francisco C; de Angeli Dutra, Daniela; Epiphanio, Sabrina; Braga, Érika M; Pistorius, Pierre A; Catão-Dias, José Luiz (Polar Research, 2018)
Babesia spp. are tick-borne parasites, and 16 avian-infecting species have been described to date, including one species ( Babesia peircei ) that infects penguins. Considering the results of a recent study reporting Babesia sp. in penguins on Deception Island, South Shetland Islands, we re-examined the samples obtained in a previous investigation on the occurrence of blood parasites in adult Adélie ( Pygoscelis adeliae ), chinstrap ( Pygoscelis antarcticus ) and gentoo penguins ( Pygoscelis papua ) on King George and Elephant islands, South Shetland Islands. Notwithstanding a comprehensive re-examination of the blood smears, Babesia sp. was not detected. When we employed two nested PCR tests targeting the 18S rRNA gene of Babesia , a considerable proportion of the samples produced positive results; however, gene sequencing revealed these were due to cross-amplification of non-target organisms. We therefore did not detect Babesia sp. infection in penguins on King George and Elephant islands. Additional studies will be valuable to clarify the distribution and epidemiology of tick-borne pathogens in sub-Antarctic and Antarctic seabirds.
Keywords: Antarktis; biologi; epidemiologi; ornitologi; parasitter; pingviner; sjøfugler; zoologi

Topographic Steering of Enhanced Ice Flow at the Bottleneck Between East and West Antarctica - Winter, Kate; Ross, Neil; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F J; Forsberg, René; Matsuoka, Kenichi; Olesen, Arne V; Casal, Tania G (Geophysical Research Letters, 2018)
Hypothesized drawdown of the East Antarctic Ice Sheet through the “bottleneck” zone between East and West Antarctica would have significant impacts for a large proportion of the Antarctic Ice Sheet. Earth observation satellite orbits and a sparseness of radio echo sounding data have restricted investigations of basal boundary controls on ice flow in this region until now. New airborne radio echo sounding surveys reveal complex topography of high relief beneath the southernmost Weddell/Ross ice divide, with three subglacial troughs connecting interior Antarctica to the Foundation and Patuxent Ice Streams and Siple Coast ice streams. These troughs route enhanced ice flow through the interior of Antarctica but limit potential drawdown of the East Antarctic Ice Sheet through the bottleneck zone. In a thinning or retreating scenario, these topographically controlled corridors of enhanced flow could however drive ice divide migration and increase mass discharge from interior West Antarctica to the Southern Ocean.
Keywords: Antarktis; glasiologi; innlandsis; isgjennomtrengende; isstrøm; radarundersøkelser

Global Cooling Contributed to the Establishment of a Modern-Like East Asian Monsoon Climate by the Early Miocene - Zhang, Ran; Zhang, Zhongshi; Jiang, Dabang (Geophysical Research Letters, 2018)
The establishment of a modern-like monsoon climate in East Asia by the early Miocene was a complex process forced by several factors, and previous studies paid less attention to global cooling. Here we investigate this process using climate modeling by considering changes in topography and global cooling under the early Miocene boundary conditions. Using early Miocene paleogeography and an atmospheric CO2 concentration of 560 ppmv, our model results indicate that a nonzonal climate pattern has appeared in East China but that this climate exhibits weak precipitation and wind seasonality. Such seasonality strengthens as the concentration of atmospheric CO2 decreases from 560 to 420 ppmv and resembles the modern-like condition after the growth of the Antarctic ice sheet. Although the development of East Asian topography can further strengthen this seasonality, our results indicate that global cooling is also pivotal for the establishment of a modern-like monsoon climate in East Asia.
Keywords: Antarktis; innlandsis; klimamodeller; klimatologi; nedbør; paleogeografi

Abnormal gonads in the Antarctic toothfish (Dissostichus mawsoni Norman, 1937 [Perciformes: Nototheniidae]): the first record and histological description - Zhukova, Kristina A; Gordeev, Ilya I; Kuznetsova, Elena N (Polar Research, 2018)
This paper describes the morphology and histology of abnormal gonads in Antarctic toothfish (Dissostichus mawsoni) and the possibility of intersexuality and senescence of some individuals. Two old (approximately 25 years) and large (184–185 cm) specimenswith abnormal gonadswere caught in the Antarctic during commercial fishing for toothfish and studied using histological methods. Although D. mawsoni is well-known and extensively studied, this is the first study dealing with abnormal gonads in the species. The histological analysis revealed that the gonads of the first specimen contained both male and female germ cells (ovotestis), the testicular and ovarian tissues being separated by a thick layer of connective tissue. The female portion was composed of secondary vitellogenic oocytes, primary vitellogenic, cortical alveolar and primary growth oocytes, while the testes contained cysts of spermatogonia and primary spermatocyte. The gonads of the second specimen were small, filiform and showed massive growth of the connective tissue, which occupied almost the entire gonad; a few spermatogonia without visible cystswere found. This study extends our understanding of sexual development in Antarctic toothfish, documenting the possibility of long-term interruptions in the reproductive cycle of this species.
Keywords: Sørishavet; fisker; gonader; histologi; marin biologi; morfologi; oseanografi; reproduksjon

Keynes, Trouton and the Hector Whaling Company. A personal and professional relationship - Basberg, Bjørn L (Business History, 2017)
John Maynard Keynes’ activities on the stock market are well known. One company in which he bought stocks was the Hector Whaling Company Ltd., London – a comparatively small and little known company founded in 1928. The director of this company was Rupert Trouton. He had worked with Keynes for the Government during the First World War, was his student at Cambridge, and became a close partner in the City from the 1920s and onwards. The reason why Keynes invested in Hector was obviously his association with Rupert Trouton. The first part of this paper explores briefly the development of the Hector Whaling Company and its origins in Norway. The main part analyses the relationship between Trouton and Keynes. The focus is on their co-operation relating to Hector Whaling, but their relationship regarding various other businesses, as well as on the personal level, is also described. The paper is based on studies of the Keynes archives in Cambridge as well as newly available archives of the Hector company. The analysis provides new insights to the more general question on the motivations and decisions behind Keynes’ stock market investments as well as the internationalization of the whaling industry in the 1920s and 30s.
Publisher: Routledge
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Persistent Organic Pollutants in the East Antarctic Atmosphere: Inter-Annual Observations from 2010 to 2015 Using High-Flow-Through Passive Sampling - Bengtson Nash, Susan M; Wild, Sean J; Hawker, Darryl W; Cropp, Roger A; Hung, Hayley; Wania, Frank; Xiao, Hang; Bohlin-Nizzetto, Pernilla; Bignert, Anders; Broomhall, Sara (Environmental Science & Technology, 2017)
In the first multiyear sampling effort for POPs in the eastern Antarctic atmosphere, 32 PCBs and 38 organochlorine pesticides were targeted in air collected with a high-flow-through passive sampler. Agricultural chemicals were found to dominate atmospheric profiles, in particular HCB and endosulfan-I, with average concentrations of 12 600 and 550 fg/m3, respectively. HCB showed higher concentrations in the austral summer, indicative of local, temperature-dependent volatilisation, while endosulfan-I appeared to show fresh, late-austral-summer input followed by temporally decreasing levels throughout the year. The current-use herbicide, trifluralin, and the legacy pesticides mirex and toxaphene, were detected in Antarctic air for the first time. Trifluralin was observed at low but increasing levels over the five-year period. Its detection in the Antarctic atmosphere provides evidence of its persistence and long-range environmental transport capability. While a time frame of five years exceeds the duration of most Antarctic air monitoring efforts, it is projected that continuous monitoring at the decadal scale is required to detect an annual 10% change in atmospheric concentrations of key analytes. This finding emphasizes the importance of continuous, long-term monitoring efforts in polar regions, that serve a special role as sentinel environments of hemispheric chemical usage trends.
Publisher: American Chemical Society
Keywords: Antarktis; atmosfæren; forurensning; kjemiske analyser; miljøgifter

Ontogenetic changes in the feeding strategy of Lepidonotothen nudifrons (Pisces, Nototheniidae) off the South Shetland Islands and the Antarctic Peninsula - Blasina, Gabriela; Cazorla, Andrea Lopez; Antoni, Mariana Deli; Bruno, Daniel; Delpiani, Matías; Díaz de Astarloa, Juan Martín (Polar Research, 2017)
The diet and feeding strategy of Lepidonotothen nudifrons off the South Shetland Islands and the Antarctic Peninsula, as well as their variation in relation to ontogenetic stage (juvenile– adult) and sampling area, were determined by stomach contents analysis. Additionally, the trophic level of this species was estimated to determine its position within the Antarctic food web. Out of 247 specimens with prey in their stomachs, 144 were caught near the South Shetland Islands and 103 off the Antarctic Peninsula. Ontogenetic changes in the trophic ecology of L. nudifrons were observed in both areas and were mainly related to a decrease of copepods and an increase of euphausiids in the diet. The diet of juveniles from the South Shetland Islands was characterized by the dominance of calanoid copepods, followed by isopods and amphipods, whereas diet off the Antarctic Peninsula was dominated by amphipods and cyclopoid copepods. The diet in adults was dominated by amphipods and euphausiids in both areas. The specialization of individual predators on different prey types was observed when considering the whole population of L. nudifrons, but when ontogenetic stages were considered separately it showed a more mixed feeding strategy, with different dominant prey for each class. Although the trophic level increased with fish size, L. nudifrons can be classified as secondary consumer throughout its lifespan.
Keywords: Sørishavet; amfipoder; copepoder; euphausiacea; fauna; fisker; isopoder; marin zoologi; økosystemer

Fracture propagation and stability of ice shelves governed by ice shelf heterogeneity - Borstad, Chris; McGrath, Daniel; Pope, Allen (Geophysical Research Letters, 2017)
Tabular iceberg calving and ice shelf retreat occurs after full-thickness fractures, known as rifts, propagate across an ice shelf. A quickly evolving rift signals a threat to the stability of Larsen C, the Antarctic Peninsula's largest ice shelf. Here we reveal the influence of ice shelf heterogeneity on the growth of this rift, with implications that challenge existing notions of ice shelf stability. Most of the rift extension has occurred in bursts after overcoming the resistance of suture zones that bind together neighboring glacier inflows. We model the stresses in the ice shelf to determine potential rift trajectories. Calving perturbations to ice flow will likely reach the grounding line. The stability of Larsen C may hinge on a single suture zone that stabilizes numerous upstream rifts. Elevated fracture toughness of suture zones may be the most important property that allows ice shelves to modulate Antarctica's contribution to sea level rise.
Keywords: Antarktis; geofysikk; glasiologi; havnivåstigning; is; isberg; isbrem; isfjell; isshelf; kalv; kalving

Tsunami and infragravity waves impacting Antarctic ice shelves - Bromirski, Peter D; Chen, Zhao; Stephen, Ralph A; Gerstoft, Peter; Arcas, Diego; Diez, Anja; Aster, Richard C; Wiens, Douglas A; Nyblade, Andrew Arnold (Journal of Geophysical Research: Oceans, 2017)
The responses of the Ross Ice Shelf (RIS) to the 16 September 2015 8.3 (Mw) Chilean earthquake tsunami (>75 s period) and to oceanic infragravity (IG) waves (50–300 s period) were recorded by a broadband seismic array deployed on the RIS from November 2014 to November 2016. Here we show that tsunami and IG-generated signals within the RIS propagate at gravity wave speeds (∼70 m/s) as water-ice coupled flexural-gravity waves. IG band signals show measureable attenuation away from the shelf front. The response of the RIS to Chilean tsunami arrivals is compared with modeled tsunami forcing to assess ice shelf flexural-gravity wave excitation by very long period (VLP; >300 s) gravity waves. Displacements across the RIS are affected by gravity wave incident direction, bathymetry under and north of the shelf, and water layer and ice shelf thicknesses. Horizontal displacements are typically about 10 times larger than vertical displacements, producing dynamical extensional motions that may facilitate expansion of existing fractures. VLP excitation is continuously observed throughout the year, with horizontal displacements highest during the austral winter with amplitudes exceeding 20 cm. Because VLP flexural-gravity waves exhibit no discernable attenuation, this energy must propagate to the grounding zone. Both IG and VLP band flexural-gravity waves excite mechanical perturbations of the RIS that likely promote tabular iceberg calving, consequently affecting ice shelf evolution. Understanding these ocean-excited mechanical interactions is important to determine their effect on ice shelf stability to reduce uncertainty in the magnitude and rate of global sea level rise.
Keywords: Sørishavet; brehylle; havnivåstigning; is; isbrem; isshelf; kalv; kalving; oseanografi; seismologi

Patterns of fungal–algal symbiont association in Usnea aurantiaco-atra reveal the succession of lichen–moss communities in Fildes Peninsula, Antarctica - Cao, Shunan; Peng, Fang; Zheng, Hongyuan; Liu, Chuanpeng; Zhou, Qiming (Polar Research, 2017)
Usnea aurantiaco-atra is the most widespread flora in Fildes Peninsula. There are two growth types of U. aurantiaco-atra: the erect form on rocks and the prostrate form associated with mosses. Phylogenetic analysis showed that individuals of the two growth forms share genotypes. Moreover, haploid disequilibrium testing indicated no significant genetic difference for the two growth forms when fungal and algal internal transcribed spacer rDNA were treated as two alleles of one lichen individual. The two growth forms of U. aurantiaco-atra appear to reflect different stages of lichen–moss community succession. A mode is proposed for demonstrating the occurrence of this succession.
Keywords: Antarktis; botanikk; flora; fylogenetikk; lav; moser; planter

Microplastic in the surface waters of the Ross Sea (Antarctica): Occurrence, distribution and characterization by FTIR - Cincinelli, Alessandra; Scopetani, Costanza; Chelazzi, David; Lombardini, Emilia; Martellini, Tania; Katsoyiannis, Athanasios; Fossi, Maria Cristina; Corsolini, Simonetta (Chemosphere, 2017)
This is the first survey to investigate the occurrence and extent of microplastic (MPs) contamination in sub surface waters collected near-shore and off-shore the coastal area of the Ross Sea (Antarctica). Moreover, a non-invasive method to analyze MPs, consisting in filtration after water sampling and analysis of the dried filter through Fourier Transform Infrared Spectroscopy (FTIR) 2D Imaging, using an FPA detector, was proposed. The non-invasiveness of analytical set-up reduces potential bias and allows subsequent analysis of the filter sample for determination of other classes of contaminants. MPs ranged from 0.0032 to 1.18 particle per m3 of seawater, with a mean value of 0.17 ± 0.34 particle m−3, showing concentrations lower than those found in the oceans worldwide. MPs included fragments (mean 71.9 ± 21.6%), fibers (mean 12.7 ± 14.3%), and others (mean 15.4 ± 12.8%). The presence of different types of MPs was confirmed by FTIR spectroscopy, with predominant abundance of polyethylene and polypropylene. The potential environmental impact arising from scientific activities, such as marine activities for scientific purposes, and from the sewage treatment plant, was also evidenced.
Keywords: Rosshavet; Sørishavet; forurensning; mikroplast; miljøgifter

On the effect of topography and wind on warm water inflow—An idealized study of the southern Weddell Sea continental shelf system - Daae, Kjersti; Hattermann, Tore; Darelius, Elin; Fer, Ilker (Journal of Geophysical Research: Oceans, 2017)
An idealized eddy-resolving numerical model, with topographic features common to the southern Weddell Sea, is constructed to study mechanisms through which warm deep water enters a wide continental shelf with a trough. The open ocean, represented by a 1700 m deep channel, is connected to a 400 m deep shelf with a continental slope. The shelf is narrow (50 km) in the east but widens to 300 km at the center of the model domain. Over the narrow shelf, the slope front is balanced by wind-driven Ekman downwelling and counteracting eddy overturning, favoring on-shelf transport of warm water in summer scenarios when fresher surface water is present. Over the wide shelf, the Ekman downwelling ceases, and the mesoscale eddies relax the front. Inflow of warm water is sensitive to along-shelf salinity gradients and is most efficient when denser water over the wide shelf favors up-slope eddy transport along isopycnals of the V-shaped slope front. Inflow along the eastern side of the trough cannot penetrate the sill region due to potential vorticity constraints, while along the western trough flank, eddy-induced inflow crosses the sill and reaches the ice front. The warm inflow into the trough is sensitive to the density of the outflowing dense shelf water. For weaker winds, absence of the dense water outflow leads to a reversal of the trough circulation and a strong inflow of warm water, while for stronger winds, baroclinic effects become less important and the inflow is similar to experiments including dense water outflow.
Keywords: Sørishavet; Weddellhavet; batymetri; geofysikk; havstrømmer; hydrografi; klimamodeller; klimatologi; kontinentalsokkel; vannvirvler

A global ocean climatology of preindustrial and modern ocean δ13C - Eide, Marie; Olsen, Are; Ninnemann, Ulysses S; Johannessen, Truls (Global Biogeochemical Cycles, 2017)
We present a global ocean climatology of dissolved inorganic carbon δ13C (‰) corrected for the 13C-Suess effect, preindustrial δ13C. This was constructed by first using Olsen and Ninnemann's (2010) back-calculation method on data from 25 World Ocean Circulation Experiment cruises to reconstruct the preindustrial δ13C on sections spanning all major oceans. Next, we developed five multilinear regression equations, one for each major ocean basin, which were applied on the World Ocean Atlas data to construct the climatology. This reveals the natural δ13C distribution in the global ocean. Compared to the modern distribution, the preindustrial δ13C spans a larger range of values. The maxima, of up to 1.8‰, occurs in the subtropical gyres of all basins, in the upper and intermediate waters of the North Atlantic, as well as in mode waters with a Southern Ocean origin. Particularly strong gradients occur at intermediate depths, revealing a strong potential for using δ13C as a tracer for changes in water mass geometry at these levels. Further, we identify a much tighter relationship between δ13C and apparent oxygen utilization (AOU) than between δ13C and phosphate. This arises because, in contrast to phosphate, AOU and δ13C are both partly reset when waters are ventilated in the Southern Ocean and underscore that δ13C is a highly robust proxy for past changes in ocean oxygen content and ocean ventilation. Our global preindustrial δ13C climatology is openly accessible and can be used, for example, for improved model evaluation and interpretation of sediment δ13C records.
Keywords: Sørishavet; klimatologi; uorganisk karbon; vannmasser

Spring phenology shapes the spatial foraging behavior of Antarctic petrels - Fauchald, Per; Tarroux, Arnaud; Tveraa, Torkild; Cherel, Yves; Ropert-Coudert, Yan; Kato, Akiko; Love, Oliver P; Varpe, Øystein; Descamps, Sébastien (Marine Ecology Progress Series, 2017)
In polar seas, the seasonal melting of ice triggers the development of an open-waterecosystem characterized by short-lived algal blooms, the grazing and development of zooplank-ton, and the influx of avian and mammalian predators. Spatial heterogeneity in the timing of icemelt generates temporal variability in the development of these events across the habitat, offeringa natural framework to assess how foraging marine predators respond to the spring phenology.We combined 4 yr of tracking data of Antarctic petrels Thalassoica antarcticawith synopticremote-sensing data on sea ice and chlorophyll ato test how the development of melting ice andprimary production drive Antarctic petrel foraging. Cross-correlation analyses of first-passagetime revealed that Antarctic petrels utilized foraging areas with a spatial scale of 300 km. Theseareas changed position or disappeared within 10 to 30 d and showed no spatial consistency amongyears. Generalized additive model (GAM) analyses suggested that the presence of foraging areaswas related to the time since ice melt. Antarctic petrels concentrated their search effort in meltingareas and in areas that had reached an age of 50 to 60 d from the date of ice melt. We found nosignificant relationship between search effort and chlorophyll aconcentration. We suggest thatthese foraging patterns were related to the vertical distribution and profitability of the main prey,the Antarctic krill Euphausia superba. Our study demonstrates that the annual ice melt in theSouthern Ocean shapes the development of a highly patchy and elusive food web, underscoringthe importance of flexible foraging strategies among top predators. KEY WORDS: Area-restricted search · Euphausia superba· Marginal ice zone · Phytoplanktonbiomass · Procellariiformes · Sea ice dynamics · Southern Ocean · Thalassoica antarctica
Keywords: Sørishavet; Weddellhavet; biologi; biomasse; fenologi; fytoplankton; fôring; havis; klima; petreller; sjøis; smelting; økosystemer

Exploring the Recovery Lakes region and interior Dronning Maud Land, East Antarctica, with airborne gravity, magnetic and radar measurements - Forsberg, Rene; Olesen, Arne; Jordan, Tom; Matsuoka, Kenny; Zakrajsek, Andres; Ghidella, Marta; Greenbaum, Jamin (Geological Society, London, Special Publications, 2017)
Long-range airborne geophysical measurements were carried out in the ICEGRAV campaigns, covering hitherto unexplored parts of interior East Antarctica and part of the Antarctic Peninsula. The airborne surveys provided a regional coverage of gravity, magnetic and icepenetrating radar measurements for major Dronning Maud Land ice stream systems, from the grounding lines up to the Recovery Lakes drainage basin, and filled in major data voids in Antarctic data compilations, such as AntGP for gravity data, ADMAP for magnetic data and BEDMAP2 for ice thickness data and the sub-ice topography. We present the first maps of gravity, magnetic and ice thickness data and bedrock topography for the region and show examples of bedrock topography and basal reflectivity patterns. The 2013 Recovery Lakes campaign was carried out with a British Antarctic Survey Twin Otter aircraft operating from the Halley and Belgrano II stations, as well as a remote field camp located at the Recovery subglacial Lake B site. Gravity measurements were the primary driver for the survey, with two airborne gravimeters (Lacoste and Romberg and Chekan-AM) providing measurements at an accuracy level of around 2 mGal r.m.s., supplementing GOCE (Gravity Field and Steady-State Ocean Circulation Explorer) satellite data and confirming an excellent sub-milligal agreement between satellite and airborne data at longer wavelengths.
Keywords: Dronning Maud Land; geofysikk; glasiologi

Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica - Goel, Vikram; Brown, Joel; Matsuoka, Kenichi (The Cryosphere, 2017)
The ice-shelf-fringed coast of Dronning Maud Land in East Antarctica contains numerous ice rises that influence the dynamics and mass balance of the region. However, only a few of these ice rises have been investigated in detail. Here, we present field measurements of Blåskimen Island, an isle-type ice rise adjacent to Fimbul Ice Shelf. This ice rise is largely dome shaped, with a pronounced ridge extending to the south-west from its summit (410 m a.s.l.). Its bed is mostly flat and about 100 m below the current sea level. Shallow radar-detected isochrones dated with a firn core reveal that the surface mass balance is higher on the south-eastern (upwind) slope than on the north-western (downwind) slope by ∼ 37 %, and this pattern has persisted for at least the past decade. Moreover, arches in radar stratigraphy suggest that the summit of the ice rise has been stable for ∼ 600 years. Ensemble estimates of the mass balance using the input–output method show that this ice rise has thickened by 0.12–0.37 m ice equivalent per year over the past decade.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Channelized Melting Drives Thinning Under a Rapidly Melting Antarctic Ice Shelf - Gourmelen, Noel; Goldberg, Dan N; Snow, Kate; Henley, Sian F; Bingham, Robert G; Kimura, Satoshi; Hogg, Anna E; Shepherd, Andrew; Mouginot, Jeremie; Lenaerts, Jan T M; Ligtenberg, Stefan R M; van de Berg, Willem Jan (Geophysical Research Letters, 2017)
Ice shelves play a vital role in regulating loss of grounded ice and in supplying freshwater to coastal seas. However, melt variability within ice shelves is poorly constrained and may be instrumental in driving ice shelf imbalance and collapse. High-resolution altimetry measurements from 2010 to 2016 show that Dotson Ice Shelf (DIS), West Antarctica, thins in response to basal melting focused along a single 5 km-wide and 60 km-long channel extending from the ice shelf's grounding zone to its calving front. If focused thinning continues at present rates, the channel will melt through, and the ice shelf collapse, within 40–50 years, almost two centuries before collapse is projected from the average thinning rate. Our findings provide evidence of basal melt-driven sub-ice shelf channel formation and its potential for accelerating the weakening of ice shelves.
Keywords: Sørishavet; glasiologi; havnivå; innlandsis; isbrem; isshelf; smelting

Volcanic passive continental margin beneath Maitri station in central DML, East Antarctica: constraints from crustal shear velocity through receiver function modelling - Gupta, Sandeep; Kanna, Nagaraju; Akilan, A (Polar Research, 2017)
Dronning Maud Land (DML) in East Antarctica is considered to be a key area for the reconstruction of the Gondwana supercontinent. We investigate the crustal shear wave velocity (Vs) model beneath the Maitri station, situated in the central DML of East Antarctica, through receiver function modelling. The analysis shows an average crustal thickness of 38.50 ± 0.5 km and a Vp/Vs ratio of 1.784 ± 0.002. The obtained Vs structure suggests that the topmost ca. 2.5 km of the crust contains ice and sediments with low Vs (1.5–2.0 km/s). This layer is underlain by a thick (ca. 12.5 km) layer of Vs = 2.25–2.6 km/s, suggestive of an extrusive igneous rock (rhyolite) at this depth range. Between 16 and 28 km depth, the Vs increases from 2.9 to 3.4 km/s. In the lower crust, a 7 km thick layer of Vs = 3.9 km/s is followed by 6 km thick underplated layer (Vs = 4.1 km/s) at the crust–mantle boundary. The uppermost mantle Vs is ca. 4.3 km/s. With the observation of underplated material in the lowermost crust, extrusive volcanic rocks in the upper crust, seaward dipping reflectors in the surrounding and a general paucity of seismicity, we believe the crust beneath the Maitri station represents a volcanic passive continental margin. We also believe that after its origin in the Precambrian and during its subsequent evolution it might have been affected by the post-Precambrian tectono-thermal event(s) responsible for the Gondwana supercontinent break-up.
Keywords: Dronning Maud Land; geofysikk; kontinentalmargin; seismologi; tektonikk; vulkaner

Distribution, density and abundance of Antarctic ice seals off Queen Maud Land and the eastern Weddell Sea - Gurarie, Eliezer; Bengtson, John L; Bester, Marthán N; Blix, Arnoldus Schytte; Cameron, Michael; Bornemann, Horst; Nordøy, Erling S; Plötz, Joachim; Steinhage, Daniel; Boveng, Peter (Polar Biology, 2017)
Keywords: Sørishavet; Weddellhavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr; zoologi

Microbes influence the biogeochemical and optical properties of maritime Antarctic snow - Hodson, Andrew; Nowak, Aga; Cook, Joseph; Sabacka, Marie; Wharfe, Emma S; Pearce, David Anthony; Convey, Peter; Vieira, Gonçalo (Journal of Geophysical Research: Biogeosciences, 2017)
Snowmelt in the Antarctic Peninsula region has increased significantly in recent decades, leading to greater liquid water availability across a more expansive area. As a consequence, changes in the biological activity within wet Antarctic snow require consideration if we are to better understand terrestrial carbon cycling on Earth's coldest continent. This paper therefore examines the relationship between microbial communities and the chemical and physical environment of wet snow habitats on Livingston Island of the maritime Antarctic. In so doing, we reveal a strong reduction in bacterial diversity and autotrophic biomass within a short (<1 km) distance from the coast. Coastal snowpacks, fertilized by greater amounts of nutrients from rock debris and marine fauna, develop obvious, pigmented snow algal communities that control the absorption of visible light to a far greater extent than with the inland glacial snowpacks. Absorption by carotenoid pigments is most influential at the surface, while chlorophyll is most influential beneath it. The coastal snowpacks also indicate higher concentrations of dissolved inorganic carbon and CO2 in interstitial air, as well as a close relationship between chlorophyll and dissolved organic carbon (DOC). As a consequence, the DOC resource available in coastal snow can support a more diverse bacterial community that includes microorganisms from a range of nearby terrestrial and marine habitats. Therefore, since further expansion of the melt zone will influence glacial snowpacks more than coastal ones, care must be taken when considering the types of communities that may be expected to evolve there.
Keywords: Antarktis; biogeokjemi; mikrobiologi; mikroorganismer; snøalger; snøpakke; snøsmelting

Om C.A. Larsen og starten på pelagisk hvalfangst - Iversen, Ragnar (Skipet, 2017)
Keywords: Sørishavet; historie; hvalfangst

An enigmatic fossil penguin from the Eocene of Antarctica - Jadwiszczaka, Piotr; Mörs, Thomas (Polar Research, 2017)
Tarsometatarsi are key skeletal elements in penguin palaeontology. They constitute, among others, type specimens of all 10 widely accepted species of fossil penguins from the Eocene La Meseta Formation on Seymour Island (Graham Land, Antarctic Peninsula). Here, we report on a recently collected large-sized tarsometatarsus from this formation that represents a new morphotype. We are convinced that the morphotype corresponds to a new species, but the material is too scarce for a taxonomic act. Undoubtedly, the bone discussed here is a valuable addition to our knowledge on diversity of early penguins.
Keywords: Antarktis; fossiler; paleobiologi; paleontologi; pingviner

Oceanographic Controls on the Variability of Ice-Shelf Basal Melting and Circulation of Glacial Meltwater in the Amundsen Sea Embayment, Antarctica - Kimura, Satoshi; Jenkins, Adrian; Regan, Heather; Holland, Paul R; Assmann, Karen M; Whitt, Daniel B; Van Wessem, Melchoir; van de Berg, Willem Jan; Reijmer, Carleen H; Dutrieux, Pierre (Journal of Geophysical Research: Oceans, 2017)
Ice shelves in the Amundsen Sea Embayment have thinned, accelerating the seaward flow of ice sheets upstream over recent decades. This imbalance is caused by an increase in the ocean-driven melting of the ice shelves. Observations and models show that the ocean heat content reaching the ice shelves is sensitive to the depth of thermocline, which separates the cool, fresh surface waters from warm, salty waters. Yet the processes controlling the variability of thermocline depth remain poorly constrained. Here we quantify the oceanic conditions and ocean-driven melting of Cosgrove, Pine Island Glacier (PIG), Thwaites, Crosson, and Dotson ice shelves in the Amundsen Sea Embayment from 1991 to 2014 using a general circulation model. Ice-shelf melting is coupled to variability in the wind field and the sea-ice motions over the continental shelf break and associated onshore advection of warm waters in deep troughs. The layer of warm, salty waters at the calving front of PIG and Thwaites is thicker in austral spring (June–October) than in austral summer (December–March), whereas the seasonal cycle at the calving front of Dotson is reversed. Furthermore, the ocean-driven melting in PIG is enhanced by an asymmetric response to changes in ocean heat transport anomalies at the continental shelf break: melting responds more rapidly to increases in ocean heat transport than to decreases. This asymmetry is caused by the inland deepening of bathymetry and the glacial meltwater circulation around the ice shelf.
Keywords: Amundsenhavet; Sørishavet; batymetri; brehylle; glasiologi; isbrem; ismeltvann; isshelf; klimatologi; oseanografi

Antarctic ice rises: small in size but big on impact - Matsuoka, Kenichi (Fram forum, 2017)
Ice discharge from the Antarctic Ice Sheet directly impacts global sea level, making ice sheet dynamics a central topic in antarctic research. Glaciologists are studying a poorly understood but potentially important phenomenon that looks like a little hill of ice. They call these hills “ice rises”.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf

Autonomous observing platform CO2 data shed new light on the Southern Ocean carbon cycle - Olsen, Are (Global Biogeochemical Cycles, 2017)
While the number of surface ocean CO2 partial pressure (pCO2) measurements has soared the recent decades, the Southern Ocean remains undersampled. Williams et al. (2017, https://doi.org/10.1002/2016GB005541) now present pCO2 estimates based on data from pH-sensor equipped Bio-Argo floats, which have been measuring in the Southern Ocean since 2014. The authors demonstrate the utility of these data for understanding the carbon cycle in this region, which has a large influence on the distribution of CO2 between the ocean and atmosphere. Biogeochemical sensors deployed on autonomous platforms hold the potential to shape our view of the ocean carbon cycle in the coming decades.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; kartlegging; klimaendringer; klimatologi; observasjoner

Occurrence and average behavior of pulsating aurora - Partamies, Noora; Whiter, Daniel; Kadokura, Akira; Kauristie, Kirsti; Nesse Tyssøy, Hilde; Massetti, Stefano; Stauning, Peter; Raita, Tero (Journal of Geophysical Research: Space Physics, 2017)
Motivated by recent event studies and modeling efforts on pulsating aurora, which conclude that the precipitation energy during these events is high enough to cause significant chemical changes in the mesosphere, this study looks for the bulk behavior of auroral pulsations. Based on about 400 pulsating aurora events, we outline the typical duration, geomagnetic conditions, and change in the peak emission height for the events. We show that the auroral peak emission height for both green and blue emission decreases by about 8 km at the start of the pulsating aurora interval. This brings the hardest 10% of the electrons down to about 90 km altitude. The median duration of pulsating aurora is about 1.4 h. This value is a conservative estimate since in many cases the end of event is limited by the end of auroral imaging for the night or the aurora drifting out of the camera field of view. The longest durations of auroral pulsations are observed during events which start within the substorm recovery phases. As a result, the geomagnetic indices are not able to describe pulsating aurora. Simultaneous Antarctic auroral images were found for 10 pulsating aurora events. In eight cases auroral pulsations were seen in the southern hemispheric data as well, suggesting an equatorial precipitation source and a frequent interhemispheric occurrence. The long lifetimes of pulsating aurora, their interhemispheric occurrence, and the relatively high-precipitation energies make this type of aurora an effective energy deposition process which is easy to identify from the ground-based image data.
Keywords: Antarktis; astronomi; atmosfæren; geofysikk; geomagnetiske stormer; mesosfæren; meteorologi; polarlys

Observation-Based Trends of the Southern Ocean Carbon Sink - Ritter, Rebecca; Landschützer, Peter; Gruber, Nicolas; Fay, Amanda R; Iida, Yosuke; Jones, Stephen Daniel; Nakaoka, Shin-ichiro; Park, Geun-Ha; Peylin, Philippe; Rödenbeck, Christian; Rodgers, Keith B; Shutler, Jamie D; et al. (Geophysical Research Letters, 2017)
The Southern Ocean (SO) carbon sink has strengthened substantially since the year 2000, following a decade of a weakening trend. However, the surface ocean pCO2 data underlying this trend reversal are sparse, requiring a substantial amount of extrapolation to map the data. Here we use nine different pCO2 mapping products to investigate the SO trends and their sensitivity to the mapping procedure. We find a robust temporal coherence for the entire SO, with eight of the nine products agreeing on the sign of the decadal trends, that is, a weakening CO2 sink trend in the 1990s (on average 0.22 ± 0.24 Pg C yr−1 decade−1), and a strengthening sink trend during the 2000s (−0.35 ± 0.23 Pg C yr−1 decade−1). Spatially, the multiproduct mean reveals rather uniform trends, but the confidence is limited, given the small number of statistically significant trends from the individual products, particularly during the data-sparse 1990–1999 period.
Keywords: Sørishavet; biogeokjemi; global oppvarming; karbondioksid; klimaendringer; klimatologi; meteorologi

Molluscan assemblages associated with Gigartina beds in the Strait of Magellan and the South Shetland Islands (Antarctica): a comparison of composition and abundance - Rosenfeld, Sebastián; Aldea, Cristian; Ojeda, Jaime; Marambio, Johanna; Hüne, Mathias; Troncoso, Jesús S; Mansilla, Andrés (Polar Research, 2017)
In this paper we evaluated the composition and abundance of molluscs associated with beds of the red algae Gigartina, located in the South Shetland Islands (Antarctic Peninsula) and the Strait of Magellan (southern Chile). During the summer season of 2013, samples were obtained by scuba diving using a 0.25 m2 quadrat, arranged randomly within the bed. We extracted a total of 15 quadrats per sampling site. For Antarctic Peninsula beds the most abundant species were the bivalve Lissarca miliaris (233 individuals) and the gastropod Laevilacunaria antarctica (94 individuals), while for Strait of Magellan beds the most abundant species was the polyplacophoran Callochiton puniceus (36 individuals). Comparative analysis between the two molluscan assemblages showed significant differences in the faunal composition between the Antarctic Peninsula and Strait of Magellan (f = 64.474; p = 0.0001). Therefore, molluscs reported in both areas are characteristic of their respective biogeographic area. Finally, Gigartina species play an important role in the formation of patterns of abundance and diversity of the communities associated with them.
Keywords: Sørishavet; alger; biodiversitet; biogeokjemi; bløtdyr; havbunnen; muslinger; snegler

Seasonal cycle of hydrography on the eastern shelf of the Filchner Trough, Weddell Sea, Antarctica - Ryan, Svenja; Hattermann, Tore; Darelius, Elin Maria K; Schröder, Michael (Journal of Geophysical Research: Oceans, 2017)
Keywords: Sørishavet; Weddellhavet; hydrografi; isshelf; kontinentalsokkel; kontinentalsokler

Potential chemical defenses of Antarctic benthic organisms against marine bacteria - Sacristán-Soriano, Oriol; Angulo-Preckler, Carlos; Vázquez, Jennifer; Avila, Conxita (Polar Research, 2017)
The continental shelf of Antarctica harbours rich suspension-feeding macroinvertebrate communities that are continuously exposed to large populations of free-living microbes. To avoid settlement or fouling by undesirable microorganisms that could cause infection or collapse filter-feeding systems, these macroinvertebrates might regulate the epibiotic microbial mat through chemical interactions. In Antarctic chemical ecology, the antibacterial roles of natural products remain mostly unknown. A necessary first step is to identify organisms that produce compounds with potential ecological relevance. For that reason, we tested the crude organic extracts of 116 taxa of Antarctic benthic organisms for antibacterial activity against a panel of seven strains of marine bacteria. Nine out of 11 phyla tested had antibacterial properties. However, inhibitory activity was quite selective and species-specific. These patterns suggest that Antarctic benthic organisms may produce diverse bioactive metabolites with different antibacterial activities or, alternatively, those contrasting profiles may be shaped by environmental and biological interactions acting at a small spatial scale. The reasons of such selectivity remain to be further investigated and may contribute to the identification of bioactive compounds with pharmaceutical applications.
Keywords: Sørishavet; alger; biodiversitet; biologi; fauna; kjemisk; kontinentalsokkel; makrovirvelløse dyr; mikrober; mikroorganismer; økologi

Benchmarks: February 5, 1931 and February 20, 1935: Antarctic firsts for women - Zalzal, Kate S (Earth, 2017)
Publisher: American Geological Institute Place: Alexandria
Keywords: Antarktis; Nordmenn; ekspedisjoner; kvinner; oppdagelsesreiser

Geomorphic and shallow-acoustic investigation of an Antarctic Peninsula fjord system using high-resolution ROV and shipboard geophysical observations: Ice dynamics and behaviour since the Last Glacial Maximum - García, Marga; Dowdeswell, J.A.; Noormets, R.; Hogan, K.A.; Evans, J.; Ó Cofaigh, C.; Larter, R.D. (Quaternary Science Reviews, 2016)
Detailed bathymetric and sub-bottom acoustic observations in Bourgeois Fjord (Marguerite Bay, Antarctic Peninsula) provide evidence on sedimentary processes and glacier dynamics during the last glacial cycle. Submarine landforms observed in the 50 km-long fjord, from the margins of modern tidewater glaciers to the now ice-distal Marguerite Bay, are described and interpreted. The landforms are grouped into four morpho-sedimentary systems: (i) glacial advance and full-glacial; (ii) subglacial and ice-marginal meltwater; (iii) glacial retreat and neoglaciation; and (iv) Holocene mass-wasting. These morpho-sedimentary systems have been integrated with morphological studies of the Marguerite Bay continental shelf and analysed in terms of the specific sedimentary processes and/or stages of the glacial cycle. They demonstrate the action of an ice-sheet outlet glacier that produced drumlins and crag-and-tail features in the main and outer fjord. Meltwater processes eroded bedrock channels and ponds infilled by fine-grained sediments. Following the last deglaciation of the fjord at about 9000 yr BP, subsequent Holocene neoglacial activity involved minor readvances of a tidewater glacier terminus in Blind Bay. Recent stillstands and/or minor readvances are inferred from the presence of a major transverse moraine that indicates grounded ice stabilization, probably during the Little Ice Age, and a series of smaller landforms that reveal intermittent minor readvances. Mass-wasting processes also affected the walls of the fjord and produced scars and fan-shaped deposits during the Holocene. Glacier-terminus changes during the last six decades, derived from satellite images and aerial photographs, reveal variable behaviour of adjacent tidewater glaciers. The smaller glaciers show the most marked recent retreat, influenced by regional physiography and catchment-area size.
Keywords: Antarctic Peninsula; Antarktis; Fjord systems; Geomorphology; Glacial sedimentary processes; Last Glacial Maximum; ROV-Derived bathymetry; Sørishavet; batymetri; geomorfologi

Naturen 1916 Roald Amundsens sydpolsfærd og dens videnskabelige resultater (Naturen, 2016)
Efterat kaptein James Ross i 1841 hadde opdaget det sydpolare eller antarktiske fastland og den store isbarriere under sin seilas i det hav som efter ham har faat navn av Ross-Havet, blev den øvrige del av dette fastland fremdeles ukjendt indtil 1898. Fra dette aar av har en række ekspeditioner med større og mindre held forsøkt at finde beliggenheten av det antarktiske fastlands kyster, og av disse har nogen opnaadd at trænge ind i det indre, endog like til sydpolen. Imidlertid er der endnu store strækninger hvor havisen har stængt seilasen og gjort det umulig at naa ind til det faste land.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; historie; oppdagelsesreiser; vitenskap

Den nyttige taperen - Scotts plass i norske nyhetsmediers fortellinger om erobringen av Sørpolen - Alnæs, Jørgen; Simonsen, Anne Hege (Norsk medietidsskrift, 2016)
Hundre år etter at Roald Amundsen nådde Sørpolen, ble han behørig feiret både av det offisielle Norge og av norske nyhetsmedier. Robert F. Scott, som nådde polen om lag en måned seinere, var en del av omtalen. Han fikk rollen som motstander og taper, og slik ble han en nyttig brikke når forestillingene om Norge som en rettmessig stormakt i Antarktis skulle etableres. Det er imidlertid mange måter å framstille Scott på, og norske aviser har ikke alltid hatt det samme synet på ham.
Publisher: Universitetsforlaget
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolsekspedisjonen; ekspedisjoner; historie; kappløpet; mediefortelling; oppdagelsesreiser

Transpression and tectonic exhumation in the Heimefrontfjella, western orogenic front of the East African/Antarctic Orogen, revealed by quartz textures of high strain domains - Bauer, Wilfried; Siemes, Heinrich; Spaeth, Gerhard; Jacobs, Joachim (Polar Research, 2016)
The metamorphic basement of the Heimefrontfjella in western Dronning Maud Land (Antarctica) forms the western margin of the major ca. 500 million year old East African/East Antarctic Orogen that resulted from the collision of East Antarctica and greater India with the African cratons. The boundary between the tectonothermally overprinted part of the orogen and its north-western foreland is marked by the subvertical Heimefront Shear Zone. North-west of the Heimefront Shear Zone, numerous low-angle dipping ductile thrust zones cut through the Mesoproterozoic basement. Petrographic studies, optical quartz c-axis analyses and x-ray texture goniometry of quartz-rich mylonites were used to reveal the conditions that prevailed during the deformation. Mineral assemblages in thrust mylonites show that they were formed under greenschist-facies conditions. Quartz microstructures are characteristic of the subgrain rotation regime and oblique quartz lattice preferred orientations are typical of simple shear-dominated deformation. In contrast, in the Heimefront Shear Zone, quartz textures indicate mainly flattening strain with a minor dextral rotational component. These quartz microstructures and lattice preferred orientations show signs of post-tectonic annealing following the tectonic exhumation. The spatial relation between the sub-vertical Heimefront Shear Zone and the low-angle thrusts can be explained as being the result of strain partitioning during transpressive deformation. The pure-shear component with a weak dextral strike-slip was accommodated by the Heimefront Shear Zone, whereas the north–north-west directed thrusts accommodate the simple shear component with a tectonic transport towards the foreland of the orogen. Keywords: Dronning Maud Land; quartz microfabrics; X-ray texture goniometry; shear zones; mylonites.
Keywords: Dronning Maud Land; geologi; mylonitter; petrografi; tektonikk

On Roald Amundsen’s scientific achievements - Blix, Arnoldus Schytte (Polar Research, 2016)
This paper describes the significant direct and indirect contributions to science made by the Norwegian polar explorer Roald Amundsen in the period 1897–1924. It documents that his expeditions through the North-west Passage (1903–06) with Gjøa, to the South Pole (1910–12) with Fram and through the North-east Passage (1918–1920) and the Chukchi and East Siberian seas (1921–25) with Maud yielded vast amounts of published scientific material on meteorology, terrestrial magnetism, geology, palaeontology, oceanography, ethnography, zoology and botany, which, though celebrated at the time, have since received scant recognition in more recent assessments of Amundsen’s achievements. Keywords: Fridtjof Nansen; polar exploration; South Pole; North-west Passage; North-east Passage; H.U. Sverdrup.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; forskning; geologi; meteorologi; oseanografi

Algal biomass and pigments along a latitudinal gradient in Victoria Land lakes, East Antarctica - Borghini, Francesca; Colacevich, Andrea; Caruso, Tancredi; Bargagli, Roberto (Polar Research, 2016)
It is generally accepted that Antarctic terrestrial diversity decreases as latitude increases, but latitudinal patterns of several organisms are not always as clear as expected. The Victoria Land region is rich in lakes and ponds and spans 8 degrees of latitude that encompasses gradients in factors such as solar radiation, temperature, ice cover and day length. An understanding of the links between latitudinally driven environmental and biodiversity changes is essential to the understanding of the ecology and evolution of Antarctic biota and the formulation of hypotheses about likely future changes in biodiversity. As several studies have demonstrated that photosynthetic pigments are an excellent, although underused, tool for the study of lacustrine algal communities, the aim of the present study was to investigate variations in algal biomass and biodiversity across the latitudinal gradient of Victoria Land using sedimentary pigments. We test the hypothesis that the biodiversity of freshwater environments decreases as latitude increases. On the basis of our results, we propose using the number of sedimentary pigments as a proxy for algal diversity and the sum of chlorophyll a and bacteriochlorophyll a with their degradation derivatives as an index of biomass. Overall, our data show that biomass and diversity decrease as latitude increases but local environmental conditions, in particular, natural levels of eutrophy, can affect both productivity and diversity. Keywords: Biodiversity; photosynthetic pigments; proxy; continental Antarctica; sediments; biogeography.
Keywords: Antarktis; alger; biodiversitet; biogeografi; biomasse; ferskvann; fotosyntese; innsjø; sedimenter; økologi

A constitutive framework for predicting weakening and reduced buttressing of ice shelves based on observations of the progressive deterioration of the remnant Larsen B Ice Shelf - Borstad, Chris; Khazendar, Ala; Scheuchl, Bernd; Morlighem, Mathieu; Larour, Eric; Rignot, Eric (Geophysical Research Letters, 2016)
The increasing contribution of the Antarctic Ice Sheet to sea level rise is linked to reductions in ice shelf buttressing, driven in large part by basal melting of ice shelves. These ocean-driven buttressing losses are being compounded as ice shelves weaken and fracture. To date, model projections of ice sheet evolution have not accounted for weakening ice shelves. Here we present the first constitutive framework for ice deformation that explicitly includes mechanical weakening, based on observations of the progressive degradation of the remnant Larsen B Ice Shelf from 2000 to 2015. We implement this framework in an ice sheet model and are able to reproduce most of the observed weakening of the ice shelf. In addition to predicting ice shelf weakening and reduced buttressing, this new framework opens the door for improved understanding and predictions of iceberg calving, meltwater routing and hydrofracture, and ice shelf collapse.
Keywords: Antarktis; glasiologi; global oppvarming; havnivåstigning; innlandsis; isbrem; isshelf; smelting

Winter distribution and size structure of Antarctic krill Euphausia superba populations in-shore along the West Antarctic Peninsula - Cleary, Alison C; Durbin, Edward G; Casas, Maria C; Zhou, Meng (Marine Ecology Progress Series, 2016)
Antarctic krill Euphausia superba are a key component of food webs in the maritime West Antarctic Peninsula, and their life history is tied to the seasonal cycles of sea ice and primary production in the region. Previous work has shown a general in-shore migration of krill in winter in this region; however, the very near-shore has not often been sampled as part of these surveys. We investigated distribution, abundance, and size structure of krill in 3 fjordic bays along the peninsula, and in the adjacent Gerlache Strait area using vertically stratified MOCNESS net tows and ADCP acoustic biomass estimates. Krill abundance was high within bays, with net estimated densities exceeding 60 krill m-3, while acoustic estimates were an order of magnitude higher. Krill within bays were larger than krill in the Gerlache Strait. Within bays, krill aggregations were observed near the seafloor during the day with aggregations extending to the sediment interface, and exhibited diel vertical migration higher into the water column at night. We suggest these high winter krill abundances within fjords are indicative of an active seasonal migration by krill in the peninsula region. Potential drivers for such a migration include reduced advective losses and costs, and availability of sediment food resources within fjords. Seasonally near-shore krill may also affect stock and recruitment assessments and may have implications for managing the krill fishery in this area. KEYWORDS: Euphausiid · Abundance · Diel vertical migration · DVM · WAP · Fjord.
Keywords: Sørishavet; biomasse; hydrografi; krill; marin biologi; oseanografi; zooplankton

Observed vulnerability of Filchner-Ronne Ice Shelf to wind-driven inflow of warm deep water - Darelius, Elin Maria K; Fer, Ilker; Nicholls, Keith William (Nature Communications, 2016)
Keywords: Antarktis; Weddellhavet; isshelf; oseanografi; sjøvann

Tourism and Arctic Observation Systems: exploring the relationships - de la Barre, Suzanne; Maher, Patrick; Dawson, Jackie; Hillmer-Pegram, Kevin; Huijbens, Edward; Lamers, Machiel; Liggett, Daniela; Müller, Dieter; Pashkevich, Albina; Stewart, Emma (Polar Research, 2016)
The Arctic is affected by global environmental change and also by diverse interests from many economic sectors and industries. Over the last decade, various actors have attempted to explore the options for setting up integrated and comprehensive trans-boundary systems for monitoring and observing these impacts. These Arctic Observation Systems (AOS) contribute to the planning, implementation, monitoring and evaluation of environmental change and responsible social and economic development in the Arctic. The aim of this article is to identify the two-way relationship between AOS and tourism. On the one hand, tourism activities account for diverse changes across a broad spectrum of impact fields. On the other hand, due to its multiple and diverse agents and far-reaching activities, tourism is also well-positioned to collect observational data and participate as an actor in monitoring activities. To accomplish our goals, we provide an inventory of tourism-embedded issues and concerns of interest to AOS from a range of destinations in the circumpolar Arctic region, including Alaska, Arctic Canada, Iceland, Svalbard, the mainland European Arctic and Russia. The article also draws comparisons with the situation in Antarctica. On the basis of a collective analysis provided by members of the International Polar Tourism Research Network from across the polar regions, we conclude that the potential role for tourism in the development and implementation of AOS is significant and has been overlooked. Keywords: Arctic; Antarctic; citizen science; observation systems; tourism; IPTRN
Keywords: Antarktis; klimaendringer; miljøendringer; polarområdene; turisme

At-Sea Distribution and Prey Selection of Antarctic Petrels and Commercial Krill Fisheries - Descamps, Sébastien; Tarroux, Arnaud; Cherel, Yves; Delord, Karine; Godø, Olaf Rune; Akiko, Kato; Krafft, Bjørn A; Lorentsen, Svein-Håkon; Ropert-Coudert, Yan; Skaret, Georg; Varpe, Øystein (PloS One, 2016)
Kommersielle fiskerier kan påvirke marine økosystemer og bestander av topp-predatorer som sjøfugl. I Sørishavet foregår et ekstensivt fiske etter Antarktisk krill (Euphausia superba), og dette er antatt å øke. En sammenligning av fordeling og uttak hos fiskeriene og tilsvarende hos topp-predatorene er nødvendig for å forutsi fiskerirelaterte påvirkninger på krillavhengige predatorer. I dette studiet kartla vi næringssøksområdene hos Antarktispetrell (Thalassoica antarctica) som hekker i verdens største koloni (Svarthammaren, Dronning Maud land) over en treårsperiode. Vi fant at det romlige overlappet mellom krillfiskerier og næringssøkende Antarktispetrell generelt var lite. Konkurranse mellom Antarktispetrell og krill-fiskerier er for tiden neglisjerbart, men kan øke hvis fiskeriet etter krill øker.
Keywords: Dronning Maud Land; Sørishavet; fiskeriforvaltning; krill; marinbiologi; ornitologi; økosystem

Gastrointestinal helminths of Adélie penguins (Pygoscelis adeliae) from Antarctica - Diaz, Julia Inés; Fusaro, Bruno; Longarzo, Lucrecia; Coria, Néstor Rubén; Vidal, Virginia; D'Amico, Verónica; Barbosa, Andrés (Polar Research, 2016)
Knowledge about parasitic organisms in Antarctica is scarce and fragmentary. The study reported here adds to the knowledge of gastrointestinal parasites of the Adélie penguin (Pygoscelis adeliae) (Sphenisciformes), from 25 de Mayo/King George Island (South Shetlands), Bahia Esperanza (Hope Bay) and Avian Island (Antarctica). Thirty-five freshly dead specimens (20 chicks and 15 adults) were collected from December 2007 to December 2014 and examined for internal macroparasites. Three adult parasite species were found: one Cestoda, Parorchites zederi, and two Nematoda, Stegophorus macronectes and Tetrameres sp. Immature Tetrabothrius sp. were found in hosts from Avian Island. Helminth communities are known to be related to host feeding behaviours. Low parasite richness observed in Adélie penguins could be related to the stenophagic and pelagic diet of this host species, which feeds almost exclusively on krill. Keywords: Parorchites zederi; Stegophorus macronectes; Tetrameres sp.; parasites; ecosystem health.
Keywords: Antarktis; krill; parasitter; pingviner; plankton; zoologi; økosystemer

Re-assessment of recent (2008 - 2013) surface mass balance over Dome Argus, Antarctica - Ding, Minghu; Xiao, Cunde; Yang, Yuande; Wang, Yetang; Li, Chuanjin; Yuan, Naiming; Shi, Guitao; Sun, Weijun; Ming, Jing (Polar Research, 2016)
At Dome Argus, East Antarctica, the surface mass balance (SMB) from 2008 to 2013 was evaluated using 49 stakes installed across a 30×30 km area. Spatial analysis showed that at least 12 and 20 stakes are needed to obtain reliable estimates of SMB at local scales (a few hundred square metres) and regional scales (tens of square kilometres), respectively. The estimated annual mean SMB was 22.9±5.9 kg m−2 yr−1, including a net loss by sublimation of −2.22±0.02 kg m−2 yr−1 and a mass gain by deposition of 1.37±0.01 kg m−2 yr−1. Therefore, ca. 14.3% of precipitation was modified after deposition, which should be considered when interpreting snow or ice core records produced by future drilling projects. The surface snow density and SMB in the western portion of Dome Argus are higher than in other areas, and these differences are likely related to the katabatic wind, which is strengthened by topography in this sector. A new digital elevation model (DEM) of Dome Argus was generated, confirming that both peaks of the dome can be considered as the summit of the East Antarctic Ice Sheet. Findings from this study should be valuable for validating SMB estimates obtained from regional climate models and DEMs established using remote-sensing data. Keywords: Snow accumulation; Kunlun Station; CHINARE; digital elevation model; deep ice core sites; East Antarctic Ice Sheet.
Keywords: Antarktis; glasiologi; innlandsis; meteorologi; snø akkumulasjon; topografi

Observations of energetic turbulence on the Weddell Sea continental slope - Fer, Ilker; Darelius, Elin; Daae, Kjersti B (Geophysical Research Letters, 2016)
Turbulence profile measurements made on the upper continental slope and shelf of the southeastern Weddell Sea reveal striking contrasts in dissipation and mixing rates between the two sites. The mean profiles of dissipation rates from the upper slope are 1–2 orders of magnitude greater than the profiles collected over the shelf in the entire water column. The difference increases toward the bottom where the dissipation rate of turbulent kinetic energy and the vertical eddy diffusivity on the slope exceed 10−7 W kg−1 and 10−2 m2 s−1, respectively. Elevated levels of turbulence on the slope are concentrated within a 100 m thick bottom layer, which is absent on the shelf. The upper slope is characterized by near-critical slopes and is in close proximity to the critical latitude for semidiurnal internal tides. Our observations suggest that the upper continental slope of the southern Weddell Sea is a generation site of semidiurnal internal tide, which is trapped along the slope along the critical latitude, and dissipates its energy in a 100 m thick layer near the bottom and within 10 km across the slope.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; havstrømmer; hydrografi; kontinentalsokkel

Tilt signals at Mount Melbourne, Antarctica: evidence of a shallow volcanic source - Gambino, Salvatore; Aloisi, Marco; Falzone, Giuseppe; Ferro, Angelo (Polar Research, 2016)
Mount Melbourne (74°21′ S, 164°43′ E) is a quiescent volcano located in northern Victoria Land, Antarctica. Tilt signals have been recorded on Mount Melbourne since early 1989 by a permanent shallow borehole tiltmeter network comprising five stations. An overall picture of tilt, air and permafrost temperatures over 15 years of continuous recording data is reported. We focused our observations on long-term tilt trends that at the end of 1997 showed coherent changes at the three highest altitude stations, suggesting the presence of a ground deformation source whose effects are restricted to the summit area of Mount Melbourne. We inverted these data using a finite spherical body source, thereby obtaining a shallow deflation volume source located under the summit area. The ground deformation observed corroborates the hypothesis that the volcanic edifice of Mount Melbourne is active and should be monitored multidisciplinarily.Keywords: Tilt monitoring; volcanic dynamics; physics volcanology; ground deformation; Victoria Land.
Keywords: Antarktis; geofysikk; tektonikk; vulkaner

Parasites of the Antarctic toothfish (Dissostichus mawsoni Norman, 1937) (Perciformes, Nototheniidae) in the Pacific sector of the Antarctic - Gordeev, Ilya I; Sokolov, Sergey G (Polar Research, 2016)
The Antarctic toothfish (Dissostichus mawsoni Norman, 1937) is one of the main target species of commercial fisheries in the Antarctic. It is an endemic and is found along the shelf of Antarctica, as well as on the slopes of seamounts, underwater elevations and islands in the sub-Antarctic. It feeds on a variety of fish and cephalopods and can be an intermediate/paratenic host of some helminthes, whose final hosts are whales, seals, large rays and sharks. This article presents new data on toothfish infection in the Pacific sector of the Antarctic. Specimens were examined during commercial longline fishing in the Ross Sea and the Amundsen Sea in January–February 2013. Fourteen species of parasites were found using standard parasitological methods and genetic analysis. Keywords: Toothfish; parasites; Antarctic fisheries; CCAMLR; infection; Southern Ocean.
Keywords: Rosshavet; Sørishavet; fiskeri; infeksjon; parasitter; parasittologi

In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

Delivering 21st century Antarctic and Southern Ocean science - Kennicutt, Mahlon C I I; Kim, Yeadong; Rogan-Finnemore, Michelle; Anandakrishnan, Sridhar; Chown, Steven L; Colwell, Steven (Antarctic Science, 2016)
The Antarctic Roadmap Challenges (ARC) project identified critical requirements to deliver high priority Antarctic research in the 21st century. The ARC project addressed the challenges of enabling technologies, facilitating access, providing logistics and infrastructure, and capitalizing on international co-operation. Technological requirements include: i) innovative automated in situ observing systems, sensors and interoperable platforms (including power demands), ii) realistic and holistic numerical models, iii) enhanced remote sensing and sensors, iv) expanded sample collection and retrieval technologies, and v) greater cyber-infrastructure to process ‘big data’ collection, transmission and analyses while promoting data accessibility. These technologies must be widely available, performance and reliability must be improved and technologies used elsewhere must be applied to the Antarctic. Considerable Antarctic research is field-based, making access to vital geographical targets essential. Future research will require continent- and ocean-wide environmentally responsible access to coastal and interior Antarctica and the Southern Ocean. Year-round access is indispensable. The cost of future Antarctic science is great but there are opportunities for all to participate commensurate with national resources, expertise and interests. The scope of future Antarctic research will necessitate enhanced and inventive interdisciplinary and international collaborations. The full promise of Antarctic science will only be realized if nations act together.
Keywords: Antarktis; forskning; vitenskap

Regurgitation of the koilin layer in chinstrap penguins (Pygoscelis antarcticus) and its association with gastric parasites - Kim, Han-Kyu; Choi, Chang-Yong; Jeong, Min-Su; Kang, Hwa-Yeon; Lee, Woo-Shin (Polar Research, 2016)
The koilin membrane, formed by the secretions of the ventricular and pyloric glands, functions as a protective layer in the gizzards of most bird species. However, the ecological functions of koilin have never been studied in free-ranging penguins. During the two austral summers from 2012 to 2014, we observed the regurgitated koilins of chinstrap penguins (Pygoscelis antarcticus) at Narębski Point on King George Island, South Shetland Islands, and we detected a significant difference in the daily accumulation of regurgitated koilins between the pre-hatching and post-hatching periods in the rookery. We also found 233 gastrointestinal parasites, all Stegophorus macronectes (Nematoda, Acuariidae), from 26 out of 45 koilins freshly regurgitated by chinstrap penguins. We suggest that the regurgitation of koilins may benefit adult chinstrap penguins in the wild by reducing parasitic loads when they fast during incubation; it may also help decrease the risk of parasite transmission to chicks. Our results present the first observations of regurgitated koilins among breeding chinstrap penguins. How koilin regurgitation functions in penguins requires further study. Among the gentoo penguins (P. papua) co-occurring at the study site, we observed no regurgitated koilin layers. Keywords: Cuticula gastris; host-parasite interaction; nematodes; parasitic load; regurgitation; Stegophorus macronectes.
Keywords: Antarktis; biologi; gastrointestinale parasitter; ornitologi; pingviner; zoologi

Ocean mixing beneath Pine Island Glacier ice shelf, West Antarctica - Kimura, Satoshi; Jenkins, Adrian; Dutrieux, Pierre; Forryan, Alexander; Naveira Garabato, Alberto C; Firing, Yvonne (Journal of Geophysical Research: Oceans, 2016)
Ice shelves around Antarctica are vulnerable to an increase in ocean-driven melting, with the melt rate depending on ocean temperature and the strength of flow inside the ice-shelf cavities. We present measurements of velocity, temperature, salinity, turbulent kinetic energy dissipation rate, and thermal variance dissipation rate beneath Pine Island Glacier ice shelf, West Antarctica. These measurements were obtained by CTD, ADCP, and turbulence sensors mounted on an Autonomous Underwater Vehicle (AUV). The highest turbulent kinetic energy dissipation rate is found near the grounding line. The thermal variance dissipation rate increases closer to the ice-shelf base, with a maximum value found ∼0.5 m away from the ice. The measurements of turbulent kinetic energy dissipation rate near the ice are used to estimate basal melting of the ice shelf. The dissipation-rate-based melt rate estimates is sensitive to the stability correction parameter in the linear approximation of universal function of the Monin-Obukhov similarity theory for stratified boundary layers. We argue that our estimates of basal melting from dissipation rates are within a range of previous estimates of basal melting.
Keywords: Sørishavet; batymetri; brehylle; isbrem; isshelf; klimatologi; målinger; oseanografi; smeltevann; vannmasser

The impact of sunlight on high-latitude equivalent currents - Laundal, Karl M; Gjerloev, Jesper; Østgaard, Nikolai; Reistad, Jone Peter; Haaland, Stein; Snekvik, Kristian; Tenfjord, Paul; Ohtani, Shin-ichi; Milan, Steve (Journal of Geophysical Research: Space Physics, 2016)
Ground magnetic field measurements can be mathematically related to an overhead ionospheric equivalent current. In this study we look in detail at how the global equivalent current, calculated using more than 30 years of SuperMAG magnetometer data, changes with sunlight conditions. The calculations are done using spherical harmonic analysis in quasi-dipole coordinates, a technique which leads to improved accuracy compared to previous studies. Sorting the data according to the location of the sunlight terminator and orientation of the interplanetary magnetic field (IMF), we find that the equivalent current resembles ionospheric convection patterns on the sunlit side of the terminator but not on the dark side. On the dark side, with southward IMF, the current is strongly dominated by a dawn cell and the current across the polar cap has a strong dawnward component. The contrast between the sunlit and dark side increases with increasing values of the F10.7 index, showing that increasing solar EUV flux changes not only the magnitude but also the morphology of the equivalent current system. The results are consistent with a recent study showing that Birkeland currents indirectly determine the equivalent current in darkness and that Hall currents dominate in sunlight. This has implication for the interpretation of ground magnetic field measurements and suggests that the magnetic disturbances at conjugate points will be asymmetrical when the solar illumination is different.
Keywords: Antarktis; geomagnetiske stormer; ionosfæren; ionosfæriske strømmer; polarlys; polarområdene; sollys; solvind

The seasonal evolution of shelf water masses around Bouvetøya, a sub-Antarctic island in the mid-Atlantic sector of the Southern Ocean, determined from an instrumented southern elephant seal - Lowther, Andrew D.; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
Our study makes use of a fortuitous oceanographic data set collected around the remote sub-Antarctic island of Bouvetøya by a conductivity–temperature–depth recorder (CTD) integrated with a satellite-relayed data logger deployed on an adult female southern elephant seal (Mirounga leonina) to describe the seasonal evolution of the western shelf waters. The instrumented seal remained in waters over the shelf for 259 days, collecting an average of 2.6 (±0.06) CTD profiles per day, providing hydrographic data encompassing the late austral summer and the entire winter. These data document the thermal stratification of the upper water layer due to summer surface heating of the previous year's Antarctic Surface Water, giving way to a cold subsurface layer at about 100 m as the austral winter progressed, with a concomitant increase in salinity of the upper layer. Upper Circumpolar Deep Water was detected at a depth of approximately 200 m along the western shelf of Bouvetøya throughout the year. These oceanographic data represent the only seasonal time series for this region and the second such animal–instrument oceanographic time series in the sub-Antarctic domain of the Southern Ocean.
Publisher: Routledge
Keywords: AABW; Bouvetøya; biotelemetri; hydrografi; marin biologi; oseanografi; seler

Adjustment of pigment composition in Desmarestia (Desmarestiaceae) species along a sub-Antarctic to Antarctic latitudinal gradient - Mansilla, Andrés; Méndez, Fabio; Murcia, Silvia; Rodriguez, Juan Pablo; Marambio, Johanna; Rosenfeld, Sebastián; Yokoya, Nair; Bischof, Kai (Polar Research, 2016)
Photosynthesis at high latitudes demands efficient strategies of light utilization to maintain algal fitness and performance. The fitness, and physiological adaptation, of a plant or algae species depends in part on the abundance and efficiency of the pigments it can produce to utilize the light resource from its environment. We quantified pigment composition and concentration in six species of the brown macroalgal genus Desmarestia, collected from sub-Antarctic sites (Strait of Magellan, Beagle Channel–Cape Horn Province) and sites on the Antarctic Peninsula and adjacent islands. Sub-Antarctic Desmarestia species exhibited lower concentrations of chlorophyll a, chlorophyll c and fucoxanthin than endemic Antarctic species. Antarctic samples of D. menziesii and D. antarctica collected along a decreasing latitudinal gradient showed spatial and interspecific differences in light-harvesting pigment composition. Our results suggest distinct physiological adjustments in Desmarestia species in response to heterogeneous abiotic environmental conditions. The marine sub-Antarctic and Antarctic ecosystems are characterized by harsh environments (e.g., extreme irradiance, photoperiod, temperature, salinity) to which the physiology of macroalgal species must adapt. Keywords: Macroalgae; Phaeophyceae; photosynthesis; physiology; environmental heterogeneity; Chile.
Keywords: Antarktis; alger; fotosyntese; fysiologi; planter

Can reducing the incoming energy flux over the Southern Ocean in a CGCM improve its simulation of tropical climate? - Mechoso, Carlos R; Losada, Teresa; Koseki, Shunya; Mohino-Harris, Elsa; Keenlyside, Noel; Castaño-Tierno, Antonio; Myers, Timothy A; Rodriguez-Fonseca, Belen; Toniazzo, Thomas (Geophysical Research Letters, 2016)
Atmosphere-ocean general circulation models (CGCMs) show important systematic errors. Simulated precipitation in the tropics is generally overestimated over the oceans south of the equator, and stratocumulus (SCu) clouds are underestimated above too warm sea surface temperatures (SSTs). In the extratropics, SSTs are also too warm over the Southern Ocean. We argue that ameliorating these extratropical errors in a CGCM can result in an improved model's performance in the tropics depending upon the success in simulating the sensitivity of SCu to underlying SST. Our arguments are supported by the very different response obtained with two CGCMs to an idealized reduction of solar radiation flux incident at the top of the atmosphere over the Southern Ocean. It is shown that local perturbation impacts are very similar in the two models but that SST reductions in the SCu regions of the southern subtropics are stronger in the model with the stronger SCu-SST feedbacks.

Gåten om Roald Amundsens varde på Bettyfjellet i Antarktis - Mehlum, Fridtjof (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Polheim: teltet på Sydpolen - Melgård, Anne (Polarboken, 2016)
Keywords: Antarktis; ekspedisjoner; historie

Local controls on sediment accumulation and distribution in a fjord in the West Antarctic Peninsula: implications for palaeoenvironmental interpretations - Munoz, Yuribia P.; Wellner, Julia S. (Polar Research, 2016)
We analyse surface sediment and its distribution in Flandres Bay, West Antarctic Peninsula, in order to understand modern day sediment dispersal patterns in a fjord with retreating, tidewater glaciers. The surface sediment descriptions of 41 cores are included in this study. The sediment facies described include muddy diatomaceous ooze, diatomaceous mud, pebbly mud, sandy mud and mud, with scattered pebbles present in most samples. In contrast to a traditional conceptual model of glacial sediment distribution in fjords, grain size in Flandres Bay generally coarsens from the inner to outer bay. The smallest grain size sediments were found in the bay head and are interpreted as fine-grained deposits resulting from meltwater plumes and sediment gravity flows occurring close to the glacier front. The middle of the bay is characterized by a high silt percentage, which correlates to diatom-rich sediments. Sediments in the outer bay have a high component of coarse material, which is interpreted as being the result of winnowing from currents moving from the Bellingshausen Sea into the Gerlache Strait. Palaeoenvironmental reconstructions of glacial environments often use grain size as an indicator of proximity to the ice margin. After a detailed analysis of a large number of cores collected in the study area, our findings highlight the variability in sedimentation patterns within a fjord and provide a valuable evidence of the complexity that may occur in the sedimentary record. Keywords: Flandres Bay; Antarctic Peninsula; sediment distribution; grain size.
Keywords: Antarktis; havbunnen; isbreer; miljøvitenskap; sedimenter; sedimentologi; topografi

Evaluating CMIP5 ocean biogeochemistry and Southern Ocean carbon uptake using atmospheric potential oxygen: Present-day performance and future projection - Nevison, Cynthia; Manizza, Manfredi; Keeling, Ralph; Stephens, Britton; Bent, Jonathan; Dunne, John P; Ilyina, Tatiana; Long, Matthew; Resplandy, Laure; Tjiputra, Jerry; Yukimoto, Seiji (Geophysical Research Letters, 2016)
Observed seasonal cycles in atmospheric potential oxygen (APO ~ O2 + 1.1 CO2) were used to evaluate eight ocean biogeochemistry models from the Coupled Model Intercomparison Project (CMIP5). Model APO seasonal cycles were computed from the CMIP5 air-sea O2 and CO2 fluxes and compared to observations at three Southern Hemisphere monitoring sites. Four of the models captured either the observed APO seasonal amplitude or phasing relatively well, while the other four did not. Many models had an unrealistic seasonal phasing or amplitude of the CO2 flux, which in turn influenced APO. By 2100 under RCP8.5, the models projected little change in the O2 component of APO but large changes in the seasonality of the CO2 component associated with ocean acidification. The models with poorer performance on present-day APO tended to project larger net carbon uptake in the Southern Ocean, both today and in 2100.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; meteorologi; oseanografi

Chinstrap and macaroni penguin diet and demography at Nyrøysa, Bouvetøya - Niemandt, Corne; Kovacs, Kit M; Lydersen, Christian; Dyer, Bruce M; Isaksen, Kjell; Hofmeyr, G J Greg; Mehlum, Fridtjof; de Bruyn, P J Nico (Antarctic Science, 2016)
Publisher: Cambridge University Press
Keywords: Bouvetøya; klimaendringer; krill; pelsseler; pingviner; plankton

Magnetotelluric investigation of the Vestfold Hills and Rauer Group, East Antarctica - Peacock, Jared; Selway, Kate (Journal of Geophysical Research: Solid Earth, 2016)
The Vestfold Hills and Rauer Group in East Antarctica have contrasting Archean to Neoproterozoic geological histories and are believed to be juxtaposed along a suture zone that now lies beneath the Sørsdal Glacier. Exact location and age of this suture zone are unknown, as is its relationship to regional deformation associated with the amalgamation of East Gondwana. To image the suture zone, magnetotelluric (MT) data were collected in Prydz Bay, East Antarctica, mainly along a profile crossing the Sørsdal Glacier and regions inland of the Vestfold Hills and Rauer Group islands. Time-frequency analysis of the MT time series yielded three important observations: (1) Wind speeds in excess of ∼8 m/s reduce coherence between electric and magnetic fields due to charged wind-blown particles of ice and snow. (2) Estimation of the MT transfer function is best between 1000 and 1400 UT when ionospheric Hall currents enhance the magnetic source field. (3) Nonplanar source field effects were minimal but detectable and removed from estimation of the MT transfer function. Inversions of MT data in 2-D and 3-D produce similar resistivity models, where structures in the preferred 3-D resistivity model correlate strongly with regional magnetic data. The electrically conductive Rauer Group is separated from the less conductive Vestfold Hills by a resistive zone under the Sørsdal Glacier, which is interpreted to be caused by oxidation during suturing. Though a suture zone has been imaged, no time constrains on suturing can be made from the MT data.
Keywords: Antarktis; geofysikk; geologi; magnetotelluriske målinger

Ice core evidence for a 20th century increase in surface mass balance in coastal Dronning Maud Land, East Antarctica - Philippe, Morgane; Tison, Jean-Louis; Fjøsne, Karen; Hubbard, Bryn; Kjær, Helle A; Lenaerts, Jan T M; Drews, Reinhard; Sheldon, Simon G; De Bondt, Kevin; Claeys, Philippe; Pattyn, Frank (The Cryosphere, 2016)
Ice cores provide temporal records of surface mass balance (SMB). Coastal areas of Antarctica have relatively high and variable SMB, but are under-represented in records spanning more than 100 years. Here we present SMB reconstruction from a 120 m-long ice core drilled in 2012 on the Derwael Ice Rise, coastal Dronning Maud Land, East Antarctica. Water stable isotope (δ18O and δD) stratigraphy is supplemented by discontinuous major ion profiles and continuous electrical conductivity measurements. The base of the ice core is dated to AD 1759 ± 16, providing a climate proxy for the past ∼ 250 years. The core's annual layer thickness history is combined with its gravimetric density profile to reconstruct the site's SMB history, corrected for the influence of ice deformation. The mean SMB for the core's entire history is 0.47 ± 0.02 m water equivalent (w.e.) a−1. The time series of reconstructed annual SMB shows high variability, but a general increase beginning in the 20th century. This increase is particularly marked during the last 50 years (1962–2011), which yields mean SMB of 0.61 ± 0.01 m w.e. a−1. This trend is compared with other reported SMB data in Antarctica, generally showing a high spatial variability. Output of the fully coupled Community Earth System Model (CESM) suggests that, although atmospheric circulation is the main factor influencing SMB, variability in sea surface temperatures and sea ice cover in the precipitation source region also explain part of the variability in SMB. Local snow redistribution can also influence interannual variability but is unlikely to influence long-term trends significantly. This is the first record from a coastal ice core in East Antarctica to show an increase in SMB beginning in the early 20th century and particularly marked during the last 50 years.
Keywords: Dronning Maud Land; glasiologi; iskjerner

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

Scleractinian corals recorded in the Argentinean Antarctic expeditions between 2012 and 2014, with comments on Flabellum (Flabellum) areum Cairns, 1982 - Schejter, Laura; Bremec, Claudia S; Cairns, Stephen D (Polar Research, 2016)
In this contribution, we provide a list of the scleractinian corals recorded during the Argentinean Antarctic expeditions on board the oceanographic vessel Puerto Deseado (Argentina) in the austral summers in 2012, 2013 and 2014. The identified taxa consist of six solitary species (Flabellum impensum, F. flexuosum, F. areum, Caryophyllia antarctica, Paraconotrochus antarcticus and Javania antarctica), recorded from 19 sampling sites located off the Antarctic Peninsula and South Shetland and South Orkney islands. We also update the information of F. areum, previously known only from south-west Atlantic waters, extending its distribution range to Antarctic waters and its upper bathymetric range to 218 m. Keywords: cold-water corals; Antarctica; range extension; bathymetric range extension; Scleractinia.
Keywords: Sørishavet; ekspedisjoner; koraller; marin zoologi; oseanografi

Den langsomme polare vippen - Sorokina, Svetlana (Naturen, 2016)
De siste 20 årene har vært de varmeste siden globale temperaturmålinger startet i 1880 (Figur 1). FNs klimapanel konkluderer med at hovedårsaken til den observerte temperaturøkningen er menneskeskapte utslipp av klimagasser. I nordområdene har temperaturen økt nesten dobbelt så raskt som i resten av verden. Isdekket er nær halvert og isvolumet er redusert til en tredjedel. Men på den andre siden av jorden, altså i Antarktis, er situasjonen en helt annen. Temperaturen har vært fallende de siste årene og isdekket har vært rekordstort. Dette paradokset brukes ofte som et argument mot menneskeskapte endring av klima. For hvordan kan det ha seg at temperaturen i Antarktis faller når klimagassutslippene øker?
Keywords: Antarktis; global oppvarming; klimaendringer; klimagasser; polarområdene

The canine explorers – the sled dogs who helped Roald Amundsen reach the South Pole - Tahan, Mary R (Journal of Antarctic Affairs, 2016)
One hundred Greenland dogs were purchased by Roald Amundsen from the Royal Greenland Trading Company in September 1909 ostensibly for a North Pole expedition, but secretly to use to reach the South Pole. Amundsen considered the dogs “equipment”. He was a complicated character in a very different time. And he compulsively pursued his mission. His actions perhaps are seen differently from the 21st century perspective and in light of our evolving attitude toward animals, especially dogs. This paper presents the facts of what happened concerning the sled dogs, using Amundsen’s own statements in his books, diaries, and letters, as well as the expedition members’ journal entries and personal letters. It focuses on the dogs who made Amundsen’s exploration possible, and who helped humankind discover the final undiscovered part of our world. Amundsen began his Norwegian expedition with 97 sturdy canine souls, who were taken on board the Fram near the coast of Kristiansand in August 1910. Through births and deaths on the ship during their five-month journey south, the dogs’ number swelled to 116 upon arrival in Antarctica. Adults and puppies alike withstood the roller-coaster ride of the Fram on the ocean waters, the heat of the tropics near the equator, and the freezing winter of Antarctica. Taking into account the birth of puppies on the ship and at their Antarctic home Framheim, the actual number of dogs involved in this significant moment in history doubles to over two hundred. But, after initially nurturing and protecting the dogs, Amundsen proceeded to cull them throughout the expedition, slaughtering those he deemed unnecessary or weak, and destroying those who had served their purpose. Amundsen began his South Pole trek in October 1911 with 52 brave canines, and returned with 11, as a result of unnatural, forced attrition. The dogs were nearly starved; at times when they were fed, it was the flesh of their fallen comrades they were given to line their empty stomachs. And yet the dogs all performed their roles brilliantly, even when death was their reward. The sled dogs were the heart and power of the South Pole expedition. The intent of this article is to shine a light on the dogs’ population, accomplishments, and sacrifices, and to give them their due recognition and place in history.
Publisher: Agenda Antártica. Antarctic and Southern Ocean Coalition (ASOC)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser; sledehunder; trekkhunder

Temporal shift in the isotopic niche of female Antarctic fur seals from Bouvetøya - Tarroux, Arnaud; Lowther, Andrew D; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
The Antarctic fur seal (Arctocephalus gazella) is a key marine predator in the Southern Ocean, a region that has recently started to show changes as a result of global climate change. Here, carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyses on whole blood and plasma samples were used to examine the isotopic niche of lactating female Antarctic fur seals. Using recently developed Bayesian approaches to determine changes in isotopic niche, a significant increase in δ 13 C and δ 15 N was found between 1997 and 2015; this change occurred at an average rate of 0.067‰ (δ 13 C) and 0.072‰ (δ 15 N) per year over this period. This suggests that a marked isotopic niche shift has occurred over this period, which very likely corresponds to a shift in diet towards prey at a higher trophic level, such as fish (replacing krill). Although our sampling design prevented us from exploring a seasonal trend in a conclusive manner, our data suggest that concurrent increases in δ 13 C and δ 15 N might occur as the breeding season progresses. At a seasonal scale, an average decrease of −0.7‰ per month (95% confidence interval=[−0.9; −0.6]) in δ 13 C might have occurred, concurrently with an average increase of 1.1‰ per month in δ 15 N. The results of this study constitute the first isotopic assessment for female Antarctic fur seals from Bouvetøya and provide a baseline for the use of this predator species as a sentinel of the marine trophic system in one of the least studied areas within this species' distributional range.
Publisher: Routledge
Keywords: Bouvetøya; Sørishavet; klimaendringer; krill; marin biologi; pelsseler; plankton; stabile isotoper; zoologi

Pacific-Atlantic Circumpolar Deep Water coupling during the last 500 ka - Ullermann, Johannes; Lamy, Frank; Ninnemann, Ulysses; Lembke-Jene, Lester; Gersonde, Rainer; Tiedemann, Ralf (Paleoceanography, 2016)
Investigating the interbasin deepwater exchange between the Pacific and Atlantic Oceans over glacial-interglacial climate cycles is important for understanding circum-Antarctic Southern Ocean circulation changes and their impact on the global Meridional Overturning Circulation. We use benthic foraminiferal δ13C records from the southern East Pacific Rise to characterize the δ13C composition of Circumpolar Deep Water in the South Pacific, prior to its transit through the Drake Passage into the South Atlantic. A comparison with published South Atlantic deepwater records from the northern Cape Basin suggests a continuous water mass exchange throughout the past 500 ka. Almost identical glacial-interglacial δ13C variations imply a common deepwater evolution in both basins suggesting persistent Circumpolar Deep Water exchange and homogenization. By contrast, deeper abyssal waters occupying the more southern Cape Basin and the southernmost South Atlantic have lower δ13C values during most, but not all, stadial periods. We conclude that these values represent the influence of a more southern water mass, perhaps Antarctic Bottom Water (AABW). During many interglacials and some glacial periods, the gradient between Circumpolar Deep Water and the deeper southern Cape Basin bottom water disappears suggesting either no presence of AABW or indistinguishable δ13C values of both water masses.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; klimatologi; oseanografi; paleoseanografi

Investigating uncertainty in the simulation of the Antarctic ice sheet during the mid-Piacenzian - Yan, Qing; Zhang, Zhongshi; Wang, Huijun (Journal of Geophysical Research: Atmospheres, 2016)
The mid-Piacenzian (~3 Ma) represents the most recent warm period in Earth's history on a geological time scale; it is characterized by a significant rise of global sea level. The simulation of the size and location of the ice sheets and the investigation of the uncertainty in the simulations are potentially helpful for constraining reconstructed sea level changes. In this study, we focus on the behavior of the Antarctic ice sheet (AIS) in the mid-Piacenzian. We investigate the influence of topography correction, model parameters, climate forcings, and model resolution on the modeled AIS and explore the isolated role of atmospheric and oceanic forcings. Forced by the simulated climate changes with the Norwegian Earth System Model, the Parallel Ice Sheet Model (15 km × 15 km) produces a nearly collapsed West AIS (WAIS) in the mid-Piacenzian, with no significant retreat of the East AIS (EAIS). The role of increased air temperature plays a key role in the mass loss of the mid-Piacenzian AIS, while its role is comparable to the role of ocean warming on the melting of the WAIS. In terms of the range of sea level changes, the largest source of uncertainty in the modeled AIS is derived from ice sheet model parameters and climate forcings. Although the employed model parameters, topography correction factors, and model resolution affect the simulated AIS in the mid-Piacenzian, large-scale deglaciation of the EAIS in our sensitivity experiments may only be possible with additional warming.
Keywords: Antarktis; atmosfæren; geologi; havnivåstigning; innlandsis; klimaendringer; paleontologi

The impact of energetic electron precipitation on mesospheric hydroxyl during a year of solar minimum - Zawedde, Annet Eva; Nesse Tyssøy, Hilde; Hibbins, Robert; Espy, Patrick J; Ødegaard, Linn-Kristine Glesnes; Sandanger, Marit Irene; Stadsnes, Johan (Journal of Geophysical Research: Space Physics, 2016)
In 2008 a sequence of geomagnetic storms occurred triggered by high-speed solar wind streams from coronal holes. Improved estimates of precipitating fluxes of energetic electrons are derived from measurements on board the NOAA/POES 18 satellite using a new analysis technique. These fluxes are used to quantify the direct impact of energetic electron precipitation (EEP) during solar minimum on middle atmospheric hydroxyl (OH) measured from the Aura satellite. During winter, localized longitudinal density enhancements in the OH are observed over northern Russia and North America at corrected geomagnetic latitudes poleward of 55°. Although the northern Russia OH enhancement is closely associated with increased EEP at these longitudes, the strength and location of the North America enhancement appear to be unrelated to EEP. This OH density enhancement is likely due to vertical motion induced by atmospheric wave dynamics that transports air rich in atomic oxygen and atomic hydrogen downward into the middle atmosphere, where it plays a role in the formation of OH. In the Southern Hemisphere, localized enhancements of the OH density over West Antarctica can be explained by a combination of enhanced EEP due to the local minimum in Earth's magnetic field strength and atmospheric dynamics. Our findings suggest that even during solar minimum, there is substantial EEP-driven OH production. However, to quantify this effect, a detailed knowledge of where and when the precipitation occurs is required in the context of the background atmospheric dynamics.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; geomagnetiske stormer; planetbølger; solvind

Advancements in decadal climate predictability: The role of nonoceanic drivers - Bellucci, Alessio; Haarsma, Rein; Bellouin, Nicolas; Booth, Ben B; Cagnazzo, Chiara; van den Hurk, Bart; Keenlyside, Noel; Koenigk, Torben; Massonnet, François; Materia, Stefano; Weiss, M (Reviews of Geophysics, 2015)
We review recent progress in understanding the role of sea ice, land surface, stratosphere, and aerosols in decadal-scale predictability and discuss the perspectives for improving the predictive capabilities of current Earth system models (ESMs). These constituents have received relatively little attention because their contribution to the slow climatic manifold is controversial in comparison to that of the large heat capacity of the oceans. Furthermore, their initialization as well as their representation in state-of-the-art climate models remains a challenge. Numerous extraoceanic processes that could be active over the decadal range are proposed. Potential predictability associated with the aforementioned, poorly represented, and scarcely observed constituents of the climate system has been primarily inspected through numerical simulations performed under idealized experimental settings. The impact, however, on practical decadal predictions, conducted with realistically initialized full-fledged climate models, is still largely unexploited. Enhancing initial-value predictability through an improved model initialization appears to be a viable option for land surface, sea ice, and, marginally, the stratosphere. Similarly, capturing future aerosol emission storylines might lead to an improved representation of both global and regional short-term climatic changes. In addition to these factors, a key role on the overall predictive ability of ESMs is expected to be played by an accurate representation of processes associated with specific components of the climate system. These act as “signal carriers,” transferring across the climatic phase space the information associated with the initial state and boundary forcings, and dynamically bridging different (otherwise unconnected) subsystems. Through this mechanism, Earth system components trigger low-frequency variability modes, thus extending the predictability beyond the seasonal scale.
Keywords: Sørishavet; geofysikk; havis; klimaendringer; klimamodeller; meteorologi; polarområdene; sjøis

Mass balance of the Sør Rondane glacial system, East Antarctica - Callens, Denis; Thonnard, Nicolas; Lenaerts, Jan T M; Van Wessem, Jan M; Van de Berg, Willem Jan; Matsuoka, Kenichi; Pattyn, Frank (Annals of Glaciology, 2015)
Mass changes of polar ice sheets have an important societal impact, because they affect global sea level. Estimating the current mass budget of ice sheets is equivalent to determining the balance between surface mass gain through precipitation and outflow across the grounding line. For the Antarctic ice sheet, grounding line outflow is governed by oceanic processes and outlet glacier dynamics. In this study, we compute the mass budget of major outlet glaciers in the eastern Dronning Maud Land sector of the Antarctic ice sheet using the input/output method. Input is given by recent surface accumulation estimates (SMB) of the whole drainage basin. The outflow at the grounding line is determined from the radar data of a recent airborne survey and satellite-based velocities using a flow model of combined plug flow and simple shear. This approach is an improvement on previous studies, as the ice thickness is measured, rather than being estimated from hydrostatic equilibrium. In line with the general thickening of the ice sheet over this sector, we estimate the regional mass balance in this area at 3.15 ± 8.23 Gt a−1 according to the most recent SMB model results.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

On-site and in situ remediation technologies applicable to petroleum hydrocarbon contaminated sites in the Antarctic and Arctic - Camenzuli, Danielle; Freidman, Benjamin L (Polar Research, 2015)
Petroleum hydrocarbon contaminated sites, associated with the contemporary and legacy effects of human activities, remain a serious environmental problem in the Antarctic and Arctic. The management of contaminated sites in these regions is often confounded by the logistical, environmental, legislative and financial challenges associated with operating in polar environments. In response to the need for efficient and safe methods for managing contaminated sites, several technologies have been adapted for on-site or in situ application in these regions. This article reviews six technologies which are currently being adapted or developed for the remediation of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Bioremediation, landfarming, biopiles, phytoremediation, electrokinetic remediation and permeable reactive barriers are reviewed and discussed with respect to their advantages, limitations and potential for the long-term management of soil and groundwater contaminated with petroleum hydrocarbons in the Antarctic and Arctic. Although these technologies demonstrate potential for application in the Antarctic and Arctic, their effectiveness is dependent on site-specific factors including terrain, soil moisture and temperature, freeze–thaw processes and the indigenous microbial population. The importance of detailed site assessment prior to on-site or in situ implementation is emphasized, and it is argued that coupling of technologies represents one strategy for effective, long-term management of petroleum hydrocarbon contaminated sites in the Antarctic and Arctic. Keywords: Petroleum hydrocarbons; remediation; Antarctica; Arctic; cold regions; contaminated site.
Keywords: Antarktis; forurensning; hydrokarboner; miljøvern; petroleum; polarområdene

Mapping lichen distribution on the Antarctic Peninsula using remote sensing, lichen spectra and photographic documentation by citizen scientists - Casanovas, Paula; Black, Martin; Fretwell, Peter; Convey, Peter (Polar Research, 2015)
On the Antarctic Peninsula, lichens are the most diverse botanical component of the terrestrial ecosystem. However, detailed information on the distribution of lichens on the Antarctic Peninsula region is scarce, and the data available exhibit significant heterogeneity in sampling frequency and effort. Satellite remote sensing, in particular the use of the Normalized Difference Vegetation Index (NDVI), has facilitated determination of vegetation richness and cover distribution in some remote and otherwise inaccessible environments. However, it is known that using NDVI for the detection of vegetation can overlook the presence of lichens even if their land cover is extensive. We tested the use of known spectra of lichens in a matched filtering technique for the detection and mapping of lichen-covered land from remote sensing imagery on the Antarctic Peninsula, using data on lichen presence collected by citizen scientists and other non-specialists as ground truthing. Our results confirm that the use of this approach allows for the detection of lichen flora on the Antarctic Peninsula, showing an improvement over the use of NDVI alone for the mapping of flora in this area. Keywords: Antarctica; NDVI; matched filtering; Landsat; remote sensing.
Keywords: Antarktis; botanikk; flora; lav; satellitt bilder; økosystemer

Evolution of Derwael Ice Rise in Dronning Maud Land, Antarctica, over the last millennia - Drews, Reinhard; Matsuoka, Kenichi; Martín, Carlos; Callens, D; Bergeot, Nicolas; Pattyn, Frank (Journal of Geophysical Research: Earth Surface, 2015)
Ice rises situated in the ice-shelf belt around Antarctica have a spatially confined flow regime with local ice divides. Beneath the divides, ice stratigraphy often develops arches with amplitudes that record the divide's horizontal residence time and surface elevation changes. To investigate the evolution of Derwael Ice Rise, Dronning Maud Land, Antarctica, we combine radar and GPS data from three consecutive surveys, with a two-dimensional, full Stokes, thermomechanically coupled, transient ice-flow model. We find that the surface mass balance (SMB) is higher on the upwind and lower on the downwind slopes. Near the crest, the SMB is anomalously low and causes arches to form in the shallow stratigraphy, observable by radar. In deeper ice, arches are consequently imprinted by both SMB and ice rheology (Raymond effect). The data show how arch amplitudes decrease as along-ridge slope increases, emphasizing that the lateral positioning of radar cross sections is important for the arch interpretation. Using the model with three rheologies (isotropic with n=3,4.5 and anisotropic with n=3), we show that Derwael Ice Rise is close to steady state but is best explained using ice anisotropy and moderate thinning. Our preferred, albeit not unique, scenario suggests that the ice divide has existed for at least 5000 years and lowered at approximately 0.03 m a−1 over the last 3400 years. Independent of the specific thinning scenario, our modeling suggests that Derwael Ice Rise has exhibited a local flow regime at least since the Mid-Holocene.
Keywords: Dronning Maud Land; fjernmåling; glasiologi; innlandsis; isbreer; stratigrafi

Kaptein Melsom. Et spennende liv som hvalfanger og skipsreder - Dyrhaug, Tore (Njotarøy : årsskrift, 2015)
1912 fikk Nøtterøy en ny innbygger. Hvalfangeren H. G. Melsom var vendt hjem fra et hvalfangerliv i det fjerne Østen og kjøpte hus på Ørsnes. Her startet han opp en ny fase i livet, som skipsreder. Høydepunktet i hans karriere var trolig da hvalskuta «Lancing» dro om bord den første hvalen fra en opphalingsslipp i hekken på båten. Med dette var den virkelige pelagiske hvalfangsten i gang. Historien om «Lancing» som det første hvalkokeriet som kunne dra en hel hval om bord, er vel kjent og beskrevet. Dette var starten på den pelagiske hvalfangsten som brakte hvalfangsten inn i en ny fase. Men historien om hvalfangeren og rederen fra Nøtterøy, som var en av dem som sto bak, har ikke vært særlig kjent. Med god hjelp fra barnebarnet Henrik Melsom Henriksen, har Tore Dyrhaug skrevet ned denne historien.
Publisher: Nøtterøy historielag
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

On-ice vibroseis and snowstreamer systems for geoscientific research - Eisen, Olaf; Hofstede, Coen; Diez, Anja; Kristoffersen, Yngve; Lambrecht, Astrid; Mayer, Christoph; Blenkner, Rick; Hilmarsson, Sverrir (Recent Advance in Polar Seismology: Global Impact of the International Polar Year, 2015)
We present implementations of vibroseis system configurations with a snowstreamer for over-ice long-distance seismic traverses (>100 km). The configurations have been evaluated in Antarctica on ice sheet and ice shelf areas in the period 2010–2014. We discuss results of two different vibroseis sources: Failing Y-1100 on skis with a peak force of 120 kN in the frequency range 10–110 Hz; IVI EnviroVibe with a nominal peak force of 66 kN in the nominal frequency range 10–300 Hz. All measurements used a well-established 60 channel 1.5 km snowstreamer for the recording. Employed forces during sweeps were limited to less than 80% of the peak force. Maximum sweep frequencies, with a typical duration of 10 s, were 100 and 250 Hz for the Failing and EnviroVibe, respectively. Three different concepts for source movement were employed: the Failing vibrator was mounted with wheels on skis and pulled by a Pistenbully snow tractor. The EnviroVibe was operated self-propelled on Mattracks on the Antarctic plateau. This lead to difficulties in soft snow. For later implementations the EnviroVibe with tracks was put on a polyethylene (PE) sled. The sled had a hole in the center to lower the vibrator baseplate directly onto the snow surface. With the latter setup, data production varied between 20 km/day for 6-fold and 40 km/day for single fold for 9 h/day of measurements. The combination of tracks with the PE-sled was especially advantageous on hard and rough surfaces because of the flexibility of each component and the relatively lose mounting. The systems presented here are suitable to obtain data of subglacial and sub-seabed sediment layers and englacial layering in comparable quality as obtained from marine geophysics and land-based explosive surveys. The large offset aperture of the streamer overcomes limitations of radar systems for imaging of steep along-track subglacial topography. With joint international scientific and logistic efforts, large-scale mapping of Antarctica's and Greenland's subglacial geology, ice-shelf cavity geometries and sea-bed strata, as well as englacial structures can be achieved.
Keywords: Dronning Maud Land; isshelf; seismologi; teknologi

Van Allen probes, NOAA, GOES, and ground observations of an intense EMIC wave event extending over 12 h in magnetic local time - Engebretson, Mark J; Posch, J L; Wygant, J R; Kletzing, Craig A; Lessard, M R; Huang, C.-L.; Spence, Harlan; Smith, C W; Singer, H J; Omura, Yoshiharu; Horne, R B; Reeves, Geoffrey; et al. (Journal of Geophysical Research: Space Physics, 2015)
Although most studies of the effects of electromagnetic ion cyclotron (EMIC) waves on Earth's outer radiation belt have focused on events in the afternoon sector in the outer plasmasphere or plume region, strong magnetospheric compressions provide an additional stimulus for EMIC wave generation across a large range of local times and L shells. We present here observations of the effects of a wave event on 23 February 2014 that extended over 8 h in UT and over 12 h in local time, stimulated by a gradual 4 h rise and subsequent sharp increases in solar wind pressure. Large-amplitude linearly polarized hydrogen band EMIC waves (up to 25 nT p-p) appeared for over 4 h at both Van Allen Probes, from late morning through local noon, when these spacecraft were outside the plasmapause, with densities ~5–20 cm−3. Waves were also observed by ground-based induction magnetometers in Antarctica (near dawn), Finland (near local noon), Russia (in the afternoon), and in Canada (from dusk to midnight). Ten passes of NOAA-POES and METOP satellites near the northern foot point of the Van Allen Probes observed 30–80 keV subauroral proton precipitation, often over extended L shell ranges; other passes identified a narrow L shell region of precipitation over Canada. Observations of relativistic electrons by the Van Allen Probes showed that the fluxes of more field-aligned and more energetic radiation belt electrons were reduced in response to both the emission over Canada and the more spatially extended emission associated with the compression, confirming the effectiveness of EMIC-induced loss processes for this event.
Keywords: Antarktis; astronomi; elektromagnetiske ionesyklotronbølger; fysikk; magnetosfæriske kompresjoner; strålingsbelter

Interhemispheric differences in ionospheric convection: Cluster EDI observations revisited - Förster, Matthias; Haaland, Stein (Journal of Geophysical Research: Space Physics, 2015)
The interaction between the interplanetary magnetic field and the geomagnetic field sets up a large-scale circulation in the magnetosphere. This circulation is also reflected in the magnetically connected ionosphere. In this paper, we present a study of ionospheric convection based on Cluster Electron Drift Instrument (EDI) satellite measurements covering both hemispheres and obtained over a full solar cycle. The results from this study show that average flow patterns and polar cap potentials for a given orientation of the interplanetary magnetic field can be very different in the two hemispheres. In particular during southward directed interplanetary magnetic field conditions, and thus enhanced energy input from the solar wind, the measurements show that the southern polar cap has a higher cross polar cap potential. There are persistent north-south asymmetries, which cannot easily be explained by the influence of external drivers. These persistent asymmetries are primarily a result of the significant differences in the strength and configuration of the geomagnetic field between the Northern and Southern Hemispheres. Since the ionosphere is magnetically connected to the magnetosphere, this difference will also be reflected in the magnetosphere in the form of different feedback from the two hemispheres. Consequently, local ionospheric conditions and the geomagnetic field configuration are important for north-south asymmetries in large regions of geospace.
Keywords: Antarktis; astrofysikk; geovitenskap; ionosfæren; magnetosfæren; polarområdene; solvind

Haematological values of three Antarctic penguins: gentoo (Pygoscelis papua), Adélie (P. adeliae) and chinstrap (P. antarcticus) - Ibañez, Andrés E; Najle, Roberto; Larsen, Karen; Pari, Marcela; Figueroa, Amalia; Montalti, Diego (Polar Research, 2015)
It is established that haematological and biochemical parameters provide important data to assess the physiological condition and health status of wild birds. To undertake conservation physiology or ecophysiology work, it is therefore essential to establish baseline physiological parameters and how these parameters change with age and life history events. In this work, we determined and compared baseline haematology and serum biochemistry between adults and chicks of three Antarctic penguin species of the genus Pygoscelis: gentoo (P. papua), Adélie (P. adeliae) and chinstrap (P. antarcticus). Differences in adults among species were observed in haemoglobin and biochemical parameters such as total proteins, glucose and alkaline phosphatase activity. In addition, differences between adults and chicks in haematocrit, haemoglobin, total proteins and glucose concentration were determined. Moreover, we evaluated the electrophoretic protein profiles between adults and chicks of the genus Pygoscelis, and a conserved protein pattern was observed among species and ages in the genus. Altogether, the results suggest that biochemical and haematological differences among pygoscelids may be related to the nutritional status and energetic expenditure during breeding as well as their feeding habits and development stage. Keywords: Antarctic; haematology; physiology; Pygoscelis; penguins; serum biochemistry.
Keywords: Antarktis; biokjemi; biologi; fysiologi; hematologi; pingviner; zoologi

Two distinct Late Mesoproterozoic/Early Neoproterozoic basement provinces in central/eastern Dronning Maud Land, East Antarctica: The missing link, 15–21°E - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Kleinhanns, Ilka C; Henjes-Kunst, Friedhelm; Estrada, Solveig; Ruppel, Antonia S; Damaske, Detlef; Montero, Pilar; Bea, Fernando (Precambrian Research, 2015)
This article highlights the field geology, geochronology and geochemistry of an important and previously unstudied region between eastern (Sør Rondane Mountains) and central Dronning Maud Land (DML). The area allows the characterisation and ground-truthing of a large and mostly ice-covered area that is geophysically distinct and which was previously interpreted as a potentially older cratonic block south of a Late Neoproterozoic/Early Paleozoic (LN/EP) mobile belt, as exposed in the Sør Rondane Mts. (SRM). SHRIMP/SIMS zircon analyses of 20 samples together with new geochemistry indicate that the exposed basement consists of a ca. 1000–900Ma juvenile terrane that is very similar to the juvenile rocks of the SW-Terrane of the SRM, a characteristic gabbro–trondhjemite–tonalite–granite (GTTG) suite, with normalised trace element patterns typical for subduction-related magmas and mostly positive initial epsilon Nd values. The area shows strong LN/EP crustal reworking, migmatisation and melt production, including 560–530Ma A-type magmatism. Therefore, this area is very similar to the SW-Terrane and differs only in the degree of LN/EP reworking. We interpret the SW-Terrane of Sør Rondane as a mega-boudin sandwiched in between rheologically weaker portions of similar oceanic arc terranes. Therefore, the study area, and thereby the aeromagnetically distinct SE DML province does neither represent the foreland of a LN/EP mobile belt, nor a craton, as speculated based on geophysical data alone. Instead, a large Tonian Oceanic Arc Super Terrane (TOAST) with significant extent emerges. Its western limit is represented by the Forster Magnetic Anomaly, which represents a suture to the Grenville-age Maud Belt. East of the TOAST, the Rayner Complex is similar in age but otherwise distinctly different. The Rayner Complex has a much longer history of island arc accretions with continent–continent collision at ca. 950Ma and it has markedly more evolved crust. In contrast, the TOAST has a pronounced juvenile character without significant inheritance and lacks metamorphic overprint immediately following crust formation. This indicates that it has not been an integral part of Rodinia. The eastern boundary of the TOAST is probably in the vicinity of the Yamato Mts., whilst its northern extension might be seen in the Vohibori Terrane (SW Madagascar), which in turn could correlate with the Arabian Nubian Shield. The LN/EP tectono-metamorphic overprint of the TOAST shows a slight decrease in ages from W to E, possibly indicating that it first amalgamated on its Kalahari side before it was attached to Rukerland/Indo-Antarctica.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi

Application of remotely piloted aircraft systems in observing the atmospheric boundary layer over Antarctic sea ice in winter - Jonassen, Marius O; Tisler, Priit; Altstädter, Barbara; Scholtz, Andreas; Vihma, Timo; Lampert, Astrid; König-Langlo, Gert; Lüpkes, Christof (Polar Research, 2015)
The main aim of this paper is to explore the potential of combining measurements from fixed- and rotary-wing remotely piloted aircraft systems (RPAS) to complement data sets from radio soundings as well as ship and sea-ice-based instrumentation for atmospheric boundary layer (ABL) profiling. This study represents a proof-of-concept of RPAS observations in the Antarctic sea-ice zone. We present first results from the RV Polarstern Antarctic winter expedition in the Weddell Sea in June–August 2013, during which three RPAS were operated to measure temperature, humidity and wind; a fixed-wing small unmanned meteorological observer (SUMO), a fixed-wing meteorological mini-aerial vehicle, and an advanced mission and operation research quadcopter. A total of 86 RPAS flights showed a strongly varying ABL structure ranging from slightly unstable temperature stratification near the surface to conditions with strong surface-based temperature inversions. The RPAS observations supplement the regular upper air soundings and standard meteorological measurements made during the campaign. The SUMO and quadcopter temperature profiles agree very well and, excluding cases with strong temperature inversions, 70% of the variance in the difference between the SUMO and quadcopter temperature profiles can be explained by natural, temporal, temperature fluctuations. Strong temperature inversions cause the largest differences, which are induced by SUMO’s high climb rates and slow sensor response. Under such conditions, the quadcopter, with its slower climb rate and faster sensor, is very useful in obtaining accurate temperature profiles in the lowest 100 m above the sea ice. Keywords: Remotely piloted aircraft systems; unmanned aerial vehicles; Weddell Sea; polar meteorology; Antarctic; boundary layer meteorology.
Keywords: Sørishavet; Weddellhavet; fjernstyrte flysystemer; havis; meteorologi; målinger; observasjoner; sjøis; ubemannede luftfartøyer

A roadmap for Antarctic and Southern Ocean science for the next two decades and beyond - Kennicutt, M.C.; Chown, S.L.; Cassano, J.J.; Liggett, D.; Peck, L.S.; Massom, R.; Rintoul, S.R.; Storey, J.; Vaughan, D.G.; Wilson, T.J.; Allison, I.; Ayton, J.; et al. (Antarctic Science, 2015)
Antarctic and Southern Ocean science is vital to understanding natural variability, the processes that govern global change and the role of humans in the Earth and climate system. The potential for new knowledge to be gained from future Antarctic science is substantial. Therefore, the international Antarctic community came together to ‘scan the horizon’ to identify the highest priority scientific questions that researchers should aspire to answer in the next two decades and beyond. Wide consultation was a fundamental principle for the development of a collective, international view of the most important future directions in Antarctic science. From the many possibilities, the horizon scan identified 80 key scientific questions through structured debate, discussion, revision and voting. Questions were clustered into seven topics: i) Antarctic atmosphere and global connections, ii) Southern Ocean and sea ice in a warming world, iii) ice sheet and sea level, iv) the dynamic Earth, v) life on the precipice, vi) near-Earth space and beyond, and vii) human presence in Antarctica. Answering the questions identified by the horizon scan will require innovative experimental designs, novel applications of technology, invention of next-generation field and laboratory approaches, and expanded observing systems and networks. Unbiased, non-contaminating procedures will be required to retrieve the requisite air, biota, sediment, rock, ice and water samples. Sustained year-round access to Antarctica and the Southern Ocean will be essential to increase winter-time measurements. Improved models are needed that represent Antarctica and the Southern Ocean in the Earth System, and provide predictions at spatial and temporal resolutions useful for decision making. A co-ordinated portfolio of cross-disciplinary science, based on new models of international collaboration, will be essential as no scientist, programme or nation can realize these aspirations alone.
Edition: 2014/09/18 Publisher: Cambridge University Press
Keywords: Antarktis; Sørishavet; forskning; teknologi

The significant inputs of trace elements and rare earth elements from melting glaciers in Antarctic coastal waters - Kim, Intae; Kim, Guebuem; Choy, Eun Jung (Polar Research, 2015)
To evaluate the impact of modern glacier melting on the chemical enrichment of Antarctic coastal waters, we measured trace elements, including dissolved iron (Fe) and rare earth elements (REEs), together with dissolved inorganic nitrogen, phosphorous, silicate and dissolved organic carbon (DOC) in ice, snow and coastal seawater of Marian Cove in the northernmost part of Antarctica (62°S). There was an increase in the concentrations of Fe and other trace elements (Al, Mn, Cr, Ni, Co, Pb and REEs) between the bay mouth and the glacier valleys. Good correlations between salinity and these chemical elements indicate that the trend was mainly due to the influence of glacier meltwater (GMW). When the effect of GMW was quantified based on plots of its presence (average 5.7%) in the surface water of the cove, the concentrations of trace elements in seawater increased 18-fold for Fe, eight- to 10-fold for Al and Mn and up to four-fold for Cr, Ni, Co, Pb and REEs by GMW. However, the contribution of GMW to inorganic nutrients and DOC was negligible. The significance of GMW-borne REE contribution in this cove was further evidenced by middle REE enrichment in cove water. Our results suggest that the currently increasing glacier melting in Antarctica has a significant influence on the level of trace elements, particularly Fe, in cove water, which in turn may have a significant impact on the biogeochemistry of coastal seawater in Antarctica. Keywords: Iron; trace elements; rare earth elements; glacier melting; Antarctica; Marian Cove.
Keywords: Antarktis; biogeokjemi; isbreer; kjemiske analyser; sjøvann; smelting

An Antarctic krill (Euphausia superba) hotspot: population characteristics, abundance and vertical structure explored from a krill fishing vessel - Krafft, Bjørn Arne; Skaret, Georg; Knutsen, Tor (Polar Biology, 2015)
Keywords: Sørishavet; krill; marin biologi; plankton; zooplankton

Western Australia-Kalahari (WAlahari) connection in Rodinia: Not supported by U/Pb detrital zircon data from the Maud Belt (East Antarctica) and the Northampton Complex (Western Australia) - Ksienzyk, Anna K; Jacobs, Joachim (Precambrian Research, 2015)
The Kalahari Craton is an important building block of the supercontinent Rodinia, but its position with respect to other cratons is still controversially discussed. The Maud Belt in East Antarctica is part of the extensive Namaqua-Natal-Maud Orogen along which Kalahari collided with another continent during Rodinia assembly. One of the continents that have been suggested as collision partners for Kalahari is Western Australia, with the Pinjarra Orogen as the counterpart to the Maud Belt. We investigate this connection from a geochronological point of view. SHRIMP U/Pb zircon analyses of three metasedimentary samples from the Maud Belt date Grenville-age metamorphism within the orogen at ca. 1100–1060Ma. One sample was later affected by Pan-African metamorphism at ca. 540Ma. A second sample is interpreted as a molasse of the Maud Belt and was deposited in the Neoproterozoic. Detrital zircons from all three samples are consistent with derivation of the sediments predominantly from within the Namaqua-Natal-Maud Belt, with minor contributions from the Kalahari Craton. No clear Western Australian fingerprint could be detected in the detrital ages and a direct comparison between detrital zircon ages from the Maud Belt and the Northampton Complex (Pinjarra Orogen, Western Australia) showed distinct differences in the age spectra. Altogether, we consider a collision between Kalahari and south-western Laurentia a more likely scenario.
Keywords: Dronning Maud Land; geokronologi; geovitenskap

Birkeland current effects on high-latitude ground magnetic field perturbations - Laundal, Karl M; Haaland, Stein; Lehtinen, N; Gjerloev, Jesper; Østgaard, Nikolai; Tenfjord, Paul; Reistad, Jone Peter; Snekvik, Kristian; Milan, Steve; Ohtani, Shin-ichi; Anderson, B J (Geophysical Research Letters, 2015)
Magnetic perturbations on ground at high latitudes are directly associated only with the divergence-free component of the height-integrated horizontal ionospheric current, J⊥,df. Here we show how J⊥,df can be expressed as the total horizontal current J⊥ minus its curl-free component, the latter being completely determined by the global Birkeland current pattern. Thus, in regions where J⊥=0, the global Birkeland current distribution alone determines the local magnetic perturbation. We show with observations from ground and space that in the polar cap, the ground magnetic field perturbations tend to align with the Birkeland current contribution in darkness but not in sunlight. We also show that in sunlight, the magnetic perturbations are typically such that the equivalent overhead current is antiparallel to the convection, indicating that the Hall current system dominates. Thus, the ground magnetic field in the polar cap relates to different current systems in sunlight and in darkness.
Keywords: Antarktis; Birkelandstrømmer; ionosfæren; ionosfæriske strømmer; polarområdene; sollys

Reliability of VHF telemetry data for measuring attendance patterns of marine predators: a comparison with time depth recorder data - Lowther, A D; Ahonen, H; Hofmeyr, G; Oosthuizen, W C; De Bruyn, P J N; Lydersen, C; Kovacs, K M (Marine Ecology Progress Series, 2015)
Very high frequency (VHF) radiotelemetry data has been used for over 30 yr to monitor the behavior patterns of otariid seals. These data have been used in a wide variety of ways, from characterizing the reproductive and foraging ecology of these species to inferring ecosystem changes based on variation in attendance patterns. Yet the accuracy of VHF data has never been appropriately evaluated. Our study compares VHF data collected on 16 lactating Antarctic fur seals to assess onshore attendance with concurrently collected time depth recorder (TDR) data used as the true measurement of time spent onshore. Within the retrieved datasets, 25% of the VHF data could not be interpreted with any reliability. Additionally, there were significant differences in the number and duration of attendance bouts between the 2 instrument types, with VHF data overestimating attendance bout duration by approximately 8.9 h on average. Importantly, the magnitude and direction of errors between VHF and TDR measurements were not systematic, suggesting that VHF data is an inappropriate method for collecting attendance data. Modelling the raw VHF data in a state-space framework elicited mean attendance durations that were indistinguishable from TDR-derived measurements, suggesting this approach may provide a means to re-examine historic VHF data. Moreover, given the evolution of electronic tags in terms of sophistication, miniaturization, longevity and decreasing cost over the last 30 yr, TDRs are a more appropriate means of collecting attendance data on centrally foraging marine mammals such as otariids.
Keywords: Bouvetøya; NARE ekspedisjoner; Sørishavet; marin zoologi; overvåking; pelsseler; pinnipedier; radio telemetri; økosystemer

The great white silence : den offisielle filmen om Robert Falcon Scotts sydpolekspedisjon og en vurdering av ekspedisjonen - Lund, Vidar (Maritimt Magasin Historie, 2015)
Publisher: Commentum Forlag Place: Oslo
Keywords: Antarktis; Robert Falcon Scott; Sydpolsekspedisjonen; oppdagelsesreiser

The potential response of the hydrate reservoir in the South Shetland Margin, Antarctic Peninsula, to ocean warming over the 21st century - Marín-Moreno, Hector; Giustiniani, Michela; Tinivella, Umberta (Polar Research, 2015)
In the South Shetland Margin (SSM), Antarctic Peninsula, a bottom-simulating reflector indicates the presence of hydrate between ca. 500 and 3000 m water depth (mwd). The cold seabed temperatures allow hydrate stability at shallower water depths. During the past five decades, the Antarctic Peninsula has been warming up faster than any other part of the Southern Hemisphere, and long-term ocean warming could affect the stability of the SSM hydrate reservoir at shallow waters. Here, we model the transient response of the SSM hydrate reservoir between 375 and 450 mwd to ocean warming for the period 1958–2100. For the period 1958–2010, seabed temperatures are given by oceanographic measurements in the area, and for 2010–2100 by two temperature scenarios represented by the observed trends for the periods 1960–2010 (0.0034°C y−1) and 1980–2010 (0.023°C y−1). Our results show no hydrate-sourced methane emissions for an ocean warming rate at the seabed of 0.0034 °C y−1. For a rate of 0.023°C y−1, emissions start in 2028 at 375 mwd and extend to 442 mwd at an average rate of about 0.91 mwd y−1, releasing ca. 1.13×103 mol y−1 of methane per metre along the margin by 2100. These emissions originate from dissociation at the top of the hydrate layer, a physical process that steady-state modelling cannot represent. Our results are speculative on account of the lack of direct evidence of a shallow water hydrate reservoir, but they illustrate that the SSM is a key area to observe the effects of ocean warming-induced hydrate dissociation in the coming decades. Keywords: Hydrate; ocean warming; methane emissions; transient modelling; South Shetland Margin; Antarctic Peninsula.
Keywords: Sørishavet; geofysikk; havbunnen; havoppvarming; metanutslipp; oseanografi

Antarctic ice rises and rumples: their properties and significance for ice-sheet dynamics and evolution - Matsuoka, Kenichi; Hindmarsh, Richard C A; Moholdt, Geir; Bentley, Michael J; Pritchard, Hamish D; Brown, Joel; Conway, Howard; Drews, Reinhard; Durand, Gaël; Goldberg, Daniel; Hattermann, Tore; Kingslake, Jonathan; et al. (Earth-Science Reviews, 2015)
Locally grounded features in ice shelves, called ice rises and rumples, play a key role buttressing discharge from the Antarctic Ice Sheet and regulating its contribution to sea level. Ice rises typically rise several hundreds of meters above the surrounding ice shelf; shelf flow is diverted around them. On the other hand, shelf ice flows across ice rumples, which typically rise only a few tens of meters above the ice shelf. Ice rises contain rich histories of deglaciation and climate that extend back over timescales ranging from a few millennia to beyond the last glacial maximum. Numerical model results have shown that the buttressing effects of ice rises and rumples are significant, but details of processes and how they evolve remain poorly understood. Fundamental information about the conditions and processes that cause transitions between floating ice shelves, ice rises and ice rumples is needed in order to assess their impact on ice-sheet behavior. Targeted high-resolution observational data are needed to evaluate and improve prognostic numerical models and parameterizations of the effects of small-scale pinning points on grounding-zone dynamics.
Keywords: Antarktis; Sørishavet; glasiologi; havis

Observational evidence of the influence of Antarctic stratospheric ozone variability on middle atmosphere dynamics - Narukull, Venkateswara Rao; Espy, Patrick Joseph; Hibbins, Robert; Fritts, David C; Kavanagh, Andrew John (Geophysical Research Letters, 2015)
Abstract Modeling results have suggested that the circulation of the stratosphere and mesosphere in spring is strongly affected by the perturbations in heating induced by the Antarctic ozone hole. Here using both mesospheric MF radar wind observations from Rothera Antarctica (67°S, 68°W) as well as stratospheric analysis data, we present observational evidence that the stratospheric and mesospheric wind strengths are highly anti-correlated, and show their largest variability in November. We find that these changes are related to the total amount of ozone loss that occurs during the Antarctic spring ozone hole and particularly with the ozone gradients that develop between 57.5°S and 77.5°S. The results show that with increasing ozone loss during spring, winter conditions in the stratosphere and mesosphere persist longer into the summer. These results are discussed in the light of observations of the onset and duration of the Antarctic polar mesospheric cloud season.
Keywords: Antarktis; klimatologi; meteorologi; ozonhull; ozonlaget

Methane and nitrous oxide fluxes in relation to vegetation covers and bird activity in ice-free soils of Rip Point, Nelson Island, Antarctica - Neufeld, Ângela Denise Hubert; de Godoi, Stefânia Guedes; Pereira, Antônio Batista; Bayer, Cimélio; Schünemann, Andriano Luis; de Carvalho Victoria, Filipe; de Albuquerque, Margéli Pereira; Camargo, Estefânia; Vieira, Frederico Costa Beber (Polar Research, 2015)
This study aimed to quantify the nitrous oxide (N2O) and methane (CH4) fluxes at sites with different vegetation covers and where bird activity was present or absent using the static chamber method, on Rip Point, Nelson Island, maritime Antarctic. The sites were soils covered by Sanionia uncinata, lichens, Prasiola crispa, Deschampsia antarctica and bare soil. Seabirds used the P. crispa and D. antarctica sites as nesting areas. Soil mineral N contents, air and soil temperature and water-filled pore space were measured, and the content of total organic C and particulate organic C, total N, bulk density and texture were determined to identify controlling variables of the gas emissions. The N2O and CH4 flux rates were low for all sampling events. Mean N2O flux rates ranged from 0.11±1.93 up to 21.25±22.14 µg N2O m−2 h−1 for the soils under lichen and P. crispa cover, respectively. For the CH4 fluxes, only the P. crispa site showed a low positive mean (0.47±3.61 µg CH4 m−2 h−1). The bare soil showed the greatest absorption of CH4 (−11.92±5.7 µg CH4 m−2 h−1), probably favoured by the coarse soil texture. Bare soil and S. uncinata sites had N2O accumulated emissions close to zero. Net CH4 accumulated emission was observed only at the P. crispa site, which was correlated with (p<0.001). These results indicate that seabird activity influences N2O and CH4 soil fluxes, while vegetation has little influence, and bare soil areas in maritime Antarctica could be greenhouse gas sinks. Keywords: Soil greenhouse gases; seabirds; vegetal cover; maritime Antarctica.
Keywords: Antarktis; biogeokjemi; drivhuseffekt; drivhusgasser; flora; global oppvarming; klimaendringer; klimagasser; planter; sjøfugler; økosystemer

Ozone-induced climate change propped up by the Southern Hemisphere oceanic front - Ogawa, Fumiaki; Omrani, Nour-Eddine; Nishii, Kazuaki; Nakamura, Hisashi; Keenlyside, Noel (Geophysical Research Letters, 2015)
The late twentieth century was marked by a significant summertime trend in the Southern Annular Mode (SAM), the dominant mode of tropospheric variability in the extratropical Southern Hemisphere (SH). This trend with poleward shifting tropospheric westerlies was attributed to downward propagation of stratospheric changes induced by ozone depletion. However, the role of the ocean in setting the SAM response to ozone depletion and its dynamical forcing remains unclear. Here we show, using idealized experiments with a state-of-the-art atmospheric model and analysis of Intergovernmental Panel on Climate Change climate simulations, that frontal sea surface temperature gradients in the midlatitude SH are critical for translating the ozone-induced stratospheric changes down to the surface. This happens through excitation of wave forcing, which controls the vertical connection of the tropospheric SAM with the stratosphere and shows the importance of internal tropospheric dynamics for stratosphere/troposphere coupling. Thus, improved simulation of oceanic fronts may reduce uncertainties in simulating SH ozone-induced climate changes.
Keywords: Sørishavet; geofysikk; havet; havstrømmer; klimaendringer; ozonhull; ozonlaget

First record of humpback anglerfish (Melanocetus johnsonii) (Melanocetidae) in Antarctic waters - Orlov, Alexei M.; Orlova, Svetlana Y.; Volkov, Alexander A.; Pelenev, Dmitry V. (Polar Research, 2015)
The first record of the humpback anglerfish (Melanocetus johnsonii) in Antarctic waters (Ross Sea) is documented. Species identification is confirmed by the structure of the escal bulb and analysis of the mitochondrial cytochrome oxidase subunit I (COI) gene. This record extends the known range of M. johnsonii by more than 1000 nm to the south. The taxonomic status of Melanocetus species in Antarctic waters is discussed. Keywords: Melanocetus sp.; new record; taxonomy; distribution; Ross Sea; Antarctic.
Keywords: Rosshavet; Sørishavet; fisker; genetisk analyse; marin zoologi; taksonomi; zoogeografi

Seismic signals from large, tabular icebergs drifting along the Dronning Maud Land coast, Antarctica, and their significance for iceberg monitoring - Pirli, Myrto; Matsuoka, Kenichi; Schweitzer, Johannes; Moholdt, Geir (Journal of Glaciology, 2015)
In this study, we analyze a large dataset of seismic signals, recorded by station TROLL in Dronning Maud Land, Antarctica. The signals, recorded in April–December 2012, came from sources near the edge of the ice shelves, at distances of 230–500 km from TROLL. The sources, which moved westward with time, could be associated with four large, tabular icebergs, drifting between 15° E and 8° W. Combining the seismological data with information from satellite remote sensing, we find that one-third of the signals can be attributed to individual icebergs. The trajectories of three of the associated icebergs are known through iceberg-tracking databases, whereas the fourth, a fragment of one of the other three, is untracked, and only scarce information is available from satellite imagery. The observed seismic signals exhibit a wide variety of frequency characteristics, from unstructured episodes to occurrences of iceberg harmonic tremor. Although we are not able to determine the exact cause of the signals, we classify them into five classes on a phenomenological basis. This study demonstrates the potential of regional seismic networks for iceberg monitoring as supplementary resources to information obtained with remote-sensing technologies.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; havis; isfjell; teknologi

More than passive drifters: a stochastic dynamic model for the movement of Antarctic krill - Richerson, Kate; Watters, George M; Santora, Jarrod A; Schroeder, Isaac D; Mangel, Marc (Marine Ecology Progress Series, 2015)
Antarctic krill Euphausia superba are a key part of the marine food web and are the target of the largest fishery in the Southern Ocean. Although ecosystem and management models typically assume that krill are passive drifters, their relatively large size and strong swimming ability suggest that the active movement of krill may play an important role in their spatial distribution. Thus, active swimming behavior by krill may influence spatial structure of food web interactions (e.g. feeding behavior of seabirds and marine mammals) and regional commercial fishery activity. The objective of this work was to model the potential for active movement to affect krill distribution, and consequently growth, reproductive success, and survival. We used state-dependent life history theory, implemented by stochastic dynamic programming, in combination with spatial information on food availability, current velocity, temperature, and predation risk, to predict krill swimming behavior near the northern Antarctic Peninsula. We found that including active krill behavior resulted in distribution patterns that are associated with increased survival, growth, and reproductive success compared to a model that treats krill as passive drifters. The expected reproductive success of actively behaving krill was about 70% greater than that of passively diffusing krill, suggesting that there are strong selective pressures for active behavior along oceanic drift trajectories. This modeling framework will benefit assessments of new catch limits as krill fishing grounds are partitioned into smaller spatial management units. KEYWORDS: Euphausia superba · Behavior · Stochastic dynamic programming · Management · Advection · Southern Ocean
Keywords: Sørishavet; krill; marin biologi; oseanografi; plankton; økosystemer

Sessile macro-epibiotic community of solitary ascidians, ecosystem engineers in soft substrates of Potter Cove, Antarctica - Rimondino, Clara; Torre, Luciana; Sahade, Ricardo; Tatián, Marcos (Polar Research, 2015)
The muddy bottoms of inner Potter Cove, King George Island (Isla 25 de Mayo), South Shetlands, Antarctica, show a high density and richness of macrobenthic species, particularly ascidians. In other areas, ascidians have been reported to play the role of ecosystem engineers, as they support a significant number of epibionts, increasing benthic diversity. In this study, a total of 21 sessile macro-epibiotic taxa present on the ascidian species Corella antarctica Sluiter, 1905, Cnemidocarpa verrucosa (Lesson, 1830) and Molgula pedunculata Herdman, 1881 were identified, with Bryozoa being the most diverse. There were differences between the three ascidian species in terms of richness, percent cover and diversity of sessile macro-epibionts. The morphological characteristics of the tunic surface, the available area for colonization (and its relation with the age of the basibiont individuals) and the pH of the ascidian tunic seem to explain the observed differences. Recent environmental changes in the study area (increase of suspended particulate matter caused by glaciers retreat) have been related to observed shifts in the benthic community structure, negatively affecting the abundance and distribution of the studied ascidian species. Considering the diversity of sessile macro-epibionts found on these species, the impact of environmental shifts may be greater than that estimated so far. Keywords: Sessile macro-epibiont; ascidian; Antarctica; ecosystem- engineer.
Keywords: Sørishavet; bentiske organismer; biodiversitet; bryozoa; havbunnen; sekkdyr; økologi; økosystemer

The Main Shear Zone in Sør Rondane, East Antarctica: Implications for the late-Pan-African tectonic evolution of Dronning Maud Land - Ruppel, Antonia S; Läufer, Andreas; Jacobs, Joachim; Elburg, Marlina; Krohne, Nicole; Damaske, Detlef; Lisker, Frank (Tectonics, 2015)
Structural investigations in western Sør Rondane, eastern Dronning Maud Land (DML), provide new insights into the tectonic evolution of East Antarctica. One of the main structural features is the approximately 120 km long and several hundred meters wide WSW-ENE trending Main Shear Zone (MSZ). It is characterized by dextral high-strain ductile deformation under peak amphibolite-facies conditions. Crosscutting relationships with dated magmatic rocks bracket the activity of the MSZ between late Ediacaran to Cambrian times (circa 560 to 530 Ma). The MSZ separates Pan-African greenschist- to granulite-facies metamorphic rocks with “East African” affinities in the north from a Rayner-age early Neoproterozoic gabbro-tonalite-trondhjemite-granodiorite complex with “Indo-Antarctic” affinities in the south. It is interpreted to represent an important lithotectonic strike-slip boundary at a position close to the eastern margin of the East African-Antarctic Orogen (EAAO), which is assumed to be located farther south in the ice-covered region. Together with the possibly coeval left-lateral South Orvin Shear Zone in central DML, the MSZ may be related to NE directed lateral escape of the EAAO, whereas the Heimefront Shear Zone and South Kirwanveggen Shear Zone of western DML are part of the south directed branch of this bilateral system.
Keywords: Dronning Maud Land; geokronologi; geologi; geovitenskap; petrografi; tektonikk

Multi-frequency observations of seawater carbonate chemistry on the central coast of the western Antarctic Peninsula - Schram, Julie B; Schoenrock, Kathryn M; McClintock, James B; Amsler, Charles D; Angus, Robert A (Polar Research, 2015)
Assessments of benthic coastal seawater carbonate chemistry in Antarctica are sparse. The studies have generally been short in duration, during the austral spring/summer, under sea ice, or offshore in ice-free water. Herein we present multi-frequency measurements for seawater collected from the shallow coastal benthos on a weekly schedule over one year (May 2012–May 2013), daily schedule over three months (March–May 2013) and semidiurnal schedule over five weeks (March–April 2013). A notable pH increase (max pH = 8.62) occurred in the late austral spring/summer (November–December 2012), coinciding with sea-ice break-out and subsequent increase in primary productivity. We detected semidiurnal variation in seawater pH with a maximum variation of 0.13 pH units during the day and 0.11 pH units during the night. Daily variation in pH is likely related to biological activity, consistent with previous research. We calculated the variation in dissolved inorganic carbon (DIC) over each seawater measurement frequency, focusing on the primary DIC drivers in the Palmer Station region. From this, we estimated net biological activity and found it accounts for the greatest variations in DIC. Our seasonal data suggest that this coastal region tends to act as a carbon dioxide source during austral winter months and as a strong sink during the summer. These data characterize present-day seawater carbonate chemistry and the extent to which these measures vary over multiple time scales. This information will inform future experiments designed to evaluate the vulnerability of coastal benthic Antarctic marine organisms to ocean acidification. Keywords: Antarctica; aragonite; calcite; pH; seawater chemistry; total alkalinity.
Keywords: Sørishavet; analyser; havis; kjemisk; sjøis; sjøvann

Polychlorinated biphenyl exposure and corticosterone levels in seven polar seabird species - Tartu, Sabrina; Angelier, Frédéric; Bustnes, Jan-Ove; Moe, Børge; Hanssen, Sven Are; Herzke, Dorte; Gabrielsen, Geir Wing; Verboven, Nanette; Verreault, J; Labadie, Pierre; Budzinski, Helene; Wingfield, John C; et al. (Environmental Pollution, 2015)
The role of polychlorinated biphenyls (PCBs) on exposure-related endocrine effects has been poorly investigated in wild birds. This is the case for stress hormones including corticosterone (CORT). Some studies have suggested that environmental exposure to PCBs and altered CORT secretion might be associated. Here we investigated the relationships between blood PCB concentrations and circulating CORT levels in seven free-ranging polar seabird species occupying different trophic positions, and hence covering a wide range of PCB exposure. Blood ∑7PCB concentrations (range: 61–115,632 ng/g lw) were positively associated to baseline or stress-induced CORT levels in three species and negatively associated to stress-induced CORT levels in one species. Global analysis suggests that in males, baseline CORT levels generally increase with increasing blood ∑7PCB concentrations, whereas stress-induced CORT levels decrease when reaching high blood ∑7PCB concentrations. This study suggests that the nature of the PCB-CORT relationships may depend on the level of PCB exposure.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; polarområdene; sjøfugler; stresshormoner; zoologi

Corticosterone, prolactin and egg neglect behavior in relation to mercury and legacy POPs in a long-lived Antarctic bird - Tartu, Sabrina; Angelier, Frédéric; Wingfield, John C; Bustamante, Paco; Labadie, Pierre; Budzinski, Helene; Weimerskirch, Henri; Bustnes, Jan-Ove; Chastel, Olivier (Science of the Total Environment, 2015)
Seabirds often have high loads of contaminants. These contaminants have endocrine disrupting properties but their relationships with some endocrine mechanisms are still poorly investigated in free-living organisms. This is the case for the stress response which shifts energy investment away from reproduction and redirects it towards survival. In birds, this stress response is achieved through a release of corticosterone and is also accompanied by a decrease in circulating prolactin, an anterior pituitary hormone widely involved in regulating parental cares. We measured blood concentrations of some legacy persistent organic pollutants (POPs) and mercury (Hg) and examined their relationships with the corticosterone and prolactin responses of known-age (9–46years old) incubating snow petrels (Pagodroma nivea) to a standardized capture/handling stress protocol. In this Antarctic seabird, we also investigated whether high contaminant burden correlates with a higher occurrence of egg neglect, a frequently observed behavior in snow petrels. POPs and Hg were unrelated to age. Stress-induced corticosterone concentrations were positively related to POPs in both sexes, and stress-induced prolactin concentrations were negatively related to Hg in males. Egg-neglect behavior was not related to POPs burden, but males with higher Hg concentrations were more likely to neglect their egg. This suggests that in birds, relationships between age and contaminants are complex and that even low to moderate concentrations of POPs and Hg are significantly related to hormonal secretion. In this Antarctic species, exposure to legacy POPs and Hg could make individuals more susceptible to environmental stressors such as ongoing disturbances in Polar Regions.
Keywords: Antarktis; forurensning; miljø; nevrobiologi; ornitologi; petreller; polarområdene; reproduksjon; sjøfugler; zoologi

Investigating the recent apparent hiatus in surface temperature increases: 2. Comparison of model ensembles to observational estimates - Thorne, Peter; Outten, Stephen; Bethke, Ingo; Seland, Øyvind (Journal of Geophysical Research: Atmospheres, 2015)
To assess published hypotheses surrounding the recent slowdown in surface warming (hiatus), we compare five available global observational surface temperature estimates to two 30-member ensembles from the Norwegian Earth System Model (NorESM). Model ensembles are initialized in 1980 from the transient historical runs and driven with forcings used in the CMIP5 experiments and updated forcings based upon current observational understanding, described in Part 1. The ensembles' surface temperature trends are statistically indistinguishable over 1998–2012 despite differences in the prescribed forcings. There is thus no evidence that forcing errors play a significant role in explaining the hiatus according to NorESM. The observations fall either toward the lower portion of the ensembles or, for some observational estimates and regions, outside. The exception is the Arctic where the observations fall toward the upper ensemble bounds. Observational data set choices can make a large difference to findings of consistency or otherwise. Those NorESM ensemble members that exhibit Nino3.4 Sea Surface Temperature (SST) trends similar to observed also exhibit comparable tropical and to some extent global mean trends, supporting a role for El Nino Southern Oscillation in explaining the hiatus. Several ensemble members capture the marked seasonality observed in Northern Hemisphere midlatitude trends, with cooling in the wintertime and warming in the remaining seasons. Overall, we find that we cannot falsify NorESM as being capable of explaining the observed hiatus behavior. Importantly, this is not equivalent to concluding NorESM could simultaneously capture all important facets of the hiatus. Similar experiments with further, distinct, Earth System Models are required to verify our findings.
Keywords: Antarktis; atmosfæren; fjernmåling; geofysikk; klimaendringer; klimatologi; meteorologi; observasjoner; polarområdene; temperatur

Norske interesser og politikk i Antarktis - Utenriksdepartementet (2015)
Publisher: Fagbokforlaget Place: Oslo
Keywords: Dronning Maud Land; forvaltning; politikk

Comment on “Unexpected Occurrence of Volatile Dimethylsiloxanes in Antarctic Soils, Vegetation, Phytoplankton, and Krill” - Warner, Nicholas A; Krogseth, Ingjerd S; Whelan, Mick J (Environmental Science & Technology, 2015)
Sanchís et al. (2015) recently reported the occurrence of volatile methyl siloxanes (VMS) in soil, vegetation, phytoplankton, and krill samples from Antarctica. As the paper’s title suggests, findings of these chemicals in such a remote region is unexpected and of significant concern. However, our experience with the analysis of these compounds at trace concentrations suggests that the observations reported may have been influenced by artifacts. Here we present our concerns based upon known emissions, physicochemical properties and on apparent quality control measures including treatment of blank samples and detection limits.
Publisher: American Chemical Society
Keywords: Antarktis; forurensning; miljøgifter

Population-specific wintering distributions of adult south polar skuas over three oceans - Weimerskirch, Henri; Tarroux, Arnoud; Chastel, Olivier; Delord, Karine; Cherel, Yves; Descamps, Sébastien (Marine Ecology Progress Series, 2015)
Migratory routes and the areas used during winter have probably been selected to maximize fitness by providing favorable environmental conditions outside the breeding season. In polar environments, because of the extreme winter weather, most breeding species migrate to encounter better conditions in areas that can differ between and also within species. Using geolocation sensors, we found that south polar skuas Catharacta maccormicki from 2 distant populations breeding on the Antarctic continent along the Atlantic and Indian Oceans migrate northward to winter in tropical Indian Ocean and in temperate North Pacific waters, respectively. Most individuals from each population winter in different environmental conditions, with water temperatures ranging from 16 to 29°C. Nevertheless, they have very similar activity patterns, spending more than 80% of their time on the water, and their feather δ15N values suggest that they probably feed at similar trophic levels during the molt. During overwintering, the overall and constant low activity level may be partly imposed by molting constraints, but it also suggests that trophic conditions are good for skuas. The wintering areas of the species correspond to sectors of high concentrations of breeding or wintering tropical, Northern, and Southern Hemisphere seabird species that are likely to be kleptoparasitized by skuas. A certain degree of individual variation exists within each population, which induces a spatial overlap in the wintering grounds of distant breeding populations. These results have potential important consequences in terms of fitness, genetic divergence, and susceptibility to climate change and marine pollution. KEYWORDS: Catharacta maccormicki · Geolocators · Migration · Population-specific strategies · Stable isotopes.
Keywords: Dronning Maud Land; geolokalisering; klimaendringer; marin forurensning; ornitologi; polarområdene; trekkfugler; zoologi

An Antarctic Research Station as a Source of Brominated and Perfluorinated Persistent Organic Pollutants to the Local Environment - Wild, Seanan; McLagan, David; Schlabach, Martin; Bossi, Rossana; Hawker, Darryl; Cropp, Roger; King, Catherine K; Stark, Jonathan S; Mondon, Julie; Nash, Susan Bengtson (Environmental Science & Technology, 2015)
This study investigated the role of a permanently manned Australian Antarctic research station (Casey Station) as a source of contemporary persistent organic pollutants (POPs) to the local environment. Polybrominated diphenyl ethers (PBDEs) and poly- and perfluoroalkylated substances (PFASs) were found in indoor dust and treated wastewater effluent of the station. PBDE (e.g., BDE-209 26–820 ng g–1 dry weight (dw)) and PFAS levels (e.g., PFOS 3.8–2400 ng g–1 (dw)) in dust were consistent with those previously reported in homes and offices from Australia, reflecting consumer products and materials of the host nation. The levels of PBDEs and PFASs in wastewater (e.g., BDE-209 71–400 ng L–1) were in the upper range of concentrations reported for secondary treatment plants in other parts of the world. The chemical profiles of some PFAS samples were, however, different from domestic profiles. Dispersal of chemicals into the immediate marine and terrestrial environments was investigated by analysis of abiotic and biotic matrices. Analytes showed decreasing concentrations with increasing distance from the station. This study provides the first evidence of PFAS input to Polar regions via local research stations and demonstrates the introduction of POPs recently listed under the Stockholm Convention into the Antarctic environment through local human activities.
Publisher: American Chemical Society
Keywords: Antarktis; forskningsstasjoner; forurensning; menneskelig påvirkning; miljøgifter

Protists in the polar regions: comparing occurrence in the Arctic and Southern oceans using pyrosequencing - Wolf, Christian; Kilias, Estelle; Metfies, Katja (Polar Research, 2015)
In the ongoing discussion of the distribution of protists, whether they are globally distributed or endemic to one or both of the polar regions is the subject of heated debate. In this study, we compared next-generation sequencing data from the Arctic and the Southern oceans to reveal the extent of similarities and dissimilarities between the protist communities in the polar regions. We found a total overlap of operational taxonomic units (OTUs) between the two regions of 11.2%. On closer inspection of different taxonomic groups, the overlap ranged between 5.5% (haptophytes) and 14.5% (alveolates). Within the different groups, the proportion of OTUs occurring in both regions greatly differed between the polar regions. On the one hand, the overlap between these two regions is remarkable, given the geographical distance between them. On the other hand, one could expect a greater overlap of OTUs between these regions on account of the similar environmental conditions. The overlap suggests a connection between the polar regions for at least certain species or that the evolutionary divergence has been slow, relative to the timescales of isolation. The different proportions of common OTUs among the groups or regions may be a result of different life cycle strategies or environmental adaptations. Keywords: 18S rDNA; bipolar; next-generation sequencing; phytoplankton; polar regions; protist distribution.
Keywords: Sørishavet; fytoplankton; marin biologi; polarområdene; protoktister; pyrosekvensering; økosystemer

Reconstruction of changes in the Weddell Sea sector of the Antarctic Ice Sheet since the Last Glacial Maximum - Hillenbrand, Claus-Dieter; Bentley, Michael J.; Stolldorf, Travis D.; Hein, Andrew S.; Kuhn, Gerhard; Graham, Alastair G.C.; Fogwill, Christopher J.; Kristoffersen, Yngve; Smith, James. A.; Anderson, John B.; Larter, Robert D.; Melles, Martin; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
The Weddell Sea sector is one of the main formation sites for Antarctic Bottom Water and an outlet for about one fifth of Antarctica's continental ice volume. Over the last few decades, studies on glacial–geological records in this sector have provided conflicting reconstructions of changes in ice-sheet extent and ice-sheet thickness since the Last Glacial Maximum (LGM at ca 23–19 calibrated kiloyears before present, cal ka BP). Terrestrial geomorphological records and exposure ages obtained from rocks in the hinterland of the Weddell Sea, ice-sheet thickness constraints from ice cores and some radiocarbon dates on offshore sediments were interpreted to indicate no significant ice thickening and locally restricted grounding-line advance at the LGM. Other marine geological and geophysical studies concluded that subglacial bedforms mapped on the Weddell Sea continental shelf, subglacial deposits and sediments over-compacted by overriding ice recovered in cores, and the few available radiocarbon ages from marine sediments are consistent with major ice-sheet advance at the LGM. Reflecting the geological interpretations, different ice-sheet models have reconstructed conflicting LGM ice-sheet configurations for the Weddell Sea sector. Consequently, the estimated contributions of ice-sheet build-up in the Weddell Sea sector to the LGM sea-level low-stand of ∼130 m vary considerably. In this paper, we summarise and review the geological records of past ice-sheet margins and past ice-sheet elevations in the Weddell Sea sector. We compile marine and terrestrial chronological data constraining former ice-sheet size, thereby highlighting different levels of certainty, and present two alternative scenarios of the LGM ice-sheet configuration, including time-slice reconstructions for post-LGM grounding-line retreat. Moreover, we discuss consistencies and possible reasons for inconsistencies between the various reconstructions and propose objectives for future research. The aim of our study is to provide two alternative interpretations of glacial–geological datasets on Antarctic Ice-Sheet History for the Weddell Sea sector, which can be utilised to test and improve numerical ice-sheet models.
Keywords: Antarctica; Cosmogenic nuclide surface exposure age dating; Deglaciation; Geomorphology; Glacial history; Ice Shelf; Ice sheet; Last Glacial Maximum; Radiocarbon dating; Sea level; Sørishavet; Weddellhavet; geologi; geomorfologi; glasiologi

HFC-43-10mee atmospheric abundances and global emission estimates - Arnold, Tim; Ivy, Diane J; Harth, Christina M; Vollmer, Martin K; Mühle, Jens; Salameh, Peter K; Paul Steele, L; Krummel, Paul B; Wang, Ray H J; Young, Dickon; Lunder, Chris R; Hermansen, Ove; et al. (Geophysical Research Letters, 2014)
We report in situ atmospheric measurements of hydrofluorocarbon HFC-43-10mee (C5H2F10; 1,1,1,2,2,3,4,5,5,5-decafluoropentane) from seven observatories at various latitudes, together with measurements of archived air samples and recent Antarctic flask air samples. The global mean tropospheric abundance was 0.21 ± 0.05 ppt (parts per trillion, dry air mole fraction) in 2012, rising from 0.04 ± 0.03 ppt in 2000. We combine the measurements with a model and an inverse method to estimate rising global emissions—from 0.43 ± 0.34 Gg yr−1 in 2000 to 1.13 ± 0.31 Gg yr−1 in 2012 (~1.9 Tg CO2-eq yr−1 based on a 100 year global warming potential of 1660). HFC-43-10mee—a cleaning solvent used in the electronics industry—is currently a minor contributor to global radiative forcing relative to total HFCs; however, our calculated emissions highlight a significant difference from the available reported figures and projected estimates.
Keywords: Antarktis; atmosfæren; forurensning; massespektrometri; meteorologi; målinger; utslipp

Late Holocene climate change recorded in proxy records from a Bransfield Basin sediment core, Antarctic Peninsula - Barnard, Alex; Wellner, Julia S; Anderson, John B (Polar Research, 2014)
The glacimarine environment of the Antarctic Peninsula region is one of the fastest warming places on Earth today, but details of changes in the recent past remain unknown. Large distances and widespread variability separate late Holocene palaeoclimate reconstructions in this region. This study focuses on a marine sediment core collected from ca. 2000 m below sea level in the Central Bransfield Strait that serves as a key for understanding changes in this region. The core yielded a high sedimentation rate and therefore provides an exceptional high-resolution sedimentary record composed of hemipelagic sediment, with some turbidites. An age model has been created using radiocarbon dates that span the Late Holocene: 3560 cal yr BP to present. This chronostratigraphic framework was used to establish five units, which are grouped into two super-units: a lower super-unit (3560–1600 cal yr BP) and an upper super-unit (1600 cal yr BP–present), based on facies descriptions, laser particle size analysis, x-ray analysis, multi-sensor core logger data, weight percentages and isotopic values of total organic carbon and nitrogen. We interpret the signal contained within the upper super-unit as an increase in surface water irradiance and/or shortening of the sea-ice season and the five units are broadly synchronous with climatic intervals across the Antarctic Peninsula region. While the general trends of regional climatic periods are represented in the Bransfield Basin core we have examined, each additional record that is obtained adds variability to the known history of the Antarctic Peninsula, rather than clarifying specific trends. Keywords: Antarctic Peninsula; palaeoclimate; Holocene; marine; isotopes.
Keywords: Antarktis; geofysikk; geokjemi; paleoklimatologi; sedimentologi

Thorbryn - en hvalbåts videverdige karriere - Basberg, Bjørn L (Norsk maritimt museum. Årbok, 2014)
Publisher: Norsk maritimt museum
Keywords: Sørishavet; historie; hvalbåter; hvalfangst; pelagisk; sjøfart; skipsfart

Inspeksjonsordningen under Antarktistraktaten - Bech, Jon (Polarboken, 2014)
Keywords: Antarktis; jus; politikk

A Nutritional-Toxicological Assessment of Antarctic Krill Oil versus Fish Oil Dietary Supplements - Bengtson Nash, Susan M; Schlabach, Martin; Nichols, Peter D (Nutrients, 2014)
Fish oil dietary supplements and complementary medicines are pitched to play a role of increasing strategic importance in meeting daily requirements of essential nutrients, such as long-chain (≥C20, LC) omega-3 polyunsaturated fatty acids and vitamin D. Recently a new product category, derived from Antarctic krill, has been launched on the omega-3 nutriceutical market. Antarctic krill oil is marketed as demonstrating a greater ease of absorption due to higher phospholipid content, as being sourced through sustainable fisheries and being free of toxins and pollutants; however, limited data is available on the latter component. Persistent Organic Pollutants (POP) encompass a range of toxic, man-made contaminants that accumulate preferentially in marine ecosystems and in the lipid reserves of organisms. Extraction and concentration of fish oils therefore represents an inherent nutritional-toxicological conflict. This study aimed to provide the first quantitative comparison of the nutritional (EPA and DHA) versus the toxicological profiles of Antarctic krill oil products, relative to various fish oil categories available on the Australian market. Krill oil products were found to adhere closely to EPA and DHA manufacturer specifications and overall were ranked as containing intermediate levels of POP contaminants when compared to the other products analysed. Monitoring of the pollutant content of fish and krill oil products will become increasingly important with expanding regulatory specifications for chemical thresholds.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; miljøgifter; plankton; toksikologi

A community-based geological reconstruction of Antarctic Ice Sheet deglaciation since the Last Glacial Maximum - Bentley, Michael J.; Ó Cofaigh, Colm; Anderson, John B.; Conway, Howard; Davies, Bethan; Graham, Alastair G.C.; Hillenbrand, Claus-Dieter; Hodgson, Dominic A.; Jamieson, Stewart S.R.; Larter, Robert D.; Mackintosh, Andrew; Smith, James A.; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
A robust understanding of Antarctic Ice Sheet deglacial history since the Last Glacial Maximum is important in order to constrain ice sheet and glacial-isostatic adjustment models, and to explore the forcing mechanisms responsible for ice sheet retreat. Such understanding can be derived from a broad range of geological and glaciological datasets and recent decades have seen an upsurge in such data gathering around the continent and Sub-Antarctic islands. Here, we report a new synthesis of those datasets, based on an accompanying series of reviews of the geological data, organised by sector. We present a series of timeslice maps for 20 ka, 15 ka, 10 ka and 5 ka, including grounding line position and ice sheet thickness changes, along with a clear assessment of levels of confidence. The reconstruction shows that the Antarctic Ice sheet did not everywhere reach the continental shelf edge at its maximum, that initial retreat was asynchronous, and that the spatial pattern of deglaciation was highly variable, particularly on the inner shelf. The deglacial reconstruction is consistent with a moderate overall excess ice volume and with a relatively small Antarctic contribution to meltwater pulse 1a. We discuss key areas of uncertainty both around the continent and by time interval, and we highlight potential priorities for future work. The synthesis is intended to be a resource for the modelling and glacial geological community.
Keywords: Antarktis; Modelling; deglasiasjon; geologi; glasiologi; innlandsis

Instrumentation and handling effects on Antarctic fur seals (Arctocephalus gazella) - Blanchet, Marie-Anne; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg; Krafft, Bjørn A.; Kovacs, Kit M. (Polar Research, 2014)
The use of biologging instruments has greatly improved our understanding of the behaviour, physiology and ecology of free-ranging marine mammals. However, handling wild animals and attaching instruments to streamlined bodies can cause stress and potentially influence behaviour and swimming/diving energetics. The goals of this study, undertaken on Bouvetøya, were (1) to determine if the first trip to sea after instrumentation is representative of subsequent trips in lactating Antarctic fur seals, to explore potential handling effects and assess possible biases in having multiple short-duration deployments (inflating N, using a limited number of tags) and (2) to evaluate potential effects of two different instrument combinations (SMRU satellite data relay loggers and very high frequency radio transmitters versus Wildlife Computers time–depth recorders and very high frequency radio transmitters) on trip durations, dive parameters, female body condition and pup growth. Handling did not appear to have any effects on the parameters studied; data from the first and second trips did not differ significantly. This implies that multiple short-term deployments are unlikely to result in biased data in this species. Instrument type did have measurable effects; time-at-sea was greater and pup growth was lower for pairs in which mothers carried bulkier instruments. This suggests that instrument streamlining is important to avoid negative impacts and that bulkier equipment should be deployed on lactating females with caution and only for short periods. The study highlights that instrument effects should be taken into account when comparing data from experiments collected using different equipment packages. Keywords: Bioenergetics; biologging; instrument effects; SRDLs; TDRs; VHFs.
Keywords: Bouvetøya; NARE ekspedisjoner; analyser; bioenergetikk; biologging; marin zoologi; pelsseler

Transition of flow regime along a marine-terminating outlet glacier in East Antarctica - Callens, Denis; Matsuoka, Kenichi; Steinhage, Daniel; Smith, Benjamin; Witrant, E; Pattyn, Frank (The Cryosphere, 2014)
We present results of a multi-methodological approach to characterize the flow regime of West Ragnhild Glacier, the widest glacier in Dronning Maud Land, Antarctica. A new airborne radar survey points to substantially thicker ice (>2000 m) than previously thought. With a discharge estimate of 13–14 Gt yr−1, West Ragnhild Glacier thus becomes of the three major outlet glaciers in Dronning Maud Land. Its bed topography is distinct between the upstream and downstream section: in the downstream section (<65 km upstream of the grounding line), the glacier overlies a wide and flat basin well below the sea level, while the upstream region is more mountainous. Spectral analysis of the bed topography also reveals this clear contrast and suggests that the downstream area is sediment covered. Furthermore, bed-returned power varies by 30 dB within 20 km near the bed flatness transition, suggesting that the water content at bed/ice interface increases over a short distance downstream, hence pointing to water-rich sediment. Ice flow speed observed in the downstream part of the glacier (~250 m yr−1) can only be explained through very low basal friction, leading to a substantial amount of basal sliding in the downstream 65 km of the glacier. All the above lines of evidence (sediment bed, wetness and basal motion) and the relatively flat grounding zone give the potential for West Ragnhild Glacier to be more sensitive to external forcing compared to other major outlet glaciers in this region, which are more stable due to their bed geometry (e.g. Shirase Glacier).
Keywords: Dronning Maud Land; glasiologi

Polynya dynamics drive primary production in the Larsen A and B embayments following ice shelf collapse - Cape, Mattias R.; Vernet, Maria; Kahru, Mati; Spreen, Gunnar (Journal of Geophysical Research: Oceans, 2014)
The climate-driven collapses of the Larsen A and B ice shelves have opened up new regions of the coastal Antarctic to the influence of sea ice resulting in increases in seasonal primary production. In this study, passive microwave remote sensing of sea ice concentration and satellite imagery of ocean color are employed to quantify the magnitude of and variability in open water area and net primary productivity (NPP) in the Larsen embayments between 1997 and 2011. Numerical model output provides context to analyze atmospheric forcing on the coastal ocean. Following ice shelf disintegration the embayments function as coastal, sensible heat polynyas. The Larsen A and B are as productive as other Antarctic shelf regions, with seasonally averaged daily NPP rates reaching 1232 and 1127 mg C m−2 d−1 and annual rates reaching 200 and 184 g C m−2 yr−1, respectively. A persistent cross-shelf gradient in NPP is present with higher productivity rates offshore, contrasting with patterns observed along the West Antarctic Peninsula. Embayment productivity is intimately tied to sea ice dynamics, with large interannual variability in NPP rates driven by open water area and the timing of embayment opening. Opening of the embayment is linked to periods of positive Southern Annular Mode and stronger westerlies, which lead to the vertical deflection of warm, maritime air over the peninsula and down the leeward side causing increases in surface air temperature and wind velocity. High productivity in these new polynyas is likely to have ramifications for organic matter export and marine ecosystem evolution.
Keywords: Sørishavet; brehylle; fjernmåling; fytoplankton; havis; isbrem; isshelf; klimaendringer; oseanografi; polynja; satellite bilder; sjøis

Svartelisting i isødet - Christensen, Stig H (LO-Aktuelt, 2014)
Hvalfangst-eventyret i Antarktis fra 1905 kostet menneskeliv og blodslit. Hvalfangernes forsøk på å organisere seg ble møtt med svartelisting, utestengelse og arrestasjoner.
Keywords: Antarktis; Sørishavet; arbeidsforhold; fagforbund; hvalfangere; hvalfangst; pelagisk; sjøfolk

Commonness and rarity in the marine biosphere - Connolly, Sean R; MacNeil, M Aaron; Caley, M Julian; Knowlton, Nancy; Cripps, Ed; Hisano, Mizue; Thibaut, Loïc M; Bhattacharya, Bhaskar D; Benedetti-Cecchi, Lisandro; Brainard, Russell E; Brandt, Angelika; Bulleri, Fabio; et al. (Proceedings of the National Academy of Sciences, 2014)
Tests of biodiversity theory have been controversial partly because alternative formulations of the same theory seemingly yield different conclusions. This has been a particular challenge for neutral theory, which has dominated tests of biodiversity theory over the last decade. Neutral theory attributes differences in species abundances to chance variation in individuals’ fates, rather than differences in species traits. By identifying common features of different neutral models, we conduct a uniquely robust test of neutral theory across a global dataset of marine assemblages. Consistently, abundances vary more among species than neutral theory predicts, challenging the hypothesis that community dynamics are approximately neutral, and implicating species differences as a key driver of community structure in nature.Explaining patterns of commonness and rarity is fundamental for understanding and managing biodiversity. Consequently, a key test of biodiversity theory has been how well ecological models reproduce empirical distributions of species abundances. However, ecological models with very different assumptions can predict similar species abundance distributions, whereas models with similar assumptions may generate very different predictions. This complicates inferring processes driving community structure from model fits to data. Here, we use an approximation that captures common features of “neutral” biodiversity models—which assume ecological equivalence of species—to test whether neutrality is consistent with patterns of commonness and rarity in the marine biosphere. We do this by analyzing 1,185 species abundance distributions from 14 marine ecosystems ranging from intertidal habitats to abyssal depths, and from the tropics to polar regions. Neutrality performs substantially worse than a classical nonneutral alternative: empirical data consistently show greater heterogeneity of species abundances than expected under neutrality. Poor performance of neutral theory is driven by its consistent inability to capture the dominance of the communities’ most-abundant species. Previous tests showing poor performance of a neutral model for a particular system often have been followed by controversy about whether an alternative formulation of neutral theory could explain the data after all. However, our approach focuses on common features of neutral models, revealing discrepancies with a broad range of empirical abundance distributions. These findings highlight the need for biodiversity theory in which ecological differences among species, such as niche differences and demographic trade-offs, play a central role.
Keywords: Sørishavet; biodiversitet; biologi; marin økologi; marine økosystemer; polarområdene; zoologi

Three artotrogids (Crustacea: Copepoda: Siphonostomatoida) from the Ross Sea, Antarctica - Conradi, Mercedes (Polar Research, 2014)
The Artotrogidae, one of the most primitive of siphonostomatoid families, consists currently of 117 species in 21 genera. Most of these species (65%) are poorly or incompletely described since they have been rarely recorded in recent decades and, when encountered, have been found in very low numbers. During the 19th Italian Antarctic Expedition, with the RV Italica, to the Ross Sea in austral summer 2004, some artotrogid copepods were collected. This paper redescribes two species of artotrogid copepods, which are known only from the Southern Ocean, Neobradypontius neglectus and Cryptopontiuslatus, and describes for the first time a male of the genus Neobradypontius. Furthermore, a new species is described and added to Sestropontius, increasing the number of known species of this genus to three. The main discrepancies between the original descriptions and the specimens of the two species collected from the Ross Sea redescribed here were on the armature of the antennary exopod and leg 5. The new species, Sestropontius italicae, shares with its most similar congener, S. mckinnoni, the armature of the third endopodal segment of leg 1 and leg 2 and that of the third exopodal segment of leg 4. However, the segmentation of the antennae and the armature on the antennary exopod are different. Keywords: Antarctica; Artotrogidae; redescription; Neobradypontius; Sestropontius; Cryptopontius.
Keywords: Rosshavet; Sørishavet; copepoder; ekspedisjoner; hoppekreps; marin biologi; zoologi

Antarktis: inlandsis, shelf-is och stigande havsnivå - Darelius, Elin (Naturen, 2014)
I klimatsammanhang har strålkastarljuset länge varit riktade mot de känsliga polarområdena och smältande is. Bilder på isbjörnar som klamrar sig fast vid ett ensamt isflak figurerar varje höst i media när årets – ofta rekordlåga – minimum i utbredning av Arktisk havsis offentliggörs. Men nyligen har is-överskrifterna allt oftare kommit söderifrån, de har handlat om Antarktis, om shelf-is som smälter, om en stigande havsnivå och om möjligheten för att inlandsisen i Väst-Antarktis ska kollapsa.
Keywords: Sørishavet; brehylle; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Hydrography and circulation in the Filchner Depression, Weddell Sea, Antarctica - Darelius, Elin Maria K; Makinson, Keith; Daae, Kjersti Birkeland; Fer, Ilker; Holland, Paul R; Nicholls, Keith W (Journal of Geophysical Research: Oceans, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; hydrografi; isfront; isshelf

On the Seasonal Signal of the Filchner Overflow, Weddell Sea, Antarctica - Darelius, Elin Maria K; Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor; Årthun, Marius; Fer, Ilker (Journal of Physical Oceanography, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi; sjøvann

Contrasting strategies of resistance vs. tolerance to desiccation in two polar dipterans - Everatt, M J; Convey, P; Worland, M R; Bale, J S; Hayward, S A L (Polar Research, 2014)
Low water availability is one of the principal stressors for terrestrial invertebrates in the polar regions, determining the survival of individuals, the success of species and the composition of communities. The Arctic and Antarctic dipterans Heleomyza borealis and Eretmoptera murphyi spend the majority of their biennial life cycles as larvae, and so are exposed to the full range of environmental conditions, including low water availability, over the annual cycle. In the current study, the desiccation resistance and desiccation tolerance of larvae were investigated, as well as their capacity for cross-tolerance to temperature stress. Larvae of H. borealis showed high levels of desiccation resistance, only losing 6.9% of their body water after 12 days at 98.2% relative humidity (RH). In contrast, larvae of E. murphyi lost 46.7% of their body water after 12 days at the same RH. Survival of E. murphyi larvae remained high in spite of this loss (>80% survival). Following exposure to 98.2% RH, larvae of E. murphyi showed enhanced survival at −18°C for 2 h. The supercooling point of larvae of both species was also lowered following prior treatment at 98.2% RH. Cross-tolerance to high temperatures (37 or 38.5°C) was not noted following desiccation in E. murphyi, and survival even fell at 37°C following a 12-day pre-treatment. The current study demonstrates two different strategies of responding to low water availability in the polar regions and indicates the potential for cross-tolerance, a capacity which is likely to be beneficial in the ever-changing polar climate. Keywords: Acclimation; dipteran; supercooling point; temperature; cross-tolerance.
Keywords: Antarktis; diptera; polarområdene; temperatur; tovinger; uttørking; virvelløse dyr

Annual cycle of Antarctic baseline aerosol: controlled by photooxidation-limited aerosol formation - Fiebig, Markus; Hirdman, David; Lunder, Chris R; Ogren, John A; Solberg, Sverre; Stohl, Andreas; Thompson, Rona L (Atmospheric Chemistry and Physics (Print), 2014)
This article investigates the annual cycle observed in the Antarctic baseline aerosol scattering coefficient, total particle number concentration, and particle number size distribution (PNSD), as measured at Troll Atmospheric Observatory. Mie theory shows that the annual cycles in microphysical and optical aerosol properties have a common cause. By comparison with observations at other Antarctic stations, it is shown that the annual cycle is not a local phenomenon, but common to central Antarctic baseline air masses. Observations of ground-level ozone at Troll as well as backward plume calculations for the air masses arriving at Troll demonstrate that the baseline air masses originate from the free troposphere and lower stratosphere region, and descend over the central Antarctic continent. The Antarctic summer PNSD is dominated by particles with diameters <100 nm recently formed from the gas-phase despite the absence of external sources of condensible gases. The total particle volume in Antarctic baseline aerosol is linearly correlated with the integral insolation the aerosol received on its transport pathway, and the photooxidative production of particle volume is mostly limited by photooxidative capacity, not availability of aerosol precursor gases. The photooxidative particle volume formation rate in central Antarctic baseline air is quantified to 207 ±4 μm3/(MJ m). Further research is proposed to investigate the applicability of this number to other atmospheric reservoirs, and to use the observed annual cycle in Antarctic baseline aerosol properties as a benchmark for the representation of natural atmospheric aerosol processes in climate models.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; klimamodeller; miljøgifter

Counteracting the climate effects of volcanic eruptions using short-lived greenhouse gases - Fuglestvedt, Jan S.; Samset, Bjørn H.; Shine, Keith P. (Geophysical Research Letters, 2014)
A large volcanic eruption might constitute a climate emergency, significantly altering global temperature and precipitation for several years. Major future eruptions will occur, but their size or timing cannot be predicted. We show, for the first time, that it may be possible to counteract these climate effects through deliberate emissions of short-lived greenhouse gases, dampening the abrupt impact of an eruption. We estimate an emission pathway countering a hypothetical eruption 3 times the size of Mount Pinatubo in 1991. We use a global climate model to evaluate global and regional responses to the eruption, with and without counteremissions. We then raise practical, financial, and ethical questions related to such a strategy. Unlike the more commonly discussed geoengineering to mitigate warming from long-lived greenhouse gases, designed emissions to counter temporary cooling would not have the disadvantage of needing to be sustained over long periods. Nevertheless, implementation would still face significant challenges.
Keywords: Antarktis; drivhusgasser; global klimamodell; global oppvarming; klimatologi; nedbør; polarområdene; vulkaner

Commercial fishing vessel as research vessels in the Antarctic – Requirements and solutions exemplified with a new vessel - Godø, Olav; Reiss, Christian; Siegel, V; Watkins, Jonathan (CCAMLR science journal of the Scientific Committee and the Commission for the Conservation of Antarctic Marine Living Resources, 2014)
Keywords: Antarktis; fiskefartøy; forskning; forskningsfartøy; klimaendringer; oseanografi; økosystem

Alien invasions in Antarctica - is anyone liable? - Hughes, Kevin A; Convey, Peter (Polar Research, 2014)
The introduction of non-native species to Antarctica in association with human activities is a major threat to indigenous biodiversity and the region's unique ecosystems, as has been well-demonstrated in other ecosystems globally. Existing legislation contained in the Protocol on Environmental Protection to the Antarctic Treaty does not specifically make the eradication of non-native species mandatory, although it is implicit that human-assisted introductions should not take place. Furthermore, to date, eradications of non-native species in the Treaty area have been infrequent and slow to progress. In 2005 an additional Annex (VI) to the Protocol was agreed concerning “Liability arising from environmental emergencies.” This annex focusses on prevention of environmental emergencies, contingency planning and reclaiming costs incurred when responding to an environmental emergency caused by another operator within the Antarctic Treaty area. However, the types of environmental emergencies covered by the annex are not defined. In this paper we highlight potential difficulties with the application of Annex VI in the context of non-native species control and eradication, including, for example, whether a non-native species introduction would be classified as an “environmental emergency” and therefore be considered under the terms of the annex. Even if this were the case, we conclude that the slow pace of approval of the annex by Antarctic Treaty Parties may prevent it coming into force for many years and, once in force, in its current form it is unlikely to be useful for reclaiming costs associated with the eradication or management of a non-native species.
Keywords: Antarktis; biodiversitet; internasjonal; miljøvern; politikk; samarbeid; økosystemer

Estimating surface mass balance variability in Antarctica: examples from Fimbulisen - Isaksson, Elisabeth (Fram forum, 2014)
If all the ice in the Antarctic ice sheet were to melt, the world’s oceans would rise about 58 metres. Although nobody expects anything that dramatic to happen, current knowledge doesn’t tell us what we might actually expect. The Fimbulisen project should help eliminate some of the uncertainty.
Keywords: Dronning Maud Land; glasiologi; innlandsis; isbrem; isshelf; klimaendringer; smelting

At the root of the early penguin neck: a study of the only two cervicodorsal spines recovered from the Eocene of Antarctica - Jadwiszczak, Piotr (Polar Research, 2014)
The spinal column of early Antarctic penguins is poorly known, mainly due to the scarcity of articulated vertebrae in the fossil record. One of the most interesting segments of this part of the skeleton is the transitional series located at the root of the neck. Here, two such cervicodorsal series, comprising reinterpreted known material and a new specimen from the Eocene of Seymour Island (Antarctic Peninsula), were investigated and contrasted with those of modern penguins and some fossil bones. The new specimen is smaller than the counterpart elements in recent king penguins, whereas the second series belonged to a large-bodied penguin from the genus Palaeeudyptes. It had been assigned by earlier researchers to P. gunnari (a species of “giant” penguins) and a Bayesian analysis—a Bayes factor approach based on size of an associated tarsometatarsus—strongly supported such an assignment. Morphological and functional studies revealed that mobility within the aforementioned segment probably did not differ substantially between extant and studied fossil penguins. There were, however, intriguing morphological differences between the smaller fossil specimen and the comparative material related to the condition of the lateral excavation in the first cervicodorsal vertebra and the extremely small size of the intervertebral foramen located just prior to the first “true” thoracic vertebra. The former feature could have resulted from discrepancy in severity of external pneumatization. Both fossils provided valuable insights into the morphology and functioning of the axial skeleton in early penguins. Keywords: Antarctic Peninsula; La Meseta Formation; Palaeogene; early Sphenisciformes; cervicodorsal vertebrae.
Keywords: Antarktis; biologi; fossiler; morfologi; paleogen; pingviner

Comparative study on PCDD/F pollution in soil from the Antarctic, Arctic and Tibetan Plateau - Jia, Shenglan; Wang, Qiang; Li, Li; Fang, Xuekun; Shi, Yehong; Xu, Weiguang; Hu, Jianxin (Science of the Total Environment, 2014)
The concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) in 35 soil samples collected from Fildes Peninsula in the Antarctic, Ny-Ålesund in the Arctic, and Zhangmu-Nyalam in the Tibetan Plateau were reported in this study. A comparison of the total concentration and TEQ of PCDD/Fs at the Three Poles was conducted. Both the total concentration and TEQ of PCDD/Fs demonstrates a decreasing trend in the order of Zhangmu-Nyalam (mean: 26.22 pg/g, 0.37 pg I-TEQ/g)>Ny-Ålesund (mean: 9.97 pg/g, 0.33 pg I-TEQ/g)>Fildes Peninsula (mean: 2.18 pg/g, 0.015 pg I-TEQ/g) (p<0.05). In all samples, the congener and homologue profiles dominated with higher (seven and eight) chlorinated PCDD/Fs (more than 85% of the total mass percentage of PCDD/Fs) at the Three Poles. Finally, a FLEXPART backward simulation was used to preliminarily identify the potential local and regional anthropogenic sources of PCDD/Fs. The results imply that the air masses passing over surrounding regions with significant PCDD/F emissions might contribute to the occurrence of PCDD/Fs in both the Arctic and Tibetan Plateau.
Keywords: Antarktis; menneskelig påvirkning; miljøgifter; miljøovervåking; polarområdene

Fjerning av reinsdyr på Sør-Georgia: nok et avsluttet kapittel i norsk hvalfangsthistorie - Kilander, Carl Erik (Polarboken, 2014)
Keywords: Sørishavet; zoologi; økologi

Decrease in stomach contents in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean - Konishi, Kenji; Hakamada, Takashi; Kiwada, Hiroshi; Kitakado, Toshihide; Walløe, Lars (Polar Biology, 2014)
Keywords: Sørishavet; hvaler; krill; marin biologi; observasjoner

Et besøk på Bettyfjellet - Kristensen, Monica; McIntyre, Neil (Polarboken, 2014)
Keywords: Antarktis; ekspedisjoner; historie

Reassembling Gondwana: A new high quality constraint from vibroseis exploration of the sub-ice shelf geology of the East Antarctic continental margin - Kristoffersen, Yngve; Hofstede, Coen; Diez, Anja; Blenkner, Richard; Lambrecht, Astrid; Mayer, Christoph; Eisen, Olaf (Journal of Geophysical Research: Solid Earth, 2014)
The breakup of Gondwana is manifested by coeval early Jurassic Karoo magmatism in South Africa and East Antarctica. In South Africa, the large volumes of volcanic rocks of the adjoining Lebombo and Mwenetzi-Save monoclines represent a volcanic rift margin, and in East Antarctica, a corresponding feature, the Explora Wedge is buried below sediments and floating ice shelves on the continental margin of Dronning Maud Land. We use the seismic vibrator source to explore the sub-ice geology in Antarctica, and the new seismic reflection and available regional aeromagnetic data enable us to outline a dogleg landward extent of the Explora Wedge in Dronning Maud Land. The congruent inboard wedge geometries on the two continents define a high quality constraint, which facilitate for the first time, a geologically consistent and tight reconstruction of Africa relative to East Antarctica within Gondwana. The uncertainties in correlations of major geological features (mobile belts) from one continent to the other may now be of the order of ten's of kilometers rather than hundreds of kilometers.
Keywords: Antarktis; geofysikk; geologi; kontinentalmargin; seismologi; stratigrafi

Low melt rates with seasonal variability at the base of Fimbul Ice Shelf, East Antarctica, revealed by in situ interferometric radar measurements - Langley, Kirsty; Kohler, Jack; Sinisalo, Anna; Øyan, Mats Jørgen; Hamran, Svein Erik; Hattermann, Tore; Matsuoka, Kenichi; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Basal melt is a major cause of ice shelf thinning affecting the stability of the ice shelf and reducing its buttressing effect on the inland ice. The Fimbul ice shelf (FIS) in Dronning Maud Land (DML), East Antarctica, is fed by the fast-flowing Jutulstraumen glacier, responsible for 10% of ice discharge from the DML sector of the ice sheet. Current estimates of the basal melt rates of the FIS come from regional ocean models, autosub measurements, and satellite observations, which vary considerably. This discrepancy hampers evaluation of the stability of the Jutulstraumen catchment. Here, we present estimates of basal melt rates of the FIS using ground-based interferometric radar. We find a low average basal melt rate on the order of 1 m/yr, with the highest rates located at the ice shelf front, which extends beyond the continental shelf break. Furthermore, our results provide evidence for a significant seasonal variability.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbre; isshelf; kontinentalsokkel; smelting

Complex network of channels beneath an Antarctic ice shelf - Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Sinisalo, Anna; Matsuoka, Kenichi; Hattermann, Tore; Humbert, Angelika; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Ice shelves play an important role in stabilizing the interior grounded ice of the large ice sheets. The thinning of major ice shelves observed in recent years, possibly in connection to warmer ocean waters coming into contact with the ice-shelf base, has focused attention on the ice-ocean interface. Here we reveal a complex network of sub ice-shelf channels under the Fimbul Ice Shelf, Antarctica, mapped using ground-penetrating radar over a 100 km2 grid. The channels are 300–500 m wide and 50 m high, among the narrowest of any reported. Observing narrow channels beneath an ice shelf that is mainly surrounded by cold ocean waters, with temperatures close to the surface freezing point, shows that channelized basal melting is not restricted to rapidly melting ice shelves, indicating that spatial melt patterns around Antarctica are likely to vary on scales that are not yet incorporated in ice-ocean models.
Keywords: Antarktis; glasiologi; innlandsis; isshelf; satellite bilder; satellite mikrobølgesensorer

High variability of climate and surface mass balance induced by Antarctic ice rises - Lenaerts, Jan T M; Joel, Brown.; Van Den Broeke, Michiel R; Matsuoka, Kenichi; Drews, Reinhard; Callens, Denis; Philippe, Morgane; Gorodetskaya, Irina V; Van Meijgaard, Erik; Reijmer, Carleen H; Pattyn, Frank; Van Lipzig, Nicole P M (Journal of Glaciology, 2014)
Ice rises play key roles in buttressing the neighbouring ice shelves and potentially provide palaeoclimate proxies from ice cores drilled near their divides. Little is known, however, about their influence on local climate and surface mass balance (SMB). Here we combine 12 years (2001–12) of regional atmospheric climate model (RACMO2) output at high horizontal resolution (5.5 km) with recent observations from weather stations, ground-penetrating radar and firn cores in coastal Dronning Maud Land, East Antarctica, to describe climate and SMB variations around ice rises. We demonstrate strong spatial variability of climate and SMB in the vicinity of ice rises, in contrast to flat ice shelves, where they are relatively homogeneous. Despite their higher elevation, ice rises are characterized by higher winter temperatures compared with the flat ice shelf. Ice rises strongly influence SMB patterns, mainly through orographic uplift of moist air on the upwind slopes. Besides precipitation, drifting snow contributes significantly to the ice-rise SMB. The findings reported here may aid in selecting a representative location for ice coring on ice rises, and allow better constraint of local ice-rise as well as regional ice-shelf mass balance.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Post-breeding at-sea movements of three central-place foragers in relation to submesoscale fronts in the Southern Ocean around Bouvetøya - Lowther, Andrew D; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg J G; Kovacs, Kit M (Antarctic Science, 2014)
Publisher: Cambridge University Press
Keywords: Bouvetøya; oseanografi; pelsseler; pingviner; satellitt; telemetri

Environmental influences on the at-sea behaviour of a major consumer, Mirounga leonina, in a rapidly changing environment - McIntyre, Trevor; Bornemann, Horst; de Bruyn, P J Nico; Reisinger, Ryan R; Steinhage, Daniel; Márquez, Maria E I; Bester, Marthán N; Plötz, Joachim (Polar Research, 2014)
Understanding the distribution and foraging ecology of major consumers within pelagic systems, specifically in relation to physical parameters, can be important for the management of bentho-pelagic systems undergoing rapid change associated with global climate change and other anthropogenic disturbances such as fishing (i.e., the Antarctic Peninsula and Scotia Sea). We tracked 11 adult male southern elephant seals (Mirounga leonina), during their five-month post-moult foraging migrations from King George Island (Isla 25 de Mayo), northern Antarctic Peninsula, using tags capable of recording and transmitting behavioural data and in situ temperature and salinity data. Seals foraged mostly within the Weddell–Scotia Confluence, while a few foraged along the western Antarctic Peninsula shelf of the Bellingshausen Sea. Mixed model outputs suggest that the at-sea behaviour of seals was associated with a number of environmental parameters, especially seafloor depth, sea-ice concentrations and the temperature structure of the water column. Seals increased dive bottom times and travelled at slower speeds in shallower areas and areas with increased sea-ice concentrations. Changes in dive depth and durations, as well as relative amount of time spent during the bottom phases of dives, were observed in relation to differences in overall temperature gradient, likely as a response to vertical changes in prey distribution associated with temperature stratification in the water column. Our results illustrate the likely complex influences of bathymetry, hydrography and sea ice on the behaviour of male southern elephant seals in a changing environment and highlight the need for region-specific approaches to studying environmental influences on behaviour. Keywords: Southern elephant seals; foraging ecology; satellite-relay data loggers; King George Island; Isla 25 de Mayo; at-sea behaviour.
Keywords: Sørishavet; batymetri; havis; klimaendringer; miljø; næring; seler; sjøis

Verification of a new NOAA/NSIDC passive microwave sea-ice concentration climate record - Meier, Walter N; Peng, Ge; Scott, Donna J; Savoie, Matt H (Polar Research, 2014)
A new satellite-based passive microwave sea-ice concentration product developed for the National Oceanic and Atmospheric Administration (NOAA) Climate Data Record (CDR) programme is evaluated via comparison with other passive microwave-derived estimates. The new product leverages two well-established concentration algorithms, known as the NASA Team and Bootstrap, both developed at and produced by the National Aeronautics and Space Administration (NASA) Goddard Space Flight Center (GSFC). The sea-ice estimates compare well with similar GSFC products while also fulfilling all NOAA CDR initial operation capability (IOC) requirements, including (1) self-describing file format, (2) ISO 19115-2 compliant collection-level metadata, (3) Climate and Forecast (CF) compliant file-level metadata, (4) grid-cell level metadata (data quality fields), (5) fully automated and reproducible processing and (6) open online access to full documentation with version control, including source code and an algorithm theoretical basic document. The primary limitations of the GSFC products are lack of metadata and use of untracked manual corrections to the output fields. Smaller differences occur from minor variations in processing methods by the National Snow and Ice Data Center (for the CDR fields) and NASA (for the GSFC fields). The CDR concentrations do have some differences from the constituent GSFC concentrations, but trends and variability are not substantially different. Keywords: Sea ice; Arctic and Antarctic oceans; climate data record; evaluation; passive microwave remote sensing.
Keywords: Sørishavet; evaluering; havis; klimaendringer; polarområdene; sjøis

Basal mass budget of Ross and Filchner-Ronne ice shelves, Antarctica, derived from Lagrangian analysis of ICESat altimetry - Moholdt, Geir; Padman, Laurie; Fricker, Helen Amanda (Journal of Geophysical Research: Earth Surface, 2014)
Traditional methods of deriving temporal variability of Antarctic ice-shelf elevation from satellite altimetry use a fixed (“Eulerian”) reference frame, where the measured changes include advection of ice thickness gradients between measurement epochs. We present a new method which removes advection effects by using an independent velocity field to compare elevations in a moving (“Lagrangian”) reference frame. Applying the technique to ICESat laser altimetry for the period 2003–2009 over the two largest Antarctic ice shelves, Ross and Filchner-Ronne, we show that the Lagrangian approach reduces the variability of derived elevation changes by about 50% compared to the Eulerian approach and reveals clearer spatial patterns of elevation change. The method simplifies the process of estimating basal mass budget from the residual of all other processes that contribute to ice-shelf elevation changes. We use field data and ICESat measurements over ice rises and the grounded ice sheet to account for surface accumulation and changes in firn air content, and remove the effect of ice-flow divergence using surface velocity and ice thickness data. The results show highest basal melt rates (>5 m a−1) near the deep grounding lines of major ice streams, but smaller melt rates (<5 m a−1) near the ice-shelf fronts are equally important to total meltwater production since they occur over larger areas. Integrating over the entire ice-shelf areas, we obtain basal mass budgets of −50 ± 64 Gt a−1 for Ross and −124 ± 66 Gt a−1 for Filchner-Ronne, with changes in firn air content as the largest error source.
Keywords: Sørishavet; batymetri; brehylle; geofysikk; innlandsis; isbrem; isshelf; oseanografi; satellite altimetri

Assessing the importance of human activities for the establishment of the invasive Poa annua in Antarctica - Molina-Montenegro, Marco A; Carrasco-Urra, Fernando; Acuña-Rodriguez, Ian; Oses, Rómulo; Torres-Diaz, Cristian; Chwedorzewska, Katarzyna J (Polar Research, 2014)
Because of its harsh environmental conditions and remoteness, Antarctica is often considered to be at low risk of plant invasion. However, an increasing number of reports have shown the presence and spread of non-native plants in Antarctica; it is therefore important to study which factors control the invasion process in this ecosystem. Here, we assessed the role of different human activities on the presence and abundance of the invasive Poa annua. In addition, we performed a reciprocal transplant experiment in the field, and a manipulative experiment of germination with P. annua and the natives Colobanthus quitensis and Deschampsia antarctica, in order to unravel the effects of physical soil disturbance on the establishment and survival of P. annua. We found a positive correlation between abundance of P. annua and level of soil disturbance, and that survival of P. annua was 33% higher in sites with disturbed soil than non-disturbed. Finally, we found that disturbance conditions increased germination for P. annua, whereas for native species germination in experimentally disturbed soil was either unchanged or reduced compared to undisturbed soil. Our results indicate that human activities that modify abiotic soil characteristics could play an important role in the abundance of this invasive species. If the current patterns of human activities are maintained in Antarctica, the establishment success and spread of P. annua could increase, negatively affecting native flora. Keywords: Alien species; Colobanthus quitensis; Deschampsia antarctica; human disturbance; Poa annua; tourists.
Keywords: Antarktis; biodiversitet; flora; menneskelig påvirkning; planter; turisme; økosystemer

Selected elements in surface waters of Antarctica and their relations with the natural environment - Nędzarek, Arkadiusz; Tórz, Agnieszka; Drost, Arkadiusz (Polar Research, 2014)
The aim of the study was to specify the concentration of selected chemical elements in surface waters of King George Island, off the western coast of the Antarctic Peninsula. The research encompassed six streams, a lake and an artificial water reservoir located on the western coast of Admiralty Bay. Measured hydrochemical parameters included pH, conductivity, total dissolved solids (TDS), and total and dissolved forms elements such as Al, Co, Ni, Cu, Zn, Cd, Pb, Mn, Fe, As and Se. The values of pH, conductivity and TDS had the following ranges: 6.09–8.21, 6.0–875 µS cm−1 and 7.0–975 mg/L, respectively, and were typical for surface waters of Antarctica. Wide disparities were discovered regarding concentrations of the investigated elements, ranging from <0.01 µg/L for Cd to 510 µg/L for Fe, and differing from one water body to another. The investigated elements are discussed with reference to environmental conditions and anthropogenic factors. Concentrations of total and dissolved forms of elements are considered in connection with the composition of soil in their surroundings and with atmospheric deposition, mostly such as that took place locally. The increased levels of Pb and Zn concentrations in the immediate proximity of a research station suggested anthropogenic contamination. Keywords: Antarctic surface waters; total and dissolved elements; baseline elements values; anthropogenic metal contamination.
Keywords: Antarktis; biologi; geokjemi; hydrokjemi; kjemiske analyser; overflatevann

Observations of cetaceans in the south-east Atlantic sector of the Southern Ocean, during summer 2008 - Nøttestad, Leif; Krafft, Bjørn; Søiland, Henrik; Skaret, Georg (Polar Biology, 2014)
Keywords: Sørishavet; hvaler; marin biologi; observasjoner; oseanografi

Deterrent activities in the crude lipophilic fractions of Antarctic benthic organisms: chemical defences against keystone predators - Núñez-Pons, Laura; Avila, Conxita (Polar Research, 2014)
Generalist predation constitutes a driving force for the evolution of chemical defences. In the Antarctic benthos, asteroids and omnivore amphipods are keystone opportunistic predators. Sessile organisms are therefore expected to develop defensive mechanisms mainly against such consumers. However, the different habits characterizing each predator may promote variable responses in prey. Feeding-deterrence experiments were performed with the circumpolar asteroid macropredator Odontaster validus to evaluate the presence of defences within the apolar lipophilic fraction of Antarctic invertebrates and macroalgae. A total of 51% of the extracts were repellent, yielding a proportion of 17 defended species out of the 31 assessed. These results are compared with a previous study in which the same fractions were offered to the abundant circum-Antarctic amphipod Cheirimedon femoratus. Overall, less deterrence was reported towards asteroids (51%) than against amphipods (80.8%), principally in sponge and algal extracts. Generalist amphipods, which establish casual host–prey sedentary associations with biosubstrata (preferentially sponges and macroalgae), may exert more localized predation pressure than sea stars on certain sessile prey, which would partly explain these results. The nutritional quality of prey may interact with feeding deterrents, whose production is presumed to be metabolically expensive. Although optimal defence theory posits that chemical defences are managed and distributed as to guarantee protection at the lowest cost, we found that only a few organisms localized feeding deterrents towards most exposed and/or valuable body regions. Lipophilic defensive metabolites are broadly produced in Antarctic communities to deter opportunistic predators, although several species combine different defensive traits. Keywords: Antarctic invertebrates; Antarctic algae; chemical ecology; sea star Odontaster validus; amphipod Cheirimedon femoratus; chemical defence.
Keywords: Antarktis; alger; kjemisk økologi; virvelløse dyr

Acidity decline in Antarctic ice cores during the Little Ice Age linked to changes in atmospheric nitrate and sea salt concentrations - Pasteris, Daniel; McConnell, Joseph R; Edwards, Ross; Isaksson, Elizabeth; Albert, Mary R (Journal of Geophysical Research: Atmospheres, 2014)
Acidity is an important chemical variable that impacts atmospheric and snowpack chemistry. Here we describe composite time series and the spatial pattern of acidity concentration (Acy = H+ − HCO3−) during the last 2000 years across the Dronning Maud Land region of the East Antarctic Plateau using measurements in seven ice cores. Coregistered measurements of the major ion species show that sulfuric acid (H2SO4), nitric acid (HNO3), and hydrochloric acid (HCl) determine greater than 98% of the acidity value. The latter, also described as excess chloride (ExCl−), is shown mostly to be derived from postdepositional diffusion of chloride with little net gain or loss from the snowpack. A strong inverse linear relationship between nitrate concentration and inverse accumulation rate provides evidence of spatially homogenous fresh snow concentrations and reemission rates of nitrate from the snowpack across the study area. A decline in acidity during the Little Ice Age (LIA, 1500–1900 Common Era) is observed and is linked to declines in HNO3 and ExCl− during that time. The nitrate decline is found to correlate well with published methane isotope data from Antarctica (δ13CH4), indicating that it is caused by a decline in biomass burning. The decrease in ExCl− concentration during the LIA is well correlated to published sea surface temperature reconstructions in the Atlantic Ocean, which suggests increased sea salt aerosol production associated with greater sea ice extent.
Keywords: Dronning Maud Land; glasiologi; holocene; hydrologi; iskjerner; lille istiden

Distribution of total alkalinity and pH in the Ross Sea (Antarctica) waters during austral summer 2008 - Rivaro, Paola; Messa, Roberta; Ianni, Carmela; Magi, Emanuele; Budillon, Giorgio (Polar Research, 2014)
Measurements of total alkalinity (AT) and pH were made in the Ross Sea in January–February 2008 in order to characterize the carbonate system in the Ross Sea and to evaluate the variability associated with different water masses. The main water masses of the Ross Sea, Antarctic Surface Water, High Salinity Shelf Water (HSSW), Deep Ice Shelf Water, Circumpolar Deep Water (CDW) and Antarctic Bottom Water, were identified on the basis of the physical and chemical data. In particular, the AT ranged between 2275 and 2374 µmol kg−1 with the lowest values in the surface waters (2275–2346 µmol kg−1), where the influence of the sea-ice melting and of the variability of the physical properties was significant. In the deep layers of the water column, the AT maxima were measured in correspondence to the preferential pathways of the spreading HSSW. The pH had variable values in the surface layer (7.890–8.033) with the highest values in Terra Nova Bay and Ross Sea polynyas. A low pH (7.969±0.025) traced the intrusion of the CDW in the Ross Sea shelf area. All samples revealed waters that were oversaturated with respect to both calcite and aragonite, but near corrosive levels of aragonite saturation state (Ω ca. 1.1–1.2) were associated with the entrainment of CDW over the slope. Aragonite undersaturation is of particular concern for the zooplankton species comprising to calcifying organisms such as pteropods. The partial pressure of CO2 at the sea surface was undersaturated with respect to the atmospheric value, particularly in Terra Nova Bay and the Ross Sea polynyas, but a large variability in the sea–air CO2 fluxes was observed associated with different responses in the strength of the biological and physical processes. Keywords: Total alkalinity; pH; saturation state; Terra Nova Bay polynya; Ross Sea.
Keywords: Rosshavet; Sørishavet; havis; hydrografi; hydrokjemi; kjemiske analyser; klimaendringer; kontinentalsokkel; sjøis; vannmasser; zooplankton

Å filme de dypfrosne hemmelighetene til en aktiv vulkan - Roberts, Jason (Polarboken, 2014)
Keywords: Antarktis; film; geofysikk; vulkaner

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

Accuracy assessment of global barotropic ocean tide models - Stammer, D; Ray, R D; Andersen, O B; Arbic, B K; Bosch, W; Carrère, L; Cheng, Y; Chinn, D S; Dushaw, B D; Egbert, G D; Erofeeva, S Y; Fok, H S; et al. (Reviews of Geophysics, 2014)
The accuracy of state-of-the-art global barotropic tide models is assessed using bottom pressure data, coastal tide gauges, satellite altimetry, various geodetic data on Antarctic ice shelves, and independent tracked satellite orbit perturbations. Tide models under review include empirical, purely hydrodynamic (“forward”), and assimilative dynamical, i.e., constrained by observations. Ten dominant tidal constituents in the diurnal, semidiurnal, and quarter-diurnal bands are considered. Since the last major model comparison project in 1997, models have improved markedly, especially in shallow-water regions and also in the deep ocean. The root-sum-square differences between tide observations and the best models for eight major constituents are approximately 0.9, 5.0, and 6.5 cm for pelagic, shelf, and coastal conditions, respectively. Large intermodel discrepancies occur in high latitudes, but testing in those regions is impeded by the paucity of high-quality in situ tide records. Long-wavelength components of models tested by analyzing satellite laser ranging measurements suggest that several models are comparably accurate for use in precise orbit determination, but analyses of GRACE intersatellite ranging data show that all models are still imperfect on basin and subbasin scales, especially near Antarctica. For the M2 constituent, errors in purely hydrodynamic models are now almost comparable to the 1980-era Schwiderski empirical solution, indicating marked advancement in dynamical modeling. Assessing model accuracy using tidal currents remains problematic owing to uncertainties in in situ current meter estimates and the inability to isolate the barotropic mode. Velocity tests against both acoustic tomography and current meters do confirm that assimilative models perform better than purely hydrodynamic models.

The influence of Nunataks on atmospheric boundary layer convection during summer in Dronning Maud Land, Antarctica - Stenmark, Aurora; Hole, Lars Robert; Voss, Paul; Reuder, Joachim; Jonassen, Marius O (Journal of Geophysical Research: Atmospheres, 2014)
The effects of nunataks on temperature profiles and wind patterns are studied using simulations from the Weather Research and Forecasting model. Simulations are compared to hourly observations from an automatic weather station located at the Troll Research Station in Dronning Maud Land. Areas of bare ground have been implemented in the model, and the simulations correspond well with meteorological measurements acquired during the 4 day simulation period. The nunataks are radiatively heated during daytime, and free convection occurs in the overlying atmospheric boundary layer. The inflow below the updraft forces strong horizontal convergence at the surface, whereas weaker divergence appears aloft. In a control run with a completely ice-covered surface, the convection is absent. In situ observations carried out by a remotely controlled balloon and a small model airplane compare well with model temperature profiles, but these are only available over the ice field upwind to the nunatak.
Keywords: Dronning Maud Land; atmosfæren; geofysikk; meteorologi; nunataker; observasjoner

Age-Related Mercury Contamination and Relationship with Luteinizing Hormone in a Long-Lived Antarctic Bird - Tartu, Sabrina; Bustamante, Paco; Goutte, Aurélie; Cherel, Yves; Weimerskirch, Henri; Bustnes, Jan Ove; Chastel, Olivier (PloS One, 2014)
Seabirds, as long-lived top predators, accumulate contaminants such as mercury (Hg), an established endocrine disruptor. In long lived species hormonal secretion varies with age; therefore, Hg-induced endocrine disruption may be exacerbated in some age classes. Here we investigated relationships between blood total Hg and luteinizing hormone (LH, a key pituitary hormone for the onset of breeding), in pre-laying known-age (11–45 years old) snow petrels (Pagodroma nivea) from Adélie Land, Antarctica. We predicted that 1) blood Hg would increase with advancing age as a consequence of bio-accumulation; and that 2) increasing blood Hg would be related to decreased concentrations of LH in the most Hg-contaminated individuals. Hg concentrations were higher in females than in males (p<0.001), and contrary to our prediction, decreased with advancing age in males (p = 0.009) and tended to do so in females (p = 0.06). The analysis of stable isotopes (δ13C and δ15N) suggested that this unexpected pattern could originate from age and sex-related variations in trophic niche, and hence Hg exposure. Regarding LH, our prediction was only supported in young birds (≤23 years) where baseline LH was inversely correlated with Hg concentrations (p = 0.04). Hg burden did not predict baseline LH or GnRH-induced LH in birds that were more than 23 years old. These results show that age and contaminants may interfere with major endocrine mechanisms and, together with other recent studies, support the view that Hg could be connected to LH secretion and could then impair the fitness of long-lived birds.
Publisher: Public Library of Science
Keywords: Antarktis; forurensning; kjemiske analyser; miljø; nevrobiologi; ornitologi; petreller; sjøfugler; stabile isotoper; zoologi; økologiske nisjer

Hvalfangerkirken i Grytviken 100 år - Tokstad, Kjell (Polarboken, 2014)
Keywords: Sørishavet; bygninger; historie

Atmosphere–sea ice interaction in early summer in the Antarctic: evaluation and challenges of a regional atmospheric model - Valkonen, T.; Vihma, T.; Johansson, M. M.; Launiainen, J. (Quarterly Journal of the Royal Meteorological Society, 2014)
Antarctic sea ice areas have only been the main focus for a few studies combining observations and three-dimensional atmospheric model experiments. This study presents simulations over the Weddell Sea in early summer, applying the polar-optimized version of the Weather Research and Forecasting model (Polar WRF). The results are compared against observations from the drifting experiment Ice Station Polarstern, which took place on 28 November 2004?2 January 2005. The Polar WRF model showed good skill in simulating synoptic-scale variations. The diurnal cycles of surface variables were reproduced, but the amplitude was overestimated for most of the variables and the simulations were characterized by a cold temperature bias at night. The major challenges related to the modelling of the atmosphere over Antarctic sea ice were found to be associated with clouds, atmospheric boundary-layer processes and processes in the sea ice and snow layer. Temporal variations in the errors in cloud cover generated large errors in long-wave radiation fluxes. In the boundary layer, the overestimated downward sensible heat flux was partly compensated for by the underestimated downward long-wave radiation at the surface. The underestimated downward long-wave flux started to dominate as the stability increased and generated the cold temperature bias at the surface. Problems with the surface energy balance, as found in this study, could be reduced by applying more advanced schemes for snow and ice thermodynamics.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; meteorologi; sjøis

Atmospheric trace elements in aerosols observed over the Southern Ocean and coastal East Antarctica - Xu, Guojie; Gao, Yuan (Polar Research, 2014)
Atmospheric aerosol samples were collected over the Southern Ocean (SO) and coastal East Antarctica (CEA) during the austral summer of 2010/11. Samples were analysed for trace elements, including Na, Mg, K, Al, Fe, Mn, Ni, Cd and Se, by inductively coupled plasma mass spectrometry (ICP-MS). The mean atmospheric concentrations over the SO were 1100 ng m−3 for Na, 190 ng m−3 for Mg, 150 ng m−3 for Al, 14 ng m−3 for Fe, 0.46 ng m−3 for Mn and 0.25 ng m−3 for Se. Over CEA, the mean concentrations were 990 ng m−3 for Na, 180 ng m−3 for Mg, 190 ng m−3 for Al, 26 ng m−3 for Fe, 0.70 ng m−3 for Mn and 0.29 ng m−3 for Se. Particle size distributions, enrichment factors (EFs) and correlation analysis indicate that Na, Mg and K mainly came from the marine source, while Al, Fe and Mn were mainly from the crustal source, which also contributed to Mg and K over CEA. High EFs were associated with Ni, Cd and Se, suggesting likely contributions from mixed sources from the Antarctic continent, long-range transport, marine biogenic emissions and anthropogenic emissions. Sea-salt elements (Na, Mg, K) were mainly accumulated in the coarse mode, and crustal elements (Al, Fe, Mn) presented a bimodal size distribution pattern. Bioactive elements (Fe, Ni, Cd) were enriched in the fine mode, especially with samples collected over the SO, possibly affecting biogeochemical cycles in this oceanic region. Keywords: Southern Ocean; coastal East Antarctica; trace elements; size distribution; sources.
Keywords: Sørishavet; atmosfærisk aerosol; biogeokjemi; kjemiske analyser; meteorologi

Wind-driven spreading of fresh surface water beneath ice shelves in the Eastern Weddell Sea - Zhou, Qiming; Hattermann, Tore; Nøst, Ole Anders; Biuw, Martin; Kovacs, Kit M; Lydersen, Christian (Journal of Geophysical Research: Oceans, 2014)
Abstract Solar heated, fresh Antarctic Surface Water (ASW) is a permanent feature along the Eastern Weddell Sea (EWS) coast in summer down to a depth of roughly 200 m. Recently, ASW has been observed beneath the Fimbul Ice Shelf, suggesting that it might play an important role in basal melting. We propose that wind-driven coastal downwelling is the main mechanism that spreads ASW beneath the ice shelf in this sector of Antarctica. We validate this hypothesis with observations, scaling analyses, and numerical modeling, along three principle lines: (i) data analyses of about 1500 salinity profiles collected by instrumented seals indicate that the observed freshening of the coastal water column is likely explained by the on-shore Ekman transport and subsequent downwelling of ASW; (ii) an analytical model of the coastal momentum balance indicates that wind-driven downwelling is capable of depressing the buoyant surface water to a depth similar to the ice shelf draft; and (iii) simulations from both idealized and regional eddy-resolving numerical ice shelf/ocean models support our proposition. Our main conclusion is that wind-driven spreading of ASW beneath the ice shelf occurs when downwelling exceeds the depth of the ice shelf base. Furthermore, our study adds to the understanding of the oceanic processes at the Antarctic Slope Front in the EWS, with possible implications for other sectors of Antarctica.
Keywords: Sørishavet; Weddellhavet; isbrem; isshelf; oseanografi; overflatevann; smelting; vannmasser; vannvirvler

Norske krav i Sørishavet - Utfordringer for Sjøforsvaret - Aase, Johnny Grøneng (Norsk Tidsskrift for Sjøvesen, 2013)
Norge gjorde i 2009 krav på økonomiske soner utenfor Bouvetøya og Dronning Maud Land. Slike krav fører i følge Lov om økonomiske soner med seg forpliktelser som over tid får konsekvenser for Sjøforsvaret. l den økonomiske sonen som ble erklært utenfor fastlands-Norge på 1970-tallet har det vært Kystvakten som har opprettholdt juridiksjon, overvåket miljøet og kontrollert fisket. Norske og utenlandsk fartøyer har alt begynt å fiske i norsk økonomisk sone utenfor Bouvetøya. Det foregår i dag en rivende utvikling av teknologi for gruvedrift på store havdyp. Statlige og kommersielle private aktører posisjonerer seg aktivt for å kunne utnytte naturressursene i Sørishavet. Denne forfatteren mener at det vil tvinge seg fram et behov for stedlig overvåkning, kontroll og miljøvern i de norske økonomiske sonene i Antarktis. Det eksisterer ingen robust søk- og redningstjeneste i Antarktis. Siden Norge har gjort territorielle krav har vi også en moralsk forpliktelse om å kunne komme skipbrudne og syke til unnsetning i disse områdene. Overvåkning og hevding av juridiksjon i slike store og fjerntliggende havområder vil bli komplisert og dyrt. Kystvakten har i dag verken fartøyer eller personell for å kunne utføre dette. Rundt 2020 vil de store kystvaktskipene Nordkapp, Senja og Andenes være rundt 40 år og nærme seg tidspunktet for utfasing. Klimaendringene fører til migrasjon av fisk nordover mot kaldere vann i Barentshavet, og det vil derfor bli behov for fiskeriinspeksjoner lenger nord enn i dag. Kystvakten trenger å anskaffe store erstatningsfartøy for Nordkapp-klassen, og ved prosjekteringen bør man ta høyde for at Norge også vil ha behov for en kystvaktkapasitet i Antarktis. For å redusere risikoen for over- eller feilinvesteringer vil jeg gjennomgå hvordan en allerede i dag kan benytte satellitter for å kartlegge skipstrafikken i de norske områdene i sør. Ut fra dette bakgrunnsmaterialet kan Forsvaret anslå hvor mange fartøyer som vil være nødvendig å ha i sør.
Publisher: Sjømilitære samfund
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; havrett; jus; miljøovervåking; miljøvern; naturressurser; økonomi

Eddy-Driven Exchange between the Open Ocean and a Sub–Ice Shelf Cavity - Årthun, Marius; Holland, Paul R; Nicholls, Keith William; Feltham, Daniel L (Journal of Physical Oceanography, 2013)
Keywords: Sørishavet; Weddellhavet; isshelf; oseanografi; sjøvirvler; vannvirvler

Thick-shelled, grazer-protected diatoms decouple ocean carbon and silicon cycles in the iron-limited Antarctic Circumpolar Current - Assmy, Philipp; Smetacek, Victor; Montresor, Marina; Klaas, Christine; Henjes, Joachim; Strass, Volker; Arrieta, Jesus M; Bathmann, Ulrich; Berg, Gry Mine; Breitbarth, Eike; Cisewski, Boris; Friedrichs, Lars; et al. (Proceedings of the National Academy of Sciences, 2013)
Diatoméer – alger med skall av silisium, som er helt avhengige av næringsstoffet silikat – dominerer fytoplankton oppblomstringer og spiller en nøkkelrolle i havets økosystemer og i global karbonsyklus. Vi viser hvordan forskjeller i økologiske karakteristikker av dominerende arter i Sørishavet, som ble observert under det in situ europeiske jerngjødslings eksperimentet (European Iron Fertilization Experiment - EIFEX), kan påvirke karbon og silisium syklusene i havet. Vi argumenterer for at økologien til tykkskallete diatomé arter, som er selektert for av sterk beiting fra kopepoder, tar opp silikat fremfor andre næringsstoffer i det dype Sørishavet og underliggende sedimenter. Fordi Sørishavet er en viktig sentral for oseanisk fordeling av næringsstoffer, selektivt opptak av silikat i dette havområdet begrenser oppblomstringene av diatoméer i andre deler av verdenshavene, noe som potensielt får konsekvenser for biotisk opptak av karbon i hele verdens havområder.
Keywords: Sørishavet; marinbiologi; oseanografi; plankton; økosystem

A Crisis that Never Came: The decline of the Antarctic Whaling Industry in the 1950s and 1960s - Basberg, Bjørn L (The Mariner's Mirror, 2013)
Publisher: Routledge
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; pelagisk; økonomi

Antarktis-isen: større og dypere - Bjermeland, Monica (Klima: norsk magasin for klimaforskning, 2013)
De siste tiårene har isen i Antarktis økt litt i utbredelse. Men ikke fordi det er blitt kaldere der.
Keywords: Antarktis; Sørishavet; glasiologi; havis; is; klima

At-sea behaviour of three krill predators breeding at Bouvetøya—Antarctic fur seals, macaroni penguins and chinstrap penguins - Blanchet, Marie-Anne; Biuw, Martin; Hofmeyr, Greg; de Bruyn, P. J. Nico; Lydersen, Christian; Kovacs, Kit M. (Marine Ecology Progress Series, 2013)
Keywords: Bouvetøya; krill; pelsseler; pingviner; pinnipedier; plankton; seler; zoologi

On-site and in situ remediation technologies applicable to metal-contaminated sites in Antarctica and the Arctic: a review - Camenzuli, Danielle; Freidman, Benjamin L; Statham, Tom M; Mumford, Kathryn A; Gore, Damian B (Polar Research, 2013)
Effective management of contaminated land requires a sound understanding of site geology, chemistry and biology. This is particularly the case for Antarctica and the Arctic, which function using different legislative frame- works to those of industrialized, temperate environments and are logistically challenging environments to operate in. This paper reviews seven remediation technologies currently used, or demonstrating potential for on-site or in situ use at metal-contaminated sites in polar environments, namely permeable reactive barriers (PRB), chemical fixation, bioremediation, phytoremediation, electrokinetic separation, land capping, and pump and treat systems. The technologies reviewed are discussed in terms of their advantages, limitations and overall potential for the management of metal-contaminated sites in Antarctica and the Arctic. This review demonstrates that several of the reviewed technologies show potential for on-site or in situ usage in Antarctica and the Arctic. Of the reviewed technologies, chemical fixation and PRB are particularly promising technologies for metal-contaminated sites in polar environments. However, further research and relevant field trials are required before these technologies can be considered proven techniques. Keywords: Polar; heavy metals; remediation; contaminants; in situ
Keywords: Antarktis; biologi; forurensning; geologi; jord; kjemi; menneskelig påvirkning; polarområdene; tungmetaller

Reading and thinking about International Polar Years: five recent books - Carlson, Dave (Polar Research, 2013)
Within the polar science community the Polar (and Geophysical) Years represent signal events. We often read, largely within geoscience literature, that those events represented positive and dramatic steps forward in international science. From five recent books - two historical compilations and three personal narratives - augmented by interviews with a few key participants, a more cautious picture emerges, of remarkable successes but also of occasional or even persistent missteps and deficiencies. An improved understanding of the IPY concept and experience can provide useful guidance for future polar and global science. Keywords: International Polar Year; International Geophysical Year; international science; history of polar science.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); IPY; bokanmeldelser; internasjonal; politikk; samarbeid; vitenskap

Dietary overlap in inshore notothenioid fish from the Danco Coast, western Antarctic Peninsula - Casaux, Ricardo; Barrera-Oro, Esteban (Polar Research, 2013)
We carried out a dietary overlap analysis between notothenioid species by examining the stomach contents of more than 900 specimens collected in a fish assemblage at the Danco Coast, western Antarctic Peninsula, in the summer of 2000. Prey reoccurrences among fish species were 32.2%, with krill Euphausia superba, salps and the gammaridean Prostebeingia longicornis the most reoccurring prey. The diet similarity between species pairs was lower than 55%, in accordance with similar fish assemblages in the South Orkney Islands, the South Shetland Islands and the Antarctic Peninsula. Whereas at those localities the higher prey overlap was between krill-feeding fish species, at the Danco Coast it was between Trematomus bernacchii and Lepidonotothen nudifrons, Notothenia coriiceps and Notothenia rossii, Notothenia coriiceps and Parachaenichthyis charcoti, and Trematomus newnesi and Notothenia rossii, which shared primarily gammaridean amphipods, algae, fish and krill, respectively. Krill is normally the main prey of fish in summer in inshore waters of the western Antarctic Peninsula, but its density in January/February 2000 was notably lower than in previous years. Therefore, at the Danco Coast, under conditions of krill shortage, most of the notothenioid species foraged more intensively on alternative prey, such as gammarideans, fish and algae. The difference between areas in the pattern of dietary overlap might be related to differences in prey availability between years and to the degree of competition for targeted prey. Keywords: Fish dietary overlap; notothenioid fish; Antarctic Peninsula.
Keywords: Sørishavet; fisker; forskning; krill; marin biologi; plankton; økosystemer

Using visible reflectance spectroscopy to reconstruct historical changes in chlorophyll a concentration in East Antarctic ponds - Chen, Qianqian; Liu, Xiaodong; Nie, Yaguang; Sun, Liguang (Polar Research, 2013)
The visible reflectance spectroscopy (VRS) and chlorophyll a concentration were determined in three sediment profiles collected from East Antarctica to investigate the potential application of VRS in reconstructing historical changes in Antarctic lake primary productivity. The results showed that the appearance of a trough at 650–700 nm is an important marker for chlorophyll a concentration and can therefore be used to distinguish the sedimentary organic matter source from guano and algae. The measured chlorophyll a content had significant positive correlations with the trough area between 650 and 700 nm, and no distinct trough was found in the sediments with organic matter completely derived from guano. Modelling results showed that the spectra spectrally inferred chlorophyll a content, and the measured data exhibit consistent trends with depth, showing that the dimensionless trough area can serve as an independent proxy for reconstructing historical fluctuations in the primary production of Antarctic ponds. The correlation of phosphorus (P) with measured and inferred chlorophyll a contents in ornithogenic sediments near penguin colonies indicates that the change in primary productivity in the Antarctic ponds investigated was closely related to the amount of guano input from these birds. Keywords: Reflectance spectroscopy; ornithogenic sediments; chlorophyll a; Antarctic ponds; primary productivity; VRS.
Keywords: Antarktis; alger; biogeokjemi; fytoplankton; innsjø; pingviner; sedimenter; sjøfugler

Tintinnid ciliates of Amundsen Sea (Antarctica) plankton communities - Dolan, John R; Yang, Eun Jin; Lee, Sang Hoon; Kim, Sun Young (Polar Research, 2013)
The Amundsen Sea has been described as one of the most productive and dynamic pelagic systems in Antarctica and is one of the least studied. Based on samples from 15 stations in the Amundsen Sea, we describe for the first time the composition of the tintinnid ciliate assemblage of the microzooplankton. We compared the species compositions of coastal polynya sites, where the phytoplankton communities are dominated by Phaeocystis, to those of the offshore deep water sites, which are dominated by diatoms. We found a total of 15 species. Polynya sites were dominated by a few species of tintinnids, mostly those endemic to the Southern Ocean. In contrast, the deep-water sites contained many widespread tintinnid species, which are known from a wide variety of systems as well as other areas of the Southern Ocean. We examined polymorphism known to characterize the Antarctic tintinnid species Cymatocylis affinis/convallaria and Codonellopsis gaussi. We found that the types or forms found appeared unrelated to the type of microplankton community, defined by the identity of the dominant phytoplankton taxa. However, the number of different morphotypes found at a site appeared related to the overall concentration of the species, suggesting that different morphologies, previously considered distinct species, may simply be developmental stages. Keywords: Zooplankton; microzooplankton; polynya; protists; Phaeocystis; diatoms.
Keywords: Sørishavet; diatomeer; fytoplankton; marin biologi; oseanografi; protoktister; zooplankton; økologi

Bedmap2: improved ice bed, surface and thickness datasets for Antarctica - Fretwell, Peter; Pritchard, Hamish; Vaughan, David; Bamber, Jonathan; Barrand, N; Bell, Robin; Bianchi, Cesidio; Bingham, R; Blankenship, D; Casassa, Gino; Catania, G; Callens, D; et al. (The Cryosphere, 2013)
We present Bedmap2, a new suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60° S. We derived these products using data from a variety of sources, including many substantial surveys completed since the original Bedmap compilation (Bedmap1) in 2001. In particular, the Bedmap2 ice thickness grid is made from 25 million measurements, over two orders of magnitude more than were used in Bedmap1. In most parts of Antarctica the subglacial landscape is visible in much greater detail than was previously available and the improved data-coverage has in many areas revealed the full scale of mountain ranges, valleys, basins and troughs, only fragments of which were previously indicated in local surveys. The derived statistics for Bedmap2 show that the volume of ice contained in the Antarctic ice sheet (27 million km3) and its potential contribution to sea-level rise (58 m) are similar to those of Bedmap1, but the mean thickness of the ice sheet is 4.6% greater, the mean depth of the bed beneath the grounded ice sheet is 72 m lower and the area of ice sheet grounded on bed below sea level is increased by 10%. The Bedmap2 compilation highlights several areas beneath the ice sheet where the bed elevation is substantially lower than the deepest bed indicated by Bedmap1. These products, along with grids of data coverage and uncertainty, provide new opportunities for detailed modelling of the past and future evolution of the Antarctic ice sheets.
Publisher: Copernicus Publications
Keywords: Antarktis; glasiologi

Genetic characterization and life cycle of the diatom Fragilariopsis kerguelensis - Fuchs, Nike; Scalco, Eleonora; Kooistra, Wiebe; Assmy, Philipp; Montresor, Marina (European Journal of Phycology, 2013)
Diatoméen Fragilariopsis kerguelensis fra Sørishavet spiller en nøkkelrolle i marin silisium syklus fordi restene av celleveggene synker til havbunnen rundt Antarktis, hvor de bygger opp de største depotene av biologisk generert silisium i verden. Tomme skall av diatomeer har også blitt brukt som indikatorer/proksier for produksjonsregimer i geologisk fortid av mikro-paleontologer. For å bedre kunne beskrive og forstå biologien av denne arten fra Sørishavet har vi adressert dens genetiske identitet ved hjelp av molekylære markører, og for første gang vært i stand til å anslå kjønn til denne arten. Dette har ført til at vi har vært i stand til å kjøre et stort antall vellykkede parringseksperimenter. Vi har vært i stand til å avdekke det intrikate parringssystemet og livssyklus karakteristikker til F. kerguelensis og demonstrere at vi kun har å gjøre med én biologisk art. En bedre forståelse av livssyklus til F. kerguelensis burde hjelpe for tolkning av geologiske tidsserier for denne arten og belyse rollen miljøfaktorer kan ha for å regulere populasjoner av arten.
Keywords: Sørishavet; genetikk; marinbiologi; plankton

Abundance and breeding distribution of seabirds in the northern part of the Danco Coast, Antarctic Peninsula - González-Zevallos, Diego; Santos, M Mercedes; Rombolá, Emilce F; Juáres, Mariana A; Coria, Néstor R (Polar Research, 2013)
Seabird abundances and breeding distribution have the potential to serve as ecological indicators. The western Antarctic Peninsula is one of the three sites in the world with the greatest increases in local temperature during the last 50 years. The aim of this study was to monitor the distribution and abundance of breeding populations of seabirds in the northern sector of the Danco Coast, north-west of the Antarctic Peninsula, during the breeding season 2010/11. The birds were the Wilson's storm petrel (Oceanites oceanicus), South Polar skua (Stercorarius maccormicki), kelp gull (Larus dominicanus), Antarctic tern (Sterna vittata), snowy sheathbill (Chionis alba), chinstrap penguin (Pygoscelis antarctica), southern giant petrel (Macronectes giganteus), gentoo penguin (Pygoscelis papua), Cape petrel (Daption capense) and Antarctic shag (Phalacrocorax bransfieldensis). Annual breeding population growth increased in pygoscelids, southern giant petrel and sheathbill, and for the remaining species, breeding population trends were stable. Given that seabird populations can provide valuable information on the conditions of their feeding and nesting environments, this study highlights the need to maintain basics monitoring studies. Keywords: Seabird abundances; breeding distribution; Danco Coast; Antarctic Peninsula.
Keywords: Antarktis; klimaendringer; ornitologi; petreller; sjøfugler; temperatur

Tre kilder til smelting av Fimbulisen - Hattermann, Tore; Nøst, Ole A; Smedsrud, Lars H (Klima: norsk magasin for klimaforskning, 2013)
Soloppvarmet overflatevann er en sentral varmekilde som bidrar til smelting av isbremmen Fimbulisen i Dronning Maud Land.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima

Assessing the potential of calcium-based artificial ocean alkalinization to mitigate rising atmospheric CO2 and ocean acidification - Ilyina, Tatiana; Wolf-Gladrow, Dieter; Munhoven, Guy; Heinze, Christoph (Geophysical Research Letters, 2013)
Enhancement of ocean alkalinity using calcium compounds, e.g., lime has been proposed to mitigate further increase of atmospheric CO2 and ocean acidification due to anthropogenic CO2 emissions. Using a global model, we show that such alkalinization has the potential to preserve pH and the saturation state of carbonate minerals at close to today's values. Effects of alkalinization persist after termination: Atmospheric CO2 and pH do not return to unmitigated levels. Only scenarios in which large amounts of alkalinity (i.e., in a ratio of 2:1 with respect to emitted CO2) are added over large ocean areas can boost oceanic CO2 uptake sufficiently to avoid further ocean acidification on the global scale, thereby elevating some key biogeochemical parameters, e.g., pH significantly above preindustrial levels. Smaller-scale alkalinization could counteract ocean acidification on a subregional or even local scale, e.g., in upwelling systems. The decrease of atmospheric CO2 would then be a small side effect.
Keywords: Sørishavet; biogeokjemi; havalkalisering; klimatologi; meteorologi; modeller

Low frequency variability on the continental slope of the southern Weddell Sea - Jensen, Mari F; Fer, Ilker; Darelius, Elin (Journal of Geophysical Research: Oceans, 2013)
One-year long records of temperature, salinity, and currents show seasonally varying, energetic oscillations with a dominant period of approximately 35 h on the upper continental slope of the southern Weddell Sea. The data set is sampled by five moorings deployed on the slope of the Crary Fan, east of the main outflow site of the Filchner overflow plume. The characteristics of the observed oscillations are compared to idealized coastal trapped waves inferred from a numerical code. The variability at 35 h period is identified as mode 1 waves with wavelengths less than 200 km and group velocity opposing the phase speed, indicating energy propagation toward east. Filchner Depression and the nearby ridges on the slope are suggested as the generation site where the dynamics associated with the overflow plume can force the variability. Historical time series at the overflow site are revisited to identify the source of previously reported variability at 3 and 6 day time scales. Mode 2 waves at wavelengths of about 100 and 1000 km were found to bear resemblance to the 3 day and 6 day variability, respectively. The seasonal variation in the energy in the 35 h band shows small but significant correlation with the low frequency easterly winds. The presence of coastal trapped waves along the continental slope of the Weddell Sea can increase the heat exchange across the shelf break and affect the dense water production rates.
Keywords: Sørishavet; Weddellhavet; batymetri; bunnvann; geofysikk; havstrømmer; kelvinbølger; saltinnhold; temperatur måling

The impact of abrupt suspension of solar radiation management (termination effect) in experiment G2 of the Geoengineering Model Intercomparison Project (GeoMIP) - Jones, Andy; Haywood, Jim M; Alterskjær, Kari; Boucher, Olivier; Cole, Jason N S; Curry, Charles L; Irvine, Peter J; Ji, Duoying; Kravitz, Ben; Egill Kristjánsson, Jón; Moore, John C; Niemeier, Ulrike; et al. (Journal of Geophysical Research: Atmospheres, 2013)
We have examined changes in climate which result from the sudden termination of geoengineering after 50 years of offsetting a 1% per annum increase in CO2 concentrations by a reduction of solar radiation, as simulated by 11 different climate models in experiment G2 of the Geoengineering Model Intercomparison Project. The models agree on a rapid increase in global-mean temperature following termination accompanied by increases in global-mean precipitation rate and decreases in sea-ice cover. There is no agreement on the impact of geoengineering termination on the rate of change of global-mean plant net primary productivity. There is a considerable degree of consensus for the geographical distribution of temperature change following termination, with faster warming at high latitudes and over land. There is also considerable agreement regarding the distribution of reductions in Arctic sea-ice, but less so for the Antarctic. There is much less agreement regarding the patterns of change in precipitation and net primary productivity, with a greater degree of consensus at higher latitudes.
Keywords: Antarktis; global oppvarming; karbondioksid; klimaendringer; klimamodeller; klimatologi; polarområdene; solstråling

Better late than never? Interannual and seasonal variability in breeding chronology of gentoo penguins at Stranger Point, Antarctica - Juáres, Mariana A; Santos, M Mercedes; Negrete, Javier; Santos, M Rita; Mennucci, Jorge A; Rombolá, Emilce; Longarzo, Lucrecia; Coria, Néstor R; Carlini, Alejandro R (Polar Research, 2013)
Rapid climate change recorded in the western Antarctic Peninsula confronts species with less predictable conditions in the marine and terrestrial environments. We analysed the breeding chronology and nesting site selection of gentoo penguins (Pygoscelis papua) at King George Island (Isla 25 de Mayo), Antarctica, during four seasons in which differences in snow presence and persistence on the ground were observed. We recorded an overall delay as well as seasonal asynchrony at the beginning of reproduction for those years with higher snow deposition. A redistribution of breeding groups was also observed. Nevertheless, the population breeding success and chicks’ weight at fledging remained relatively constant, despite the delay in breeding chronology, the increased duration of foraging trips during the guard stage and the decreased weight of stomach contents during the crèche stage. We suggest that the plasticity of their trophic biology, along with the flexibility of their breeding phenology and relocation of breeding groups, may be complementary reasons why gentoo penguin populations in the region have remained stable in spite of the changing conditions currently registered. Keywords: Antarctica; breeding delay; breeding phenology; snow; Pygoscelis papua; Euphausia superba.
Keywords: Antarktis; klimaendringer; krill; observasjoner; pingviner; plankton; reproduksjon; snø; zoologi

Long-term monitoring of persistent organic pollutants (POPs) at the Norwegian Troll station in Dronning Maud Land, Antarctica - Kallenborn, Roland; Breivik, Knut; Eckhardt, Sabine; Lunder, C R; Manø, S; Schlabach, Martin; Stohl, Andreas (Atmospheric Chemistry and Physics (Print), 2013)
A first long-term monitoring of selected persistent organic pollutants (POPs) in Antarctic air has been conducted at the Norwegian research station Troll (Dronning Maud Land). As target contaminants 32 PCB congeners, α- and γ-hexachlorocyclohexane (HCH), trans- and cis-chlordane, trans- and cis-nonachlor, p,p'- and o,p-DDT, DDD, DDE as well as hexachlorobenzene (HCB) were selected. The monitoring program with weekly samples taken during the period 2007–2010 was coordinated with the parallel program at the Norwegian Arctic monitoring site (Zeppelin mountain, Ny-Ålesund, Svalbard) in terms of priority compounds, sampling schedule as well as analytical methods. The POP concentration levels found in Antarctica were considerably lower than Arctic atmospheric background concentrations. Similar to observations for Arctic samples, HCB is the predominant POP compound, with levels of around 22 pg m−3 throughout the entire monitoring period. In general, the following concentration distribution was found for the Troll samples analyzed: HCB > Sum HCH > Sum PCB > Sum DDT > Sum chlordanes. Atmospheric long-range transport was identified as a major contamination source for POPs in Antarctic environments. Several long-range transport events with elevated levels of pesticides and/or compounds with industrial sources were identified based on retroplume calculations with a Lagrangian particle dispersion model (FLEXPART).
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; miljøgifter; miljøovervåking

Standardized algal growth potential and/or algal primary production rates of maritime Antarctic stream waters (King George Island, South Shetlands) - Kvíderová, Jana; Elster, Josef (Polar Research, 2013)
In addition to the chemical analyses providing total nutrient content, standardized water trophic status bioassays are useful in the determination of available nutrients for primary producers. The aim of the study was to determine the standardized values of algal growth potential (AGP) and algal primary productivity rate (APPR) of maritime Antarctic stream water using modified AGP/APPR protocols. The standardized values of AGP and the APPR of oligotrophic and mesotrophic water samples from snow-melt streams were measured, and possible nutrient limitation and heavy metal inhibition were evaluated at 5°C and 25°C using polar and temperate strains of Stichococcus bacillaris, respectively. The water samples were enriched for the nutrient limitation tests with 1000 mμ l-1 NO3- -N, 50 μg l-1 PO43- -P, and a mixture of 1000 μg l-1 NO3- -N + 50 μg l-1 PO43- -P, and for the heavy metal inhibition tests with 1000 mg l-1 Na2-ethylenediaminetetraacetic acid (EDTA). The AGP of oligotrophic samples was significantly lower than that of the mesotrophic ones at both temperatures. In addition, AGP was significantly higher at 5°C than at 25°C. Oligotrophic samples were identified as being nitrogen limited, while no nutrient limitation was observed in the mesotrophic samples. No statistically significant heavy metal inhibition was observed at either temperature. The positive correlation of AGP and water nutrient content indicates that the method used accurately and comprehensively monitors the changes in biological availability of mineral nutrients and can provide a standardized reference point for similar exploration of freshwater ecosystems across both polar regions. Keywords: Maritime Antarctic; microalgae; nutrient limitations; snow-melt stream water.
Keywords: Antarktis; alger; analyser; ferskvann; innsjø; kjemisk; klimaendringer; næringsstoff; polarområdene; snø; strøm; økosystemer

Recent snowfall anomalies in Dronning Maud Land, East Antarctica, in a historical and future climate perspective - Lenaerts, Jan T M; van Meijgaard, Erik; van den Broeke, Michiel R; Ligtenberg, Stefan R M; Horwath, Martin; Isaksson, Elisabeth (Geophysical Research Letters, 2013)
Enhanced snowfall on the East Antarctic ice sheet is projected to significantly mitigate 21st century global sea level rise. In recent years (2009 and 2011), regionally extreme snowfall anomalies in Dronning Maud Land, in the Atlantic sector of East Antarctica, have been observed. It has been unclear, however, whether these anomalies can be ascribed to natural decadal variability, or whether they could signal the beginning of a long-term increase of snowfall. Here we use output of a regional atmospheric climate model, evaluated with available firn core records and gravimetry observations, and show that such episodes had not been seen previously in the satellite climate data era (1979). Comparisons with historical data that originate from firn cores, one with records extending back to the 18th century, confirm that accumulation anomalies of this scale have not occurred in the past ~60 years, although comparable anomalies are found further back in time. We examined several regional climate model projections, describing various warming scenarios into the 21st century. Anomalies with magnitudes similar to the recently observed ones were not present in the model output for the current climate, but were found increasingly probable toward the end of the 21st century.
Keywords: Dronning Maud Land; glasiologi; global oppvarming; havnivåstigning; innlandsis; klimaendringer; klimatologi

Automated ice-sheet snowmelt detection using microwave radiometer measurements - Liang, Lei; Guo, Huadong; Li, Xinwu; Cheng, Xiao (Polar Research, 2013)
Monitoring ice-sheet snowmelt is fundamental to understanding global climate change. A simple and automated snowmelt detection process is critical to the establishment of an ice-sheet snowmelt monitoring system. However, different ice-sheet snowmelt detection methods are based on a variety of thresholding schemes using different melt signals for dry and wet snow; these complicate the regular operation of an ice-sheet snowmelt monitoring. We propose an automated melt signal detection method developed using melt signals derived from the cross-gradient polarization ratio snowmelt detection method over Greenland and the wavelet transformation-based snowmelt detection method over Antarctica. Initial results indicate that the proposed method not only increases computational efficiency, practicability and operability but is also more accurate. Keywords: Ice sheet; snowmelt detection; radiometer; cross-gradient polarization ratio; wavelet transformation; generalized Gaussian model.
Keywords: Antarktis; innlandsis; klimaendringer; mikrobølge; målinger; polarområdene; radiometer; snøsmelting; statistisk analyse; temperatur måling

Electrical structure beneath Schirmacher Oasis, East Antarctica: a magnetotelluric study - Murthy, D N; Veeraswamy, K; Harinarayana, T; Singh, U K; Santosh, M (Polar Research, 2013)
Maitri Station (70.76°S; 11.73°E) is located in Schirmacher Oasis, a coastal nunatak in north-central Dronning Maud Land covering an area of 35 km2. Here, we report results from the first magnetotelluric experiments and delineate the deep electrical conductivity structure under Schirmacher Oasis using the data acquired during the 24th Indian Antarctic Scientific Expedition. The magnetotelluric method has the advantage of shallow to deeper level coverage as the data acquisition covers a wide frequency band of 10-3103 Hz, permitting different penetration depths depending on the frequency and conductivity of the layer under investigation. The modelling results indicate the presence of a highly resistive (8000-10 000 ohm m) upper crust, which shows a lateral variation in thickness from 20 km (below site 6) in the east to 10 km (between sites 1 and 2) in the west. It is underlain by a less resistive (500-600 ohm m) lower crust. The highly resistive upper crustal structure supports the existing notion that western Dronning Maud Land is a stable, cratonic platform. Results of free-air gravity, seismic, geomagnetic and surface wave dispersion investigations in East Antarctica also indicate a cratonic-type crust. The results of our study allow us to identify a westward thinning of the upper crust with a marked boundary between sites 1 and 2. We also find evidence for the continuity of the Mozambique mobile belt in East Antarctica on the western side of Schirmacher Oasis. Keywords: Magnetotellurics; Schirmacher Oasis crustal structure; East Antarctica; Mozambique Belt; electrical conductivity.
Keywords: Dronning Maud Land; geofysikk; geologi; magnetotelluriske eksperimenter

Observations of nitric oxide in the Antarctic middle atmosphere during recurrent geomagnetic storms - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Straub, Corinne; Holmén, Kim; Horne, Richard B (Journal of Geophysical Research: Space Physics, 2013)
We report ground-based measurements of the polar middle atmosphere made using a 230–250 GHz passive microwave radiometer deployed at Troll station (72°01′S 02°32′E, L shell of L = 4.8), Antarctica. Our observations show enhanced mesospheric nitric oxide (NO) volume mixing ratio (VMR) during a series of small recurrent geomagnetic storms in the 2008 austral winter, reaching 1.2 ppmv on day 200 (18 July). The Lomb normalized periodogram of the NO VMR time series averaged over 65-80 km for days 130 to 220 of 2008 (9 May to 7 August) shows a peak exceeding the 95% confidence limit at 25.8 days, close to the synodic rotation period for low-latitude solar coronal holes. The highest correlations between the radiometer NO VMR data and trapped and quasi-trapped electron count rates for L = 3.5-5.5 from the Polar Orbiting Environment Satellites 90° telescope are for the >30 keV (90e1) channel (rmax = 0.56, lag time of 5.1 days) and >100 keV (90e2) channel (rmax = 0.57, lag time of 4.4 days). Maximum correlation between NO VMR and the >700 keV (90P6) channel data is lower but lag times are close to zero. Superposed epoch analyses for the eight most significant geomagnetic storm periods and three Carrington rotations (2070-2072) within the 90 day observation period indicate that significant NO abundance observed at 65-80 km in the Antarctic mesosphere may be produced directly by >200 keV electron precipitation or originate from a source at higher altitudes, e.g., production by >30 keV electrons followed by downward transport.
Keywords: Antarktis; atmosfæren; fysikk; geomagnetiske stormer; meteorologi; polarområdene

Arctic and Antarctic sea ice acts as a sink for atmospheric CO2 during periods of snowmelt and surface flooding - Nomura, Daiki; Granskog, Mats A; Assmy, Philipp; Simizu, Daisuke; Hashida, Gen (Journal of Geophysical Research: Oceans, 2013)
In this study, we present evidence that Antarctic and Arctic sea ice act as sink for atmospheric CO2 during periods of snowmelt and surface flooding. The CO2 flux measured directly at the flooded sea ice surface (Fflood) constituted a net CO2 sink of −1.1 ± 0.9 mmol C m−2 d−1 (mean ± 1 SD), which was an order of magnitude higher than the flux measured at the snow-air surface (Fsnow) and bare ice surface (Fice). The Fsnow/Fflood ratio decreased with increasing water equivalent of snow and superimposed-ice, suggesting that the properties of snow and superimposed-ice formation affect the magnitude of the CO2 flux. The Fsnow/Fflood ratio ranged from 0.1 to 0.5, illustrating that 50–90% of the potential flux at the flooded surface was reduced due to the presence of snow/superimposed-ice. Hence, snow cover properties and superimposed-ice play an important role in the CO2 fluxes across the sea ice-snow-atmosphere interface.
Keywords: Sørishavet; atmosfæren; gassutveksling; havis; karbondioksid; klimaendringer; klimatologi; meteorologi; polarområdene; sjøis

Microbial biogeography during austral summer 2007 in the surface waters around the South Shetland Islands, Antarctica - Olsen, Lasse Mork; Ardelan, Murat van; Hewes, Christopher D; Holm-Hansen, Osmund; Reiss, Christian; Bizsel, Nihayet; Sakshaug, Egil; Vadstein, Olav (Aquatic Microbial Ecology, 2013)
Recent studies have concluded that different water bodies in the ocean can contain different microbial communities. The goal of the present study was to determine if biogeographic patterns are present for aquatic microbes in waters which meet around the South Shetland Islands(SSI), Antarctica. Prokaryotic and eukaryotic marine microbial communities were monitored during the 2007 austral summer by use of polymerase chain reaction (PCR) and denaturing gradientgel electrophoresis (DGGE) of small subunit ribosomal DNA. Hydrographic properties, nutrients and chlorophyll a were also measured. There was an onshore to offshore gradient in temperature, salinity and iron concentration and a unimodal distribution of chlorophyll a concentration in rela-tion to the middle of this gradient that occurred near the SSI. The differences in microbial community structure among stations in the studied area were correlated with both geographical distance and environmental factors. For eukaryotes, the correlation was strongest for environment, where as it was strongest for geographical distance for the prokaryotes. Eukaryotic and prokaryotic community structures were highly correlated. Surface water from the Weddell Sea had a different community of eukaryotes than the water in the Antarctic Circumpolar Current in the Drake Passage, whereas the prokaryotic community was not significantly different. The area close to theSSI where the 2 water types mix had the highest chlorophyll concentration and significantly dif-ferent communities of eukaryotes and prokaryotes from both of the inflowing water types. These results suggest that the prokaryote community structure was more affected by productivity thanby environmental variables. KEY WORDS: Microbial biogeography. Microbial community. Natural iron enrichment. Southern Ocean.
Keywords: Sørishavet; biogeografi; marin biologi; mikroorganismer; oseanografi; overflatevann; økosystemer

New at-sea records of pelagic seabirds in the South Atlantic Ocean and Antarctica - Orgeira, José Luis; Scioscia, Gabriela; Torres, Mónica Anilía; Dellabianca, Natalia Andrea (Polar Research, 2013)
During ship-based seabird surveys in the south Atlantic and Antarctica in the austral summers of 1994/95, 2009, 2010, 2011 and 2012, we documented at-sea distributions of Buller’s albatross (Thalassarche bulleri), Atlantic petrel (Pterodroma incerta), soft-plumaged petrel (Pterodroma mollis), Kerguelen petrel (Lugensa brevirostris) and great-winged petrel (Pterodroma macroptera). In some cases, sightings were considered as extralimital, but for other species updating their distributions in the literature seems warranted. Atlantic petrel, for example, has been regularly observed in the Drake Passage and north of the Antarctic Peninsula for about 30 years, but the distribution of this species has not been updated in the literature. The observations reported here will contribute to update the at-sea distributions of these species and to changes in their distributions. Keywords: Seabirds; Antarctica; South Atlantic Ocean; distribution.
Keywords: Antarktis; Sørishavet; marin zoologi; observasjoner; ornitologi; petreller; sjøfugler

Environmental conditions, particle flux and sympagic microalgal succession in spring before the sea-ice break-up in Adélie Land, East Antarctica - Riaux-Gobin, Catherine; Dieckmann, Gerhard S; Poulin, Michel; Neveux, Jacques; Labrune, Céline; Vétion, Gilles (Polar Research, 2013)
Data pertaining to environmental conditions, sympagic (sea ice) microalgal dynamics and particle flux were collected before the spring ice break-up 2001 in Pierre Lejay Bay, adjacent to the Dumont d'Urville Station, Petrel Island, East Antarctica. An array of two multiple sediment traps and a current meter was deployed for five weeks, from 8 November to 6 December 2001. The sea-ice chlorophyll a and particulate organic carbon (POC) averaged 0.6 mg l−1 (30 mg m−2) and 20 mg l−1 (1 g m−2) near the coast. The POC export flux that reached a maximum of 79 mg m−2 d−1 during the study period was high compared to the one for the Weddell Sea. The flux was homogeneous from the surface to 47 m depth and increased sharply 33 days before the effective ice break-up. A north-western progressive vector of currents (i.e., Lagrangian drift) in the sub-ice surface waters was demonstrated. Bottom ice, platelet ice and under-ice water at 5 m were characterized by differences in colonization and short-term succession of microalgae. Keywords: Land-fast ice; oceanic short-term regime; POM flux; sympagic communities; East Antarctica.
Keywords: Sørishavet; Weddellhavet; alger; fysisk oseanografi; geokjemi; havis; sjøis; sympagisk økologi

Interpretation of new regional aeromagnetic data over Dronning Maud Land (East Antarctica) - Riedel, Sven; Jacobs, Joachim; Jokat, Wilfried (Tectonophysics, 2013)
The geology of Dronning Maud Land (East Antarctica) is so far deduced from isolated outcrops along the coast and from a major coast parallel escarpment surmounting the thick ice sheet. Large parts of Dronning Maud Land are, however, hidden underneath thick ice. In this study we attempt to connect geological information with aeromagnetic data in order to unveil the subglacial geology of this part of East Antarctica. During four austral summer campaigns (2001–2005) in Dronning Maud Land, new aeromagnetic data were gathered across an area of 1.2million square kilometers of which a portion of 65% was previously unexplored. In total 100,000 line kilometers were flown over Dronning Maud Land between 14°W/20° E and 70°S/78.5°S. A striking result was the discovery of a pronounced magnetic anomaly, named here Forster Magnetic Anomaly, east of the Jutulstraumen. It starts at approximately 72°S/007°E and strikes in southwesterly direction as far south as 75°S/1°W. The Forster Magnetic Anomaly likely forms a major tectonic block boundary and/or a suture zone within the East African–Antarctic Orogen (EAAO). The shape and distribution of other magnetic anomalies are discussed in the context of the Proterozoic to Mesozoic geological history of this part of Antarctica.
Keywords: Dronning Maud Land; innlandsis; subglasial geologi

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis

Reproductive biology of the Antarctic ‘‘sea pen’’ Malacobelemnon daytoni (Octocorallia, Pennatulacea, Kophobelemnidae) - Servetto, Natalia; Torre, Luciana; Sahade, Ricardo (Polar Research, 2013)
The reproductive biology of the sea pen Malacobelemnon daytoni was studied at Potter Cove, South Shetland Islands, where it is one of the dominant species in shallow waters. Specimens collected at 15–22 m depth were examined by histological analysis. M. daytoni is gonochoristic and exhibited a sex ratio of 1:1. Oocyte sizes (>300 µm) and the absence of embryos or newly developed larvae in the colonies suggest that this species can have lecithotrophic larvae and experience external fertilization. This life strategy is in line with other members of the group and supports the hypothesis that this could be a phylogenetically fixed trait for pennatulids. It was observed that oocytes were generated by gastrodermic tissue and released to the longitudinal canal. Thereafter, they migrate along the canal until they reach maturity and are released by autozooids at the top of the colonies. This striking feature has not yet been reported for other pennatulaceans. Mature oocytes were observed from colonies of 15 mm in length, suggesting that sexual maturity can be reached rapidly. This is contrary to what is hypothesized for the vast majority of Antarctic benthic invertebrates, namely that rates of activities associated with development, reproduction and growth are almost universally very slow. This strategy may also explain the ecological success of M. daytoni in areas with high ice impact as in the shallow waters of Potter Cove.
Keywords: Sørishavet; bentos; havbunnen; marin biologi; nesledyr; reproduksjon

Observed variations in multidecadal Antarctic sea ice trends during 1979–2012 - Simpkins, Graham R; Ciasto, Laura M; England, Matthew H (Geophysical Research Letters, 2013)
The spatiotemporal sensitivity of Antarctic sea ice season length trends are examined using satellite-derived observations over 1979–2012. While the large-scale spatial structure of multidecadal trends has varied little during the satellite record, the magnitude of trends has undergone substantial weakening over the past decade. This weakening is particularly evident in the Ross and Bellingshausen Seas, where a ∼25–50% reduction is observed when comparing trends calculated over 1979–2012 and 1979–1999. Multidecadal trends in the Bellingshausen Sea are found to be dominated by variability over subdecadal time scales, particularly the rapid decline in season length observed between 1979 and 1989. In fact, virtually no trend is detectable when the first decade is excluded from trend calculations. In contrast, the sea ice expansion in the Ross Sea is less influenced by shorter-term variability, with trends shown to be more consistent at decadal time scales and beyond. Understanding these contrasting characteristics have implications for sea ice trend attribution.
Keywords: Sørishavet; havis; klimatologi; observasjoner; satellite bilder; sjøis

Surface mass balance on Fimbul ice shelf, East Antarctica: Comparison of field measurements and large-scale studies - Sinisalo, Anna; Anschütz, Helgard; Aasen, Anne Tårånd; Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Matsuoka, Kenichi; Hamran, Svein- Erik; Øyan, Mats-Jørgen; Schlosser, Elisabeth; Hagen, Jon Ove; Nøst, Ole Anders; et al. (Journal of Geophysical Research: Atmospheres, 2013)
Many challenges remain for estimating the Antarctic ice sheet surface mass balance (SMB), which represents a major uncertainty in predictions of future sea-level rise. Validating continental scale studies is hampered by the sparse distribution of in situ data. Here we present a 26 year mean SMB of the Fimbul ice shelf in East Antarctica between 1983–2009, and recent interannual variability since 2010. We compare these data to the results of large-scale SMB studies for similar time periods, obtained from regional atmospheric modeling and remote sensing. Our in situ data include ground penetrating radar, firn cores, and mass balance stakes and provide information on both temporal and spatial scales. The 26 year mean SMB on the Fimbul ice shelf varies between 170 and 620 kg m−2 a−1 giving a regional average value of 310 ± 70 kg m−2 a−1. Our measurements indicate higher long-term accumulation over large parts of the ice shelf compared to the large-scale studies. We also show that the variability of the mean annual SMB, which can be up to 90%, can be a dominant factor in short-term estimates. The results emphasize the importance of using a combination of ground-based validation data, regional climate models, and remote sensing over a relevant time period in order to achieve a reliable SMB for Antarctica.
Keywords: Dronning Maud Land; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi

Da Norge annekterte Bouvetøya - Skagestad, Odd Gunnar (Historie (Bergen), 2013)
Keywords: Bouvetøya; historie; politikk

Hvordan Bouvetøya ble norsk - Skagestad, Odd Gunnar (UD-posten: husorgan for utenrikstjenesten, 2013)
Keywords: Bouvetøya; historie; politikk

Vår sydligste provins: Dronning Maud Land 75 år - Skagestad, Odd Gunnar (Historie (Bergen), 2013)
Keywords: Dronning Maud Land; historie; politikk

The first men on the last continent – Carsten Egeberg Borchgrevink and the Southern Cross expedition, 1898 -1900 - Smelror, Morten (Fram forum, 2013)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; første landgang; geologi; oppdagelsesreiser; overvintring

Trends in Antarctic ecological research in Latin America shown by publications in international journals - Stotz, Gisela C; Salgado-Luarte, Cristian; Rios, Rodrigo S; Acuña-Rodriguez, Ian S; Carrasco-Urra, Fernando; Molina-Montenegro, Marco A; Gianoli, Ernesto (Polar Research, 2013)
Antarctica is a highly interesting region for ecologists because of its extreme climatic conditions and the uniqueness of its species. In this article, we describe the trends in Antarctic ecological research participation by Latin American countries. In a survey of articles indexed by the ISI Web of Science, we searched under the categories ‘‘Ecology,’’ ‘‘Biodiversity Conservation’’ and ‘‘Evolutionary Biology’’ and found a total of 254 research articles published by Latin American countries. We classified these articles according to the country of affiliation, kingdom of the study species, level of biological organization and environment. Our main finding is that there is a steady increase in the relative contribution of Latin American countries to Antarctic ecological research. Within each category, we found that marine studies are more common than terrestrial studies. Between the different kingdoms, most studies focus on animals and most studies use a community approach. The leading countries in terms of productivity were Argentina, Chile and Brazil, with Argentina showing the highest rate of increase. Keywords: Antarctica; Argentina; Brazil; Chile; research trends; scientific productivity.
Keywords: Antarktis; biodiversitet; forskning; vitenskap; økologi

Sources and geographic heterogeneity of trace metals in the sediments of Prydz Bay, East Antarctica - Sun, Wei-Ping; Hu, Chuan-Yu; Weng, Huan-Xin; Han, Zheng-Bing; Shen, Chen; Pan, Jian-Ming (Polar Research, 2013)
In this study, we have determined the contents and distribution of zinc and cadmium in the surface sediments from Prydz Bay, East Antarctica. The main sources of the trace elements and their geographic heterogeneity, and the relation between Zn and Cd, are discussed based on the cluster analysis, principle component analysis and considerations of biogenic and lithogenic inputs. The results show that the contents of trace metals range from 34.6 to 96.6 mg kg-1 for Zn, and from 0.254 to 0.441 mg kg-1 for Cd. Calculations of the enrichment factor indicated no significant anthropogenic impact. Biogenic and lithogenic inputs are the main sources of trace metals. They are almost equal for Zn and Cd at the Amery Ice Shelf edge, while the continental shelf and deep ocean are dominated by biogenic inputs. The contribution of biogenic inputs is much higher for Zn than for Cd at the deep ocean. Calculations of biogenic trace metals revealed different relationships between biogenic Zn and biogenic Cd, which reflect the biological uptake by phytoplankton in the water column. Keywords: Trace elements; sources; enrichment factor; cluster analysis; principal component analysis; Antarctica.
Keywords: Sørishavet; fytoplankton; geografi; kjemiske analyser; kontinentalmargin; kontinentalsokkel; marin biologi; oseanografi; sedimenter; sedimentologi

Inorganic C utilization and C isotope fractionation by pelagic and sea ice algal assemblages along the Antarctic continental shelf - Tortell, Philippe D; Mills, Mathew M; Payne, Christopher D; Maldonado, Maria T; Chierici, Melissa; Fransson, Agneta; Alderkamp, Anne-Carlijn; Arrigo, Kevin R (Marine Ecology Progress Series, 2013)
Physiological characteristics of inorganic C uptake were examined in Southern Ocean ice algae and phytoplankton assemblages. Ice algal and phytoplankton assemblages were largely dominated by diatoms and Phaeocystis antarctica, and showed a high capacity for HCO3- utilization, with direct HCO3- transport accounting for ~60% of total inorganic C uptake. Extracellular carbonic anhydrase (eCA) was detectable in all samples, but with significantly lower activity in sea ice algae. Neither HCO3- transport nor eCA activity was related to the in situ partial pressure of CO2 (pCO2) or taxonomic composition of samples. The half-saturation constant (KS) for inorganic C ranged from ~100 to 5000 µM, and showed significantly more variability among sea ice algae than phytoplankton assemblages. For the phytoplankton assemblages, there were significant positive correlations between in situ pCO2 and KS (higher C substrate affinity in low pCO2 waters), and also between KS and maximum C uptake rates (Vmax). In contrast, KS and Vmax in sea-ice algal assemblages were not correlated to each other, or to any other measured variables. The C isotope composition of particulate organic carbon(δ13C-POC) in the phytoplankton assemblages showed modest variability (range -30 to -24.6‰) and was significantly correlated to the ratio of inferred growth rates (derived from Vmax) and in situ CO2 concentrations, but not to any measured C uptake parameters. δ13C-POC in sea ice algal samples (range -25.7 to -12.9‰) was significantly heavier than in the phytoplankton assemblages, and not correlated to any other variables. Our results provide evidence for the widespread occurrence of carbon-concentrating mechanisms in Southern Ocean sea ice algae and phytoplankton assemblages. KEYWORDS: Phytoplankton · Sea ice algae · Inorganic carbon uptake · HCO3- · Carbonic anhydrase
Keywords: Sørishavet; alger; biokjemi; diatomeer; fytoplankton; kjemiske analyser; kontinentalsokkel; marin biologi

Characterization and mapping of plant communities at Hennequin Point, King George Island, Antarctica - Victoria, Filipe de C; de Albuquerque, Margéli P; Pereira, Antonio B; Simas, Felipe N B; Spielmann, Adriano A; Schaefer, Carlos E G R (Polar Research, 2013)
King George Island is the largest island and the principal area used for research bases in Antarctica. Argentina, Brazil, Chile, China, Poland, Russia, South Korea and Uruguay have permanent open bases on this island. Other countries have seasonal summer stations on different parts of this island, which demonstrates that human impact is strong on King George Island relative to other areas in the maritime and continental Antarctica. The objective of this work was to present a phytosociological approach for ice-free areas of Hennequin Point, eastern coast of Admiralty Bay, King George Island. The study started with the classification and description of the plant communities based primarily on phytosociological and biodiversity data. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The plant communities were described as follows: (1) lichen and moss cushion formation; (2) moss carpet formation; (3) fellfield formation; (4) grass and cushion chamaephyte formation; and (5) Deschampsia Antarctica–lichen formation. Characterizations and distributions of the plant communities are presented on a map at a scale of 1:5000. The plant communities found at Hennequin Point, in general, differ from those found in other areas of the Admiralty Bay region, probably because of the concentration of skua nests in the area and the relief singularities. We conclude by highlighting the importance of the study of plant species found in the ice-free areas of the Antarctic with respect to environmental monitoring and for evaluating global climate and environmental changes. Keywords: Plant communities mapping; lichens; mosses; flowering plants; Antarctic
Keywords: Antarktis; biodiversitet; fytososiologi; klimaendringer; lav; miljøendringer; moser; planter; plantesosiologi

Isolation and description of a globally distributed cryosphere cyanobacterium from Antarctica - Won Hong, Ji; Kim, Sung Hong; Choi, Han-Gu; Kang, Sung-Ho; Yoon, Ho-Sung (Polar Research, 2013)
A previously uncultured cyanobacterium, strain KNUA009, was axenically isolated from a meltwater stream on Barton Peninsula, King George Island, South Shetland Islands, Antarctica. Molecular evidences showed that the isolate belongs to groups of globally distributed cryosphere cyanobacterial clones and this new isolate represents the first laboratory culture to be assigned to these groups. Strain KNUA009 was able to thrive at low temperatures ranging between 5°C and 20°C, but did not survive at temperatures of 25°C and above. As the isolate morphologically resembled Oscillatoria species, it is suggested that this cyanobacterium may represent a new species clade with cold resistance within the genus Oscillatoria. Keywords: Barton Peninsular; cryosphere cyanobacteria; King George Island; uncultured Oscillatoria species.
Keywords: Antarktis; bakterier; biologi; ferskvann; fylogenetikk

Seasonal inflow of warm water onto the southern Weddell Sea continental shelf, Antarctica - Årthun, Marius; Nicholls, Keith William; Makinson, Keith; Fedak, Michael A; Boehme, Lars (Geophysical Research Letters, 2012)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi

Den japanske antarktisekspedisjonen i 1912 - Barr, Susan (Polarboken, 2012)
Keywords: Antarktis; ekspedisjoner; historie

Can we use ice sheet reconstructions to constrain meltwater for deglacial simulations? - Bethke, Ingo; Li, Camille; Nisancioglu, Kerim H (Paleoceanography, 2012)
Freshwater pulses from melting ice sheets are thought to be important for driving deglacial climate variability. This study investigates challenges in simulating and understanding deglacial climate evolution within this framework, with emphasis on uncertainties in the ocean overturning sensitivity to meltwater inputs. The response of an intermediate complexity model to a single Northern Hemisphere meltwater pulse is familiar: a weakening of the ocean overturning circulation in conjunction with an expansion of sea ice cover and a meridional temperature seesaw. Nonlinear processes are vital in shaping this response and are found to have a decisive influence when more complex scenarios with a history of pulses are involved. A meltwater history for the last deglaciation (21–9 ka) was computed from the ICE-5G ice sheet reconstruction, and the meltwater was routed into the ocean through idealized ice sheet drainages. Forced with this meltwater history, model configurations with altered freshwater sensitivity produce a range of outcomes for the deglaciation, from those in which there is a complete collapse of the overturning circulation to those in which the overturning circulation weakens slightly. The different outcomes are interpreted in terms of the changing hysteresis behavior of the overturning circulation (i.e., non-stationary freshwater sensitivity) as the background climate warms through the course of the deglaciation. The study illustrates that current uncertainties in model sensitivity are limiting in efforts to forward-model deglacial climate variability. Furthermore, ice sheet reconstructions are shown to provide poor constraints on meltwater forcing for simulating the deglaciation.
Keywords: Sørishavet; global oppvarming; havnivåstigning; innlandsis; isavsmelting; klimamodeller; klimatologi; polarområdene; smeltevann

Roald Amundsen: Forsker eller grobian? - Blix, Arnoldus Schytte (Nordisk tidskrift för vetenskap, konst och industri, 2012)
Roald Amundsens (1872-1928) liv og bedrifter er fremstilt i en rekke biografier, men det er oppdageren og eventyreren som blir tillagt mest vekt, mens vitenskapsmannen og forskeren tidvis underkjennes. Professor i arktisk biologi ved Universitetet i Tromsø, Arnoldus Schytte Blix, er kritisk til mye av det biografiske arbeidet som er gjort, og mener det er et åpent spørsmål om kontorhistorikere og journalister har noen reell mulighet til fullt ut å forstå Roald Amundsens situasjon og reaksjoner. Artikkelen er basert på et foredrag med en rekke illustrasjoner i Det Norske Videnskabs-Akademi, 17. november 2011.
Publisher: Föreningen Norden Place: Stockholm
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; biografier; oppdagelsesreiser

Ecosystem response to climatic change: the importance of the cold season - Bokhorst, Stef; Bjerke, Jarle W; Tømmervik, Hans; Preece, Catherine; Phoenix, Gareth K (Ambio, 2012)
Winter climate and snow cover are the important drivers of plant community development in polar regions. However, the impacts of changing winter climate and associated changes in snow regime have received much less attention than changes during summer. Here, we synthesize the results from studies on the impacts of extreme winter weather events on polar heathland and lichen communities. Dwarf shrubs, mosses and soil arthropods were negatively impacted by extreme warming events while lichens showed variable responses to changes in extreme winter weather events. Snow mould formation underneath the snow may contribute to spatial heterogeneity in plant growth, arthropod communities and carbon cycling. Winter snow cover and depth will drive the reported impacts of winter climate change and add to spatial patterns in vegetation heterogeneity. The challenges ahead lie in obtaining better predictions on the snow patterns across the landscape and how these will be altered due to winter climate change.
Publisher: Springer Netherlands
Keywords: Antarktis; biologi; botanikk; dyr; klimaendringer; leddyr; planter; snø; sopper; zoologi; økosystemer

Environmental monitoring and management proposals for the Fildes Region, King George Island, Antarctica - Braun, Christina; Mustafa, Osama; Nordt, Anja; Pfeiffer, Simone; Peter, Hans-Ulrich (Polar Research, 2012)
The Antarctic terrestrial environment is under increasing pressure from human activities. The Fildes Region is characterized by high biodiversity, but is also a major logistic centre for the northern Antarctic Peninsula. Different interests, from scientific research, nature conservation, protection of geological and historical values, station operations, transport logistics and tourism, regularly overlap in space and time. This has led to increasing conflict among the multiple uses of the region and breaches of the legal requirements for environmental protection that apply in the area. The aim of this study was to assess the impacts of human activities in the Fildes Region by monitoring the distribution of bird and seal breeding sites and recording human activities and their associated environmental impacts. Data from an initial monitoring period 200306 were compared with data from 200810. We observed similar or increased levels of air, land and ship traffic, but fewer violations of overflight limits near Antarctic Specially Protected Area No. 150 Ardley Island. Open waste dumping and oil contamination are still major environmental impacts. Scientific and outdoor leisure activities undertaken by station personnel are more frequent than tourist activities and are likely to have a commensurate level of environmental impact. Despite the initial success of some existing management measures, it is essential that scientific and environmental values continue to be safeguarded, otherwise environmental impacts will increase and the habitat will be further degraded. We argue that the Fildes Region should be considered for designation as an Antarctic Specially Managed Area, a measure that has proven effective for environmental management of vulnerable areas of the Antarctic.
Keywords: Antarktis; biodiversitet; miljøvern

The effect of energetic electron precipitation on middle mesospheric night-time ozone during and after a moderate geomagnetic storm - Daae, Marianne; Espy, Patrick J; Nesse Tyssøy, Hilde; Newnham, David A; Stadsnes, Johan; Søraas, Finn (Geophysical Research Letters, 2012)
Using a ground-based microwave radiometer at Troll Station, Antarctica (72°S, 2.5°E,L = 4.76), we have observed a decrease of 20–70% in the mesospheric ozone, coincident with increased nitric oxide, between 60 km and 75 km altitude associated with energetic electron precipitation (E > 30 keV) during a moderate geomagnetic storm (minimum Dst of −79 nT) in late July 2009. NOAA satellite data were used to identify the precipitating particles and to characterize their energy, spatial distribution and temporal variation over Antarctica during this isolated storm. Both the ozone decrease and nitric oxide increase initiate with the onset of the storm, and persist for several days after the precipitation ends, descending in the downward flow of the polar vortex. These combined data present a unique case study of the temporal and spatial morphology of chemical changes induced by electron precipitation during moderate geomagnetic storms, indicating that these commonplace events can cause significant effects on the middle mesospheric ozone distribution.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; mikrobølge; ozonlaget; radiometer

Feeding grounds of the eastern South Pacific humpback whale population include the South Orkney Islands - Dalla Rosa, Luciano; Félix, Fernando; Stevick, Peter T; Secchi, Eduardo R; Allen, Judith M; Chater, Kim; Martin, Anthony R; Basso, Manuela (Polar Research, 2012)
This paper reports on two photo-identified humpback whales (Megaptera novaeangliae) that were sighted in different years in the proximity of the South Orkney Islands, at the boundary between the Scotia and Weddell seas (60o54.5’S – 46o40.4’W and 60o42.6’S – 45o33’W). One of the whales had been previously sighted off Ecuador, a breeding ground for the eastern South Pacific population. The other whale was subsequently resighted in Bransfield Strait, off the western Antarctic Peninsula, a well-documented feeding ground for the same population. These matches give support to a hypothesis that the area south of the South Orkney Islands is occupied by whales from the eastern South Pacific breeding stock. Consequently, we propose 40oW as a new longitudinal boundary between the feeding grounds associated with the eastern South Pacific and western South Atlantic breeding stocks. Keywords: Humpback whale; photo-identification; breeding stocks; migration; South Orkney Islands; Southern Ocean
Keywords: Rosshavet; Sørishavet; knølhvaler; marin zoologi; migrasjon; oseanografi

Aerosol-Mediated Transport and Deposition of Brominated Diphenyl Ethers to Antarctica - Dickhut, Rebecca M; Cincinelli, Alessandra; Cochran, Michele; Kylin, Henrik (Environmental Science & Technology, 2012)
Brominated diphenyl ethers (BDE47, 99, 100, and 209) were measured in air, snow and sea ice throughout western Antarctica between 2001 and 2007. BDEs in Antarctic air were predominantly associated with aerosols and were low compared to those in remote regions of the northern hemisphere, except in Marguerite Bay following the fire at Rothera research station in Sept 2001, indicating that this event was a local source of BDE209 to the Antarctic environment. Aerosol BDE47/100 reflects a mixture of commercial pentaBDE products; however, BDE99/100 is suggestive of photodegradation of BDE99 during long-range atmospheric transport (LRAT) in the austral summer. BDEs in snow were lower than predicted based on snow scavenging of aerosols indicating that atmospheric deposition events may be episodic. BDE47, -99, and -100 significantly declined in Antarctic sea ice between 2001 and 2007; however, BDE209 did not decline in Antarctic sea ice over the same time period. Significant losses of BDE99 and -100 from sea ice were recorded over a 19 day period in spring 2001 demonstrating that seasonal ice processes result in the preferential loss of some BDEs. BDE47/100 and BDE99/100 in sea ice samples reflect commercial pentaBDE products, suggesting that photodegradation of BDE99 is minimal during LRAT in the austral winter.
Publisher: American Chemical Society
Keywords: Antarktis; Sørishavet; atmosfæren; forurensning; miljøgifter; polarområdene

Low genetic diversity in Antarctic populations of the lichenforming ascomycete Cetraria aculeata and its photobiont - Domaschke, Stephanie; Fernández-Mendoza, Fernando; Garcia, Miquel A; Martín, Maria P; Printzen, Christian (Polar Research, 2012)
Lichens, symbiotic associations of fungi (mycobionts) and green algae or cyanobacteria (photobionts), are poikilohydric organisms that are particularly well adapted to withstand adverse environmental conditions. Terrestrial ecosystems of the Antarctic are therefore largely dominated by lichens. The effects of global climate change are especially pronounced in the maritime Antarctic and it may be assumed that the lichen vegetation will profoundly change in the future. The genetic diversity of populations is closely correlated to their ability to adapt to changing environmental conditions and to their future evolutionary potential. In this study, we present evidence for low genetic diversity in Antarctic mycobiont and photobiont populations of the widespread lichen Cetraria aculeata. We compared between 110 and 219 DNA sequences from each of three gene loci for each symbiont. A total of 222 individuals from three Antarctic and nine antiboreal, temperate and Arctic populations were investigated. The mycobiont diversity is highest in Arctic populations, while the photobionts are most diverse in temperate regions. Photobiont diversity decreases significantly towards the Antarctic but less markedly towards the Arctic, indicating that ecological factors play a minor role in determining the diversity of Antarctic photobiont populations. Richness estimators calculated for the four geographical regions suggest that the low genetic diversity of Antarctic populations is not a sampling artefact. Cetraria aculeata appears to have diversified in the Arctic and subsequently expanded its range into the Southern Hemisphere. The reduced genetic diversity in the Antarctic is most likely due to founder effects during long-distance colonization. The environmental conditions of the Antarctic are among the most adverse on Earth and are generally characterized by low mean annual temperatures, high wind velocities, extreme drought and extended periods of darkness. The effects of global climate change are especially pronounced in parts of the Antarctic (Turner et al. 2005). Air temperature in the maritime Antarctic has steadily increased within the last years (Smith & Stammerjohn 1996; Turner et al. 2005). On the western Antarctic Peninsula a temperature increase of more than 2.5 K has been observed over the last 50 years. The overall effect of such a temperature increase on terrestrial Antarctic organisms could be beneficial. For example, glacial melting will increase the availability of terrestrial (page number not for citation purpose). Keywords Genetic diversity; lichens; Cetraria aculeata; Trebouxia jamesii; polar lichens; global change.
Keywords: Antarktis; alger; fotobiont; genetisk mangfold; klimaendringer; lav; sopper; økosystemer

Leadership in politics and science within the Antarctic Treaty - Dudeney, John R; Walton, David W H (Polar Research, 2012)
For over 50 years the Antarctic has been governed through the Antarctic Treaty, an international agreement now between 49 nations of whom 28 Consultative Parties (CPs) undertake the management role. Ostensibly, these Parties have qualified for their position on scientific grounds, though diplomacy also plays a major role. This paper uses counts of policy papers and science publications to assess the political and scientific outputs of all CPs over the last 18 years. We show that a subset of the original 12 Treaty signatories, consisting of the seven claimant nations, the USA and Russia, not only set the political agenda for the continent but also provide most of the science, with those CPs producing the most science generally having the greatest political influence. None of the later signatories to the Treaty appear to play a major role in managing Antarctica compared with this group, with half of all CPs collectively producing only 7% of the policy papers. Although acceptance as a CP requires demonstration of a substantial scientific programme, the Treaty has no formal mechanism to review whether a CP continues to meet this criterion. As a first step to addressing this deficiency, we encourage the CPs collectively to resolve to hold regular international peer reviews of their individual science programmes and to make the results available to the other CPs. Keywords: Governance; claimant states; Antarctic policy; scientific publications.
Keywords: Antarktis; Antarktistraktaten; forvaltning; politikk; vitenskap

Southern Weddell Sea shelf edge geomorphology: Implications for gully formation by the overflow of high-salinity water - Gales, Jennifer A; Larter, Robert David; Mitchell, Neil; Hillenbrand, Claus-Dieter; Østerhus, Svein; Shoosmith, Deb R (Journal of Geophysical Research: Earth Surface, 2012)
Keywords: Sørishavet; Weddellhavet; forskning; geomorfologi; isshelf; oseanografi

Correlative and dynamic species distribution modelling for ecological predictions in the Antarctic: a cross-disciplinary concept - Gutt, Julian; Zurell, Damaris; Bracegridle, Thomas J; Cheung, William; Clark, Melody S; Convey, Peter; Danis, Bruno; David, Bruno; De Broyer, Claude; di Prisco, Guido; Griffiths, Huw; Laffont, Rémi; et al. (Polar Research, 2012)
Keywords: Antarktis; biodiversitet; biosfære; miljø; oseanografi; økologi; økosystemer

Two years of oceanic observations below the Fimbul Ice Shelf, Antarctica - Hattermann, Tore; Nøst, Ole Anders; Lilly, Jonathan M; Smedsrud, Lars H (Geophysical Research Letters, 2012)
The mechanisms by which heat is delivered to Antarctic ice shelves are a major source of uncertainty when assessing the response of the Antarctic ice sheet to climate change. Direct observations of the ice shelf-ocean interaction are extremely scarce and in many regions melt rates from ice shelf-ocean models are not constrained by measurements. Our two years of data (2010 and 2011) from three oceanic moorings below the Fimbul Ice Shelf in the Eastern Weddell Sea show cold cavity waters, with average temperatures of less than 0.1°C above the surface freezing point. This suggests low basal melt rates, consistent with remote sensing-based, steady-state mass balance estimates for this sector of the Antarctic coast. Oceanic heat for basal melting is found to be supplied by two sources of warm water entering below the ice: (i) eddy-like bursts of Modified Warm Deep Water that access the cavity at depth for eight months of the record; and (ii) fresh surface water that flushes parts of the ice base with temperatures above freezing during late summer and fall. This interplay of processes implies that basal melting at the Fimbul Ice Shelf cannot simply be parameterized by coastal deep ocean temperatures, but instead appears directly linked to both solar forcing at the surface as well as to the dynamics of the coastal current system.
Keywords: Sørishavet; Weddellhavet; fysisk oseanografi; innlandsis; isbrem; isshelf; klimaendringer; smelting

Review of Race for the South Pole: the expedition diaries of Scott and Amundsen, by Roland Huntford - Jølle, Harald Dag (Polar Research, 2012)
Roland Huntford is the grand old man among polar historians. After his classic Scott and Amundsen in 1979 (later editions were retitled, The last place on Earth), he wrote a series of books on Norwegian and British polar heroes as well as a thorough study of the history of skiing (2006). Huntford challenged the British admiration of Robert Falcon Scott’s scientific programme and great courage*and insisted that Roald Amundsen’s expedition was far better prepared and carried out. Huntford’s scathing criticism of Scott’s fatal choices and lack of competence dared to assault this cherished British polar icon in a manner that would be unthinkable for Norwegian authors.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; Sørpolen; bokanmeldelser; dagbøker; kappløpet; polarhistorie; polarområdene

The South Pole expedition of Roald Amundsen: how did he prepare for the expedition and what do his crewmembers' diaries tell us about it? / Geir O. Kløver. - Kløver, Geir Olav (Nimrod : the Journal of the Ernest Shackleton Autumn School, 2012)
Describes Amundsen's experience on de Gerlache's 1897-99 Belgica Antarctic expedition, scientific interests, lessons learned on his 1903-06 Gjøa Northwest Passage expedition, and experience on 1910-12 Fram Antarctic expedition. Gives details of crew members on Antarctic expedition with account of their diaries. Author is director of Fram Museum and editor of South Pole diaries of Amundsen and fourteen of his crew members.
Keywords: Antarktis; Belgica ekspedisjon; Sydpolsekspedisjonen; dagbøker; polarhistorie

Antarctic krill swarm characteristics in the Southeast Atlantic sector of the Southern Ocean - Krafft, Bjørn A.; Skaret, Georg; Knutsen, Tor; Melle, Webjørn; Klevjer, Thor; Søiland, Henrik (Marine ecology. Progress series, 2012)
Knowledge about swarm dynamics and underlying causes is essential to understand the ecology and distribution of Antarctic krill . We collected acoustic data and key environmental data continuously across extensive gradients in the little-studied Southeast Atlantic sector of the Southern Ocean. A total of 4791 krill swarms with swarm descriptors including swarm height and length, packing density, swimming depth and inter-swarm distance were extracted. Through multivariate statistics, swarms were categorized into 4 groups. Group 2 swarms were largest (median length 108 m and thickness 18 m), whereas swarms in both Groups 1 and 4 were on average small, but differed markedly in depth distribution (median: 52 m for Group 1 vs. 133 m for Group 4). There was a strong spatial autocorrelation in the occurrence of swarms, and an autologistic regression model found no prediction of swarm occurrence from environmental variables for any of the Groups 1, 2 or 4. Probability of occurrence of Group 3 swarms, however, increased with increasing depth and temperature. Group 3 was the most distinctive swarm group with an order of magnitude higher packing density (median: 226 ind. m ) than swarms from any of the other groups and about twice the distance to nearest neighbor swarm (median: 493 m). The majority of the krill were present in Group 3 swarms, and the absence of association with hydrographic or topographic concentrating mechanisms strongly suggests that these swarms aggregate through their own locomotion, possibly associated with migration.
Publisher: Inter-Research
Keywords: Bouvetøya; Sørishavet; datainnsamling; ekkolodd; krill; marin biologi; plankton; økologi

Perspective: Strategic challenges of tourism development and governance in Antarctica: taking stock and moving forward - Lamers, Machiel; Liggett, Daniela; Amelung, Bas (Polar Research, 2012)
Keywords: Antarktis; forvaltning; turisme

Deciphering the role of southern gateways and carbon dioxide on the onset of the Antarctic Circumpolar Current - Lefebvre, Vincent; Donnadieu, Yannick; Sepulchre, Pierre; Swingedouw, Didier; Zhang, Zhong-Shi (Paleoceanography, 2012)
Growth of Antarctic ice sheet during the Cenozoic 34 million years ago appears as a potential tipping point in the long term cooling trend that began 50 Ma ago. For decades, the onset of the Antarctic Circumpolar Current (ACC) following the opening of the Drake Passage and of the Tasman Seaway has been suggested as the main driver of the continental-scale Antarctic glaciation. However, recent modeling works emphasized that the Eocene/Oligocene atmospheric carbon dioxide (CO2) lowering could be the primary forcing of the Antarctic glaciation, questioning the ACC theory. Here, we investigate the response of the ACC to changes in CO2concentrations occurring from the late Eocene to the late Oligocene. We used a fully coupled atmosphere-ocean model (FOAM) with a mid-Oligocene geography. We find that the opening of southern oceanic gateways does not trigger the onset of the ACC for CO2typical of the late Eocene (>840 ppm). A cooler background climatic state such as the one prevalent at the end of the Oligocene is required to simulate a well-developed ACC. In this cold configuration, the intensified sea-ice development around Antarctica and the resulting brine formation lead to a strong latitudinal density gradient in the Southern Ocean favoring the compensation of the Ekman transport, and consequently the ACC. Our results imply that the ACC has acted as a feedback rather than as a driver of the global cooling.
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; karbondioksid; klimatologi; paleogeografi

Spatial variation of englacial radar attenuation: Modeling approach and application to the Vostok flowline - MacGregor, Joseph A.; Matsuoka, Kenichi; Waddington, Edwin D.; Winebrenner, Dale P.; Pattyn, Frank (Journal of Geophysical Research: Earth Surface, 2012)
Constraining the spatial variation of englacial radar attenuation is critical for accurate inference of the spatial variation of the englacial and basal properties of ice sheets from radar returned power. Here we evaluate attenuation models that account for spatial variations in ice temperature and chemistry and test them along the flowline that passes through the Vostok ice core site, Antarctica. The simplest model, often used but rarely valid, assumes a uniform attenuation rate everywhere along the flowline, so that total attenuation is proportional to ice thickness. The next simplest model uses spatially varying temperatures predicted by an ice-flow model and assumes uniform chemistry. Additional models account for spatially varying chemistry using englacial stratigraphy. We find that the roundtrip attenuation to the bed can easily differ by 10 dB or more between the uniform attenuation-rate model and models that account for variable ice temperature. Such differences are sufficient to confound the delineation of dry and wet beds. Also including spatial variations in chemistry produces smaller differences (<10 dB), but the magnitude of these differences depends on the relative importance of dry and wet deposition of impurities in the past. Accounting for dry-deposited impurities requires ice-flow modeling and results in larger differences from all other models, which assume uniform chemistry or wet deposition only. These results indicate that modeling the spatial variation of attenuation requires a spatially varying temperature model in order to infer bed conditions from bed returned power accurately, and that both ice core data and radar stratigraphy are also strongly desirable.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis

Radar characterization of the basal interface across the grounding zone of an ice-rise promontory in East Antarctica - Matsuoka, Kenichi; Pattyn, Frank; Callens, Denis; Conway, Howard (Annals of Glaciology, 2012)
Radar power returned from the basal interface along a 42 km long profile over an ice-rise promontory and the adjacent Roi Baudouin ice shelf, Dronning Maud Land, East Antarctica, is analyzed to infer spatial variations in basal reflectivity and hence the basal environment. Extracting basal reflectivity from basal returned power requires an englacial attenuation model. We estimate attenuation in two ways: (1) using a temperature-dependent model with input from thermomechanical ice-flow models; and (2) using a radar method that linearly approximates the geometrically corrected returned power with ice thickness. The two methods give different results. We argue that attenuation calculated using a modeled temperature profile is more robust than the widely used radar method, especially in locations where depth-averaged attenuation varies spatially or where the patterns of basal reflectivity correlate with the patterns of the ice thickness.
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf

Rapid development of anisotropic ice-crystal-alignment fabrics inferred from englacial radar polarimetry, central West Antarctica - Matsuoka, Kenichi; Power, Donovan; Fujita, Shuji; Raymond, Charles F (Journal of Geophysical Research: Earth Surface, 2012)
Anisotropy in englacial radar power was measured using 60-MHz and 179-MHz copolarized pulse-modulated radar at 19 sites in central West Antarctica. The study region is a 100 × 300 km2area near the West Antarctic Ice Sheet Divide that separates ice flow toward the Ross and Amundsen Embayments. The frequency dependence of the returned power indicates that most of the radar data are affected by vertical variations in the crystal-orientation fabric (COF), though the 60-MHz data are more affected by acidity contrasts in the top 1000 m. Significant polarimetric variations occur at most sites, likely due to effects of the anisotropic COF patterns. More anisotropic variations occur at sites with significant horizontal strain, whereas more isotropic variations occur at sites where vertical compression dominates. Azimuthal shifts with depth of the principal axes of COF were found in shallow ice near the current flow divide and at greater depths over locations of rough bed. The former indicates that the divide has differentially migrated, resulting in a rotation of the principal COF axes. Nevertheless, the regionally consistent radar signatures suggest that the first-order ice properties in this area have remained constant and that no major changes in the strain configuration or ice topography have occurred for the past five to eight thousand years. We conclude that shallow polarimetric features can be related to the current strain configurations, and that englacial polarimetric features can help constrain current ice rheology and evolution of the ice topography.
Keywords: Antarktis; glasiologi; innlandsis; iskrystaller; polarimetrisk radar; topografi

Review of A complete guide to Antarctic wildlife: birds and mammals of the Antarctic Continent and the Southern Ocean, by Hadoram Shirihai - Mehlum, Fridtjof (Polar Research, 2012)
This impressive book is an invaluable, fully illustrated, wildlife guide for tourists and scientists visiting the Southern Ocean and Antarctica.
Keywords: Antarktis; Sørishavet; bokanmeldelser; dyreliv; fugler; marin biologi; ornitologi; pattedyr; zoologi

Polar operations in Antarctica – operating the Troll Research Station, Dronning Maud Land - Mikelborg, Øystein; Pedersen, Ken (Fram forum, 2012)
Keywords: Dronning Maud Land; Troll forskningsstasjon; ekspedisjoner; logistikk; polarområdene

The oldest elasmosaurs (Sauropterygia, Plesiosauria) from Antarctica, Santa Marta Formation (upper Coniacian? Santonian-upper Campanian) and Snow Hill Island Formation (upper Campanian-lower Maastrichtian), James Ross Island - O'Gorman, José P (Polar Research, 2012)
Elasmosaurs are recorded for the first time in the Lachman Crags Member (Beta Member) of the Santa Marta Formation (lower Campanian) and in the Herbert Sound Member of the Snow Hill Island Formation (upper Campanian). These are the first elasmosaurids from James Ross Island, Antarctic Peninsula. These records greatly improve our knowledge of the taxonomic diversity of plesiosaurs of the Santa Marta Formation and Herbert Sound Member of the Snow Hill Island Formation, and extend the lower limit of the record of Elasmosauridae in Antarctica to the lower Campanian, making this the oldest record of an Antarctic elasmosaur. Keywords: Elasmosauridae; Antarctica; Late Cretaceous.
Keywords: Antarktis; geologi; paleontologi

Atmospheric mercury observations from Antarctica: seasonal variation and source and sink region calculations - Pfaffhuber, Katrine Aspmo; Berg, Torunn; Hirdman, D; Stohl, Andreas (Atmospheric Chemistry and Physics (Print), 2012)
Long term atmospheric mercury measurements in the Southern Hemisphere are scarce and in Antarctica completely absent. Recent studies have shown that the Antarctic continent plays an important role in the global mercury cycle. Therefore, long term measurements of gaseous elemental mercury (GEM) were initiated at the Norwegian Antarctic Research Station, Troll (TRS) in order to improve our understanding of atmospheric transport, transformation and removal processes of GEM. GEM measurements started in February 2007 and are still ongoing, and this paper presents results from the first four years. The mean annual GEM concentration of 0.93 ± 0.19 ng m−3 is in good agreement with other recent southern-hemispheric measurements. Measurements of GEM were combined with the output of the Lagrangian particle dispersion model FLEXPART, for a statistical analysis of GEM source and sink regions. It was found that the ocean is a source of GEM to TRS year round, especially in summer and fall. On time scales of up to 20 days, there is little direct transport of GEM to TRS from Southern Hemisphere continents, but sources there are important for determining the overall GEM load in the Southern Hemisphere and for the mean GEM concentration at TRS. Further, the sea ice and marginal ice zones are GEM sinks in spring as also seen in the Arctic, but the Antarctic oceanic sink seems weaker. Contrary to the Arctic, a strong summer time GEM sink was found, when air originates from the Antarctic plateau, which shows that the summertime removal mechanism of GEM is completely different and is caused by other chemical processes than the springtime atmospheric mercury depletion events. The results were corroborated by an analysis of ozone source and sink regions.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; miljøgifter; ozonlaget

Being there: examining the behaviour of Antarctic tourists through their blogs - Roura, Ricardo M (Polar Research, 2012)
Most visitors to Antarctica today are commercial tourists. Over 150 000 tourists visited Antarctica between 2007 and 2010, making up more than 700 000 person/landings. Despite the scale of tourism in Antarctica, knowledge about its environmental impacts is generally inconclusive, and monitoring is limited. This article examines tourist behaviour regarding the environment using information available on travel weblogs (blogs) posted by tourists on the Internet. Fifty blogs describing Antarctic travel were analysed, mostly as part of organized tourism cruises, during the four Antarctic summer seasons between 2007 and 2010, both qualitatively and quantitatively. The blogs described the activities of 90 people who had visited Deception Island as part of their itinerary and who, overall, had undertaken at least 190 person/landings in Antarctica. Blog analysis highlighted the importance of wildlife as a tourist attraction. In the blogs it was apparent that touristwildlife interactions result in a range of behaviours from both individual tourists and animals. Tourism results in cultural traces and other environmental consequences, although some of these would not be judged as ‘‘impacts’’ under the current practice of implementing the Protocol on Environmental Protection to the Antarctic Treaty. Blogs showed many more instances of compliance than of noncompliance with environmental regulations. Tourist blogs illustrate the behavioural processes by which environmental impacts from tourism could occur, which are repeated through thousands of person-landings and other activities in Antarctica every season. Precautionary action may be a practical alternative to manage tourism at some sites until it is clearer how this activity affects the environment.
Keywords: Antarktis; miljøvern; polarområdene; turisme

Extent of low-accumulation 'wind glaze' areas on the East Antarctic plateau: implications for continental ice mass balance - Scambos, Ted A; Frezzotti, Massimo; Haran, T; Bohlander, J; Lenaerts, Jan T M; Van Den Broeke, M R; Jezek, K; Long, D; Urbini, S; Farness, K; Neumann., T; Albert, M; et al. (Journal of Glaciology, 2012)
Persistent katabatic winds form widely distributed localized areas of near-zero net surface accumulation on the East Antarctic ice sheet (EAIS) plateau. These areas have been called 'glaze' surfaces due to their polished appearance. They are typically 2-200 km2 in area and are found on leeward slopes of ice-sheet undulations and megadunes. Adjacent, leeward high-accumulation regions (isolated dunes) are generally smaller and do not compensate for the local low in surface mass balance (SMB). We use a combination of satellite remote sensing and field-gathered datasets to map the extent of wind glaze in the EAIS above 1500 m elevation. Mapping criteria are derived from distinctive surface and subsurface characteristics of glaze areas resulting from many years of intense annual temperature cycling without significant burial. Our results show that 11.2 ± 1.7%, or 950 ± 143 × 103km2, of the EAIS above 1500 m is wind glaze. Studies of SMB interpolate values across glaze regions, leading to overestimates of net mass input. Using our derived wind-glaze extent, we estimate this excess in three recent models of Antarctic SMB at 46-82 Gt. The lowest-input model appears to best match the mean in regions of extensive wind glaze.
Keywords: Antarktis; glasiologi

Surface mass balance and stable oxygen isotope ratios from shallow firn cores on Fimbulisen, East Antarctica - Schlosser, Elisabeth; Anschütz, Helgard; Isaksson, Elisabeth; Martma, T; Divine, Dmitry; Nøst, Ole Anders (Annals of Glaciology, 2012)
The mass balance of Antarctica is one of the crucial factors for determining sea-level change in a warming climate. The marginal zones of the continent, namely the ice shelves, are most sensitive to climate change. During the 2009/10 austral summer an extensive glaciological field campaign was carried out on Fimbulisen, an ice shelf in East Antarctica, to investigate its recent surface mass balance. Shallow (10–18 m) firn cores were drilled and accumulation rates and stable-isotope ratios determined. For firn-core dating, two different methods were compared: (1) seasonal variations of stable oxygen isotope ratios (δ18O), and (2) dielectric profiling, including using the volcanic eruptions of Pinatubo, Philippines (1991), and El Chichόn, Mexico (1982), as time markers. The mean annual accumulation for the period 1992–2009 ranges from 298 to 349 mmw.e. a–1. The interannual variability at the drilling sites is >30%. Accumulation rates show a weak decreasing trend during the past 20–30 years, which is statistically significant only for one of the cores. Stable-isotope ratios were compared to the snowfall temperature of Neumayer station. Neither the temperatures nor the δ18O values show any trend for the investigated time period.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi

Sydpolen eller Sørpolen? - Skagestad, Odd Gunnar (Ordet: kvartalsskrift for riksmålsbevegelsen, 2012)
Keywords: Antarktis; språk; stedsnavn

Virvler øker smeltingen - Smedsrud, Lars H; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Kovacs, Kit M; Nøst, Ole A (Klima: norsk magasin for klimaforskning, 2012)
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; klima; oseanografi

The impact of human activities on wilderness and aesthetic values in Antarctica - Summerson, Rupert; Bishop, Ian D. (Polar Research, 2012)
There has been little progress in implementing protection of wilderness and aesthetic values in Antarctica since the coming into force of the Protocol on Environmental Protection to the Antarctic Treaty in 1998. This can in part be attributed to a lack of research defining these values and showing how they may be assessed. In 2009, a survey comprising 90 images of Antarctic landscapes was established on the Internet to canvass as wide a cross-section of people with an interest in Antarctica as possible on their perceptions of wilderness and their aesthetic preference. At the time of writing, over 337 respondents from 23 nationalities have taken part in the survey. Responses were analysed to determine the effect of human presence, both transient and as infrastructure, on perceptions of wilderness and aesthetic values. The analysis was in three parts: (1) all images combined; (2) images grouped by landscape type, derived from the Environmental Domains of Antarctica regionalization; and (3) 16 pairs of digitally manipulated images of which respondents were shown either an original image or one in which human presence had been either digitally removed or added. Responses to images grouped by landscape type show that coastal and ice-free areas are less valued both aesthetically and as wilderness than mountainous and ice-covered terrains. Signs of human presence were found to make images significantly less likely to be considered as wilderness and also reduced their aesthetic rating. This demonstrates that human impacts on these values are measureable. Keywords: Antarctica; Madrid Protocol; wilderness; aesthetic; values; photographs.
Keywords: Antarktis; Antarktistraktaten; estetikk; menneskelig påvirkning; miljøpåvirkning; miljøvern

Chronostratigraphic framework for the IODP Expedition 318 cores from the Wilkes Land Margin: Constraints for paleoceanographic reconstruction - Tauxe, Lisa; Stickley, Catherine; Sugisaki, Saiko; Bijl, Peter K; Bohaty, S M; Brinkhuis, Henk; Escutia, Carlota; Flores, J A; Houben, A J P; Iwai, Masao; Jiménez-Espejo, Francisco J; McKay, Robert; et al. (Paleoceanography, 2012)
The Integrated Ocean Drilling Program Expedition 318 to the Wilkes Land margin of Antarctica recovered a sedimentary succession ranging in age from lower Eocene to the Holocene. Excellent stratigraphic control is key to understanding the timing of paleoceanographic events through critical climate intervals. Drill sites recovered the lower and middle Eocene, nearly the entire Oligocene, the Miocene from about 17 Ma, the entire Pliocene and much of the Pleistocene. The paleomagnetic properties are generally suitable for magnetostratigraphic interpretation, with well-behaved demagnetization diagrams, uniform distribution of declinations, and a clear separation into two inclination modes. Although the sequences were discontinuously recovered with many gaps due to coring, and there are hiatuses from sedimentary and tectonic processes, the magnetostratigraphic patterns are in general readily interpretable. Our interpretations are integrated with the diatom, radiolarian, calcareous nannofossils and dinoflagellate cyst (dinocyst) biostratigraphy. The magnetostratigraphy significantly improves the resolution of the chronostratigraphy, particularly in intervals with poor biostratigraphic control. However, Southern Ocean records with reliable magnetostratigraphies are notably scarce, and the data reported here provide an opportunity for improved calibration of the biostratigraphic records. In particular, we provide a rare magnetostratigraphic calibration for dinocyst biostratigraphy in the Paleogene and a substantially improved diatom calibration for the Pliocene. This paper presents the stratigraphic framework for future paleoceanographic proxy records which are being developed for the Wilkes Land margin cores. It further provides tight constraints on the duration of regional hiatuses inferred from seismic surveys of the region.
Keywords: Sørishavet; biostratigrafi; chronostratigrafi; magnetostratigrafi; paleoklimatologi; paleoseanografi; seismologi

Trampling on maritime Antarctica: can soil ecosystems be effectively protected through existing codes of conduct? - Tejedo, Pablo; Pertierra, Luis R; Benayas, Javier; Convey, Peter; Justel, Ana; Quesada, Antonio (Polar Research, 2012)
Soil trampling is one of the most obvious direct negative human impacts in Antarctica. Through a range of experiments and field studies based on quantitative physical (soil penetration resistance) and biological (collembolan abundance) indicators, we evaluate the current codes of conduct relating to the protection of Antarctic soils from the consequences of pedestrian impacts. These guidelines include using, where available, established paths that cross vegetation-free soils. However, the effectiveness of this strategy is highly dependent on context. Limited intensity use - below 100 foot passes per year - produces small changes at the soil surface that can recover relatively rapidly, suggesting that the dispersal of activity across wider corridors may be the most appropriate option. However, for paths with a higher use level and those located in steep-sloped sites, it is desirable to define a single track, following stony or bouldery surfaces wherever possible, to keep the disturbed area to a minimum. It is clear that both environmental conditions and expected use levels must be taken into account in determining when and where it is more appropriate to concentrate or disperse human activities. Even though they may have performed satisfactorily to date, the increasing pressure in terms of numbers of visits for certain sites may make it necessary to revise existing codes of conduct. Keywords: Trampling impacts; environmental monitoring; low impact practices; soil resilience; soil penetration resistance; collembolan abundance.
Keywords: Antarktis; jord; menneskelig påvirkning; miljøvern; økosystemer

Foreword: The complex business of managing human activities and protecting the environment of the polar regions - Tin, Tina; Liggett, Daniela; Maher, Patrick T (Polar Research, 2012)
The thematic cluster ‘‘Human impacts in the Arctic and Antarctic’’ in Polar Research has its origins in the International Polar Year (2007-09) Oslo Science Conference held in Oslo, Norway, from 8 to 12 June 2010. We were the co-convenors of the session ‘‘Human impacts in the Arctic and Antarctic: regulatory and management implications,’’ in which 27 talks and 21 posters were presented over the course of two days. We invited contributors to the conference session to explore all types of impacts of human activities and regional environmental change in the polar regions, with a special focus on highlighting the management priorities for the protection of the landscape (environment and people) of the polar regions in the face of increasing human activity. Exploring a wide range of topics ranging from human wildlife interactions to chemical contamination and from whaling to polar tourism, contributors provided examples of existing environmental management regimes that are working as well as those that are not.
Keywords: Antarktis; forurensning; menneskelig påvirkning; miljøvern; polarområdene; turisme; økosystemer

Culturable heterotrophic bacteria from Potter Cove, Antarctica, and their hydrolytic enzymes production - Tropeano, Mauro; Coria, Silvia; Turjanski, Adrían; Cicero, Daniel; Bercovich, Andrés; Mac Cormack, Walter; Vázquez, Susana (Polar Research, 2012)
Affiliations of the dominant culturable bacteria isolated from Potter Cove, South Shetland Islands, Antarctica, were investigated together with their production of cold-active hydrolytic enzymes. A total of 189 aerobic heterotrophic bacterial isolates were obtained at 4°C and sorted into 63 phylotypes based on their amplified ribosomal DNA restriction analysis profiles. The sequencing of the 16S rRNA genes of representatives from each phylotype showed that the isolates belong to the phyla Proteobacteria (classes Alpha- and Gamma-proteobacteria), Bacteroidetes (class Flavobacteria), Actinobacteria (class Actinobacteria) and Firmicutes (class Bacilli). The predominant culturable group in the site studied belongs to the class Gammaproteobacteria, with 65 isolates affiliated to the genus Pseudoalteromonas and 58 to Psychrobacter. Among the 189 isolates screened, producers of amylases (9.5%), pectinases (22.8%), cellulases (14.8%), CM-cellulases (25.4%), xylanases (20.1%) and proteases (44.4%) were detected. More than 25% of the isolates produced at least one extracellular enzyme, with some of them producing up to six of the tested extracellular enzymatic activities. These results suggest that a high culturable bacterial diversity is present in Potter Cove and that this place represents a promising source of biomolecules. Keywords: Microbial enzymes; Antarctic bacteria; marine bacteria; cold enzymes; psychrophiles.
Keywords: Sørishavet; alger; bakterier; biodiversitet; marin biologi; sjøvann; økologi; økosystemer

Impact of increasing Antarctic ice-shelf melting on Southern Ocean hydrography - Wang, Caixin; Wang, Keguang (Journal of Glaciology, 2012)
Southern Ocean hydrography has undergone substantial changes in recent decades, concurrent with an increase in the rate of Antarctic ice-shelf melting (AISM). We investigate the impact of increasing AISM on hydrography through a twin numerical experiment, with and without AISM, using a global coupled sea-ice/ocean climate model. The difference between these simulations gives a qualitative understanding of the impact of increasing AISM on hydrography. It is found that increasing AISM tends to freshen the surface water, warm the intermediate and deep waters, and freshen and warm the bottom water in the Southern Ocean. Such effects are consistent with the recent observed trends, suggesting that increasing AISM is likely a significant contributor to the changes in the Southern Ocean. Our analyses indicate potential positive feedback between hydrography and AISM that would amplify the effect on both Southern Ocean hydrography and Antarctic ice-shelf loss caused by external factors such as changing Southern Hemisphere winds.
Keywords: Sørishavet; glasiologi; hydrografi

Chemical composition of tropospheric air masses encountered during high altitude flights (>11.5 km) during the 2009 fall Operation Ice Bridge field campaign - Yang, Mei Ying Melissa; Vay, Stephanie A; Stohl, Andreas; Choi, Yonghoon; Diskin, Glenn S; Sachse, Glen W; Blake, Donald R (Journal of Geophysical Research: Atmospheres, 2012)
As part of the 2009 Operation Ice Bridge campaign, the NASA DC-8 aircraft was used to fill the data-time gap in laser observation of the changes in ice sheets, glaciers and sea ice between ICESat-I (Ice, Cloud, and land Elevation Satellite) and ICESat-II. Complementing the cryospheric instrument payload were four in situ atmospheric sampling instruments integrated onboard to measure trace gas concentrations of CO2, CO, N2O, CH4, water vapor and various VOCs (Volatile Organic Compounds). This paper examines two plumes encountered at high altitude (12 km) during the campaign; one during a southbound transit flight (13°S) and the other at 86°S over Antarctica. The data presented are especially significant as the Southern Hemisphere is heavily under-sampled during the austral spring, with few if any high-resolution airborne observations of atmospheric gases made over Antarctica. Strong enhancements of CO, CH4, N2O, CHCl3, OCS, C2H6, C2H2 and C3H8 were observed in the two intercepted air masses that exhibited variations in VOC composition suggesting different sources. The transport model FLEXPART showed that the 13°S plume contained predominately biomass burning emissions originating from Southeast Asia and South Africa, while both anthropogenic and biomass burning emissions were observed at 86°S with South America and South Africa as indicated source regions. The data presented here show evidence that boundary layer pollution is transported from lower latitudes toward the upper troposphere above the South Pole, which may not have been observed in the past.
Keywords: Antarktis; atmosfæren; atmosfæriske gasser; forurensning; havis; innlandsis; isbreer; isbrem; kjemi; kjemiske analyser; menneskelig påvirkning; meteorologi; sjøis; sporgass

Variation of accumulation rates over the last eight centuries on the East Antarctic Plateau derived from volcanic signals in ice cores - Anschütz, Helgard; Sinisalo, Anna; Isaksson, Elisabeth; McConnell, Joseph R; Hamran, Svein Erik; Bisiaux, M M; Pasteris, Daniel R; Neumann, Thomas; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2011)
Volcanic signatures in ice-core records provide an excellent means to date the cores and obtain information about accumulation rates. From several ice cores it is thus possible to extract a spatio-temporal accumulation pattern. We show records of electrical conductivity and sulfur from 13 firn cores from the Norwegian-USA scientific traverse during the International Polar Year 2007–2009 (IPY) through East Antarctica. Major volcanic eruptions are identified and used to assess century-scale accumulation changes. The largest changes seem to occur in the most recent decades with accumulation over the period 1963–2007/08 being up to 25% different from the long-term record. There is no clear overall trend, some sites show an increase in accumulation over the period 1963 to present while others show a decrease. Almost all of the sites above 3200 m above sea level (asl) suggest a decrease. These sites also show a significantly lower accumulation value than large-scale assessments both for the period 1963 to present and for the long-term mean at the respective drill sites. The spatial accumulation distribution is influenced mainly by elevation and distance to the ocean (continentality), as expected. Ground-penetrating radar data around the drill sites show a spatial variability within 10–20% over several tens of kilometers, indicating that our drill sites are well representative for the area around them. Our results are important for large-scale assessments of Antarctic mass balance and model validation.
Keywords: Antarktis; akkumulasjon; geovitenskap; glasiologi; innlandsis; iskjerner; klimatologi

Implications of meltwater pulse events for soil biology and biogeochemical cycling in a polar desert - Ball, Becky A; Barrett, J E; Gooseff, Mike N; Virginia, Ross A; Wall, Diana H (Polar Research, 2011)
The McMurdo Dry Valleys are one of the most arid environments on Earth. Over the soil landscape for the majority of the year, biological and ecosystem processes in the dry valleys are constrained by the low temperatures and limited availability of water. The prevalence of these physical limitations in controlling biological and ecosystem processes makes the dry valleys a climatesensitive system, poised to experience substantial changes following projected future warming. Short-duration increases in summer temperatures are associated with pulses of water from melting ice reserves, including glaciers, snow and permafrost. Such pulses alter soil geochemistry by mobilizing and redistributing soil salts (via enhanced weathering, solubility and mobility), which can alter habitat suitability for soil organisms. Resulting changes in soil community composition or distribution may alter the biogeochemical processes in which they take part. Here, we review the potential impacts of meltwater pulses and present new field data documenting instances of meltwater pulse events that result from different water sources and hydrological patterns, and discuss their potential influence on soil biology and biogeochemistry. We use these examples to discuss the potential impacts of future climate change on the McMurdo Dry Valley soil ecosystem.Keywords: Water pulse; climate change; polar desert; International Polar Year; discrete warming events; soil biogeochemistry.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); IPY; biogeokjemi; biologi; jord; klimaendringer; polarørken

Some like it cold: microbial transformations of mercury in polar regions - Barkay, Tamar; Kroer, Niels; Poulain, Alexandre J (Polar Research, 2011)
The contamination of polar regions with mercury that is transported from lower latitudes as inorganic mercury has resulted in the accumulation of methylmercury (MeHg) in food chains, risking the health of humans and wildlife. While production of MeHg has been documented in polar marine and terrestrial environments, little is known about the responsible transformations and transport pathways and the processes that control them. We posit that as in temperate environments, microbial transformations play a key role in mercury geochemical cycling in polar regions by: (1) methylating mercury by one of four proposed pathways, some not previously described; (2) degrading MeHg by activities of mercury resistant and other bacteria; and (3) carrying out redox transformations that control the supply of the mercuric ion, the substrate of methylation reactions. Recent analyses have identified a high potential for mercury-resistant microbes that express the enzyme mercuric reductase to affect the production of gaseous elemental mercury when and where daylight is limited. The integration of microbially mediated processes in the paradigms that describe mercury geochemical cycling is therefore of high priority especially in light of concerns regarding the effect of global warming and permafrost thawing on input of MeHg to polar regions. Keywords: Microbiology; mercury biogeochemistry; redox transformations; polar regions; methylation
Keywords: Antarktis; biogeokjemi; forurensning; mikrobiologi; miljøvern; polarområdene; økosystemer

Environmental forcings of Paleogene Southern Ocean dinoflagellate biogeography - Bijl, Peter K; Pross, Jörg; Warnaar, Jeroen; Stickley, Catherine E; Huber, Matthew; Guerstein, Raquel; Houben, Alexander J P; Sluijs, Appy; Visscher, Henk; Brinkhuis, Henk (Paleoceanography, 2011)
Despite warm polar climates and low meridional temperature gradients, a number of different high-latitude plankton assemblages were, to varying extents, dominated by endemic species during most of the Paleogene. To better understand the evolution of Paleogene plankton endemism in the high southern latitudes, we investigate the spatiotemporal distribution of the fossil remains of dinoflagellates, i.e., organic-walled cysts (dinocysts), and their response to changes in regional sea surface temperature (SST). We show that Paleocene and early Eocene (∼65–50 Ma) Southern Ocean dinocyst assemblages were largely cosmopolitan in nature but that a distinct switch from cosmopolitan-dominated to endemic-dominated assemblages (the so-called “transantarctic flora”) occurred around the early-middle Eocene boundary (∼50 Ma). The spatial distribution and relative abundance patterns of this transantarctic flora correspond well with surface water circulation patterns as reconstructed through general circulation model experiments throughout the Eocene. We quantitatively compare dinocyst assemblages with previously published TEX86–based SST reconstructions through the early and middle Eocene from a key locality in the southwest Pacific Ocean, ODP Leg 189 Site 1172 on the East Tasman Plateau. We conclude that the middle Eocene onset of the proliferation of the transantarctic flora is not linearly correlated with regional SST records and that only after the transantarctic flora became fully established later in the middle Eocene, possibly triggered by large-scale changes in surface-ocean nutrient availability, were abundances of endemic dinocysts modulated by regional SST variations.
Keywords: Sørishavet; biogeografi; fossiler; paleobotanikk; paleoseanografi; plankton

Variability of nutrient and thermal structure in surface waters between New Zealand and Antarctica, October 2004-January 2005 - Campanelli, Alessandra; Massolo, Serena; Grilli, Federica; Marini, Mauro; Paschini, Elio; Rivaro, Paola; Artegiani, Antonio; Jacobs, Stanley S (Polar Research, 2011)
We describe the upper ocean thermal structure and surface nutrient concentrations between New Zealand and Antarctica along five transects that cross the Subantarctic Front, the Polar Front and the southern Antarctic Circumpolar Current front. The surface water thermal structure is coupled with variations in surface nutrient concentrations, making water masses identifiable by both temperature and nutrient ranges. In particular, a strong latitudinal gradient in orthosilicate concentration is centred at the Polar Front. On the earlier sections, which extend south-west from the Campbell Plateau, orthosilicate increases sharply southward from 10-15 to 50-55µmol l-1, between 58°S and 60°S, while surface temperature drops from 7°C to 2°C. Nitrate increases more regularly toward the south, with concentrations ranging from 10-12µmol l-1 at 54°S to 25-30µmol l-1 at 66°S. The same features are observed during the later transects between New Zealand and the Ross Sea, but the sharp silica and surface temperature gradients are shifted between 60°S and 64°S. Both temporal and spatial factors may influence the observed variability. The January transect suggests an uptake of silica, orthophosphate and nitrate between 63°S and 70°S over the intervening month, with an average depletion near 37%, 44% and 29%, respectively. An N/P apparent drawdown ratio of 8.8±4.1 and an Si/N apparent drawdown ratio >1 suggests this depletion results from a seasonal diatom bloom. A southward movement of the oceanic fronts between New Zealand and the Ross Sea relative to prior measurements is consistent with reports of recent warming and changes in the Antarctic Circumpolar Current. Keywords: Southern Ocean, nutrients, silica belt, Antarctic Circumpolar Current, expendable bathythermograph.
Keywords: Rosshavet; Sørishavet; fytoplankton; havstrømmer; næringsstoff; vannmasser; økosystemer

Review of Tourism and change in polar regions: climate, environment and experience and Cruise tourism in polar regions: promoting environmental and social sustainability? - Capelotti, P J (Polar Research, 2011)
These two edited volumes, which cover much of the same ground, both begin from a common premise: polar tourism, as its been experienced by wealthy travellers for over a century, has a very definite shelf life. With the acceleration of global climate change, the Arctic and Antarctic are being changed, changed rapidly, perhaps permanently and, if one pays attention to the news, seemingly by the day. When combined with popular documentaries and feature films like An inconvenient truth, March of the penguins and Happy feet potential polar tourists have been sensitized to see the polar regions not as implacably hostile wastes once challenged only by the likes of Nansen, Amundsen, Scott and Shackleton but as irreplaceably fragile zones that, once lost, will take some essential part of the planet with them.
Keywords: Antarktis; bokanmeldelser; cruiseturisme; global oppvarming; klimaendringer; miljøvern; polarområdene; turisme; økologi

Princess Elisabeth Antarctica: an International Polar Year outreach and media success story - Cheek, Joseph; Huyge, Ben; Pomereu, Jean de (Polar Research, 2011)
One of the priorities of the fourth International Polar Year (IPY) was to increase awareness of the polar regions and polar science among the general public through education, communication and other forms of outreach. This paper reports on the media coverage of Princess Elisabeth Antarctica (PEA), Belgium’s ‘‘zero-emission’’ Antarctic research station designed by the nonprofit International Polar Foundation (IPF) to run on wind and solar energy and to employ state-of-the-art forms of energy management and other ‘‘green’’ technology. This paper provides background information on PEA, a review of IPF’s media strategy for the project, a description of media coverage of the station and a discussion of the way in which the IPF’s main messages were reported in the media. IPF staff surveyed approximately 300 media reports released between February 2004, when the PEA project was announced to the general public, and June 2010, when the IPF presented their findings at the IPY conference in Oslo. PEA was featured 580 times in print and web media in Belgium, and 303 times outside Belgium. Major international agencies such as the Associated Press, Agence France Presse, the BBC, Al-Jazeera and Reuters covered the project. On television and radio, PEA was featured in news broadcasts from all four major television networks in Belgium, most major radio stations and 34 different television and radio news outlets outside Belgium. The paper concludes that the media coverage for PEA was significant and suggests reasons why the project was so widely reported. Keywords: Media and outreach; media strategy; Antarctic research stations; energy management system; renewable energy; reducing environmental footprint
Keywords: Antarktis; Det internasjonale polaråret; fornybar energi; forskningsstasjoner; fotavtrykk; mediadekning; miljø; polarområdene

Global southern limit of flowering plants and moss peat accumulation - Convey, Peter; Hopkins, David W; Roberts, Stephen J; Tyler, Andrew N (Polar Research, 2011)
The ecosystems of the western Antarctic Peninsula, experiencing amongst the most rapid trends of regional climate warming worldwide, are important “early warning” indicators for responses expected in more complex systems elsewhere. Central among responses attributed to this regional warming are widely reported population and range expansions of the two native Antarctic flowering plants, Deschampsia antarctica and Colobanthus quitensis. However, confirmation of the predictions of range expansion requires baseline knowledge of species distributions. We report a significant southwards and westwards extension of the known natural distributions of both plant species in this region, along with several range extensions in an unusual moss community, based on new survey work in a previously unexamined and un-named low altitude peninsula at 69º22.0’S 71º50.7’W in Lazarev Bay, north-west Alexander Island, southern Antarctic Peninsula. These plant species therefore have a significantly larger natural range in the Antarctic than previously thought. This site provides a potentially important monitoring location near the southern boundary of the region currently demonstrated to be under the influence of rapidly changing climate trends. Combined radiocarbon and lead isotope radiometric dating suggests that this location was most likely deglaciated sufficiently to allow peat to start accumulating towards the end of the 19th century, which we tentatively link to a phase of post-1870 climate amelioration. We conclude that the establishment of vegetation in this location is unlikely to be linked to the rapid regional warming trends recorded along the Antarctic Peninsula since the mid-20th century. Antarctic plants, distribution limits, peat accumulation, dating.
Keywords: Antarktis; hårgress; klimaendringer; perleurt; planter; økosystemer

Polythermal glacier hydrology: a review - Irvine-Fynn, Tristram D L; Hodson, Andrew J; Moorman, Brian J; Vatne, Geir; Hubbard, Alun L (Reviews of Geophysics, 2011)
The manner by which meltwater drains through a glacier is critical to ice dynamics, runoff characteristics, and water quality. However, much of the contemporary knowledge relating to glacier hydrology has been based upon, and conditioned by, understanding gleaned from temperate valley glaciers. Globally, a significant proportion of glaciers and ice sheets exhibit nontemperate thermal regimes. The recent, growing concern over the future response of polar glaciers and ice sheets to forecasts of a warming climate and lengthening summer melt season necessitates recognition of the hydrological processes in these nontemperate ice masses. It is therefore timely to present an accessible review of the scientific progress in glacial hydrology where nontemperate conditions are dominant. This review provides an appraisal of the glaciological literature from nontemperate glaciers, examining supraglacial, englacial, and subglacial environments in sequence and their role in hydrological processes within glacierized catchments. In particular, the variability and complexity in glacier thermal regimes are discussed, illustrating how a unified model of drainage architecture is likely to remain elusive due to structural controls on the presence of water. Cold ice near glacier surfaces may reduce meltwater flux into the glacier interior, but observations suggest that the transient thermal layer of near surface ice holds a hydrological role as a depth-limited aquifer. Englacial flowpaths may arise from the deep incision of supraglacial streams or the propagation of hydrofractures, forms which are readily able to handle varied meltwater discharge or act as locations for water storage, and result in spatially discrete delivery of water to the subglacial environment. The influence of such drainage routes on seasonal meltwater release is explored, with reference to summer season upwellings and winter icing formation. Moreover, clear analogies emerge between nontemperate valley glacier and ice sheet hydrology, the discussion of which indicates how persistent reassessment of our conceptualization of glacier drainage systems is required. There is a clear emphasis that continued, integrated endeavors focused on process glaciology at nontemperate glaciers are a scientific imperative to augmenting the existing body of research centered on ice mass hydrology.
Keywords: Antarktis; geografi; glasiologi; global oppvarming; hydrologi; innlandsis; isbreer; isbrem; polarområdene

Low-ozone events in the southern polar summer as indicated by Met Office ozone analyses - Jackson, David; Orsolini, Yvan Joseph; Engelsen, Ola (Journal of Geophysical Research: Atmospheres, 2011)
Southern summer low-ozone events (LOEs) are examined using Met Office ozone analyses for 2005–2007. At 31 hPa, tongues of low-ozone air are pulled out of the polar region and extend to lower latitudes. Low tongues are also seen at 100 hPa, but there the low ozone is transported from low to high latitudes. These low tongues are frequently superimposed on one another, meaning that there are often also reductions in total ozone. What is striking is that at high latitudes, summer total ozone is typically lower over the Weddell Sea than at other longitudes. The low-ozone tongues at 31 and 100 hPa are consistent with transport associated with planetary waves. Daily geopotential height fields show a poleward and westward wave tilt with height, indicating the presence of baroclinic waves. The tilt enables the superimposition of the low-ozone tongues at 100 and 31 hPa. Filtered geopotential height anomalies reveal the presence of waves reported in other studies and indicate the connection between tropospheric and stratospheric wave dynamics in driving the LOEs. There is also a high connection between the LOEs and ultraviolet (UV) Index. The Weddell Sea region gets up to 20–30% more UV than the zonal mean, and the tip of South America gets about 10–25% more. There have been numerous studies of the impacts of increased UV on the Antarctic marine ecosystem during the springtime ozone hole, and our results indicate there is a case for these studies being extended to the summer LOEs.
Keywords: Antarktis; UV-stråling; Weddellhavet; ozonlaget; polarområdene; stratosfæren; ultrafiolett stråling

The oldest plesiosaur (Reptilia, Sauropterygia) from Antarctica - Kellner, Alexander Wilhelm Armin; Simões, Tiago Rodrigues; Riff, Douglas; Grillo, Orlando; Romano, Pedro; Paula, Helder de; Ramos, Renato; Carvalho, Marcelo; Sayão, Juliana; Oliveira, Gustavo; Rodrigues, Taissa (Polar Research, 2011)
Antarctic plesiosaurs are known from the Upper Cretaceous López de Bertodano and Snow Hill Island formations (Campanian to upper Maastrichtian), which crop out within the James Ross Basin region of the Antarctic Peninsula. Here we describe the first plesiosaur fossils from the Lachman Crags Member of the Santa Marta Formation, north-western James Ross Island. This material constitutes the stratigraphically oldest plesiosaur occurrence presently known from Antarctica, extending the occurrence of plesiosaurians in this continent back to Santonian times (86.3-83.5 Mya). Furthermore, MN 7163-V represents the first plesiosaur from this region not referable to the Elasmosauridae nor Aristonectes, indicating a greater diversity of this group of aquatic reptiles in Antarctica than previously suspected. Keywords: James Ross Island; Antarctica; plesiosauria; Late Cretaceous; Museu Nacional.
Keywords: Antarktis; geologi; paleontologi; svaneøgler

Meteoritten som vitnet om liv på Mars - Knutsen, Henning; Matland, Aleksander (Naturen, 2011)
Har livet på Jorda blitt ført hit fra tidligere liv på planeten Mars? I 1996 hevdet en gruppe forskere at en meteoritt fra Mars faktisk inneholdt spor etter organisk liv. Hvis dette virkelig var tilfelle, ville det medføre en revolusjon for vårt syn på verden og det univers vi befinner oss i. Men vitenskapsfolk besitter sunn skepsis, og hos dem kommer ikke tvilen tiltalte til gode. Nå mener de fleste ekspertene at funnet var for godt til å være sant.
Keywords: Antarktis; astrofysikk; mikrobiologi

Recovery Lakes, East Antarctica: Radar assessment of sub-glacial water extent - Langley, Kirsty; Kohler, Jack; Matsuoka, Kenichi; Sinisalo, Anna; Scambos, Ted; Neumann, Thomas; Muto, Atsuhiro; Winther, Jan-Gunnar; Albert, Mary (Geophysical Research Letters, 2011)
A fast-flowing tributary of Recovery ice stream penetrates more than 500 km into the interior of East Antarctica. Recent satellite-based studies found surface features in the onset area of this tributary that indicate a significant subglacial hydraulic system, including four large smooth basins, the typical surface expression of large subglacial lakes, as well as eleven smaller areas over which ice-sheet surface elevations rapidly changed by discharge/filling of subglacial water. Here we present the first ice-penetrating radar evidence of subglacial conditions in this area. We identified a distinct ice-water interface only over a limited area within the boundaries of the investigated large smooth basins, previously hypothesized to be water-filled lakes. The radar characteristics in some areas are similar to those of a drained lake, indicating that parts of the bed are wet, but not a typical lake. We also find evidence for discrete water bodies outside of the lake boundaries. The lines of evidence indicate that the northern most two Recovery Lakes have recently drained.
Keywords: Antarktis; geofysikk; glasiologi; isbre; isstrøm; radar observasjoner; subglasial innsjø

Antarctic bacterial isolates that produce cold-active extracellular proteases at low temperature but are active and stable at high temperature - Martínez-Rosales, Cecilia; Castro-Sowinski, Susana (Polar Research, 2011)
We report the isolation and identification of bacteria that produce extracellular cold-active proteases, obtained from water samples collected near the Uruguayan Antarctic Base on King George Island, South Shetlands. The bacteria belonged to the genera Pseudomonas (growth between 4 and 30°C) and Flavobacterium (growth between 4 and 18°C). In all cases, extracellular protease production was evident when reaching the stationary phase at 18 and 4ºC, but was not detected at 30ºC. The zymogram revealed the secretion of one extracellular protease per isolate, each with different relative electrophoretic mobility. The extracellular proteases produced at 4ºC showed thermal activity and stability at 30ºC. Both activity and stability at temperature higher that 10ºC have no physiological meaning because the isolates do not experience such temperatures in the Antarctic environment; however, the possible ecological value of cold-active and -stable extracellular proteases is discussed. Keywords: Antarctic, cold-active enzymes, protease.
Keywords: Sørishavet; bakterier; biokjemi; marin biologi; oseanografi

A comparison of the present and last interglacial periods in six Antarctic ice cores - Masson-Delmotte, Valerie; Buiron, Daphné; Ekaykin, Alexey Anatolievich; Frezzotti, M; Gallée, Hubert; Jouzel, Jean; Krinner, Gerhard; Landais, Amaelle; Motoyama, Hideaki; Oerter, Hans; Pol, K; Pollard, D; et al. (Clim. Past, 2011)
We compare the present and last interglacial periods as recorded in Antarctic water stable isotope records now available at various temporal resolutions from six East Antarctic ice cores: Vostok, Taylor Dome, EPICA Dome C (EDC), EPICA Dronning Maud Land (EDML), Dome Fuji and the recent TALDICE ice core from Talos Dome. We first review the different modern site characteristics in terms of ice flow, meteorological conditions, precipitation intermittency and moisture origin, as depicted by meteorological data, atmospheric reanalyses and Lagrangian moisture source diagnostics. These different factors can indeed alter the relationships between temperature and water stable isotopes. Using five records with sufficient resolution on the EDC3 age scale, common features are quantified through principal component analyses. Consistent with instrumental records and atmospheric model results, the ice core data depict rather coherent and homogenous patterns in East Antarctica during the last two interglacials. Across the East Antarctic plateau, regional differences, with respect to the common East Antarctic signal, appear to have similar patterns during the current and last interglacials. We identify two abrupt shifts in isotopic records during the glacial inception at TALDICE and EDML, likely caused by regional sea ice expansion. These regional differences are discussed in terms of moisture origin and in terms of past changes in local elevation histories, which are compared to ice sheet model results. Our results suggest that elevation changes may contribute significantly to inter-site differences. These elevation changes may be underestimated by current ice sheet models.
Publisher: Copernicus Publications
Keywords: Antarktis; Dronning Maud Land; Sørishavet; atmosfæren; glasiologi; iskjerner; klimatologi; meteorologi; stabile isotoper

Pitfalls in radar diagnosis of ice-sheet bed conditions: Lessons from englacial attenuation models - Matsuoka, Kenichi (Geophysical Research Letters, 2011)
Radar power returned from ice-sheet beds has been widely accepted as an indicator of bed conditions. However, the bed returned power also depends on englacial attenuation, which is primarily a function of ice temperature. Here, using a one-dimensional attenuation model, it is demonstrated that, in most cases, variations in bed returned power are dominated by variations in englacial attenuation, rather than bed reflectivity. Both accumulation rate and geothermal flux anomalies can interfere with the interpretation. With the consequence, analytical radar algorithms that have been widely accepted likely yield false delineations of wet/dry beds. More careful consideration is needed when diagnosing bed conditions. Spatial patterns of shallow englacial radar reflectors can be used as a proxy for accumulation rates, which affect ice temperature and thus returned power. I argue that it is necessary to simultaneously interpret the returned power and englacial-reflector patterns to improve the bed diagnosis.
Keywords: Antarktis; geotermisk strømning; glasiologi; innlandsis; istykkelse; overflateakkumulering; polarområdene

Direct observations of nitric oxide produced by energetic electron precipitation into the Antarctic middle atmosphere - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Holmén, Kim; Horne, Richard B (Geophysical Research Letters, 2011)
We report the first ground-based passive microwave observations made from Troll station, Antarctica, which show enhanced mesospheric nitric oxide (NO) volume mixing ratio reaching levels of 1.2 ppmv, or 2–3 orders of magnitude above background, at 70–80 km during small, relatively isolated geomagnetic storms in 2008. The mesospheric NO peaked 2 days after enhanced NO at higher altitudes (110–150 km) measured by the SABER satellite, and 2 days after peaks in the >30 keV and >300 keV electron flux measured by POES, although the 300 keV electron flux remained high. High time resolution data shows that mesospheric NO was enhanced at night and decayed during the day and built up to high levels over a period of 3–4 days. The altitude profile of mesospheric NO suggests direct production by ∼300 keV electron precipitation. Simulations using the Sodankylä Ion and Neutral Chemistry model show that the delay between thermospheric and mesospheric NO enhancements was primarily a result of the weaker production rate at lower altitudes by ∼300 keV electrons competing against strong day-time losses.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; meteorologi; observasjoner; radiometer

Eddy overturning of the Antarctic Slope Front controls glacial melting in the Eastern Weddell Sea - Nøst, Ole Anders; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Zhou, Qianhe; Smedsrud, Lars Henrik; Kovacs, Kit M (Journal of Geophysical Research: Oceans, 2011)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; oseanografi

Resources for fish feed in future mariculture - Olsen, Yngvar (Aquaculture Environment Interactions, 2011)
There is a growing concern about the ability to produce enough nutritious food to feed the global human population in this century. Environmental conflicts and a limited freshwater supply constrain further developments in agriculture; global fisheries have levelled off, and aquaculture may have to play a more prominent role in supplying human food. Freshwater is important, but it is also a major challenge to cultivate the oceans in an environmentally, economically and energy-friendly way. To support this, a long-term vision must be to derive new sources of feed, primarily taken from outside the human food chain, and to move carnivore production to a lower trophic level. The main aim of this paper is to speculate on how feed supplies can be produced for an expanding aquaculture industry by and beyond 2050 and to establish a roadmap of the actions needed to achieve this. Resources from agriculture, fish meal and fish oil are the major components of pellet fish feeds. All cultured animals take advantage of a certain fraction of fish meal in the feed, and marine carnivores depend on a supply of marine lipids containing highly unsaturated fatty acids (HUFA, with ≥3 double bonds and ≥20 carbon chain length) in the feed. The availability of HUFA is likely the main constraint for developing carnivore aquaculture in the next decades. The availability of fish meal and oil will decrease, and the competition for plant products will increase. New harvested resources are herbivore zooplankton, such as Antarctic krill and red feed, and new produced resources are macroalgae, transgenic higher HUFA-producing plants and bacterial biomass. These products are to a limited extent components of the human food chain, and all these resources will help to move cultured carnivores to lower trophic levels and can thereby increase the production capacity and the sustainability of the production. Mariculture can only become as successful as agriculture in the coming century if carnivores can be produced at around Trophic Level 2, based mainly on plant resources. There is little potential for increasing the traditional fish meal food chain in aquaculture. KEYWORDS: Global aquaculture · Mariculture · Feed resources · Marine lipids · HUFA · Trophic level
Keywords: Sørishavet; alger; bakterier; biomasse; bioressurser; fiskeri; havbruksnæring; jordbruk; krill; marin biologi; marine planter; matproduksjon; oseanografi; zooplankton

The present location of the tent that Roald Amundsen left behind at the South Pole in December 1911 - Orheim, Olav (Polar Record, 2011)
Determining the present precise location of Amundsen's tent is a function of 1) the precision of Amundsen's navigation in 1911, 2) the flow of ice since then, and 3) the amount of burial by intervening snow fall. These factors are discussed and it is concluded that the best location that can be given for the tent in December 2011 is 89° 58′ 51″ S, 46° 14′ E, and lying 17 m below the present snow surface. The uncertainty in the position is 0.3 km, and is mainly related to uncertainties in the original positioning. It can be concluded with high certainty that the tent lies between 1.8 and 2.5 km from the South Pole.
Keywords: Antarktis; ekspedisjoner; glasiologi; historie

Spring phytoplankton onset after the ice break-up and sea-ice signature (Adélie Land, East Antarctica) - Riaux-Gobin, Catherine; Poulin, Michel; Dieckmann, Gerhard; Labrune, Céline; Vétion, Gilles (Polar Research, 2011)
The phytoplankton onset following the spring ice break-up in Adélie Land, East Antarctica, was studied along a short transect, from 400 m off the continent to 5 km offshore, during the austral summer of 2002. Eight days after the ice break-up, some large colonial and solitary diatom cells, known to be associated with land-fast ice and present in downward fluxes, were unable to adapt in ice-free waters, while some other solitary and short-colony forming taxa (e.g., Fragilariopsis curta, F. cylindrus) did develop. Pelagic species were becoming more abundant offshore, replacing the typical sympagic (ice-associated) taxa. Archaeomonad cysts, usually associated with sea ice, were recorded in the surface waters nearshore. Rough weather restricted the data set, but we were able to confirm that some microalgae may be reliable sea-ice indicators and that seeding by sea ice only concerns a few taxa in this coastal area of East Antarctica. Keywords: Ice break-up; phytoplankton; sea-ice signature; East Antarctica
Keywords: Sørishavet; biogeokjemi; biomasse; fytoplankton; havis; oseanografi; sjøis

Hva er en helt? Kjønn i antarktislitteraturen - Ryall, Anka (Fortid : historiestudentenes tidsskrift, UiO, 2011)
Menneskenes historie i Antarktis er ikke mer enn noen hundre år gammel. De viktigste kildene til denne historien er ekspedisjonsberetningene – en omfangsrik litteratur som kan leses på mange måter, også fra et kjønnsperspektiv.
Keywords: Antarktis; ekspedisjoner; litteratur; polarhistorie

Deglacial history of the West Antarctic Ice Sheet in the western Amundsen Sea Embayment - Smith, James A.; Hillenbrand, Claus-Dieter; Kuhn, Gerhard; Larter, Robert D.; Graham, Alastair G.C.; Ehrmann, Werner; Moreton, Steven G.; Forwick, Matthias (Quaternary Science Reviews, 2011)
The Amundsen Sea Embayment (ASE) drains approximately 35% of the West Antarctic Ice Sheet (WAIS) and is one of the most rapidly changing parts of the cryosphere. In order to predict future ice sheet behaviour, modellers require long-term records of ice-sheet melting to constrain and build confidence in their simulations. Here, we present detailed marine geological and radiocarbon data along three palaeo-ice stream tributary troughs in the western ASE to establish vital information on the timing of deglaciation of the WAIS since the Last Glacial Maximum (LGM). We have undertaken multi-proxy analyses of the cores (core description, shear strength, x-radiographs, magnetic susceptibility, wet bulk density, total organic carbon/nitrogen, carbonate content and clay mineral analyses) in order to: (1) characterise the sedimentological facies and depositional environments; and (2) identify the horizon(s) in each core that would yield the most reliable age for deglaciation. In accordance with previous studies we identify three key facies, which offer the most reliable stratigraphies for dating deglaciation by recording the transition from a grounded ice sheet to open marine environments. These facies are: i) subglacial, ii) proximal grounding line, and iii) seasonal open marine. In addition, we incorporate ages from other facies (e.g., glaciomarine diamictons deposited at some distance from the grounding line, such as glaciogenic debris flows and iceberg-rafted diamictons and turbates) into our deglacial model. In total, we have dated 78 samples (mainly the acid insoluble organic (AIO) fraction, but also calcareous foraminifers), which include 63 downcore and 15 surface samples. Through careful sample selection prior to dating, we have established a robust deglacial chronology for this sector of the WAIS. Our data show that deglaciation of the western ASE was probably underway as early as 22,351 calibrated years before present (cal yr BP), reaching the mid-shelf by 13,837 cal yr BP and the inner shelf to within c.10–12 km of the present ice shelf front between 12,618 and 10,072 cal yr BP. The deglacial steps in the western ASE broadly coincide with the rapid rises in sea-level associated with global meltwater pulses 1a and 1b, although given the potential dating uncertainty, additional, more precise ages are required before these findings can be fully substantiated. Finally, we show that the rate of ice-sheet retreat increased across the deep (up to1600 m) basins of the inner shelf, highlighting the importance of reverse slope and pinning points in accelerated phases of deglaciation.
Keywords: Amundsenhavet; Sørishavet; deglasiasjon; glasiologi; innlandsis; isshelf; marin geologi

Using fluorescence to characterize dissolved organic matter in Antarctic sea ice brines - Stedmon, Colin A; Thomas, David N; Papadimitriou, Stathys; Granskog, Mats A; Dieckmann, Gerhard S (Journal of Geophysical Research: Biogeosciences, 2011)
Sea ice plays a dynamic role in the air-sea exchange of CO2. In addition to abiotic inorganic carbon fluxes, an active microbial community produces and remineralizes organic carbon, which can accumulate in sea ice brines as dissolved organic matter (DOM). In this study, the characteristics of DOM fluorescence in Antarctic sea ice brines from the western Weddell Sea were investigated. Two humic-like components were identified, which were identical to those previously found to accumulate in the deep ocean and represent refractory material. Three amino-acid-like signals were found, one of which was unique to the brines and another that was spectrally very similar to tryptophan and found both in seawater and in brine samples. The tryptophan-like fluorescence in the brines exhibited intensities higher than could be explained by conservative behavior during the freezing of seawater. Its fluorescence was correlated with the accumulation of nitrogen-rich DOM to concentrations up to 900 μmol L−1 as dissolved organic carbon (DOC) and, thus, potentially represented proteins released by ice organisms. A second, nitrogen-poor DOM fraction also accumulated in the brines to concentrations up to 200 μmol L−1 but was not correlated with any of the fluorescence signals identified. Because of the high C:N ratio and lack of fluorescence, this material is thought to represent extracellular polymeric substances, which consist primarily of polysaccharides. The clear grouping of the DOM pool into either proteinaceous or carbohydrate-dominated material indicates that the production and accumulation of these two subpools of DOM in sea ice brines is, to some extent, decoupled.
Keywords: Sørishavet; Weddellhavet; fluorescens; gassutveksling; havis; karbondioksid; marin økologi; mikrobielle organismer; mikrobiologi; sjøis

Spatial modelling of wetness for the Antarctic Dry Valleys - Stichbury, Glen; Brabyn, Lars; Green, T G Allan; Cary, Craig (Polar Research, 2011)
This paper describes a method used to model relative wetness for part of the Antarctic Dry Valleys using Geographic Information Systems (GIS) and remote sensing. The model produces a relative index of liquid water availability using variables that influence the volume and distribution of water. Remote sensing using Moderate Resolution Imaging Spectroradiometer (MODIS) images collected over four years is used to calculate an average index of snow cover and this is combined with other water sources such as glaciers and lakes. This water source model is then used to weight a hydrological flow accumulation model that uses slope derived from Light Detection and Ranging (LIDAR) elevation data. The resulting wetness index is validated using three-dimensional visualization and a comparison with a high-resolution Advanced Land Observing Satellite image that shows drainage channels. This research demonstrates that it is possible to produce a wetness model of Antarctica using data that are becoming widely available. Keywords: GIS; water; Antarctica; remote sensing.
Keywords: Antarktis; geografi; hydrologi; innsjø; isbreer; satellitt bilder; snø; vann; økosystemer

Using transport diagnostics to understand chemistry climate model ozone simulations - Strahan, Susan; Douglass, A R; Stolarski, R S; Akiyoshi, Hideharu; Bekki, Slimane; Braesicke, P; Butchart, N; Chipperfield, Martyn; Cugnet, David; Dhomse, Sandip; Frith, Stacey; Gettelman, Andrew; et al. (Journal of Geophysical Research: Atmospheres, 2011)
We use observations of N2O and mean age to identify realistic transport in models in order to explain their ozone predictions. The results are applied to 15 chemistry climate models (CCMs) participating in the 2010 World Meteorological Organization ozone assessment. Comparison of the observed and simulated N2O, mean age and their compact correlation identifies models with fast or slow circulations and reveals details of model ascent and tropical isolation. This process-oriented diagnostic is more useful than mean age alone because it identifies models with compensating transport deficiencies that produce fortuitous agreement with mean age. The diagnosed model transport behavior is related to a model's ability to produce realistic lower stratosphere (LS) O3 profiles. Models with the greatest tropical transport problems compare poorly with O3 observations. Models with the most realistic LS transport agree more closely with LS observations and each other. We incorporate the results of the chemistry evaluations in the Stratospheric Processes and their Role in Climate (SPARC) CCMVal Report to explain the range of CCM predictions for the return-to-1980 dates for global (60°S–60°N) and Antarctic column ozone. Antarctic O3 return dates are generally correlated with vortex Cly levels, and vortex Cly is generally correlated with the model's circulation, although model Cl chemistry and conservation problems also have a significant effect on return date. In both regions, models with good LS transport and chemistry produce a smaller range of predictions for the return-to-1980 ozone values. This study suggests that the current range of predicted return dates is unnecessarily broad due to identifiable model deficiencies.
Keywords: Antarktis; drivhusgasser; fysikk; geovitenskap; klimamodeller; meteorologi; ozonlaget; stratosfæren

Overvåking av havklima i Antarktis - Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor (Klima : norsk magasin for klimaforskning, 2011)
Publisher: CICERO senter for klimaforskning Place: Oslo
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer

Amundsens omstridte forløper ; Innsjøen under isen - Thuesen, Nils Petter (Vi menn vitenskap & historie, 2011)
Publisher: Egmont Place: Oslo
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Vostoksjøen; ekspedisjoner; glasiologi; subglasial innsjø

Near-surface eddy dynamics in the Southern Ocean - Trani, Marilisa; Falco, Pierpaolo; Zambianchi, Enrico (Polar Research, 2011)
The Antarctic Circumpolar Current (ACC) is a crucial component of the global ocean conveyor belt, acting as a zonal link among the major ocean basins but, to some extent, limiting meridional exchange and tending to isolate the ocean south of it from momentum and heat income. In this work we investigate one of the most important mechanisms contributing to the poleward transfer of properties in the Southern Ocean, that is the eddy component of the dynamics. For this particular purpose, observations obtained from near-surface drifters have been used: they represent a very useful data set to analyse the eddy field because of their ability to catch a large number of scales of motion while providing a quasi-synoptic coverage of the investigated area. Estimates of the eddy heat and momentum fluxes are carried out using data taken from the Global Drifter Program databank; they refer to Surface Velocity Program drifter trajectories collected in the area south of 358S between 1995 and 2006. Eddy kinetic energies, variance ellipses, momentum and heat fluxes have been calculated using the pseudo-Eulerian method, showing patterns in good agreement with those present in the literature based on observational and model data, although there are some quantitative differences. The eddy fluxes have been separated into their rotational and divergent portions, the latter being responsible for the meridional transports. The associated zonal and depth-exponentially integrated meridional heat transport exhibits values spanning over a range between -0.4 PW and -1.1 PW in the ACC region, consistent with previous estimates. Keywords: Antarctic Circumpolar Current; eddy fluxes; Global Drifter Program data; Lagrangian oceanography; Helmholtz decomposition.
Keywords: Sørishavet; havstrømmer; hydrografi; oseanografi; virvelstrømmer

Colonization and demographic structure of Deschampsia antarctica and Colobanthus quitensis along an altitudinal gradient on Livingston Island, South Shetland Islands, Antarctica - Vera, María Luisa (Polar Research, 2011)
The colonization capacity and demographic structure of populations of Deschampsia antarctica and Colobanthus quitensis were studied in different microhabitats between 10 and 147 m a.s.l. on Livingston Island, South Shetland Islands, near the Spanish Antarctic base Juan Carlos I, in February 2002. At the highest site (147 m a.s.l.), mean temperatures were about 1 ºC lower than at sea level. Both species are less common in inland areas and at the highest altitudes only occur at restricted sites that are frequently snow-free in the early austral summer. The diameters of the largest plants (C. quitensis cushions 7-8 cm ; D. antarctica tufts 10-11 cm) in the populations growing at the highest altitudes (110 and 147 m a.s.l.) suggest that these populations were established about 24-28 years ago. The largest diameter plants (Deschampsia 20 cm; Colobanthus 18 cm) were found at the lowest altitudes on deep soil. The presence of numerous seedlings and young individuals on the periphery of populations established several years ago or at recently colonized sites suggests an active process of expansion. There were more emerged seedlings of C. quitensis than of D. antarctica, but the density of established individuals was higher for D. antarctica, suggesting these species have different demographic strategies. Keywords: Antarctic vascular plants; altitude and habitat effect; colonization; population structure.
Keywords: Antarktis; biologi; flora; planter

Atmospheric histories and global emissions of the anthropogenic hydrofluorocarbons HFC-365mfc, HFC-245fa, HFC-227ea, and HFC-236fa - Vollmer, Martin K; Miller, Benjamin R; Rigby, Matthew; Reimann, Stefan; Mühle, Jens; Krummel, Paul B; O'Doherty, Simon; Kim, Jooil; Rhee, Tae Siek; Weiss, Ray F; Fraser, Paul J; Simmonds, Peter G; et al. (Journal of Geophysical Research: Atmospheres, 2011)
We report on ground-based atmospheric measurements and emission estimates of the four anthropogenic hydrofluorocarbons (HFCs) HFC-365mfc (CH3CF2CH2CF3, 1,1,1,3,3-pentafluorobutane), HFC-245fa (CHF2CH2CF3, 1,1,1,3,3-pentafluoropropane), HFC-227ea (CF3CHFCF3, 1,1,1,2,3,3,3-heptafluoropropane), and HFC-236fa (CF3CH2CF3, 1,1,1,3,3,3-hexafluoropropane). In situ measurements are from the global monitoring sites of the Advanced Global Atmospheric Gases Experiment (AGAGE), the System for Observations of Halogenated Greenhouse Gases in Europe (SOGE), and Gosan (South Korea). We include the first halocarbon flask sample measurements from the Antarctic research stations King Sejong and Troll. We also present measurements of archived air samples from both hemispheres back to the 1970s. We use a two-dimensional atmospheric transport model to simulate global atmospheric abundances and to estimate global emissions. HFC-365mfc and HFC-245fa first appeared in the atmosphere only ∼1 decade ago; they have grown rapidly to globally averaged dry air mole fractions of 0.53 ppt (in parts per trillion, 10−12) and 1.1 ppt, respectively, by the end of 2010. In contrast, HFC-227ea first appeared in the global atmosphere in the 1980s and has since grown to ∼0.58 ppt. We report the first measurements of HFC-236fa in the atmosphere. This long-lived compound was present in the atmosphere at only 0.074 ppt in 2010. All four substances exhibit yearly growth rates of >8% yr−1 at the end of 2010. We find rapidly increasing emissions for the foam-blowing compounds HFC-365mfc and HFC-245fa starting in ∼2002. After peaking in 2006 (HFC-365mfc: 3.2 kt yr−1, HFC-245fa: 6.5 kt yr−1), emissions began to decline. Our results for these two compounds suggest that recent estimates from long-term projections (to the late 21st century) have strongly overestimated emissions for the early years of the projections (∼2005–2010). Global HFC-227ea and HFC-236fa emissions have grown to average values of 2.4 kt yr−1 and 0.18 kt yr−1 over the 2008–2010 period, respectively.
Keywords: Dronning Maud Land; atmosfæren; drivhusgasser; global oppvarming; klimaendringer; klimatologi; målinger

Mesospheric wind semidiurnal tides within the Canadian Middle Atmosphere Model Data Assimilation System - Xu, Xiaoyong; Manson, Alan H; Meek, Christopher; Jacobi, Christoph; Hall, Chris; Drummond, James (Journal of Geophysical Research: Atmospheres, 2011)
The horizontal wind data from the standard version of Canadian Middle Atmosphere Model Data Assimilation System (CMAM-DAS) for the years 2006–2008 are analyzed to obtain the global structure and seasonal variability of the semidiurnal tide (SDT) in the mesosphere. The modeled amplitudes and phases of the SDTs at single stations from middle/high northern latitudes are quite similar to those observed by radars. The primary nonmigrating tides identified in both the meridional wind and zonal wind semidiurnal spectra at 88 km include the westward propagating wave numbers s = 1 (SW1), 3 (SW3), 4 (SW4), 6 (SW6), the standing s = 0 (S0), and the eastward propagating s = 2 (SE2). The migrating SDT (SW2) amplitude maxima usually occur at 40°N–60°N during December–February and August–September, and also at 40°S–60°S in April–May, with the dominance of (2, 4) during October–April and (2, 3) and (2, 5) dominance for other months. The CMAM-DAS is quite successful in reproducing the dominance of SW1 in the Antarctic summer mesosphere. The modeled SW1 shows very good overall agreement in both amplitude and phase with wind measurements from UARS High Resolution Doppler Imager and Wind Imaging Interferometer (UARS-HRDI/WINDII) and from TIMED Doppler Interferometer (TIDI). The CMAM-DAS analyses for SW3, SW4, SW6, and S0 are also in reasonable agreement with those determined from the HRDI/WINDII or TIDI wind measurements. This work provides further evidence for the tidal forcing from below.
Keywords: Antarktis; atmosfæren; atmosfærisk tidevann; geofysikk; meteorologi

An inter-comparison of six latent and sensible heat flux products over the Southern Ocean - Yu, Lejiang; Zhang, Zhanhai; Zhong, Shiyuan; Zhou, Mingyu; Gao, Zhiqiu; Wu, Huiding; Sun, Bo (Polar Research, 2011)
The latent heat fluxes (LHF) and sensible heat fluxes (SHF) over the Southern Ocean from six different data sets are inter-compared for the period 1988- 2000. The six data sets include three satellite-based products, namely, the second version of the Goddard Satellite-Based Surface Turbulent Fluxes data set (GSSTF-2), the third version of the Hamburg Ocean Atmosphere Parameters and Fluxes from Satellite Data (HOAPS-3) and the Japanese Ocean Fluxes Data Sets with Use of Remote Sensing Observations (J-OFURO); two global reanalysis products, namely, the National Centers for Environmental Prediction-Department of Energy Reanalysis 2 data set (NCEP-2) and the European Centre for Medium-Range Weather Forecasts 40 Year Re-analysis data set (ERA-40); and the Objectively Analyzed Air-Sea Fluxes for the Global Oceans data set (OAFlux). All these products reveal a similar pattern in the averaged flux fields. The zonal mean LHF fields all exhibit a continuous increase equatorward. With an exception of HOAPS-3, the zonal mean SHF fields display a minimum value near 50°S, increasing both pole- and equatorward. The differences in the standard deviation for LHF are larger among the six data products than the differences for SHF. Over the regions where the surface fluxes are significantly influenced by the Antarctic Oscillation and the Pacific-South American teleconnection, the values and distributions of both LHF and SHF are consistent among the six products. It was found that the spatial patterns of the standard deviations and trends of LHF and SHF can be explained primarily by sea-air specific humidity and temperature differences; wind speed plays a minor role. Keywords: Latent heat flux; sensible heat flux; Southern Ocean.
Keywords: Sørishavet; klimatologi; meteorologi; observasjoner

The intraseasonal variability of winter semester surface air temperature in Antarctica - Yu, Lejiang; Zhang, Zhanhai; Zhou, Mingyu; Zhong, Shiyuan; Sun, Bo; Hsu, Hsiaoming; Gao, Zhiqiu; Wu, Huiding; Ban, Junmei (Polar Research, 2011)
This study investigates systematically the intraseasonal variability of surface air temperature over Antarctica by applying empirical orthogonal function (EOF) analysis to the National Centers for Environmental Prediction, US Department of Energy, Reanalysis 2 data set for the period of 1979 through 2007. The results reveal the existence of two major intraseasonal oscillations of surface temperature with periods of 26 - 30 days and 14 days during the Antarctic winter season in the region south of 60°S. The first EOF mode shows a nearly uniform spatial pattern in Antarctica and the Southern Ocean associated with the Antarctic Oscillation. The mode-1 intraseasonal variability of the surface temperature leads that of upper atmosphere by one day with the largest correlation at 300-hPa level geopotential heights. The intraseasonal variability of the mode-1 EOF is closely related to the variations of surface net longwave radiation the total cloud cover over Antarctica. The other major EOF modes reveal the existence of eastward propagating phases over the Southern Ocean and marginal region in Antarctica. The leading two propagating modes respond to Pacific-South American modes. Meridional winds induced by the wave train from the tropics have a direct influence on the surface air temperature over the Southern Ocean and the marginal region of the Antarctic continent. Keywords: Antarctic climate, surface air temperature, intraseasonal variability, Antarctic Oscillation.
Keywords: Antarktis; forskning; klima; lufttemperatur

Mindre snø enn forventet i Antarktis - Anschütz, Helgard; Isaksson, Elisabeth (Klima: norsk magasin for klimaforskning, 2010)
Keywords: Dronning Maud Land; glasiologi; is; klima; snø

East Antarctic snow accumulation changes - Anschütz, Helgard; Isaksson, Elisabeth; Müller, Karsten; Winther, Jan-Gunnar; Albert, Mary (Ice and climate news, 2010)
Keywords: Antarktis; glasiologi

Natural iron enrichment around the Antarctic Peninsula in the Southern Ocean - Ardelan, M. V.; Holm-Hansen, O.; Hewes, C. D.; Reiss, C. S.; Silva, N. S.; Dulaiova, H.; Steinnes, E.; Sakshaug, E. (Biogeosciences, 2010)
As part of the US-AMLR program in January-February of 2006, 99 stations in the South Shetland Islands-Antarctic Peninsula region were sampled to understand the variability in hydrographic and biological properties related to the abundance and distribution of krill in this area. Concentrations of dissolved iron (DFe) and total acid-leachable iron (TaLFe) were measured in the upper 150 m at 16 of these stations (both coastal and pelagic waters) to better resolve the factors limiting primary production in this area and in downstream waters of the Scotia Sea. The concentrations of DFe and TaLFe in the upper mixed layer (UML) were relatively high in Weddell Sea Shelf Waters (~0.6 nM and 15 nM, respectively) and low in Drake Passage waters (~0.2 nM and 0.9 nM, respectively). In the Bransfield Strait, representing a mixture of waters from the Weddell Sea and the Antarctic Circumpolar Current (ACC), concentrations of DFe were ~0.4 nM and of TaLFe ~1.7 nM. The highest concentrations of DFe and TaLFe in the UML were found at shallow coastal stations close to Livingston Island (~1.6 nM and 100 nM, respectively). The ratio of TaLFe:DFe varied with the distance to land: ~45 at the shallow coastal stations, ~15 in the high-salinity waters of Bransfield Strait, and ~4 in ACC waters. Concentrations of DFe increased slightly with depth in the water column, while that of TaLFe did not show any consistent trend with depth. Our Fe data are discussed in regard to the hydrography and water circulation patterns in the study area, and with the hypothesis that the relatively high rates of primary production in the central regions of the Scotia Sea are partially sustained by natural iron enrichment resulting from a northeasterly flow of iron-rich coastal waters originating in the South Shetland Islands-Antarctic Peninsula region.
Keywords: Sør-Shetlandsøyene; Sørishavet; biogeokjemi; fytoplankton; hydrografi; marin biologi; marin kjemi; oseanografi

An isopycnic ocean carbon cycle model - Assmann, K. M.; Bentsen, M.; Segschneider, J.; Heinze, C. (Geoscientific Model Development, 2010)
The carbon cycle is a major forcing component in the global climate system. Modelling studies, aiming to explain recent and past climatic changes and to project future ones, increasingly include the interaction between the physical and biogeochemical systems. Their ocean components are generally z-coordinate models that are conceptually easy to use but that employ a vertical coordinate that is alien to the real ocean structure. Here, we present first results from a newly-developed isopycnic carbon cycle model and demonstrate the viability of using an isopycnic physical component for this purpose. As expected, the model represents well the interior ocean transport of biogeochemical tracers and produces realistic tracer distributions. Difficulties in employing a purely isopycnic coordinate lie mainly in the treatment of the surface boundary layer which is often represented by a bulk mixed layer. The most significant adjustments of the ocean biogeochemistry model HAMOCC, for use with an isopycnic coordinate, were in the representation of upper ocean biological production. We present a series of sensitivity studies exploring the effect of changes in biogeochemical and physical processes on export production and nutrient distribution. Apart from giving us pointers for further model development, they highlight the importance of preformed nutrient distributions in the Southern Ocean for global nutrient distributions. The sensitivity studies show that iron limitation for biological particle production, the treatment of light penetration for biological production, and the role of diapycnal mixing result in significant changes of nutrient distributions and liniting factors of biological production.
Keywords: Sørishavet; biogeokjemi; karbon syklus; klimamodeller

Long-range migration of a chinstrap penguin from Bouvetøya to Montagu Island, South Sandwich Islands - Biuw, Martin; Lydersen, Christian; Nico de Bruyn, P. J.; Arriola, Aline; Hofmeyr, Greg G. J.; Kritzinger, Petrus; Kovacs, Kit M. (Antarctic Science, 2010)
We describe a long-range migration of a pre-moulting adult chinstrap penguin from Bouvetøya, a small relatively recently established colony, to the South Sandwich Islands, where large, established colonies of this species reside. The trip lasted around three weeks, covered ∼3600 km, and the time of arrival was consistent with the annual moult. The bird did not travel along the shortest path or along a constant bearing, but instead followed what appeared to be a series of two or three rhumb lines of constant bearing. Small southward and northward deviations from the general path were consistent with local water currents. Travel speeds were high during daylight but decreased at night, suggesting that resting or opportunistic feeding occurred preferentially at night. While long-range winter migrations of chinstraps to feeding areas in the vicinity of distant colonies have been previously described, this is the first observation of such a trip during the period between breeding and moulting, and the first record of an individual actually arriving at one of these distant colonies. This has implications for understanding population structure and management of this important Southern Ocean predator.
Publisher: Cambridge University Press
Keywords: Bouvetøya; NARE 2007/08; Sør-Sandwichøyene; marin biologi; pingviner; sjøfugler

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Millennial scale evolution of the Southern Ocean chemical divide - Charles, Christopher D.; Pahnke, Katharina; Zahn, Rainer; Mortyn, P.G.; Ninnemann, Ulysses; Hodell, D.A. (Quaternary Science Reviews, 2010)
The chemical properties of the mid-depth and deep Southern Ocean are diagnostic of the mechanisms of abrupt changes in the global ocean throughout the late Pleistocene, because the regional water mass conversion and mixing help determine global ocean gradients. Here we define continuous time series of Southern Ocean vertical gradients by differencing the records from two high deposition rate deep sea sedimentary sequences that span the last several ice age cycles. The inferred changes in vertical carbon and oxygen isotopic gradients were dominated by variability on the millennial scale, and they followed closely the abrupt climate events of the high latitude Northern Hemisphere. In particular, the stadial events of at least the last 200kyr were characterized by enhanced mid-deep gradients in both δ13C (dissolved inorganic carbon) and δ18O (temperature). Interstadial events, conversely, featured reduced vertical gradients in both properties. The glacial terminations represented exceptions to this pattern of variability, as the vertical carbon isotopic gradient flattened dramatically at times of peak warmth in the Southern Ocean surface waters and with little or no corresponding change δ18O gradient. The available evidence suggests that properties of the upper layer of the Southern Ocean (Antarctic Intermediate Water) were influenced by an atmospherically mediated teleconnection to high latitude Northern Hemisphere.
Keywords: Sørishavet; geologi; oseanografi; paleoklimatologi

Observations of the Antarctic Slope Undercurrent in the southeastern Weddell Sea - Chavanne, Cédric P; Heywood, Karen J; Nicholls, Keith W; Fer, Ilker (Geophysical Research Letters, 2010)
The Antarctic Slope Front presents a dynamical barrier between the cold Antarctic shelf waters in contact with ice shelves and the warmer subsurface waters offshore. Two hydrographic sections with full-depth current measurements were undertaken in January and February 2009 across the slope and shelf in the southeastern Weddell Sea. Southwestward surface-intensified currents of ∼30 cm s−1, and northeastward undercurrents of 6–9 cm s−1, were in thermal-wind balance with the sloping isopycnals across the front, which migrated offshore by 30 km in the time interval between the two sections. A mid-depth undercurrent on February 23 was associated with a 130-m uplift of the main pycnocline, bringing Warm Deep Water closer to the shelf break. This vertical displacement, comparable to that caused by seasonal variations in wind speed, implies that undercurrents may affect the exchanges between coastal and deep waters near the Antarctic continental margins.
Keywords: Sørishavet; Weddellhavet; hydrografi; isbrem; isshelf; kontinentalmargin; kontinentalsokkel; oseanografi; understrømmer

Patterns of variation of serum oxidative stress markers in two seabird species - Costantini, David; Bonadonna, Francesco (Polar Research, 2010)
Variation in oxidative stress markers in natural populations may provide a useful background for understanding variation in life history strategies. In this study, we seek to evaluate patterns of variation in levels of reactive oxygen metabolites (markers of oxidative damage), serum antioxidant capacity, and serum concentration of thiols (antioxidants endogenously synthesized) in nestling and breeding blue petrels (Halobaena caerulea) and in breeding Antarctic prions (Pachyptila desolata). Male and female prions and nestling petrels did not differ in any of the oxidative stress markers. The serum antioxidant capacity positively correlated with the sample time in nestling blue petrels. Breeding petrels with higher body condition index had higher serum antioxidant capacity and circulating thiols. Finally, both seabird species showed lower levels of reactive oxygen metabolites and higher levels of serum antioxidant capacity than previously studied bird species.
Keywords: Antarktis; marin biologi; ornitologi; petreller; reproduksjon; sjøfugler; zoologi; økologi

Holocene Antarctic climate variability from ice and marine sediment cores: insights on ocean-atmosphere interaction - Divine, Dmitry; Koç, Nalân; Isaksson, Elisabeth; Nielsen, Simon H; Crosta, Xavier; Godtliebsen, Fred (Quaternary Science Reviews, 2010)
Holocene climate variability in the southeast Atlantic sector of the Southern Ocean and Antarctic is assessed and quantified through integration of available marine sediment core and Antarctic ice core data. We use summer sea surface temperature (SSST) and sea ice presence (SIP) reconstructions from two marine sediment cores recovered north (50 °S) and south (53.2 °S) of the present day Antarctic Polar Front (APF), as well as an atmospheric temperature and sea ice proxy from the EPICA ice core from Dronning Maud Land (EDML). We find reasonably good agreement in the timing of climate evolution in the analyzed series. Almost all records show a gradual glacial-to-Holocene climate transition, interrupted by the Antarctic cold reversal around 13 000 cal yr BP, and early Holocene climatic optimum (HCO) at about 11 000 cal yr BP. During the early HCO, the seasonal ice cover retreats to south of 53 °S; it then readvances in the course of the mid- to late Holocene. The maximum winter sea ice edge position during the recent 10 000 years varied mainly within 51–53 °S, with sporadic growth to north of 50 °S, a position similar to that during the last glacial. The onset of the Neoglacial period after ca 4000 yr BP is associated with a steepening of the SSST gradient between the marine core sites, strengthening of the westerlies and cooling in the inland ice sheet. The agreement in timing between elevated SSST during the early HCO and decreased deuterium excess in EDML and other ice cores from different locations in the East Antarctic suggests that the retreat of sea ice during the early HCO and weakening of the APF was a general feature of the East Antarctic climate during that time.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; glasiologi; holocene; iskjerner; klimaendringer; oseanografi; paleoklimatologi

Guest editorial—the 1959 Antarctic Treaty: reflecting on the 50th anniversary of a landmark agreement - Dodds, Klaus (Polar Research, 2010)
Commemorating a particular anniversary is always an arbitrary affair, an act of whimsy. After all, why acknowledge the 50th anniversary of someone or some event as opposed to the 48th? In terms of birthdays, we tend to celebrate each year as another rite of human passage. However, when it comes to events such as wars and diplomatic encounters, the media and political commentators like more substantial blocks of time: 10th, 25th, 50th, 75th and 100th anniversaries are particularly noteworthy. The year 2009 has proven no different in terms of representing a temporal marker for the 50th anniversary of the signing of the 1959 Antarctic Treaty. In December 2009 a so-called Antarctic Treaty Summit was held in Washington, D.C. to take advantage of not only such a milestone, but also “to highlight lessons learned about international governance ‘with the interests of science and the progress of all mankind’ ” (Antarctic Treaty Summit 2009, emphasis added).
Keywords: Antarktis; Antarktistraktaten; historie; internasjonal samarbeid; politikk

Review of Legacies and change in polar sciences: historical, legal and political reflections on the International Polar Year, edited by JM Shadian & M Tennberg - Dodds, Klaus (Polar Research, 2010)
The International Polar Year (IPY) of 2007–09 was an international scientific enterprise that encompassed all polar regions, and built on the legacies bequeathed by earlier endeavours stretching back to the late 19th century. The first such venture was initiated in 1882–83, the second was in 1932–33 and the last, the International Geophysical Year (IGY), occurred in 1957–58, and involved thousands of scientists working inter alia in the polar continent. Activity in the Arctic, for geopolitical reasons, was rather more limited, and was certainly not epitomized by free and unfettered scientific investigation. Sponsored by the International Council for Science, the most recent IPY was noteworthy for its explicit bi-polar focus, and its integration of the humanities and social sciences with the physical and environmental sciences. The role of indigenous communities was also notable in Arctic-based projects, a development that would have been inconceivable during the IGY. As with the IGY, however, a spectacular event in one of the theatres of scientific interest grabbed world headlines: in 1957 it was Sputnik orbiting the Earth, and in 2007 it was a Russian submersible planting a flag on the bottom of the central Arctic Ocean basin.
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); bokanmeldelser; forskning; geopolitikk; internasjonal; polarområdene; samarbeid; vitenskap

A New Approach for Exploring Ice Sheets and Sub-Ice Geology - Eisen, Olaf; Hofstede, Coen; Miller, Heinrich; Kristoffersen, Yngve; Blenkner, Rick; Lambrecht, Astrid; Mayer, Christoph (Eos Transactions American Geophysical Union, 2010)
Keywords: Antarktis; geofysikk; geologi; innlandsis; seismologi

Glaciomarine sediments and suspended particulate matter, Weddell Sea Shelf, Antarctica - Elverhøi, Anders; Roaldset, Elen (Polar Research, 2010)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; sedimentologi; stratigrafi

Hva skjedde med vågehvalen i Antarktis? - Fujise, Yoshihiro; Hatanaka, Hiroshi; Ohsumi, Seiji (Ottar, 2010)
Jakten på de store bardehvalene i antarktiske farvann startet på begynnelsen av 1900-tallet og reduserte bestandene sterkt. Vågehvalen ble mindre utsatt for fangst og fikk kanskje en fordel da de større konkurrentene forsvant? Det japanske forskningsprogrammet JARPA har studert endringer i det marine økosystemet i Antarktis.
Keywords: Sørishavet; kval; marin biologi; økosystemer

Neogene biochronology of Antarctic diatoms: A comparison between two quantitative approaches, CONOP and UAgraph - Galster, Federico; Guex, Jean; Hammer, Oyvind (Palaeogeography, Palaeoclimatology, Palaeoecology, 2010)
A quantitative biochronological study by Cody et al. (2008) integrates comprehensive diatom biostratigraphy, magnetostratigraphy, and tephrostratigraphy from 32 Neogene sections around the Southern Ocean and Antarctic continental margin. A recent method, known as Constrained Optimization (CONOP), which can be viewed as a multidimensional version of graphic correlation, is applied to that very interesting database. The goal of the present paper is to discuss some theoretical aspects of quantitative biochronology and to compare the constrained optimization with the deterministic method called Unitary Associations (UAM), a graph theoretical model. We illustrate the fact that the UAM is an extremely powerful and unique theory allowing an in-depth analysis of the internal conflicting inter-taxon stratigraphic relationships, inherent to any complex biostratigraphical database.
Keywords: Antarktis; Sørishavet; biokronologi; diatomeer; paleogeografi; paleoklimatologi; paleontologi; paleoøkologi

Regime Management at the Bottom of the Food Web - Gjelsvik Tiller, Rachel (The Journal of Environment & Development, 2010)
Fishing down the food chain is a controversial issue that demands further exploration. Redfeed is a marine species located on the second to last level on the food web. It is also one of the potential saviors of the aquaculture industry. The role of effective management of this species is of utmost importance to avoid the potential catastrophe associated with its overharvesting. Using a calculation of behavioral effectiveness, a blueprint redfeed regime is compared with the Convention for the Conservation of the Antarctic Marine Living Resources (CCAMLR), an ecosystem-based management regime with the now famous krill as its key species. Though the regimes are similar in nature, their geopolitical differences suggest that a future redfeed regime will be effective even though CCAMLR has not been. Ensuring that the redfeed is not merely incorporated into existing regimes, but is treated separately in an ecosystem-based regime, will alleviate the interplay this future redfeed regime otherwise would encounter.
Publisher: SAGE Publications Inc
Keywords: Antarktistraktaten; Sørishavet; fiskerier; internasjonal rett; krill; marin økologi; marine økosystemer; plankton; polarområdene

Polarskipet Antarctics stolte historie. Del 2 - Goldberg, Fred (Polarboken, 2010)
Keywords: Antarktis; Sørishavet; ekspedisjoner; historie; logistikk

Isopycnal diffusivities in the Antarctic Circumpolar Current inferred from Lagrangian floats in an eddying model - Griesel, Alexa; Gille, Sarah T; Sprintall, Janet; McClean, Julie L; Lacasce, Joseph H; Maltrud, Mathew E (Journal of Geophysical Research: Oceans, 2010)
Lagrangian subsurface isopycnal eddy diffusivities are calculated from numerical floats released in several regions of the Antarctic Circumpolar Current (ACC) of the 0.1° Parallel Ocean Program. Lagrangian diffusivities are horizontally highly variable with no consistent latitudinal dependence. Elevated values are found in some areas in the core of the ACC, near topographic features, and close to the Brazil-Malvinas Confluence Zone and Agulhas Retroflection. Cross-stream eddy diffusivities are depth invariant in the model ACC. An increase of Lagrangian eddy length scales with depth is masked by the strong decrease with depth of eddy velocities. The cross-stream diffusivities average 750 ± 250 m2 s−1 around the Polar Frontal Zone. The results imply that parameterizations that (only) use eddy kinetic energy to parameterize the diffusivities are incomplete. We suggest that dominant correlations of Lagrangian eddy diffusivities with eddy kinetic energy found in previous studies may have been due to the use of too short time lags in the integration of the velocity autocovariance used to infer the diffusivities. We find evidence that strong mean flow inhibits cross-stream mixing within the ACC, but there are also areas where cross-stream diffusivities are large in spite of strong mean flows, for example, in regions close to topographic obstacles such as the Kerguelen Plateau.
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; oseanografi; vannmasser; vannvirvler

Data-based estimation of anthropogenic carbon and acidification in the Weddell Sea on a decadal timescale - Hauck, J.; Hoppema, M.; Bellerby, R. G. J.; Völker, C.; Wolf-Gladrow, D. (Journal of Geophysical Research: Oceans, 2010)
The amount of anthropogenic CO2 (Cant) that entered the Weddell Sea between 1992 and 2008 (Cant1992?2008) was assessed using the extended multiple linear regression (eMLR) method. In the Warm Deep Water (WDW) and the Weddell Sea Bottom Water (WSBW), Cant1992?2008 values were insignificant, whereas values as high as 8 ?mol kg?1 were observed over the shelf. Cant1992?2008 concentrations in the surface layer varied with latitude between 2 and 11 ?mol kg?1. Weak intrusion of anthropogenic CO2 into Weddell Sea Deep Water (WSDW) was demonstrated (Cant1992?2008 yields 1.5?2 ?mol kg?1). That more Cant1992?2008 was found in the WSDW than in the WSBW is surprising, but can be explained by intense ventilation of the WSDW originating from east of the Weddell Gyre. The invasion of Cant1992?2008 provokes a shift in the equilibria of the carbonate system, resulting in acidification and reduction of CO32? concentration. The mean decrease of pH in the upper 200 m layer was 0.016. The largest decrease of calcite and aragonite saturation states was observed at the surface. This implies that surface waters might become undersaturated with respect to aragonite in the future while the underlying WDW is still saturated. Results of this analysis suggest that complete undersaturation of surface waters in the Weddell Sea will be reached after the 21st century.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; antropogenisk CO2; havforsuring; karbondioksid; oseanografi

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Bester, Marthán; Kirkman, Stephen; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2010)
Intraspecific differences in the diets of many species of pinnipeds are to be expected in view of the great differences in morphology, life history and foraging behaviour between the sexes of many species. We examined the diet of the Antarctic fur seal population at Bouvetoya, Southern Ocean, to assess intersexual differences. This was made possible by the analysis of prey remains extracted from scats and regurgitations collected in areas used primarily by one or the other sex. The results indicate that both males and females feed primarily on Antarctic krill Euphausia superba with several species of fish and squid being taken, likely opportunistically given their prevalence. Significant differences were identified in the frequency of occurrence of otoliths in scats and the percentage numerical abundance of the major fish prey species in the diet. Adult males ate a smaller quantity of fish overall, but ate significantly more of the larger fish species. The greater diving capabilities of males and the fact that they are not limited in the extent of their foraging area by having to return regularly to feed dependant offspring may play a role in the differences found between the diets of males and females. Additionally, females might be more selective, favouring myctophids because they are richer in energy than krill. The absence of major differences in the diet between the sexes at this location is likely due to the high overall abundance of prey at Bouvetoya.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; sjøpattedyr

Evaluating CERES angular distribution models for snow using surface reflectance observations from the East Antarctic Plateau - Hudson, Stephen R; Kato, Seiji; Warren, Stephen G (Journal of Geophysical Research: Atmospheres, 2010)
Clouds and the Earth's radiant energy system (CERES) is a satellite-based remote sensing system designed to monitor the Earth's radiation budget. In this paper we examine uncertainties in the angular distribution models (ADMs) used by CERES over permanently snow covered surfaces with clear skies. These ADMs are a key part of the CERES data processing algorithms, used to convert the observed upwelling radiance to an estimate of the upwelling hemispheric flux. We model top-of-atmosphere anisotropic reflectance factors using an atmospheric radiative transfer model with a lower boundary condition based on extensive reflectance observations made at Dome C, Antarctica. The model results and subsequent analysis show that the CERES operational clear-sky permanent-snow ADMs are appropriate for use over Dome C, with differences of less than 5% between the model results and the ADMs at most geometries used by CERES operationally. We show that the uncertainty introduced into the flux estimates through the use of the modeled radiances used in the ADM development is small when the fluxes are averaged over time and space. Finally, we show that variations in the angular distribution of radiance at the top of the atmosphere due to atmospheric variability over permanently snow covered regions are in most cases unlikely to mask the real variations in flux caused by these atmospheric variations.
Keywords: Antarktis; atmosfæren; fjernmåling; klima; meteorologi; observasjoner; snø; solstråling

A comparison of shortwave reflectance over the East Antarctic Plateau observed by CERES to that estimated from surface reflectance observations - Hudson, Stephen R; Warren, Stephen G; Kato, Seiji (Journal of Geophysical Research: Atmospheres, 2010)
Spectral albedo and bidirectional reflectance of snow were measured at Dome C on the East Antarctic Plateau for wavelengths of 350–2400 nm and solar zenith angles of 52°–87°. A parameterization of bidirectional reflectance, based on those measurements, is used as the lower boundary condition in the atmospheric radiation model SBDART to calculate radiance and flux at the top of the atmosphere (TOA). The model's atmospheric profile is based on radiosoundings at Dome C and ozonesoundings at the South Pole. Computed TOA radiances are integrated over wavelength for comparison with the Clouds and the Earth's Radiant Energy System (CERES) shortwave channel. CERES radiance observations and flux estimates from four clear days in January 2004 and January 2005 from within 200 km of Dome C are compared with the TOA radiances and fluxes computed for the same solar zenith angle and viewing geometry, providing 11,000 comparisons. The measured radiance and flux are lower than the computed values. The median difference is about 7% for CERES on Terra, and 9% on Aqua. Sources of uncertainty in the model and observations are examined in detail and suggest that the measured values should be less than the computed values, but only by 1.7% ± 4%. The source of the discrepancy of about 6% cannot be identified here; however, the modeled values do agree with observations from another satellite instrument (Multiangle Imaging Spectroradiometer), suggesting that the CERES calibration must be considered a possible source of the discrepancy.
Keywords: Antarktis; atmosfæren; fjernmåling; meteorologi; observasjoner; solstråling

Heat conservation during cold exposure in birds (vasomotor and respiratory implications) - Johansen, Kjell; Bech, Claus (Polar Research, 2010)
The mechanisms by :vhich peripheral circulation and respiration serve in maintaining thermal homeostasis in birds living in cold climates are reviewed. Three types of arteriovenous heat exchanger (an elaborate rete, asimple rete, and a venue comirantes system) are found in the legs of birds. The anatomical differences between the different types of A-V associations are described, and the regulation of peripheral blood flow, in respect to maximal heat conservation and prevention of tissue damage, is discussed. A nasal temporal counter current heat exchanger, lowering the temperature of the expired air to values considerably below the body temperature, is the most important mechanism for minimizing the respiratory heat and water loss. In addition, a decreased ventilatory requirement, caused by a changed respiratory pattern and an increased parabronchial oxygen extraction, lowers the amount of air ventilated relative to the amount of oxygen uptake. Thus, the relative loss of heat and water is reduced.
Keywords: Antarktis; fugler; kuldeeksponering; kuldetoleranse; ornitologi; zoofysiologi; zoologi

Swarm characteristics of Antarctic krill Euphausia superba relative to the proximity of land during summer in the Scotia Sea - Klevjer, Thor Aleksander; Tarling, Geraint A.; Fielding, S. (Marine Ecology Progress Series, 2010)
We studied the relationship between the proximity of land and the distribution and swarming characteristics of Antarctic krill across the Scotia Sea in January and February 2003. Krill swarms identified with a Simrad EK60 (38 kHz, 120 kHz) echosounder were grouped into 4 categories according to distance from shoreline: 0 to 50 km, 50 to 100 km, 100 to 200 km and >200 km. Cross-sectional areas of swarms were significantly larger inshore, with a mean value of 120 m^2 in the 0 to 50 km zone compared to <80 m^2 further offshore. The packing concentration of krill within inshore swarms was also significantly greater, with an average density of 95 ind. m^–3 compared to between 24 and 31 ind. m^–3 elsewhere. A large proportion of the biomass was concentrated into a small number of large, dense swarms throughout the survey area, and this trend increased with decreasing distance from shore. The highest median number of swarms per km and krill acoustic biomass per km was found in the 50 to 100 km zone. However, a significantly greater number of large, biomass-rich swarms occurred in the 0 to 50 km zone compared to all other zones. Swarms in the 0 to 50 km zone were also significantly further apart. The majority of swarms were located in the upper 50 m during the daytime although they were marginally deeper in the night in offshore regions. Krill are likely to move between inshore and offshore environments continuously over their lifetimes. The change in krill behaviour between environments could be a response to local predatory threats over short spatial and temporal scales.
Keywords: Scotiahavet; Sørishavet; ekkolodd; krill; marin biologi; oseanografi; plankton

Distribution and demography of Antarctic krill in the Southeast Atlantic sector of the Southern Ocean during the austral summer 2008 - Krafft, Bjørn A.; Melle, W.; Knutsen, T.; Bagøien, E.; Broms, C.; Ellertsen, B.; Siegel, V. (Polar Biology, 2010)
This study documents horizontal distribution and demography of Antarctic krill (Euphausia superba) from the Southern Ocean during January–March 2008. The cruise predominantly occurred in CCAMLR Subarea 48.6, where knowledge about the ecosystem is limited. E. superba were not found north of 52°S. The biomass, estimated from trawl catches, was highest (63.09 g/m2) at a station 680 km southeast of Bouvetøya and at two stations 1,400 and 600 km southeast and southwest of Bouvetøya, 54.67 and 61.38 g/m2, respectively. Body length ranged from 19 to 61 mm (N = 8,538), with a mean of 42.0 ± 6.4 mm (SD). The overall sex ratio was 1:1, 46.2% males (13.2% adults and 33.0% subadults), 46.1% females (33.6% adults and 12.5% subadults), while 7.5% were juveniles. Trawl stations dominated by adults were found west and north of Bouvetøya. Stations with high proportions of subadults and juveniles were mainly found southeast of the island. Four cluster groups were differentiated: analyzing data on krill sex proportions, maturity stages, hydrography, nutrients and chlorophyll concentrations. Two groups represented stations located in the northern part of the study area, where E. superba were absent; water temperatures were higher and the nutrient concentrations lower compared to the groups where E. superba were present. This study shows that bathymetric features like the North Weddell Ridge including Bouvetøya are important for concentrating krill probably due to water mass characteristics and advective processes which influence regional krill demography. The southern regions of CCAMLR sector 48.6 are essential for understanding regional krill recruitment and production.
Keywords: Bouvetøya; Sørishavet; krill; marin biologi; marine økosystemer; zooplankton

Antarctic clouds - Lachlan-Cope, Tom (Polar Research, 2010)
Sensitivity studies with global climate models show that, by their influence on the radiation balance, Antarctic clouds play a major role in the climate system, both directly at high southern latitudes and indirectly globally, as the local circulation changes lead to global teleconnections. Unfortunately, observations of cloud distribution in the Antarctic are limited and often of low quality because of the practical difficulty in observing clouds in the harsh Antarctic environment. The best surface observations suggest that the fractional cloud cover at the South Pole is around 50–60% in all seasons, whereas the cloud cover rises to around 80–90% close to the coast of the continent. Microphysical observations of cloud parameters are also very sparse in the Antarctic. However, the few measurements that do exist show predominantly ice-crystal clouds across the interior, with mixed-phase clouds close to the coasts. Crystal sizes vary from 5 to 30 mm (effective radius) in the interior to somewhat larger ice crystals and water drops near the coast. A wide range of crystal shapes is observed at all sites. This review considers the available cloud observations and highlights the importance of Antarctic clouds and the need for better observations in the future.
Keywords: Antarktis; klimatologi; meteorologi; observasjoner; satellitt bilder; skyer

Importance of the contribution of Limacina helicina faecal pellets to the carbon pump in Terra Nova Bay (Antarctica) - Manno, C.; Tirelli, V.; Accornero, A.; Fonda Umani, S. (Journal of Plankton Research, 2010)
The understanding of the role of the pteropods Limacina helicina in the ecosystem has become of greater interest as the debate on ocean acidification and its consequences for calcifying organisms has increased. Four incubation experiments were carried out in January and February 2006 in Terra Nova Bay Polynya (Ross Sea) to identify the faecal pellets (FPs) produced by L. helicina. Mean FP production rates were 6.1 ± 1.3 and 10.9 ± 2.1 pellets day−1 individual−1 in January and February, respectively. FPs produced by L. helicina had an oval shape with a more lengthened side. The identification of L. helicina faeces allowed us to quantify the amounts of L. helicina FPs in the material collected by sediment traps deployed in the same area from 1998 to 2001. We found that L. helicina FPs flux ranged from 71 × 103 FP m−2 year−1 to 362 × 103 FP m−2 year−1 and reach maximum values in March–April every year. The FPs flux of this organism contributed 19% of the particle organic carbon flux. The carbon pump may be modified if the L. helicina population declines as a consequence of the predicted acidification in polar and subpolar waters.
Keywords: Rosshavet; Sørishavet; havforsuring; krill; marin biologi; oseanografi; plankton

Review of Health of Antarctic wildlife: a challenge for science and policy, edited by Kerry R. Knowles & Martin J. Riddle - McMahon, Clive R (Polar Research, 2010)
Climate change and disease, among other factors, play an important role in the regulation and evolution of animal populations through the differential survival of individuals (Holmes 1996; Harvell et al. 2002). The study and monitoring of disease is important because diseases are likely to be spread more rapidly now than in the recent past because of increased globalization and rapid humaninduced climate change (Daszak et al. 2000; Ward & Lafferty 2004). Antarctic wildlife offers a unique opportunity to study disease spread in terms of globalization and climate change because: (1) Antarctic animals are increasingly exposed to humans and other disease vectors, such as introduced species; and (2) there is strong evidence of climatic changes in and around Antarctica (Mayewski et al. 2009), which together may affect the composition and virulence of pathogens or increase the overlap between Antarctic and other seabirds and their parasites (e.g., Kovats et al. 2001).

An 860 km surface mass-balance profile on the East Antarctic plateau derived by GPR - Müller, Karsten; Sinisalo, Anna; Anschütz, Helgard; Hamran, Svein-Erik; Hagen, Jon-Ove; McConnell, Joseph R; Pasteris, Daniel R (Annals of Glaciology, 2010)
Snow accumulation and its variability on the East Antarctic plateau are poorly understood due to sparse and regionally confined measurements. We present a 5.3 GHz (C-band) ground-penetrating radar (GPR) profile with a total length of 860 km recovered during the joint Norwegian–US International Polar Year traverse 2007/08. Mean surface mass balance (SMB) over the last 200 years was derived from the GPR data by identifying the volcanic deposition of the Tambora eruption in 1815. It varies between 9.1 and 37.7 kg m−2 a−1 over the profile, with a mean of 23.7 kg m−2 a−1 and a standard deviation of 4.7 kg m−2 a−1. The 200 year SMB estimated is significantly lower than most of the SMB estimates over shorter time periods in this region. This can be partly explained by a SMB minimum in the vicinity of the ice divide. However, it is more likely that a recent increase in SMB observed by several studies is largely responsible for the observed discrepancy.
Keywords: Antarktis; Dronning Maud Land; glasiologi

An observation of the banded structure of the Antarctic Coastal Current at the prime meridian - Núñez-Riboni, Ismael; Fahrbach, Eberhard (Polar Research, 2010)
Observations of three bands of westward flow and two countercurrents, spanning roughly 50 km from the ice-shelf edge in front of the Fimbul Ice Shelf (prime meridian) in Antarctica, are presented. A comparison with a numerical model and the proximity of two of these current cores to the ice shelf suggest that they split from the Antarctic Coastal Current because of the influence of sea ice on the surface drag. A comparison with previous studies suggests that the other core is the current associated with the Antarctic Slope Front. Because the Fimbul ice shelf overhangs the continental shelf, the Antarctic Coastal Current displaces offshore, getting close to the Antarctic Slope Front. The obtained structure is derived from conductivity–temperature–depth geostrophic velocities from February 2005, referenced with detided acoustic Doppler current profiler velocities.
Keywords: Sørishavet; geostrofisk; havis; havstrømmer; hydrografi; kyststrøm; meteorologi; sjøis

Glacier advance in southern middle-latitudes during the Antarctic Cold Reversal - Putnam, Aaron E.; Denton, George H.; Schaefer, Joerg M.; Barrell, David J. A.; Andersen, Bjørn G.; Finkel, Robert C.; Schwartz, Roseanne; Doughty, Alice M.; Kaplan, Michael R.; Schlüchter, Christian (Nature Geoscience, 2010)
The geographic extent of cooling associated with the Antarctic Cold Reversal is unclear. Dating of glacial moraines in New Zealand suggests that the cooling extended into the southern mid-latitudes, possibly as a result of the northward migration of the southern subtropical front.
Keywords: Antarktis; deglasiasjon; holocene; kryosfæren; paleoglasiologi; paleoklimatologi

Land and sea-ice properties in Antarctica: bridging the gap between the ground and satellite measurements in the western Ross Sea region - Rack, Wolfgang; Langhorne, Pat; Haas, Christian; Clavano, Wendy; Gough, Alex; Kruetzmann, Nikolai; Pinchin, James; Riger-Kusk, Mette (Ice and climate news, 2010)
Keywords: Antarktis; Sørishavet; glasiologi; havis; isshelf

An extreme precipitation event in Dronning Maud Land, Antarctica: a case study with the Antarctic Mesoscale Prediction System - Schlosser, Elisabeth; Powers, Jordan G.; Duda, Michael G.; Manning, Kevin W.; Reijmer, Carleen H.; van den Broeke, Michiel R. (Polar Research, 2010)
An extreme precipitation event that influenced almost the whole polar plateau of Dronning Maud Land, Antarctica, is investigated using Antarctic Mesoscale Prediction System archive data. For the first time a high-resolution atmospheric model especially adapted for polar regions was used for such a study in Dronning Maud Land. The outstanding event of 21–25 February 2003 was connected to a strong north-westerly flow, caused by a blocking high above eastern Dronning Maud Land, that persisted for several days and brought unusually large levels of moisture to the Antarctic Plateau. This weather situation is most effective in bringing precipitation to high-altitude interior Antarctic ice-core drilling sites, where precipitation in the form of diamond dust usually dominates. However, a few such precipitation events per year can account for a large percentage of the annual accumulation, which can cause a strong bias in ice-core data. Additionally, increased temperatures and wind speeds during these events need to be taken into account for the correct climatic interpretation of ice cores. A better understanding of the frequency of occurrence of intermittent precipitation in the interior of Antarctica in past and future climates is necessary for both palaeoclimatological studies and estimates of future sea-level change.
Keywords: Dronning Maud Land; havnivåstigning; klimaendringer; klimatologi; meteorologi; nedbør; polarområdene

Wintertime mixed layer measurements at Maud Rise, Weddell Sea - Sirevaag, Anders; McPhee, Miles G; Morison, James H; Shaw, William J; Stanton, Timothy P (Journal of Geophysical Research: Oceans, 2010)
Sea ice plays a crucial role in the exchange of heat between the ocean and the atmosphere, and areas of intense air-sea-ice interaction are important sites for water mass modification. The Weddell Sea is one of these sites where a relatively thin first-year ice cover is constantly being changed by mixing of heat from below and stress exerted from the rapidly changing and intense winds. This study presents mixed layer turbulence measurements obtained during two wintertime drift stations in August 2005 in the eastern Weddell Sea, close to the Maud Rise seamount. Turbulence in the boundary layer is found to be controlled by the drifting ice. Directly measured heat fluxes compare well with previous studies and are well estimated from the mixed layer temperatures and mixing. Heat fluxes are also found to roughly balance the conductive heat flux in the ice; hence, little freezing/melting was observed. The under-ice topography is estimated to be hydraulically very smooth; comparison with a steady 1-D model shows that these estimates are made too close to the ice-ocean interface to be representative for the entire ice floe. The main source and sink of turbulent kinetic energy are shear production and dissipation. Observations indicate that the dynamics of the under-ice boundary layer are influenced by a horizontal variability in mixed layer density and an increasing amount of open leads in the area.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; havis; hydrografi; oseanografi; pyknoklin; sjøis

Antarktistraktatens effekt på norsk politikk 1959-2009: fra polarimperium på sparebluss til nye utfordringer - og ny giv? - Skagestad, Odd Gunnar (Norsk militært tidsskrift, 2010)
Keywords: Antarktis; politikk

Characteristics of atmospheric transport into the Antarctic troposphere - Stohl, Andreas; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2010)
We have developed a 5.5 year climatology of atmospheric transport into the Antarctic troposphere, which uses the same data set and methods as described in a recent study for the Arctic. This allows direct comparisons of transport properties for the two polar regions. The climatology is based on a simulation with the Lagrangian particle dispersion model FLEXPART, where the model atmosphere was globally filled with particles. Transport characteristics as well as emission sensitivities were derived from 6 hourly particle positions. We found that the probability for near-surface air to originate from the stratosphere on a time scale of 10 days is an order of magnitude higher near the South Pole than near the North Pole, a result of higher topography and descent that partly compensates for the flow of air down the Antarctic Plateau with the katabatic winds. The stratospheric influence is largest in fall, which is opposite to the seasonality in the Arctic. Stratospheric influence is much smaller over the shelf ice regions and in a band around Antarctica. The average time for which air near the surface has been exposed to continuous darkness in July (continuous light in January) is longest over the Ronne Ice Shelf and Ross Ice Shelf at ∼11 days (20 days). We calculated how sensitive Antarctic air masses are to emission input up to 30 days before arriving in Antarctica if removal processes are ignored. The emission sensitivity shows strong meridional gradients and, as a result, is generally low over South America, Africa, and Australia. For a 10 day time scale, the largest emission sensitivities over these continents are 1–2 orders of magnitude smaller than over Eurasia for transport to the Arctic, showing that foreign continents have a much smaller potential to pollute the Antarctic than the Arctic troposphere. Emission sensitivities and derived black carbon (BC) source contributions over South America, Africa, and Australia are substantially (a factor 10 for Africa) larger in winter than in summer. In winter, biomass burning contributes more BC than anthropogenic sources. For typical aerosol lifetimes of 5–10 days, ship emissions south of 60°S account for half of the total BC concentrations in the lowest 1000 m of the atmosphere south of 70°S in December. The increasing number of tourists visiting Antarctica and fishing vessels operating close to Antarctica are, therefore, a matter of concern.
Keywords: Antarktis; cruiseturisme; forurensning; klimatologi; polarområdene; stratosfæren; utslipp

A consistent data set of Antarctic ice sheet topography, cavity geometry, and global bathymetry - Timmermann, Ralph; Le Brocq, Anne M; Deen, Tara J; Domack, Eugene W; Dutrieux, Pierre; Galton-Fenzi, Benjamin K; Hellmer, Hartmut H; Humbert, Angelika; Jansen, Daniela; Jenkins, Adrian; Lambrecht, Astrid; Makinson, Keith; et al. (Earth Syst. Sci. Data, 2010)
Sub-ice shelf circulation and freezing/melting rates in ocean general circulation models depend critically on an accurate and consistent representation of cavity geometry. Existing global or pan-Antarctic data sets have turned out to contain various inconsistencies and inaccuracies. The goal of this work is to compile in- dependent regional fields into a global data set. We use the S-2004 global 1-minute bathymetry as the backbone and add an improved version of the BEDMAP topography (ALBMAP bedrock topography) for an area that roughly coincides with the Antarctic continental shelf. The position of the merging line is individually chosen in different sectors in order to get the best out of each data set. High resolution gridded data for upper and lower ice surface topographies and cavity geometry of the Amery, Fimbul, Filchner-Ronne, Larsen C and George VI Ice Shelves, and for Pine Island Glacier are carefully merged into the ambient ice and ocean topographies. Multibeam survey data for bathymetry in the former Larsen B cavity and the southeastern Bellingshausen Sea have been obtained from the data centers of Alfred Wegener Institute (AWI), British Antarctic Survey (BAS) and Lamont-Doherty Earth Observatory (LDEO), gridded, and blended into the existing bathymetry map. The resulting global 1-minute topography data set (RTopo-1) contains maps for upper and lower ice surface heights, bedrock bathymetry, and consistent masks for open ocean, grounded ice, floating ice, and bare land surface.
Publisher: Copernicus Publications
Keywords: Antarktis; Sørishavet; batymetri; glasiologi; havbunnen; topografi

Venom on ice: First insights into Antarctic octopus venoms - Undheim, E.A.B.; Georgieva, D.N.; Thoen, H.H.; Norman, J.A.; Mork, J.; Betzel, C.; Fry, B.G. (Toxicon, 2010)
The venom of Antarctic octopus remains completely unstudied. Here, a preliminary investigation was conducted into the properties of posterior salivary gland (PSG) extracts from four Antarctica eledonine (Incirrata; Octopodidae) species (Adelieledone polymorpha, Megaleledone setebos, Pareledone aequipapillae, and Pareledone turqueti) collected from the coast off George V’s Land, Antarctica. Specimens were assayed for alkaline phosphatase (ALP), acetylcholinesterase (AChE), proteolytic, phospholipase A2 (PLA2), and haemolytic activities. For comparison, stomach tissue from Cirroctopus sp. (Cirrata; Cirroctopodidae) was also assayed for ALP, AChE, proteolytic and haemolytic activities. Dietary and morphological data were collected from the literature to explore the ecological importance of venom, taking an adaptive evolutionary approach. Of the incirrate species, three showed activities in all assays, while P. turqueti did not exhibit any haemolytic activity. There was evidence for cold-adaptation of ALP in all incirrates, while proteolytic activity in all except P. turqueti. Cirroctopus sp. stomach tissue extract showed ALP, AChE and some proteolytic activity. It was concluded that the AChE activity seen in the PSG extracts was possibly due to a release of household proteins, and not one of the secreted salivary toxins. Although venom undoubtedly plays an important part in prey capture and processing by Antarctica eledonines, no obvious adaptations to differences in diet or morphology were apparent from the enzymatic and haemolytic assays. However, several morphological features including enlarged PSG, small buccal mass, and small beak suggest such adaptations are present. Future studies should be conducted on several levels: Venomic, providing more detailed information on the venom compositions as well as the venom components themselves; ecological, for example application of serological or genetic methods in identifying stomach contents; and behavioural, including observations on capture of different types of prey.
Keywords: Sørishavet; biokjemi; bløtdyr; marin biologi; toksikologi

Genetic identification of Southern Ocean octopod samples using mtCOI - Undheim, Eivind Andreas Baste; Norman, Janette Ann; Thoen, Hanne Halkinrud; Fry, Bryan Grieg (Comptes Rendus. Biologies, 2010)
East Antarctic octopods were identified by sequencing mtCOI and using four analytical approaches: Neighbor-joining by Kimura-2-Parameter-based distances, character-based, BLAST, and Bayesian Inference of Phylogeny. Although the distance-based analytical approaches identified a high proportion of the sequences (99.5% to genus and 88.1% to species level), these results are undermined by the absence of a clear gap between intra-and interspecific variation. The character-based approach gave highly conflicting results compared to the distance-based methods and failed to identify apomorphic characters for many of the species. While a DNA independent approach is necessary for validation of the method comparisons, crude morphological observations give early support to the distance-based results and indicate extensive range expansions of several species compared to previous studies. Furthermore, the use of distance-based phylogenetic methods nevertheless group specimens into plausible species clades that are highly useful in non-taxonomical or non-systematic studies. (C) 2010 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Publisher: Elsevier
Keywords: Sørishavet; blekksprut; genetikk; marin biologi; taksonomi

Biogeochemical weathering under ice: Size matters - Wadham, Jemma L; Tranter, Martyn; Skidmore, Mark; Hodson, Andy; Priscu, John C; Lyons, W Berry; Sharp, Martin; Wynn, Peter; Jackson, Miriam (Global Biogeochemical Cycles, 2010)
The basal regions of continental ice sheets are gaps in our current understanding of the Earth's biosphere and biogeochemical cycles. We draw on existing and new chemical data sets for subglacial meltwaters to provide the first comprehensive assessment of sub-ice sheet biogeochemical weathering. We show that size of the ice mass is a critical control on the balance of chemical weathering processes and that microbial activity is ubiquitous in driving dissolution. Carbonate dissolution fueled by sulfide oxidation and microbial CO2 dominate beneath small valley glaciers. Prolonged meltwater residence times and greater isolation characteristic of ice sheets lead to the development of anoxia and enhanced silicate dissolution due to calcite saturation. We show that sub-ice sheet environments are highly geochemically reactive and should be considered in regional and global solute budgets. For example, calculated solute fluxes from Antarctica (72–130 t yr−1) are the same order of magnitude as those from some of the world's largest rivers and rates of chemical weathering (10–17 t km−2 yr−1) are high for the annual specific discharge (2.3–4.1 × 10−3 m). Our model of chemical weathering dynamics provides important information on subglacial biodiversity and global biogeochemical cycles and may be used to design strategies for the first sampling of Antarctic Subglacial Lakes and other sub-ice sheet environments for the next decade.
Keywords: Antarktis; biogeokjemi; biosfære; brehylle; glasiologi; innlandsis; isbrem; isshelf; subglasial biodiversitet; subglasial innsjø

The acoustic properties of Salpa thompsoni - Wiebe, Peter H.; Chu, Dezhang; Kaartvedt, Stein; Hundt, Anna; Melle, Webjorn; Ona, Egil; Batta-Lona, Paola (ICES Journal of Marine Science, 2010)
Wiebe, P. H., Chu, D., Kaartvedt, S., Hundt, A., Melle, W., Ona, E., and Batta-Lona, P. 2010. The acoustic properties of Salpa thompsoni. – ICES Journal of Marine Science, 67: 583–593.Aggregations of the salp Salpa thompsoni were encountered during the Antarctic krill and ecosystem-studies cruise on the RV “G.O. Sars” from 19 February to 27 March 2008. The salp's in situ target strength (TS), size, number of individuals in aggregate chains, and chain angle of orientation were determined. Shipboard measurements were made of Salpa thompsoni's material properties. Individual aggregates were mostly 45.5–60.6 mm in mean length; relatively rare solitaries were ∼100 mm. Chains ranged from 3 to at least 121 individuals, and in surface waters (<20 m), they showed no preferred angle of orientation. Sound-speed contrast (h) ranged from 1.0060 to 1.0201 and density contrast (g) estimates between 1.0000 and 1.0039. The in situ TS distributions peaked between −75 and −76 dB at 38 kHz, with a secondary peak at approximately −65 dB. TS ranged between −85 and −65 dB at 120 and 200 kHz and peaked around −74 dB. The measured in situ TS of salps reasonably matched the theoretical scattering-model predictions based on multi-individual chains. The backscattering from aggregate salps gives rise to TS values that can be similar to krill and other zooplankton with higher density and sound-speed contrasts.
Keywords: Bouvetøya; Sørishavet; copepoder; ekkolodd; krill; marin biologi; marine økosystemer; oseanografi; plankton

Cloning and heterologous expression of two cold-active lipases from the Antarctic bacterium Psychrobacter sp. G - Xuezheng, Lin; Shuoshuo, Cui; Guoying, Xu; Shuai, Wang; Ning, Du; Jihong, Shen (Polar Research, 2010)
Antarctic bacteria producing extracellular lipolytic enzymes with activity at low temperature were isolated, and the most promising strain, named G, was identified as a Psychrobacter species based on 16S rDNA sequence alignment. The genomic DNA of this bacterium was used to construct its plasmid genomic library into pUC118 plasmid vectors, and to screen the cold-active lipolytic enzyme genes. Two genes encoding for cold-active lipolytic enzymes, Lip-1452 (with an open reading frame of 1452 bp in length) and Lip-948 (with an open reading frame of 948 bp in length), were screened. The primary structure of the two lipases deduced from the nucleotide sequence showed a consensus pentapeptide containing the active serine (Lip-1452, GDSAG, and Lip-948, GNSMG) and a conserved His-Gly dipeptide in the N-terminal part of the enzyme. Protein sequence alignment and conserved regions analysis indicated that the two lipases probably belonged to family IV and family V of the bacterial lipolytic enzymes, respectively. The upstream and downstream sequences of the two lipolytic lipases were also obtained. The two lipase genes were cloned into the expression vector pCold III and integrated into Escherichia coli BL21 (DE3). The functional expression of both lipase genes by E. coli BL21 (DE3) cells was observed as the formation of clear haloes around colonies on a 1% (vol/vol) tributyrin plate upon induction with isopropyl-b-Dthiogalactopyranoside at 5°C. A lipase activity assay showed that the specific activity of the pCold III+Lip-948 expression system was up to 3.7 U ml-1, whereas that of pCold III+Lip-1452 was very low.
Keywords: Sørishavet; bakterier; bioteknologi; genkloning; genuttrykk; marin biologi; mikroorganismer

Seismic and radar investigations of Fourcade Glacier on King George Island, Antarctica - Young Kim, Ki; Lee, Joohan; Ho Hong, Myung; Kuk Hong, Jong; Keun Jin, Young; Shon, Howong (Polar Research, 2010)
To determine P- and S-wave velocities, elastic properties and subglacial topography of the polythermal Fourcade Glacier, surface seismic and radar surveys were conducted along a 470-m profile in November 2006. P- and S-wave velocity structures were determined by travel-time tomography and inversion of Rayleigh wave dispersion curves, respectively. The average P- and S-wave velocities of ice are 3466 and 1839 m s-1, respectively. Radar velocities were obtained by migration velocity analysis of 112 diffraction events. An estimate of 920 kg m-3 for the bulk density of wet ice corresponds to water contents of 5.1 and 3.2%, which were derived from the average P-wave and radar velocities, respectively. Using this density and the average P- and S-wave velocities, we estimate that the corresponding incompressibility and rigidity of the ice are 6.925 and 3.119 GPa, respectively. Synergistic interpretation of the radar profile and P- and S-wave velocities indicates the presence of a fracture zone above a subglacial high. Here, the P- and S-wave velocities are approximately 5 and 3% less than in the ice above a subglacial valley, respectively. The S-wave velocities indicate that warmer and less rigid ice underlies 10–15 m of colder ice near the surface of the glacier. Such layering is characteristic of polythermal glaciers. As a relatively simple non-invasive approach, integration of P-wave tomography, Rayleigh wave inversion and ground-towed radar is effective for various glaciological studies, including the elastic properties of englacial and subglacial materials, cold/warm ice interfaces, topography of a glacier bed and location of fracture zones.
Keywords: Antarktis; geofysikk; glasiologi; isbre; radarundersøkelse; seismisk undersøkelse; subglasial; tomografi; topografi